Administering analgesia sublingually is a suitable option for children with acute abdominal pain in the emergency department. - Cozzi, Giorgio; Zanchi, Chiara; Chiaretti, Antonio; Tipo, Vincenzo; Cernich, Marta; D'Anna, Carolina; Fantacci, Claudia; Conversano, Ester; Zanon, Davide; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2019)
AIM: Acute abdominal pain is a frequent complaint in children attending emergency departments. The aim of this study was to investigate the pain score reductions when children with acute abdominal pain received medication sublingually. METHODS: We carried out a multicentre randomised controlled trial in three children's hospitals in Italy between March 2015 and June 2017. Children from four to 18 years of age with acute abdominal pain were recruited if their self-reported pain was at least six on a scale from 0-10. The children were randomised to receive ketorolac 0.5 mg/kg (n = 70) or tramadol 2 mg/kg (n = 70) sublingually or a melt in the mouth powder of 20 mg/kg paracetamol (n = 70). The main study outcome was the pain scores for the three drugs after two hours. RESULTS: The 210 children (58.6% girls) had a median age of 12 years with an interquartile range of 9-14.3. The median pain scores at two hours were not significantly different between ketorolac 2.0 (interquartile ranges, IQR 0.0-4.3) and tramadol 3.0 (IQR 1.0-5.0) vs paracetamol 3.0 (IQR 0.8-5.0). The median pain reductions were all 5.0 points. CONCLUSION: Delivering analgesia sublingually was a suitable option for pain relief in children with acute abdominal pain in the emergency department.

Antibodies reacting to mimotopes of Simian virus 40 large T antigen, the viral oncoprotein, in sera from children. - Mazzoni, Elisa; Frontini, Francesca; Rotondo, John Charles; Zanotta, Nunzia; Fioravanti, Arianna; Minelli, Francesca; Torreggiani, Elena; Campisciano, Giuseppina; Marcuzzi, Annalisa; Guerra, Giovanni; Tommasini, Alberto; Touzé, Antoine; et al. (J Cell Physiol, 2019)
Recent data indicate that the Simian virus 40 (SV40) infection appears to be transmitted in humans independently from early SV40-contaminated antipolio vaccines. Serum antibodies against SV40 large T antigen (Tag) were analyzed in children/adolescents and young adults. To investigate antibodies reacting to SV40 Tag antigens, serum samples ( n = 812) from children and young adults were analyzed by indirect ELISAs using specific SV40 Tag mimotopes. Mimotopes were synthetic peptides corresponding to SV40 Tag epitopes. In sera ( n = 412) from healthy children up to 17 years old, IgG antibodies against SV40 Tag mimotopes reached an overall prevalence of 15%. IgM antibodies against SV40 Tag were detected in sera of children 6-8 months old confirming and extending the knowledge that SV40 seroconversion occurs early in life. In children/adolescents affected by different diseases ( n = 180) SV40 Tag had a prevalence of 18%, being the difference no significant compared to healthy subjects ( n = 220; 16%) of the same age. Our immunological data indicate that SV40 circulates in children and young adults, both in healthy conditions and affected by distinct diseases. The IgM detection in sera from healthy children suggests that the SV40 infection/seroconversion occurs early in life (>6 months). Our immunological data support the hypothesis that SV40, or a closely related still unknown polyomavirus, infects humans. The SV40 seroprevalence is lower than common polyomaviruses, such as BKPyV and JCPyV, and other new human polyomaviruses. In addition, our immunological surveillance indicates a lack of association between different diseases, considered herein, and SV40.

Cervico-vaginal secretion cytokine profile: A non-invasive approach to study the endometrial receptivity in IVF cycles. - Zanotta, Nunzia; Monasta, Lorenzo; Skerk, Kristina; Luppi, Stefania; Martinelli, Monica; Ricci, Giuseppe; Comar, Manola (Am J Reprod Immunol, 2019)
PROBLEM: Cytokines have a significant role in the process of embryo implantation, trophoblast growth, and differentiation by modulating the immune and endocrine system. The aim of this study was to investigate the profile of a large set of cytokines in the cervico-vaginal washing of women undergoing IVF, to explore the association of these proteins with a good receptive endometrium. METHOD OF STUDY: A cohort of 155 women scheduled for IVF cycle was recruited. All patients were asymptomatic for genitourinary infections and had been screened for chlamydia, mycoplasma, and other bacterial infections. All IVF subjects were treated according to standard clinical and laboratory protocols. A panel of 48 immune factors was analyzed on cervico-vaginal washing, using magnetic bead-based multiplex immunoassays (Bio-Plex, BIO-RAD Laboratories, Milano, Italy). RESULTS: A total of 99 patients reached embryo transfer, of which 31 had a clinical pregnancy. A pattern of four pro-inflammatory immune molecules, IL-12p40, IFN-a, MIF, and MCP3 (P < 0.001), was found significantly up-regulated in the cervico-vaginal fluid of women with clinical pregnancy. A significantly increased expression of IL-9, Gro , and SDF-1 (P < 0.05) was observed in the presence of endometriosis, while high levels of IL-13 and L-15 were associated with ovulatory infertility factor (P < 0.05). CONCLUSION: In this pilot study, we demonstrated that the expression of specific cytokines in the cervico-vaginal washing on the day of oocyte retrieval might have a positive correlation with the potential clinical pregnancy. Therefore, cervico-vaginal secretion cytokine profiling might be a new, non-invasive approach to study the endometrial receptivity in IVF management.

An evaluation of the Movement ABC-2 Test for use in Italy: A comparison of data from Italy and the UK. - Zoia, Stefania; Biancotto, Marina; Guicciardi, Marco; Lecis, Romina; Lucidi, Fabio; Pelamatti, Giovanna M; Carrozzi, Marco; Skabar, Aldo; Sugden, David A; Barnett, Anna L; Henderson, Sheila E (Res Dev Disabil, 2019)
BACKGROUND: The standardized test within the Movement Assessment Battery for Children-2nd edition (MABC-2) is used worldwide to assess motor problems in children. Ideally, any country using a test developed in another country should produce national norms to ensure that it functions effectively in the new context. AIM: The first objective of this study was to explore the differences in motor performance between Italian and British children. The second was to examine the structural validity of the test for the Italian sample. METHOD: A total of 718 Italian (IT) and 765 British (UK) children, aged 3-10 years, were individually tested on the age-appropriate items of the MABC-2 Test. RESULTS: Developmental trends emerged on every task and differences between IT and UK children were obtained on 11 of 27 task comparisons. Interactions between age and country indicated that differences were not consistently in favor of one culture. Confirmatory factor analysis generally supported the proposed structure of the MABC-2 Test. CONCLUSION: Although the differences between the IT and the UK children were relatively few, those that did emerge emphasize the need for population specific norms and suggest that cultural diversity in motor experiences should be considered when evaluating motor abilities in children.

Four-miRNA Signature to Identify Asbestos-Related Lung Malignancies. - Santarelli, Lory; Gaetani, Simona; Monaco, Federica; Bracci, Massimo; Valentino, Matteo; Amati, Monica; Rubini, Corrado; Sabbatini, Armando; Pasquini, Ernesto; Zanotta, Nunzia; Comar, Manola; Neuzil, Jiri; et al. (Cancer Epidemiol Biomarkers Prev, 2019)
BACKGROUND: Altered miRNA expression is an early event upon exposure to occupational/environmental carcinogens; thus, identification of a novel asbestos-related profile of miRNAs able to distinguish asbestos-induced cancer from cancer with different etiology can be useful for diagnosis. We therefore performed a study to identify miRNAs associated with asbestos-induced malignancies. METHODS: Four groups of patients were included in the study, including patients with asbestos-related (NSCLC) and asbestos-unrelated non-small cell lung cancer (NSCLC) or with malignant pleural mesothelioma (MPM), and disease-free subjects (CTRL). The selected miRNAs were evaluated in asbestos-exposed population. RESULTS: Four serum miRNAs, that is miR-126, miR-205, miR-222, and miR-520g, were found to be implicated in asbestos-related malignant diseases. Notably, increased expression of miR-126 and miR-222 were found in asbestos-exposed subjects, and both miRNAs are involved in major pathways linked to cancer development. Epigenetic changes and cancer-stroma cross-talk could induce repression of miR-126 to facilitate tumor formation, angiogenesis, and invasion. CONCLUSIONS: This study indicates that miRNAs are potentially involved in asbestos-related malignancies, and their expression outlines mechanism(s) whereby miRNAs may be involved in an asbestos-induced pathogenesis. IMPACT: The discovery of a miRNA panel for asbestos-related malignancies would impact on occupational compensation and may be utilized for screening asbestos-exposed populations.

Gadolinium tissue deposition in the periodontal ligament of mice with reduced renal function exposed to Gd-based contrast agents. - Delfino, Riccarda; Biasotto, Matteo; Candido, Riccardo; Altissimo, Matteo; Stebel, Marco; Salomè, Murielle; van Elteren, Johannes T; Vogel Mikuš, Katarina; Zennaro, Cristina; Šala, Martin; Addobbati, Riccardo; Tromba, Giuliana; et al. (Toxicol Lett, 2019)
Gadolinium deposition in tissue is linked to nephrogenic systemic fibrosis (NSF): a rare disorder occurring in patients with severe chronic kidney disease and associated with administration of Gd-based contrast agents (GBCAs) for Magnetic Resonance Imaging (MRI). It is suggested that the GBCAs prolonged permanence in blood in these patients may result in a Gd precipitation in peripheral or central organs, where it initiates a fibrotic process. In this study we investigated new sites of retention/precipitation of Gd in a mouse model of renal disease (5/6 nephrectomy) receiving two doses (closely after each other) of a linear GBCA. Two commercial GBCAs (Omniscan® and Magnevist®) were administered at doses slightly higher than those used in clinical practice (0.7 mmol/kg body weight, each). The animals were sacrificed one month after the last administration and the explanted organs (kidney, liver, femur, dorsal skin, teeth) were analysed by X-ray fluorescence (XRF) at two synchrotron facilities. The XRF analysis with a millimetre-sized beam at the SYRMEP beamline (Elettra, Italy) produced no detectable levels of Gd in the examined tissues, with the notable exception of the incisors of the nephrectomised mice. The XRF analyses at sub-micron resolution performed at ID21 (ESRF, France) allowed to clearly localize Gd in the periodontal ligaments of teeth both from Omniscan® and Magnevist® treated nephrectomised mice. The latter results were further confirmed by laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). The study prompts that prolonged permanence of GBCAs in blood may result in Gd retention in this particular muscular tissue, opening possibilities for diagnostic applications at this level when investigating Gd-related toxicities.
Keywords: Animals; Contrast Media; Disease Models, Animal; Dose-Response Relationship, Drug; Female; Gadolinium; Gadolinium DTPA; Magnetic Resonance Imaging; Mice; Nephrogenic Fibrosing Dermopathy; Periodontal Ligament; Renal Insufficiency; Tissue Distribution

Management of endometrial, ovarian and cervical cancer in the elderly: current approach to a challenging condition. - Vitale, Salvatore Giovanni; Capriglione, Stella; Zito, Gabriella; Lopez, Salvatore; Gulino, Ferdinando Antonio; Di Guardo, Federica; Vitagliano, Amerigo; Noventa, Marco; La Rosa, Valentina Lucia; Sapia, Fabrizio; Valenti, Gaetano; Rapisarda, Agnese Maria Chiara; et al. (Arch Gynecol Obstet, 2019)
PURPOSE: Gynaecological cancer management in older people represents a current challenge. Therefore, in the present paper, we aimed to gather all the evidence reported in the literature concerning gynecological cancers in the elderly, illustrating the state of art and the future perspectives. METHODS: We searched MEDLINE (PubMed), EMBASE, Cochrane Central Register of Controlled Trials, IBECS, BIOSIS, Web of Science, SCOPUS and Grey literature (Google Scholar; British Library) from January 1952 to May 2017, using the terms "ovarian cancer", "endometrial cancer", "cervical cancer", "gynecological cancers" combined with 'elderly', 'cancer', 'clinical trial' and 'geriatric assessment'. RESULTS: The search identified 81 citations, of which 65 were potentially relevant after initial evaluation and met the criteria for inclusion and were analyzed. We divided all included studies into three different issue: "Endometrial cancer", "Ovarian cancer" and "Cervical cancer". CONCLUSIONS: The present literature review shows that, in spite of the higher burden of comorbidities, elderly patients can also benefit from standard treatment to manage their gynecological cancers. It is important to overcome the common habit of undertreating the elderly patients because they are more fragile and with a lower life expectancy than their younger counterpart. Further trials with elderly women are warranted.

MYH9-Related Thrombocytopenia: Four Novel Variants Affecting the Tail Domain of the Non-Muscle Myosin Heavy Chain IIA Associated with a Mild Clinical Evolution of the Disorder. - Zaninetti, Carlo; De Rocco, Daniela; Giangregorio, Tania; Bozzi, Valeria; Demeter, Judit; Leoni, Pietro; Noris, Patrizia; Ryhänen, Samppa; Barozzi, Serena; Pecci, Alessandro; Savoia, Anna (Hamostaseologie, 2019)
-related disease (-RD) is an autosomal-dominant thrombocytopenia caused by mutations in the gene for non-muscle myosin heavy chain IIA (NMMHC-IIA). Patients present congenital macrothrombocytopenia and inclusions of NMMHC-IIA in leukocytes, and have a variable risk of developing kidney damage, sensorineural deafness, presenile cataracts and/or liver enzymes abnormalities. The spectrum of mutations found in -RD patients is limited and the incidence and severity of the non-congenital features are predicted by the causative variant. In particular, different alterations of the C-terminal tail domain of NMMHC-IIA associate with remarkably different disease evolution. We report four novel mutations affecting the tail domain of NMMHC-IIA and responsible for -RD in four families. Two variants cause amino acid substitutions in the coiled-coil region of NMMHC-IIA, while the other two are a splicing variant and a single nucleotide deletion both resulting in frameshift alterations of the short non-helical tailpiece. Characterization of phenotypes of affected individuals shows that all of these novel variants are associated with a mild clinical evolution of the disease.

Prevalence and phenotype of the c.1529C>T SPG7 variant in adult-onset cerebellar ataxia in Italy. - Mancini, C; Giorgio, E; Rubegni, A; Pradotto, L; Bagnoli, S; Rubino, E; Prontera, P; Cavalieri, S; Di Gregorio, E; Ferrero, M; Pozzi, E; Riberi, E; et al. (Eur J Neurol, 2019)
BACKGROUND AND PURPOSE: Hereditary ataxias are heterogeneous groups of neurodegenerative disorders, characterized by cerebellar syndromes associated with dysarthria, oculomotor and corticospinal signs, neuropathy and cognitive impairment. Recent reports have suggested mutations in the SPG7 gene, causing the most common form of autosomal recessive spastic paraplegia (MIM#607259), as a main cause of ataxias. The majority of described patients were homozygotes or compound heterozygotes for the c.1529C>T (p.Ala510Val) change. We screened a cohort of 895 Italian patients with ataxia for p.Ala510Val in order to define the prevalence and genotype-phenotype correlation of this variant. METHODS: We set up a rapid assay for c.1529C>T using restriction enzyme analysis after polymerase chain reaction amplification. We confirmed the diagnosis with Sanger sequencing. RESULTS: We identified eight homozygotes and 13 compound heterozygotes, including two novel variants affecting splicing. Mutated patients showed a pure cerebellar ataxia at onset, evolving in mild spastic ataxia (alternatively) associated with dysarthria (~80% of patients), urinary urgency (~30%) and pyramidal signs (~70%). Comparing homozygotes and compound heterozygotes, we noted a difference in age at onset and Scale for the Assessment and Rating of Ataxia score between the two groups, supporting an earlier and more severe phenotype in compound heterozygotes versus homozygotes. CONCLUSIONS: The SPG7 c.1529C>T (p.Ala510Val) mutants accounted for 2.3% of cerebellar ataxia cases in Italy, suggesting that this variant should be considered as a priority test in the presence of late-onset pure ataxia. Moreover, the heterozygous/homozygous genotype appeared to predict the onset of clinical manifestation and disease progression.

Antibody response to polyomavirus primary infection: high seroprevalence of Merkel cell polyomavirus and lymphoid tissue involvement. - Cason, Carolina; Monasta, Lorenzo; Zanotta, Nunzia; Campisciano, Giuseppina; Maestri, Iva; Tommasino, Massimo; Pawlita, Michael; Villani, Sonia; Comar, Manola; Delbue, Serena (J Neurovirol, 2018)
Human polyomaviruses (HPyVs) asymptomatically infect the human population establishing latency in the host, and their seroprevalence can reach 90% in healthy adults. Few studies have focused on the pediatric population, and there are no reports regarding the seroprevalence of all the newly isolated HPyVs among Italian children. Therefore, we investigated the frequency of serum antibodies against 12 PyVs in 182 immunocompetent children from Northeast Italy, by means of a multiplex antibody detection system. Additionally, secondary lymphoid tissues were collected to analyze the presence of HPyV DNA sequences using a specific real-time PCRs or PCRs. Almost 100% of subjects were seropositive for at least one PyV. Seropositivity ranged from 3% for antibodies against simian virus 40 (SV40) in children from 0 to 3 years, to 91% for antibodies against WU polyomavirus (WUPyV) and HPyV10 in children from 8 to 17 years. The mean number of PyV for which children were seropositive increased with the increasing of age: 4 standard deviations (SD) 1.8 in the 0-3-year group, 5 (SD 1.9) in the 4-7-year group, and 6 (SD 2.2) in the 8-17-year group. JC polyomavirus (JCPyV) DNA was detected in 1% of the adenoids, WUPyV in 12% of the tonsils, and 28% of the adenoids, and Merkel cell polyomavirus (MCPyV) was present in 6 and 2% of the tonsils and adenoids, respectively. Our study gives new insights on the serological evidence of exposure to PyVs during childhood, and on their possible respiratory route of transmission.

Anti-transglutaminase 6 Antibody Development in Children With Celiac Disease Correlates With Duration of Gluten Exposure. - De Leo, Luigina; Aeschlimann, Daniel; Hadjivassiliou, Marios; Aeschlimann, Pascale; Salce, Nicola; Vatta, Serena; Ziberna, Fabiana; Cozzi, Giorgio; Martelossi, Stefano; Ventura, Alessandro; Not, Tarcisio (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: Antibodies against transglutaminase 6 (anti-TG6) have been implicated in neurological manifestations in adult patients with genetic gluten intolerance, and it is unclear whether autoimmunity to TG6 develops following prolonged gluten exposure. We measured the anti-TG6 in children with celiac disease (CD) at the diagnosis time to establish a correlation between these autoantibodies and the duration of gluten exposure. We investigated a correlation between anti-TG6 and the presence of neurological disorders. METHODS: Anti-TG6 (IgA/IgG) were measured by ELISA in sera of children with biopsy-proven CD and of children experiencing gastrointestinal disorders. CD patients positive for anti-TG6 were retested after 2 years of gluten-free diet (GFD). RESULTS: We analyzed the sera of 274 CD children and of 121 controls. Anti-TG6 were detected in 68/274 (25%) CD patients and in 19/121 (16%) controls, with significant difference between the 2 groups (P = 0.04). None of the CD patients and of the controls testing positive for anti-TG6 were experiencing neurological disorders. Eleven of 18 (61%) CD patients with other autoimmune diseases were positive for anti-TG6. In CD patients, a significant correlation between the gluten exposure before the CD diagnosis and anti-TG6 concentration was found (P = 0.006 for IgA; P < 0.0001 for IgG). After GFD anti-TG6 concentrations were significantly reduced (P < 0.001). No significant correlation was observed between anti-TG6 and anti-TG2 serum concentrations. CONCLUSIONS: Anti-TG6 are more prevalent in children with untreated CD in the absence of overt neurological disorders. The synthesis of the anti-TG6 is related to a longer exposure to gluten before the CD diagnosis, and the autoimmunity against TG6 is gluten dependent and disappeared during GFD.

Benign hereditary chorea and deletions outside NKX2-1: What's the role of MBIP? - Invernizzi, Federica; Zorzi, Giovanna; Legati, Andrea; Coppola, Giovanni; d'Adamo, Pio; Nardocci, Nardo; Garavaglia, Barbara; Ghezzi, Daniele (Eur J Med Genet, 2018)
Heterozygous point mutations or deletions of the NKX2-1 gene cause benign hereditary chorea (BHC) or a various combinations of primary hypothyroidism, respiratory distress and neurological disorders. Deletions proximal to, but not encompassing, NKX2-1 have been described in few subjects with brain-lung-thyroid syndrome. We report on a three-generation Italian family, with 6 subjects presenting BHC and harboring a genomic deletion adjacent to NKX2-1 and including the gene MBIP, recently proposed to be relevant for the pathogenesis of brain-lung-thyroid syndrome. We observed a clear reduction of NKX2-1 transcript levels in fibroblasts from our patients compared to controls; this finding suggests that MBIP deletion affects NKX2-1 expression, mimicking haploinsufficiency caused by classical NKX2-1 related mutations.
Keywords: Cells, Cultured; Chorea; Haploinsufficiency; Humans; Intracellular Signaling Peptides and Proteins; Pedigree; Sequence Deletion; Thyroid Nuclear Factor 1

Cell-autonomous and cell non-autonomous downregulation of tumor suppressor DAB2IP by microRNA-149-3p promotes aggressiveness of cancer cells. - Bellazzo, Arianna; Di Minin, Giulio; Valentino, Elena; Sicari, Daria; Torre, Denis; Marchionni, Luigi; Serpi, Federica; Stadler, Michael B; Taverna, Daniela; Zuccolotto, Gaia; Montagner, Isabella Monia; Rosato, Antonio; et al. (Cell Death Differ, 2018)
The tumor suppressor DAB2IP contributes to modulate the network of information established between cancer cells and tumor microenvironment. Epigenetic and post-transcriptional inactivation of this protein is commonly observed in multiple human malignancies, and can potentially favor progression of tumors driven by a variety of genetic mutations. Performing a high-throughput screening of a large collection of human microRNA mimics, we identified miR-149-3p as a negative post-transcriptional modulator of DAB2IP. By efficiently downregulating DAB2IP, this miRNA enhances cancer cell motility and invasiveness, facilitating activation of NF-kB signaling and promoting expression of pro-inflammatory and pro-angiogenic factors. In addition, we found that miR-149-3p secreted by prostate cancer cells induces DAB2IP downregulation in recipient vascular endothelial cells, stimulating their proliferation and motility, thus potentially remodeling the tumor microenvironment. Finally, we found that inhibition of endogenous miR-149-3p restores DAB2IP activity and efficiently reduces tumor growth and dissemination of malignant cells. These observations suggest that miR-149-3p can promote cancer progression via coordinated inhibition of DAB2IP in tumor cells and in stromal cells.

Cerebrospinal Fluid Cytokine Expression Profile in Multiple Sclerosis and Chronic Inflammatory Demyelinating Polyneuropathy. - Bonin, Serena; Zanotta, Nunzia; Sartori, Arianna; Bratina, Alessio; Manganotti, Paolo; Trevisan, Giusto; Comar, Manola (Immunol Invest, 2018)
BACKGROUND: Cerebrospinal fluid (CSF) analysis in patients with particular neurologic disorders is a powerful tool to evaluate specific central nervous system inflammatory markers for diagnostic needs, because CSF represents the specific immune micro-environment to the central nervous system. METHODS: CSF samples from 49 patients with multiple sclerosis (MS), chronic inflammatory demyelinating polyneuropathy (CIDP), and non-inflammatory neurologic disorders (NIND) as controls were submitted to protein expression profiles of 47 inflammatory biomarkers by multiplex Luminex bead assay to investigate possible differences in the inflammatory process for MS and CIDP. RESULTS: Our results showed differences in CSF cytokine levels in MS and CIDP; in particular, IL12 (p40) was significantly highly expressed in MS in comparison with CIDP and NIND, while SDF-1α and SCGF-β were significantly highly expressed in CIDP cohort when compared to MS and NIND. IL-9, IL-13, and IL-17 had higher expression levels in NIND if compared with the other groups. CONCLUSIONS: Our study showed that, despite some common pathogenic mechanisms, central and peripheral nervous system demyelinating diseases, such as MS and CIDP, differ in some specific inflammatory soluble proteins in CSF, underlining differences in the immune response involved in those autoimmune diseases.
Keywords: Adult; Aged; Biomarkers; Central Nervous System; Diagnosis, Differential; Female; Hematopoietic Cell Growth Factors; Humans; Interleukin-12; Lectins, C-Type; Male; Middle Aged; Multiple Sclerosis; Peripheral Nervous System; Polyradiculoneuropathy, Chronic Inflammatory Demyelinating; Proteins

Complete Remission of a Refractory Acute Myeloid Leukemia with Myelodysplastic- and Monosomy 7-Related Changes after a Combined Conditioning Regimen of Plerixafor, Cytarabine and Melphalan in a 4-Year-Old Boy: A Case Report and Review of Literature. - Grasso, Antonio G; Granzotto, Marilena; Zanon, Davide; Maestro, Alessandra; Loiacono, Stefano; Maximova, Natalia (Cancers (Basel), 2018)
Acute myeloid leukemia with myelodysplastic changes and monosomy 7 is a rare form of pediatric leukemia associated with very poor disease-free survival. The refractoriness of the disease is due to the protection offered by the bone marrow niche, making leukemic stem cells impervious to whatever chemotherapy or myeloablative regimen is chosen. Using a mobilizing agent for haematopoietic stem cells, Plerixafor, could sensitise leukemic cells to the myeloablative therapy. This approach was not previously used in a pediatric population, and in adult populations, was used in combination with busulphan with no difference in overall survival. We describe the case of a 4-year-old boy affected by refractory acute myeloid leukemia with myelodysplastic changes and monosomy 7. The child had never achieved a remission. We proposed a combined time-scheduled scheme of therapy with plerixafor and melphalan. Combining pharmacokinetics of plerixafor with pharmacokinetics and rapid and elevated myeloablative potential of melphalan in high dosage (200 mg/m²), we succeeded in mobilizing more than 85% of stem blasts immediately before infusion of Melphalan. The count of residual blasts after 8 h from melphalan infusion was only 1.3 cells/μL. The child achieved an engraftment at day +32 with full donor chimerism. Sixteen months after haematopoietic stem cell transplantation (HSCT), he is well and in complete remission. Our case suggests that the use of plerixafor before a conditioning therapy with melphalan could induce remission in acute myeloid leukemia refractory to the usual conditioning therapy in pediatric patients. This work adds strength to the body of knowledge regarding the "personalized" conditioning regimen for high-risk leukemic patients.

Cx26 partial loss causes accelerated presbycusis by redox imbalance and dysregulation of Nfr2 pathway. - Fetoni, Anna Rita; Zorzi, Veronica; Paciello, Fabiola; Ziraldo, Gaia; Peres, Chiara; Raspa, Marcello; Scavizzi, Ferdinando; Salvatore, Anna Maria; Crispino, Giulia; Tognola, Gabriella; Gentile, Giulia; Spampinato, Antonio Gianmaria; et al. (Redox Biol, 2018)
Mutations in GJB2, the gene that encodes connexin 26 (Cx26), are the most common cause of sensorineural hearing impairment. The truncating variant 35delG, which determines a complete loss of Cx26 protein function, is the prevalent GJB2 mutation in several populations. Here, we generated and analyzed Gjb2 mice as a model of heterozygous human carriers of 35delG. Compared to control mice, auditory brainstem responses (ABRs) and distortion product otoacoustic emissions (DPOAEs) worsened over time more rapidly in Gjb2 mice, indicating they were affected by accelerated age-related hearing loss (ARHL), or presbycusis. We linked causally the auditory phenotype of Gjb2 mice to apoptosis and oxidative damage in the cochlear duct, reduced release of glutathione from connexin hemichannels, decreased nutrient delivery to the sensory epithelium via cochlear gap junctions and deregulated expression of genes that are under transcriptional control of the nuclear factor erythroid 2-related factor 2 (Nrf2), a pivotal regulator of tolerance to redox stress. Moreover, a statistically significant genome-wide association with two genes (PRKCE and TGFB1) related to the Nrf2 pathway (p-value < 4 × 10) was detected in a very large cohort of 4091 individuals, originating from Europe, Caucasus and Central Asia, with hearing phenotype (including 1076 presbycusis patients and 1290 healthy matched controls). We conclude that (i) elements of the Nrf2 pathway are essential for hearing maintenance and (ii) their dysfunction may play an important role in the etiopathogenesis of human presbycusis.
Keywords: Animals; Apoptosis; Connexin 26; Female; Gene Deletion; Male; Mice; Mice, Inbred C57BL; NF-E2-Related Factor 2; Oxidation-Reduction; Presbycusis; Signal Transduction

Cytokine profiles of women with vulvodynia: Identification of a panel of pro-inflammatory molecular targets. - Zanotta, Nunzia; Campisciano, Giuseppina; Scrimin, Federica; Blendi, Ura; Marcuzzi, Annalisa; Vincenti, Ezio; Crovella, Sergio; Comar, Manola (Eur J Obstet Gynecol Reprod Biol, 2018)
OBJECTIVE: The vulvar pain syndrome (VPS) is a multifactorial disease severely influencing the lifestyle of affected women. Among possible etiological factors, local injury, peripheral and/or central sensitization of the nervous system, and a chronic inflammatory status have been positively associated with the development of VPS. The identification of a constitutive altered local inflammatory profile in VPS women may represent an important point in the characterization of patients' phenotype as a useful marker influencing the vulvar micro-environment. The aim of this study was to investigative the possible role of the local cytokines production in women with VPS in comparison to healthy women. STUDY DESIGN: In this study were collected vaginal swabs from 57 healthy women (HC) who never suffered from VPS and from 30 patients diagnosed with vulvodynia (VPS) by at least 3 years and currently symptomatic. All patients included in this study showed the absence of Sexually Transmitted (STD) diseases and Reproductive Tract Infection. Real-time PCR was performed to assess the genomic sequences of ST pathogens. The Luminex Bio-Plex platform was used for the analysis of a panel of 48 immune factors. RESULTS: Eleven molecules, specifically involved in the pro-inflammatory pathway were significantly modulated in VPS patients in comparison to healthy women, suggesting a persistent inflammatory process. CONCLUSIONS: Therefore, these inflammatory factors could be possible biological markers involved in this disease. Nevertheless, other studies are needed to consider this specific immune profile as a valid marker of the vulvodynia.
Keywords: Adult; Aged; Cytokines; Female; Humans; Inflammation; Middle Aged; Vaginal Smears; Vulva; Vulvodynia; Women's Health

De novo unbalanced translocations have a complex history/aetiology. - Bonaglia, Maria Clara; Kurtas, Nehir Edibe; Errichiello, Edoardo; Bertuzzo, Sara; Beri, Silvana; Mehrjouy, Mana M; Provenzano, Aldesia; Vergani, Debora; Pecile, Vanna; Novara, Francesca; Reho, Paolo; Di Giacomo, Marilena Carmela; et al. (Hum Genet, 2018)
We investigated 52 cases of de novo unbalanced translocations, consisting in a terminally deleted or inverted-duplicated deleted (inv-dup del) 46th chromosome to which the distal portion of another chromosome or its opposite end was transposed. Array CGH, whole-genome sequencing, qPCR, FISH, and trio genotyping were applied. A biparental origin of the deletion and duplication was detected in 6 cases, whereas in 46, both imbalances have the same parental origin. Moreover, the duplicated region was of maternal origin in more than half of the cases, with 25% of them showing two maternal and one paternal haplotype. In all these cases, maternal age was increased. These findings indicate that the primary driver for the occurrence of the de novo unbalanced translocations is a maternal meiotic non-disjunction, followed by partial trisomy rescue of the supernumerary chromosome present in the trisomic zygote. In contrast, asymmetric breakage of a dicentric chromosome, originated either at the meiosis or postzygotically, in which the two resulting chromosomes, one being deleted and the other one inv-dup del, are repaired by telomere capture, appears at the basis of all inv-dup del translocations. Notably, this mechanism also fits with the origin of some simple translocations in which the duplicated region was of paternal origin. In all cases, the signature at the translocation junctions was that of non-homologous end joining (NHEJ) rather than non-allelic homologous recombination (NAHR). Our data imply that there is no risk of recurrence in the following pregnancies for any of the de novo unbalanced translocations we discuss here.
Keywords: DNA End-Joining Repair; Female; Humans; Male; Meiosis; Recombinational DNA Repair; Translocation, Genetic

DEFB1 polymorphisms and HIV-1 mother-to-child transmission in Zambian population. - Zupin, Luisa; Polesello, Vania; Segat, Ludovica; Kamada, Anselmo Jiro; Kuhn, Louise; Crovella, Sergio (J Matern Fetal Neonatal Med, 2018)
INTRODUCTION: Human Beta Defensin-1 (hBD-1) is a component of the innate immune system, the first line of defence against pathogens, already reported as involved in the susceptibility to HIV-1 infection and HIV-1 mother-to-child transmission (MTCT) in different populations. We investigated the role of DEFB1 gene (encoding for hBD-1) functional polymorphisms in the susceptibility to HIV-1 MTCT in a population from Zambia. METHODS: Four selected polymorphisms within DEFB1 gene, three at the 5' untranslated region (UTR), namely -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362) and one in the 3'UTR, c.*87A > G (rs1800972), were genotyped in 101 HIV-1 positive mothers (26 transmitters -27% and 75 not transmitters -73%) and 331 infants born to HIV-1 infected mothers (85 HIV-1 positive -26% and 246 exposed but not infected -74%). RESULTS: DEFB1 c.*87-A allele was more frequent among HIV- children with respect to HIV+ (with intrauterine MTCT). Concerning DEFB1 haplotypes, GCGA haplotype resulted more represented in HIV- than HIV+ infants and DEFB1 ACGG haplotype presented increased frequency in HIV- children respect to HIV+ (with intra-partum MTCT) (p = .02, p = .002 and p = .006, respectively). CONCLUSIONS: DEFB1 polymorphisms were significantly associated with decreased risk of HIV-1 infection acquisition in the studied Zambian population suggesting that they may play a role in HIV-1 MTCT.

Efficacy and Safety of Adalimumab in Pediatric Ulcerative Colitis: A Real-life Experience from the SIGENP-IBD Registry. - Aloi, Marina; Bramuzzo, Matteo; Arrigo, Serena; Romano, Claudio; D'Arcangelo, Giulia; Lacorte, Doriana; Gatti, Simona; Illiceto, Maria T; Zucconi, Francesca; Dilillo, Dario; Zuin, Giovanna; Knafelz, Daniela; et al. (J Pediatr Gastroenterol Nutr, 2018)
OBJECTIVES: The aim of this study was to evaluate the effectiveness and safety of adalimumab (ADA) in children with ulcerative colitis (UC) previously treated with infliximab (IFX). METHODS: Retrospective study including children with UC from a national registry who received ADA therapy. The primary endpoint was the rate of corticosteroid-free remission at week 52. Secondary outcomes were the rate of sustained clinical remission, primary nonresponse, and loss of response at weeks 12, 30, and 52 and rate of mucosal healing and side effects at week 52. RESULTS: Thirty-two children received ADA (median age 10 ± 4 years). Median disease duration before ADA therapy was 27 months. All patients received previous IFX (43% intolerant, 50% nonresponders [37.5% primary, 42.5% secondary nonresponders], 6.7% positive anti-IFX antibodies). Fifty-two weeks after ADA initiation, 13 patients (41%) were in corticosteroid-free remission. Mucosal healing occurred in 9 patients (28%) at 52 weeks. The cumulative probability of a clinical relapse-free course was 69%, 59%, and 53% at 12, 30, and 52 weeks, respectively. Ten patients (31%) had a primary failure and 5 (15%) a loss of response to ADA. No significant differences in efficacy were reported between not-responders and intolerant to IFX (P = 1.0). Overall, 19 patient (59%) maintained ADA during 52-week follow-up. Seven patients (22%) experienced an adverse event, no serious side effects were observed and none resulted in ADA discontinuation. CONCLUSIONS: Based on our data, ADA seems to be effective in children with UC, allowing to recover a significant percentage of patients intolerant or not-responding to IFX. The safety profile was good.

Fractional CO laser for genitourinary syndrome of menopause in breast cancer survivors: clinical, immunological, and microbiological aspects. - Becorpi, Angelamaria; Campisciano, Giuseppina; Zanotta, Nunzia; Tredici, Zelinda; Guaschino, Secondo; Petraglia, Felice; Pieralli, Annalisa; Sisti, Giovanni; De Seta, Francesco; Comar, Manola (Lasers Med Sci, 2018)
The composition of vaginal microbiome in menopause and cancer survivor women changes dramatically leading to genitourinary syndrome of menopause (GSM) in up to 70% of patients. Recent reports suggest that laser therapy may be valuable as a not hormonal therapeutic modality. The aim of the present study was to evaluate the effects of fractional CO laser treatment on the vaginal secretory pathway of a large panel of immune mediators, usually implicated in tissue remodeling and inflammation, and on microbiome composition in postmenopausal breast cancer survivors. The Ion Torrent PGM platform and the Luminex Bio-Plex platform were used for microbiome and immune factor analysis. The significant reduction of clinical symptoms and the non-significant changes in vaginal microbiome support the efficacy and safety of laser treatment. Moreover, the high remodeling status in vaginal epithelium is demonstrated by the significant changes in inflammatory and modulatory cytokine patterns. Laser therapy can be used for the treatment of GSM symptoms and does not show any adverse effects. However, further studies will be needed to clarify its long-term efficacy and other effects.
Keywords: Breast Neoplasms; Cancer Survivors; Cytokines; Dyspareunia; Female; Humans; Lasers, Gas; Menopause; Microbiota; Middle Aged; Prospective Studies; Syndrome; Vagina; Vaginal Diseases

Gene discovery and polygenic prediction from a genome-wide association study of educational attainment in 1.1 million individuals. - Lee, James J; Wedow, Robbee; Okbay, Aysu; Kong, Edward; Maghzian, Omeed; Zacher, Meghan; Nguyen-Viet, Tuan Anh; Bowers, Peter; Sidorenko, Julia; Karlsson Linnér, Richard; Fontana, Mark Alan; Kundu, Tushar; et al. (Nat Genet, 2018)
Here we conducted a large-scale genetic association analysis of educational attainment in a sample of approximately 1.1 million individuals and identify 1,271 independent genome-wide-significant SNPs. For the SNPs taken together, we found evidence of heterogeneous effects across environments. The SNPs implicate genes involved in brain-development processes and neuron-to-neuron communication. In a separate analysis of the X chromosome, we identify 10 independent genome-wide-significant SNPs and estimate a SNP heritability of around 0.3% in both men and women, consistent with partial dosage compensation. A joint (multi-phenotype) analysis of educational attainment and three related cognitive phenotypes generates polygenic scores that explain 11-13% of the variance in educational attainment and 7-10% of the variance in cognitive performance. This prediction accuracy substantially increases the utility of polygenic scores as tools in research.

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.

A genetic variant of NLRP1 gene is associated with asbestos body burden in patients with malignant pleural mesothelioma. - Crovella, S; Moura, R R; Cappellani, S; Celsi, F; Trevisan, E; Schneider, M; Brollo, A; Nicastro, E M; Vita, F; Finotto, L; Zabucchi, G; Borelli, V (J Toxicol Environ Health A, 2018)
The presence of asbestos bodies (ABs) in lung parenchyma is considered a histopathologic hallmark of past exposure to asbestos fibers, of which there was a population of longer fibers. The mechanisms underlying AB formation are complex, involving inflammatory responses and iron (Fe) metabolism. Thus, the responsiveness to AB formation is variable, with some individuals appearing to be poor AB formers. The aim of this study was to disclose the possible role of genetic variants of genes encoding inflammasome and iron metabolism proteins in the ability to form ABs in a population of 81 individuals from North East Italy, who died after having developed malignant pleural mesothelioma (MPM). This study included 86 genetic variants distributed in 10 genes involved in Fe metabolism and 7 genetic variants in two genes encoding for inflammasome molecules. Genotypes/haplotypes were compared according to the number of lung ABs. Data showed that the NLRP1 rs12150220 missense variant (H155L) was significantly correlated with numbers of ABs in MPM patients. Specifically, a low number of ABs was detected in individuals carrying the NLRP1 rs12150220 A/T genotype. Our findings suggest that the NLRP1 inflammasome might contribute in the development of lung ABs. It is postulated that the NLRP1 missense variant may be considered as one of the possible host genetic factors contributing to individual variability in coating efficiency, which needs to be taken when assessing occupational exposure to asbestos.

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.

Genome-wide association meta-analysis highlights light-induced signaling as a driver for refractive error. - Tedja, Milly S; Wojciechowski, Robert; Hysi, Pirro G; Eriksson, Nicholas; Furlotte, Nicholas A; Verhoeven, Virginie J M; Iglesias, Adriana I; Meester-Smoor, Magda A; Tompson, Stuart W; Fan, Qiao; Khawaja, Anthony P; Cheng, Ching-Yu; et al. (Nat Genet, 2018)
Refractive errors, including myopia, are the most frequent eye disorders worldwide and an increasingly common cause of blindness. This genome-wide association meta-analysis in 160,420 participants and replication in 95,505 participants increased the number of established independent signals from 37 to 161 and showed high genetic correlation between Europeans and Asians (>0.78). Expression experiments and comprehensive in silico analyses identified retinal cell physiology and light processing as prominent mechanisms, and also identified functional contributions to refractive-error development in all cell types of the neurosensory retina, retinal pigment epithelium, vascular endothelium and extracellular matrix. Newly identified genes implicate novel mechanisms such as rod-and-cone bipolar synaptic neurotransmission, anterior-segment morphology and angiogenesis. Thirty-one loci resided in or near regions transcribing small RNAs, thus suggesting a role for post-transcriptional regulation. Our results support the notion that refractive errors are caused by a light-dependent retina-to-sclera signaling cascade and delineate potential pathobiological molecular drivers.

Genome-wide association meta-analysis of individuals of European ancestry identifies new loci explaining a substantial fraction of hair color variation and heritability. - Hysi, Pirro G; Valdes, Ana M; Liu, Fan; Furlotte, Nicholas A; Evans, David M; Bataille, Veronique; Visconti, Alessia; Hemani, Gibran; McMahon, George; Ring, Susan M; Smith, George Davey; Duffy, David L; et al. (Nat Genet, 2018)
Hair color is one of the most recognizable visual traits in European populations and is under strong genetic control. Here we report the results of a genome-wide association study meta-analysis of almost 300,000 participants of European descent. We identified 123 autosomal and one X-chromosome loci significantly associated with hair color; all but 13 are novel. Collectively, single-nucleotide polymorphisms associated with hair color within these loci explain 34.6% of red hair, 24.8% of blond hair, and 26.1% of black hair heritability in the study populations. These results confirm the polygenic nature of complex phenotypes and improve our understanding of melanin pigment metabolism in humans.

A genome-wide association study of corneal astigmatism: The CREAM Consortium. - Shah, Rupal L; Li, Qing; Zhao, Wanting; Tedja, Milly S; Tideman, J Willem L; Khawaja, Anthony P; Fan, Qiao; Yazar, Seyhan; Williams, Katie M; Verhoeven, Virginie J M; Xie, Jing; Wang, Ya Xing; et al. (Mol Vis, 2018)
Purpose: To identify genes and genetic markers associated with corneal astigmatism. Methods: A meta-analysis of genome-wide association studies (GWASs) of corneal astigmatism undertaken for 14 European ancestry (n=22,250) and 8 Asian ancestry (n=9,120) cohorts was performed by the Consortium for Refractive Error and Myopia. Cases were defined as having >0.75 diopters of corneal astigmatism. Subsequent gene-based and gene-set analyses of the meta-analyzed results of European ancestry cohorts were performed using VEGAS2 and MAGMA software. Additionally, estimates of single nucleotide polymorphism (SNP)-based heritability for corneal and refractive astigmatism and the spherical equivalent were calculated for Europeans using LD score regression. Results: The meta-analysis of all cohorts identified a genome-wide significant locus near the platelet-derived growth factor receptor alpha () gene: top SNP: rs7673984, odds ratio=1.12 (95% CI:1.08-1.16), p=5.55×10. No other genome-wide significant loci were identified in the combined analysis or European/Asian ancestry-specific analyses. Gene-based analysis identified three novel candidate genes for corneal astigmatism in Europeans-claudin-7 (), acid phosphatase 2, lysosomal (), and TNF alpha-induced protein 8 like 3 (). Conclusions: In addition to replicating a previously identified genome-wide significant locus for corneal astigmatism near the gene, gene-based analysis identified three novel candidate genes, , , and , that warrant further investigation to understand their role in the pathogenesis of corneal astigmatism. The much lower number of genetic variants and genes demonstrating an association with corneal astigmatism compared to published spherical equivalent GWAS analyses suggest a greater influence of rare genetic variants, non-additive genetic effects, or environmental factors in the development of astigmatism.
Keywords: Acid Phosphatase; Asian Continental Ancestry Group; Astigmatism; Claudins; Cohort Studies; Cornea; Corneal Diseases; European Continental Ancestry Group; Gene Expression; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Intracellular Signaling Peptides and Proteins; Odds Ratio; Polymorphism, Single Nucleotide; Receptor, Platelet-Derived Growth Factor alpha; Software

High-Throughput Sequencing of microRNAs in Glucocorticoid Sensitive Paediatric Inflammatory Bowel Disease Patients. - De Iudicibus, Sara; Lucafò, Marianna; Vitulo, Nicola; Martelossi, Stefano; Zimbello, Rosanna; De Pascale, Fabio; Forcato, Claudio; Naviglio, Samuele; Di Silvestre, Alessia; Gerdol, Marco; Stocco, Gabriele; Valle, Giorgio; et al. (Int J Mol Sci, 2018)
The aim of this research was the identification of novel pharmacogenomic biomarkers for better understanding the complex gene regulation mechanisms underpinning glucocorticoid (GC) action in paediatric inflammatory bowel disease (IBD). This goal was achieved by evaluating high-throughput microRNA (miRNA) profiles during GC treatment, integrated with the assessment of expression changes in GC receptor (GR) heterocomplex genes. Furthermore, we tested the hypothesis that differentially expressed miRNAs could be directly regulated by GCs through investigating the presence of GC responsive elements (GREs) in their gene promoters. Ten IBD paediatric patients responding to GCs were enrolled. Peripheral blood was obtained at diagnosis (T0) and after four weeks of steroid treatment (T4). MicroRNA profiles were analyzed using next generation sequencing, and selected significantly differentially expressed miRNAs were validated by quantitative reverse transcription-polymerase chain reaction. In detail, 18 miRNAs were differentially expressed from T0 to T4, 16 of which were upregulated and 2 of which were downregulated. Out of these, three miRNAs (miR-144, miR-142, and miR-96) could putatively recognize the 3’UTR of the GR gene and three miRNAs (miR-363, miR-96, miR-142) contained GREs sequences, thereby potentially enabling direct regulation by the GR. In conclusion, we identified miRNAs differently expressed during GC treatment and miRNAs which could be directly regulated by GCs in blood cells of young IBD patients. These results could represent a first step towards their translation as pharmacogenomic biomarkers.
Keywords: Adolescent; Biomarkers; Child; Female; Gene Expression Regulation; Glucocorticoids; High-Throughput Nucleotide Sequencing; Humans; Inflammatory Bowel Diseases; Male; MicroRNAs; Receptors, Glucocorticoid; Transcriptome

Human beta defensin-1 is involved in the susceptibility to adeno-tonsillar hypertrophy. - Zupin, Luisa; Celsi, Fulvio; Bresciani, Martina; Orzan, Eva; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2018)
INTRODUCTION: Innate immunity molecules are known to play a pivotal role in the homeostasis of the oral mucosa, permitting the presence of commensal microflora and, at the same time, providing a first line of defense against pathogens attempting to invade the oral cavity. Tonsils represent the local immune tissue in oral cavity, being able to provide a non-specific response to pathogens; however, in the presence of microbes or foreign materials present in the mouth tonsils could became infected and develop chronic inflammation, thus leading to hypertrophy. The etiology of the disease is multifactorial depending upon environmental and host factors, the latter including molecules of mucosal innate immunity. METHODS: Ninety-five children with adeno-tonsillar hypertrophy subjected to adeno-tonsillectomy were recruited at the pediatric otorhinolaryngology service of the Institute for Maternal and Child Health IRCCS Burlo Garofolo, Trieste (Italy). The specimen discarded from the surgery were used for genomic DNA extraction and genotyping, for mRNA extraction and gene expression analysis, finally the samples were cut and used to prepare slides to perform immunohistochemistry. RESULTS: Functional polymorphisms within DEFB1 gene, encoding the human beta defensin-1 (hBD-1), were analyzed finding association between DEFB1 rare haplotypes and susceptibility to adeno-tonsillar hypertrophy. DEFB1 mRNA expression was detected in the tonsils and the hBD-1 protein was localized at the epithelia of tonsils mainly in the proximity of the basal lamina. CONCLUSION: Our findings lead us to hypothesize an involvement of hBD-1 mediated innate immunity in the modulation of the susceptibility towards adeno-tonsillar hypertrophy development.
Keywords: Adenoidectomy; Adenoids; Adolescent; beta-Defensins; Child; Child, Preschool; Female; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Hypertrophy; Immunity, Innate; Immunohistochemistry; Italy; Male; Palatine Tonsil; Tonsillectomy

Immunohistologic analysis of the duodenal bulb: a new method for celiac disease diagnosis in children. - De Leo, Luigina; Villanacci, Vincenzo; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Di Leo, Grazia; Zanchi, Chiara; Bramuzzo, Matteo; Giudici, Fabiola; Ventura, Alessandro; Not, Tarcisio (Gastrointest Endosc, 2018)
BACKGROUND AND AIMS: Anti-tissue transglutaminase antibodies (anti-tTG) have simplified celiac disease (CD) diagnosis. However, in atypical forms of CD, intestinal biopsy sampling is still required. This prospective study investigates whether histologic analysis of the duodenal bulb combined with intestinal IgA anti-tTG deposit immunoassay makes CD diagnosis possible in at-risk children with low concentrations of serum anti-tTG. METHODS: Histologic and intestinal IgA anti-tTG deposit immunoassays were used. RESULTS: Two hundred forty-five symptomatic children positive for serum anti-tTG (>7 U/mL) were enrolled and divided into 3 groups: extensive duodenal atrophy (n = 209), with IgA anti-tTG deposits throughout the duodenum and high serum anti-tTG concentrations (157 ± 178 U/mL); bulb duodenal atrophy (n = 22), with widespread IgA anti-tTG deposits in 9 and in the bulb alone in 13 and low serum anti-tTG concentrations (13.9 ± 8.7 U/mL); and normal duodenum (n = 14), with widespread IgA anti-tTG deposits in 8 and in the bulb alone in 6 and low serum anti-tTG concentrations (10.6 ± 6.2 U/mL). All patients in the first 2 groups were diagnosed with CD and 8 from the third group. All improved after 1 year of gluten-free diet. Bulb duodenal analysis led to a 12% (30/245) increase in CD diagnosis. No CD-related lesions were observed in the 30 control subjects. CONCLUSIONS: In children at risk for CD, bulb duodenum biopsy sampling is essential to identify villous atrophy and detect IgA anti-tTG deposits even in absence of intestinal lesions. These mucosal autoantibodies could well represent a new standard for diagnosing CD.
Keywords: Adolescent; Autoantibodies; Celiac Disease; Child; Child, Preschool; Duodenum; Female; Humans; Immunoglobulin A; Immunohistochemistry; Infant; Male; Prospective Studies; Transglutaminases

In vivo microbiome and associated immune markers: New insights into the pathogenesis of vaginal dysbiosis. - Campisciano, Giuseppina; Zanotta, Nunzia; Licastro, Danilo; De Seta, Francesco; Comar, Manola (Sci Rep, 2018)
The microbiota fulfils a key role in the training and function of the immune system, which contributes to the symbiosis between the host and complex microbial communities. In this study, we characterized the interplay between vaginal bacteria and local immune mediators during dysbiosis in selected women of reproductive age who were grouped according to Nugent's criteria. The abundance of Gardnerella vaginalis and Bifidobacterium breve was increased in the intermediate dysbiotic status, while the presence of a plethora of non-resident bacteria characterized the group with overt vaginosis. In response to these increases, the anti-inflammatory IL1ra and pro-inflammatory IL2 increased, while the embryo trophic factors FGFβ and GMCSF decreased compared to the healthy milieu. A specific pattern, including IL1α, IL1β, IL8, MIG, MIP1α and RANTES, distinguished the intermediate group from the vaginosis group, while IL5 and IL13, which are secreted by Th2 cells, were significantly associated with the perturbation of the commensals Lactobacilli, Gardnerella and Ureaplasma. Summarizing, we postulate that although the dysbiotic condition triggers a pro-inflammatory process, the presence of a steady state level of Th2 may influence clinical manifestations. These results raise clinically relevant questions regarding the use of vaginal immunological markers as efficacious tools to monitor microbial alterations.
Keywords: Adult; Biomarkers; Cytokines; Dysbiosis; Female; Humans; Microbiota; Th2 Cells; Vagina

Iron-related toxicity of single-walled carbon nanotubes and crocidolite fibres in human mesothelial cells investigated by Synchrotron XRF microscopy. - Cammisuli, Francesca; Giordani, Silvia; Gianoncelli, Alessandra; Rizzardi, Clara; Radillo, Lucia; Zweyer, Marina; Da Ros, Tatiana; Salomè, Murielle; Melato, Mauro; Pascolo, Lorella (Sci Rep, 2018)
Carbon nanotubes (CNTs) are promising products in industry and medicine, but there are several human health concerns since their fibrous structure resembles asbestos. The presence of transition metals, mainly iron, in the fibres seems also implicated in the pathogenetic mechanisms. To unravel the role of iron at mesothelial level, we compared the chemical changes induced in MeT-5A cells by the exposure to asbestos (crocidolite) or CNTs at different content of iron impurities (raw-SWCNTs, purified- and highly purified-SWCNTs). We applied synchrotron-based X-Ray Fluorescence (XRF) microscopy and soft X-ray imaging (absorption and phase contrast images) to monitor chemical and morphological changes of the exposed cells. In parallel, we performed a ferritin assay. X-ray microscopy imaging and XRF well localize the crocidolite fibres interacting with cells, as well as the damage-related morphological changes. Differently, CNTs presence could be only partially evinced by low energy XRF through carbon distribution and sometimes iron co-localisation. Compared to controls, the cells treated with raw-SWCNTs and crocidolite fibres showed a severe alteration of iron distribution and content, with concomitant stimulation of ferritin production. Interestingly, highly purified nanotubes did not altered iron metabolism. The data provide new insights for possible CNTs effects at mesothelial/pleural level in humans.
Keywords: Asbestos, Crocidolite; Cell Line; Epithelial Cells; Humans; Iron; Microscopy, Fluorescence; Nanotubes, Carbon

Joint Data Analysis in Nutritional Epidemiology: Identification of Observational Studies and Minimal Requirements. - Pinart, Mariona; Nimptsch, Katharina; Bouwman, Jildau; Dragsted, Lars O; Yang, Chen; De Cock, Nathalie; Lachat, Carl; Perozzi, Giuditta; Canali, Raffaella; Lombardo, Rosario; D'Archivio, Massimo; Guillaume, Michèle; et al. (J Nutr, 2018)
Background: Joint data analysis from multiple nutrition studies may improve the ability to answer complex questions regarding the role of nutritional status and diet in health and disease. Objective: The objective was to identify nutritional observational studies from partners participating in the European Nutritional Phenotype Assessment and Data Sharing Initiative (ENPADASI) Consortium, as well as minimal requirements for joint data analysis. Methods: A predefined template containing information on study design, exposure measurements (dietary intake, alcohol and tobacco consumption, physical activity, sedentary behavior, anthropometric measures, and sociodemographic and health status), main health-related outcomes, and laboratory measurements (traditional and omics biomarkers) was developed and circulated to those European research groups participating in the ENPADASI under the strategic research area of "diet-related chronic diseases." Information about raw data disposition and metadata sharing was requested. A set of minimal requirements was abstracted from the gathered information. Results: Studies (12 cohort, 12 cross-sectional, and 2 case-control) were identified. Two studies recruited children only and the rest recruited adults. All studies included dietary intake data. Twenty studies collected blood samples. Data on traditional biomarkers were available for 20 studies, of which 17 measured lipoproteins, glucose, and insulin and 13 measured inflammatory biomarkers. Metabolomics, proteomics, and genomics or transcriptomics data were available in 5, 3, and 12 studies, respectively. Although the study authors were willing to share metadata, most refused, were hesitant, or had legal or ethical issues related to sharing raw data. Forty-one descriptors of minimal requirements for the study data were identified to facilitate data integration. Conclusions: Combining study data sets will enable sufficiently powered, refined investigations to increase the knowledge and understanding of the relation between food, nutrition, and human health. Furthermore, the minimal requirements for study data may encourage more efficient secondary usage of existing data and provide sufficient information for researchers to draft future multicenter research proposals in nutrition.
Keywords: Adult; Biomarkers; Blood Glucose; Case-Control Studies; Child; Chronic Disease; Cohort Studies; Cross-Sectional Studies; Diet; Epidemiology; Europe; Genomics; Health Status; Humans; Inflammation; Insulin; Life Style; Lipoproteins; Longitudinal Studies; Metabolomics; Nutritional Status; Observational Studies as Topic; Statistics as Topic

A Klinefelter boy with congenital adrenal hyperplasia: too much or too little androgens? - Zanella, Giada; Tornese, Gianluca; Mascheroni, Elisabetta; Faleschini, Elena; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2018)
BACKGROUND: The simultaneous occurrence of Klinefelter Syndrome (KS) and Congenital Adrenal Hyperplasia (CAH) is an exceptional event: there are just three case reports (two children and a 51 years old man) describing males affected by both KS and 21OHD (21-hydroxylase deficiency) CAH, the first causing androgen deficiency, the latter leading to androgen excess. CASE REPORT: We report the 4th case of association of KS and CAH in a young man with CAH with good androgen control and with normal secondary sex characteristics, whose Klinefelter syndrome was diagnosed because of reduced testicular volume. He was the first reported case of association of KS and CAH who started androgen replacement therapy in the pubertal age and whose pubertal development was described and followed up step by step. CONCLUSION: In a boy with CAH and small testicular volume, it's important to consider that hypogonadism may be masked by the adrenal androgens excess and a karyotype should be performed once testicular adrenal rests have been ruled out.
Keywords: Adolescent; Adrenal Hyperplasia, Congenital; Androgens; Follow-Up Studies; Hormone Replacement Therapy; Humans; Klinefelter Syndrome; Male; Rare Diseases; Risk Assessment; Testis

A Large-Scale Multi-ancestry Genome-wide Study Accounting for Smoking Behavior Identifies Multiple Significant Loci for Blood Pressure. - Sung, Yun J; Winkler, Thomas W; de Las Fuentes, Lisa; Bentley, Amy R; Brown, Michael R; Kraja, Aldi T; Schwander, Karen; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Lu, Yingchang; Cheng, Ching-Yu; et al. (Am J Hum Genet, 2018)
Genome-wide association analysis advanced understanding of blood pressure (BP), a major risk factor for vascular conditions such as coronary heart disease and stroke. Accounting for smoking behavior may help identify BP loci and extend our knowledge of its genetic architecture. We performed genome-wide association meta-analyses of systolic and diastolic BP incorporating gene-smoking interactions in 610,091 individuals. Stage 1 analysis examined ∼18.8 million SNPs and small insertion/deletion variants in 129,913 individuals from four ancestries (European, African, Asian, and Hispanic) with follow-up analysis of promising variants in 480,178 additional individuals from five ancestries. We identified 15 loci that were genome-wide significant (p < 5 × 10) in stage 1 and formally replicated in stage 2. A combined stage 1 and 2 meta-analysis identified 66 additional genome-wide significant loci (13, 35, and 18 loci in European, African, and trans-ancestry, respectively). A total of 56 known BP loci were also identified by our results (p < 5 × 10). Of the newly identified loci, ten showed significant interaction with smoking status, but none of them were replicated in stage 2. Several loci were identified in African ancestry, highlighting the importance of genetic studies in diverse populations. The identified loci show strong evidence for regulatory features and support shared pathophysiology with cardiometabolic and addiction traits. They also highlight a role in BP regulation for biological candidates such as modulators of vascular structure and function (CDKN1B, BCAR1-CFDP1, PXDN, EEA1), ciliopathies (SDCCAG8, RPGRIP1L), telomere maintenance (TNKS, PINX1, AKTIP), and central dopaminergic signaling (MSRA, EBF2).
Keywords: Blood Pressure; Cohort Studies; Continental Population Groups; Diastole; Epistasis, Genetic; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Smoking; Systole

Learning curve for the ultrasonographic diagnosis of deep endometriosis using a structured off-line training program. - Guerriero, Stefano; Pascual, M Angela; Ajossa, Silvia; Rodriguez, Ignacio; Zajicek, Michal; Rolla, Martino; Rams, Noelia Llop; Yulzari, Vered; Bardin, Ron; Buonomo, Francesca; Comparetto, Ornella; Perniciano, Maura; et al. (Ultrasound Obstet Gynecol, 2018)
OBJECTIVE: The aim of the present study was to assess the learning curves of trainees during a structured off-line/hands-on training program on the diagnosis of deep infiltrating endometriosis (DIE). METHODS: A two-week training program was conducted. One day was devoted to theoretical issues and guided off-line analysis of 10 volumes of three-dimensional (3D) ultrasound. During the following days, five sessions of real-time sonographic examinations were performed in a DIE referral center Ultrasound unit. In between sessions, the trainees analyzed four off-line sets, containing twenty-five 3D volumes each. At the end of each set, misinterpreted volumes were assessed with the trainer. One trainer and 4 trainees (all post-graduated Ob/Gyn with at least 5 years of experience in ultrasonography in Obstetrics and Gynecology but with no experience in DIE sonographic examinations) participated in the study. Presence or absence of DIE at surgery was considered as gold standard for the trainees. Trainee's results were evaluated by learning curve cumulative summation (LC-CUSUM) and the deviations of the level of trainees' performance at the control stage by CUSUM (standard CUSUM) for different locations of DIE. RESULTS: The trainees reached competence on average after 17 evaluations (range 21-14) for bladder locations, after 39 evaluations (range 60-30) for rectosigmoid locations, after 25 evaluations (range 34-14) for forniceal locations, after 44 evaluations (range 66-25) for utero-sacral locations (USL), after 21 evaluations (range 43-14) for rectovaginal septum (RVS) locations respectively, and kept the process under control with error levels of less than 4.5% until the end of the test. The overall accuracy for each trainee at the different locations ranged from 0.91 to 0.96 for bladder DIE, from 0.80 to 0.94 for recto-sigmoid DIE, from 0.90 to 0.94% for forniceal DIE, from 0.79 to 0.82 for utero-sacral ligaments DIE and from 0.89 to 0.97 for recto-vaginal septum DIE. CONCLUSIONS: The suggested two-weeks learning program based on a mix of off-line and live sessions is feasible and suggests a good performance in training for the diagnosis of DIE. This article is protected by copyright. All rights reserved.

Light element distribution in fresh and frozen-thawed human ovarian tissues: a preliminary study. - Pascolo, Lorella; Venturin, Irene; Gianoncelli, Alessandra; Bortul, Roberta; Zito, Gabriella; Giolo, Elena; Salomè, Murielle; Bedolla, Diana E; Altissimo, Matteo; Zweyer, Marina; Ricci, Giuseppe (Reprod Biomed Online, 2018)
RESEARCH QUESTION: Does synchrotron X-ray fluorescence (XRF) provide novel chemical information for the evaluation of human ovarian tissue cryopreservation protocols? DESIGN: Tissues from five patients undergoing laparoscopic surgery for benign gynaecological conditions were fixed for microscopic analysis either immediately or after cryopreservation. After fixation, fresh and slowly frozen samples were selected by light microscopy and transmission electron microscopy, and subsequently analysed with synchrotron XRF microscopy at different incident energies. RESULTS: The distributions of elements detected at 7.3 keV (S, P, K, Cl, Fe, and Os) and 1.5 keV (Na and Mg) were related to the changes revealed by light microscopy and transmission electron microscopy analyses. The light elements showed highly informative findings. The S distribution was found to be an indicator of extracellular component changes in the stromal tissues of the freeze-stored samples, further revealed by the transmission electron microscopy analyses. Low-quality follicles, frequent in the freeze-thawed tissues, showed a high Na level in the ooplasm. On the contrary, good-quality follicles were detected by a homogeneous Cl distribution. The occurrence of vacuolated follicles increased after cryopreservation, and the XRF analyses showed that the vacuolar structures contained mainly Cl and Na. CONCLUSIONS: The study demonstrates that elemental imaging techniques, particularly revealing the distribution of light elements, could be useful in establishing new cryopreservation protocols.
Keywords: Cryopreservation; Female; Humans; Microscopy, Electron, Transmission; Organ Preservation; Ovarian Follicle; Ovary

Multicenter randomized, double-blind controlled trial to evaluate the efficacy of laser therapy for the treatment of severe oral mucositis induced by chemotherapy in children: laMPO RCT. - Gobbo, Margherita; Verzegnassi, Federico; Ronfani, Luca; Zanon, Davide; Melchionda, Fraia; Bagattoni, Simone; Majorana, Alessandra; Bardellini, Elena; Mura, Rosamaria; Piras, Alessandra; Petris, Maria Grazia; Mariuzzi, Maria Livia; et al. (Pediatr Blood Cancer, 2018)
OBJECTIVES: To demonstrate the efficacy of laser photobiomodulation (PBM) compared to that of placebo on severe oral mucositis (OM) in pediatric oncology patients. The primary objective was the reduction of OM grade (World Health Organization [WHO] scale) 7 days after starting PBM. Secondary objectives were reduction of pain, analgesic consumption, and incidence of side effects. METHODS: One hundred and one children with WHO grade > 2 chemotherapy-induced OM were enrolled in eight Italian hospitals. Patients were randomized to either PBM or sham treatment for four consecutive days (days +1 to +4). On days +4, +7, and +11, OM grade, pain (following a 0-10 numeric pain rating scale, NRS) and need for analgesics were evaluated by an operator blinded to treatment. RESULTS: Fifty-one patients were allocated to the PBM group, and 50 were allocated to the sham group. In total, 93.7% of PBM patients and 72% of sham patients had OM grade < 3 WHO on day +7 (P = 0.01). A significant reduction of pain was registered on day +7 in the PBM versus sham group (NRS 1 [0-3] vs. 2.5 [1-5], P < 0.006). Reduced use of analgesics was reported in the PBM group, although it was not statistically significant. No significant adverse events attributable to treatment were recorded. CONCLUSIONS: PBM is a safe, feasible, and effective treatment for children affected by chemotherapy-induced OM, as it accelerates mucosal recovery and reduces pain.

Neuronal Dysfunction Associated with Cholesterol Deregulation. - Marcuzzi, Annalisa; Loganes, Claudia; Valencic, Erica; Piscianz, Elisa; Monasta, Lorenzo; Bilel, Sabrine; Bortul, Roberta; Celeghini, Claudio; Zweyer, Marina; Tommasini, Alberto (Int J Mol Sci, 2018)
Cholesterol metabolism is crucial for cells and, in particular, its biosynthesis in the central nervous system occurs in situ, and its deregulation involves morphological changes that cause functional variations and trigger programmed cell death. The pathogenesis of rare diseases, such as Mevalonate Kinase Deficiency or Smith⁻Lemli⁻Opitz Syndrome, arises due to enzymatic defects in the cholesterol metabolic pathways, resulting in a shortage of downstream products. The most severe clinical manifestations of these diseases appear as neurological defects. Expanding the knowledge of this biological mechanism will be useful for identifying potential targets and preventing neuronal damage. Several studies have demonstrated that deregulation of the cholesterol pathway induces mitochondrial dysfunction as the result of respiratory chain damage. We set out to determine whether mitochondrial damage may be prevented by using protective mitochondria-targeted compounds, such as MitoQ, in a neuronal cell line treated with a statin to induce a biochemical block of the cholesterol pathway. Evidence from the literature suggests that mitochondria play a crucial role in the apoptotic mechanism secondary to blocking the cholesterol pathway. Our study shows that MitoQ, administered as a preventive agent, could counteract the cell damage induced by statins in the early stages, but its protective role fades over time.
Keywords: Anticholesteremic Agents; Cell Line, Tumor; Cholesterol; Electron Transport; Humans; Lovastatin; Mitochondria; Neurons; Neuroprotective Agents; Organophosphorus Compounds; Ubiquinone

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Continental Population Groups; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Young Adult

Pain Intensity and Risk of Bone Fracture in Children With Minor Extremity Injuries. - Zanchi, Chiara; Giangreco, Manuela; Ronfani, Luca; Germani, Claudio; Giorgi, Rita; Calligaris, Lorenzo; Norbedo, Stefania; Liccari, Giulio; Cozzi, Giorgio; Barbi, Egidio (Pediatr Emerg Care, 2018)
OBJECTIVES: Injuries are one of the most common causes of pediatric emergency department (ED) visit. The aim of this study was to investigate the relationship between the intensity of pain at the ED visit of children presenting with an extremity injury and the risk of fracture. METHODS: We conducted a retrospective study, considering all patients presenting to the ED of a children's hospital in Italy, with an accidental extremity injury, between May and December 2015. We selected all children aged 8 to 17 years who underwent an x-ray. Children with major, multiple, or nonextremity injuries were excluded. Age, sex, spontaneous and palpation pain, local swelling, time between injury, and medical evaluation were recorded. Sensibility and specificity of spontaneous and palpation pain in detecting a fracture were calculated. RESULTS: We reviewed 994 medical records; of these, 344 (34.6%) reported a fracture. Children's median age was 12 years (interquartile range [IQR], 10-14). Median spontaneous pain at the ED visit was not significantly different between children with and without a fracture: 4.0 (1.0-6.0) and 5 (1.0-6.0), respectively (P = 0.129). Children with mild palpation pain and children without an increase of pain of at least 2 points between spontaneous and palpation pain were fractured in 3.2% and 0.97% of cases, respectively. CONCLUSIONS: In this series, pain intensity in children with a minor extremity injury was not a good marker of fracture. Nevertheless, children with mild palpation pain or with a mild increase of pain between spontaneous and palpation pain had a low risk of fracture.

Pathological Significance and Prognostic Value of Surfactant Protein D in Cancer. - Mangogna, Alessandro; Belmonte, Beatrice; Agostinis, Chiara; Ricci, Giuseppe; Gulino, Alessandro; Ferrara, Ines; Zanconati, Fabrizio; Tripodo, Claudio; Romano, Federico; Kishore, Uday; Bulla, Roberta (Front Immunol, 2018)
Surfactant protein D (SP-D) is a pattern recognition molecule belonging to the Collectin (collagen-containing C-type lectin) family that has pulmonary as well as extra-pulmonary existence. In the lungs, it is a well-established opsonin that can agglutinate a range of microbes, and enhance their clearance phagocytosis and super-oxidative burst. It can interfere with allergen-IgE interaction and suppress basophil and mast cell activation. However, it is now becoming evident that SP-D is likely to be an innate immune surveillance molecule against tumor development. SP-D has been shown to induce apoptosis in sensitized eosinophils derived from allergic patients and a leukemic cell line p53 pathway. Recently, SP-D has been shown to suppress lung cancer progression interference with the epidermal growth factor signaling. In addition, a truncated form of recombinant human SP-D has been reported to induce apoptosis in pancreatic adenocarcinoma Fas-mediated pathway in a p53-independent manner. To further establish a correlation between SP-D presence/levels and normal and cancer tissues, we performed a bioinformatics analysis, using Oncomine dataset and the survival analysis platforms Kaplan-Meier plotter, to assess if SP-D can serve as a potential prognostic marker for human lung cancer, in addition to human gastric, breast, and ovarian cancers. We also analyzed immunohistochemically the presence of SP-D in normal and tumor human tissues. We conclude that (1) in the lung, gastric, and breast cancers, there is a lower expression of SP-D than normal tissues; (2) in ovarian cancer, there is a higher expression of SP-D than normal tissue; and (3) in lung cancer, the presence of SP-D could be associated with a favorable prognosis. On the contrary, at non-pulmonary sites such as gastric, breast, and ovarian cancers, the presence of SP-D could be associated with unfavorable prognosis. Correlation between the levels of SP-D and overall survival requires further investigation. Our analysis involves a large number of dataset; therefore, any trend observed is reliable. Despite apparent complexity within the results, it is evident that cancer tissues that produce less levels of SP-D compared to their normal tissue counterparts are probably less susceptible to SP-D-mediated immune surveillance mechanisms infiltrating immune cells.

Photobiomodulation at Multiple Wavelengths Differentially Modulates Oxidative Stress and . - Rupel, Katia; Zupin, Luisa; Colliva, Andrea; Kamada, Anselmo; Poropat, Augusto; Ottaviani, Giulia; Gobbo, Margherita; Fanfoni, Lidia; Gratton, Rossella; Santoro, Massimo; Di Lenarda, Roberto; Biasotto, Matteo; et al. (Oxid Med Cell Longev, 2018)
Photobiomodulation (PBM) is emerging as an effective strategy for the management of multiple inflammatory conditions, including oral mucositis (OM) in cancer patients who receive chemotherapy or radiotherapy. Still, the poor understanding of the mechanisms by which the light interacts with biological tissues and the heterogeneity of light sources and protocols employed worldwide significantly limits its applicability. Reactive oxygen species (ROS) are massively generated during the early phases of OM and play a major role in the pathogenesis of inflammation in general. Here, we report the results of a clinical and experimental study, aimed at evaluating the effect of laser light at different wavelengths on oxidative stress in oncologic patients suffering from OM and in two cell types abundantly present within the inflamed oral mucosa, neutrophil polymorphonuclear (PMN) granulocytes, and keratinocytes. In addition to standard ROS detection methods, we exploited a roGFP2-Orp1 genetically encoded sensor, allowing specific, quantitative, and dynamic imaging of redox events in living cells in response to oxidative stress and PBM. We found that the various wavelengths differentially modulate ROS production. In particular, the 660 nm laser light increases ROS production when applied either before or after an oxidative stimulus. In contrast, the 970 nm laser light exerted a moderate antioxidant activity both in the saliva of OM patients and in both cell types. The most marked reduction in the levels of ROS was detected in cells exposed either to the 800 nm laser light or to the combination of the three wavelengths. Overall, our study demonstrates that PBM exerts different effects on the redox state of both PMNs and keratinocytes depending on the used wavelength and prompts the validation of a multiwavelength protocol in the clinical settings.
Keywords: Adult; Aged; Aged, 80 and over; Female; Humans; Keratinocytes; Lasers, Semiconductor; Low-Level Light Therapy; Male; Middle Aged; Neutrophils; Oxidation-Reduction; Oxidative Stress; Stomatitis

PR interval genome-wide association meta-analysis identifies 50 loci associated with atrial and atrioventricular electrical activity. - van Setten, Jessica; Brody, Jennifer A; Jamshidi, Yalda; Swenson, Brenton R; Butler, Anne M; Campbell, Harry; Del Greco, Fabiola M; Evans, Daniel S; Gibson, Quince; Gudbjartsson, Daniel F; Kerr, Kathleen F; Krijthe, Bouwe P; et al. (Nat Commun, 2018)
Electrocardiographic PR interval measures atrio-ventricular depolarization and conduction, and abnormal PR interval is a risk factor for atrial fibrillation and heart block. Our genome-wide association study of over 92,000 European-descent individuals identifies 44 PR interval loci (34 novel). Examination of these loci reveals known and previously not-yet-reported biological processes involved in cardiac atrial electrical activity. Genes in these loci are over-represented in cardiac disease processes including heart block and atrial fibrillation. Variants in over half of the 44 loci were associated with atrial or blood transcript expression levels, or were in high linkage disequilibrium with missense variants. Six additional loci were identified either by meta-analysis of ~105,000 African and European-descent individuals and/or by pleiotropic analyses combining PR interval with heart rate, QRS interval, and atrial fibrillation. These findings implicate developmental pathways, and identify transcription factors, ion-channel genes, and cell-junction/cell-signaling proteins in atrio-ventricular conduction, identifying potential targets for drug development.
Keywords: Atrial Function; Atrioventricular Node; Electrocardiography; Electrophysiological Phenomena; Female; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Mutation, Missense; Risk Factors

Pre-eclampsia affects procalcitonin production in placental tissue. - Agostinis, Chiara; Rami, Damiano; Zacchi, Paola; Bossi, Fleur; Stampalija, Tamara; Mangogna, Alessandro; Amadio, Leonardo; Vidergar, Romana; Vecchi Brumatti, Liza; Ricci, Giuseppe; Celeghini, Claudio; Radillo, Oriano; et al. (Am J Reprod Immunol, 2018)
PROBLEM: Procalcitonin (PCT) is the prohormone of calcitonin which is usually released from neuroendocrine cells of the thyroid gland (parafollicular) and the lungs (K cells). PCT is synthesized by almost all cell types and tissues, including monocytes and parenchymal tissue, upon LPS stimulation. To date, there is no evidence for PCT expression in the placenta both in physiological and pathological conditions. METHOD: Circulating and placental PCT levels were analysed in pre-eclamptic (PE) and control patients. Placental cells and macrophages (PBDM), stimulated with PE sera, were analysed for PCT expression. The effect of anti-TNF-α antibody was analysed. RESULTS: Higher PCT levels were detected in PE sera and in PE placentae compared to healthy women. PE trophoblasts showed increased PCT expression compared to those isolated from healthy placentae. PE sera induced an upregulation of PCT production in macrophages and placental cells. The treatment of PBDM with PE sera in the presence of anti-TNF-α completely abrogated the effect induced by pathologic sera. CONCLUSION: Trophoblast cells are the main producer of PCT in PE placentae. TNF-α, in association with other circulating factors present in PE sera, upregulates PCT production in macrophages and normal placental cells, thus contributing to the observed increased in circulating PCT in PE sera.
Keywords: Adult; Calcitonin; Cohort Studies; Female; Humans; Macrophages; Placenta; Pre-Eclampsia; Pregnancy; Trophoblasts; Tumor Necrosis Factor-alpha; Up-Regulation; Young Adult

The Role of Oxidative Stress and Membrane Transport Systems during Endometriosis: A Fresh Look at a Busy Corner. - Vitale, Salvatore Giovanni; Capriglione, Stella; Peterlunger, Isabel; La Rosa, Valentina Lucia; Vitagliano, Amerigo; Noventa, Marco; Valenti, Gaetano; Sapia, Fabrizio; Angioli, Roberto; Lopez, Salvatore; Sarpietro, Giuseppe; Rossetti, Diego; et al. (Oxid Med Cell Longev, 2018)
Endometriosis is a condition characterized by the presence of endometrial tissue outside the uterine cavity, leading to a chronic inflammatory reaction. It is one of the most widespread gynecological diseases with a 10-15% prevalence in the general female population, rising up to 30-45% in patients with infertility. Although it was first described in 1860, its etiology and pathogenesis are still unclear. It is now accepted that inflammation plays a central role in the development and progression of endometriosis. In particular, it is marked by an inflammatory process associated with the overproduction of an array of inflammatory mediators such as prostaglandins, metalloproteinases, cytokines, and chemokines. In addition, the growth and adhesion of endometrial cells in the peritoneal cavity due to reactive oxygen species (ROS) and free radicals lead to disease onset, its ensuing symptoms-among which pain and infertility. The aim of our review is to evaluate the role of oxidative stress and ROS in the pathogenesis of endometriosis and the efficacy of antioxidant therapy in the treatment and mitigation of its symptoms.
Keywords: Endometriosis; Female; Humans; Oxidative Stress

Serum Stem Cell Growth Factor Beta for the Prediction of Therapy Response in Hepatocellular Carcinoma. - Sukowati, Caecilia H C; Patti, Riccardo; Pascut, Devis; Ladju, Rusdina B; Tarchi, Paola; Zanotta, Nunzia; Comar, Manola; Tiribelli, Claudio; Crocè, Lory S (Biomed Res Int, 2018)
Introduction: Chronic inflammatory response is one of major contributors in the development of hepatocellular carcinoma (HCC). Inflammatory molecules, such as cytokines and growth factors in the circulation, can be useful in the diagnosis and prognosis of the patients. The stem cell growth factor beta (SCGF), a newly found protein, is a secreted sulfated glycoprotein and it functions as a growth factor for primitive hematopoietic progenitor cells. The level of SCGF had been reported to be elevated in several cancer types. However, there is very few or even no information on this protein in the study of HCC, even more in clinical studies. Methods: A multiplex immunoassay panel of 48 cytokines and growth factors were utilized to screen 68 sera from 29 HCC patients at pretreatment (T0), 1 month (T1), and 6 months (T6) after treatment by either radiofrequency ablation (RF) or transarterial chemoembolization (TACE). Treatment response was evaluated according to mRECIST criteria. Results: Immunoassay screening showed that the levels of IL-17, CTACK, TNF, IL-2R, IL-8, and SCGF were different in Complete Responders (CR) and Nonresponders (NR) groups. At T0 and T1, the SCGF level was significantly the highest in NR (23.8 and 40.7 ng/mL, respectively), followed by early recurrence (25.4 and 25.0 ng/mL), and CR (6.7 and 5.3 ng/mL), independently from HCV, stages, and treatment type. Low basal SCGF level was associated with longer disease-free survival compared to high SCGF. Conclusion: In this study, for the first time, we demonstrate that the high level of serum SCGF at pre- and posttreatment is associated with HCC nonresponsiveness.
Keywords: Aged; Carcinoma, Hepatocellular; Chemoembolization, Therapeutic; Female; Hematopoietic Cell Growth Factors; Humans; Liver Neoplasms; Male; Middle Aged; Neoplasm Recurrence, Local; Retrospective Studies; Stem Cells; Treatment Outcome

Total body irradiation and iron chelation treatment are associated with pancreatic injury following pediatric hematopoietic stem cell transplantation. - Maximova, Natalia; Gregori, Massimo; Simeone, Roberto; Sonzogni, Aurelio; Zanon, Davide; Boz, Giulia; D'Antiga, Lorenzo (Oncotarget, 2018)
Whereas many studies have addressed the risk of organ dysfunction following hematopoietic stem cell transplantation (HSCT), little is known about pancreatic susceptibility in this setting. We aimed to investigate the effect of iron overload (IO) and total body irradiation (TBI) on pancreatic function of children undergoing HSCT. We retrospectively evaluated children admitted between 2012-2016 fulfilling the following criteria: normal pancreatic iron concentration (PIC), regular pancreatic function before HSCT, availability of abdominal magnetic resonance imaging with gradient-recalled-echo sequences and a full set of biochemical markers of IO and pancreatic function performed before HSCT and at discharge. We divided the patients according to the use of TBI or myeloablative chemotherapy (MCHT) in the conditioning regimen. All patients with severe IO or moderate IO with a high risk of engraftment delay or transplantation-related complications underwent chelation therapy with deferoxamine (DFO) from the first day of conditioning to discharge. 63 patients had a HSCT in the study period, 13 did not fulfill the inclusion criteria; 50 (25 in each group) are included in the analysis, and did not show differences at baseline evaluation. At follow up testing the TBI group showed a significantly higher PIC (107,8±100,3 μmol/g vs 28,4±37,9 in MCHT group, p<0,0001). In the TBI group the patients who had DFO treatment had higher PIC (223,2±48,8 μmol/g vs 55,7±10,5 without DFO treatment, p<0,0001), and all patients having PIC >100 μmol/g at follow up had DFO-based chelation therapy, versus 26% of those with lower PIC (p<0,0001). The number of patients presenting exocrine pancreatic dysfunctions one month after transplantation was significantly higher in the TBI group (48% vs 4%; p<0.0001). The mean pancreatic volume reduction was significantly greater in the TBI group (39,1% vs 0,9% in the MCHT group; p<0,05), and was significantly worse on those who received DFO therapy. Based on our data, we suggest that TBI is detrimental for pancreatic functions, and speculate that DFO may contribute to the rapid pancreatic IO observed in these patients.

A transcriptomics study of hereditary angioedema attacks. - Castellano, Giuseppe; Divella, Chiara; Sallustio, Fabio; Montinaro, Vincenzo; Curci, Claudia; Zanichelli, Andrea; Bonanni, Erika; Suffritti, Chiara; Caccia, Sonia; Bossi, Fleur; Gallone, Anna; Schena, Francesco Paolo; et al. (J Allergy Clin Immunol, 2018)
BACKGROUND: Hereditary angioedema (HAE) caused by C1-inhibitor deficiency is a lifelong illness characterized by recurrent acute attacks of localized skin or mucosal edema. Activation of the kallikrein/bradykinin pathway at the endothelial cell level has a relevant pathogenetic role in acute HAE attacks. Moreover, other pathways are involved given the variable clinical expression of the disease in different patients. OBJECTIVE: We sought to explore the involvement of other putative genes in edema formation. METHODS: We performed a PBMC microarray gene expression analysis on RNA isolated from patients with HAE during an acute attack and compared them with the transcriptomic profile of the same patients in the remission phase. RESULTS: Gene expression analysis identified 23 genes significantly modulated during acute attacks that are involved primarily in the natural killer cell signaling and leukocyte extravasation signaling pathways. Gene set enrichment analysis showed a significant activation of relevant biological processes, such as response to external stimuli and protein processing (q < 0.05), suggesting involvement of PBMCs during acute HAE attacks. Upregulation of 2 genes, those encoding adrenomedullin and cellular receptor for urokinase plasminogen activator (uPAR), which occurs during an acute attack, was confirmed in PBMCs of 20 additional patients with HAE by using real-time PCR. Finally, in vitro studies demonstrated the involvement of uPAR in the generation of bradykinin and endothelial leakage. CONCLUSIONS: Our study demonstrates the increase in levels of adrenomedullin and uPAR in PBMCs during an acute HAE attack. Activation of these genes usually involved in regulation of vascular tone and in inflammatory response might have a pathogenic role by amplifying bradykinin production and edema formation in patients with HAE.

Ultrasound-guided genitofemoral nerve block for inguinal hernia repair in the male adult: a randomized controlled pilot study. - Frassanito, Luciano; Zanfini, Bruno A; Pitoni, Sara; Germini, Paolo; Del Vicario, Miryam; Draisci, Gaetano (Minerva Anestesiol, 2018)
BACKGROUND: Ultrasound-guided (USG) ilioinguinal/iliohypogastric nerve (II/IHN) block is a widely validated anesthetic technique for inguinal herniorrhaphy. As the spermatic cord, scrotum, and adjacent thigh receive sensory innervation from the genital branch of genitofemoral nerve (GFN), the addition of GFN block has been suggested to improve the quality of perioperative anesthesia and analgesia. The aim of this study is to compare GFN block plus II/IHN block with II/IHN block alone for intraoperative anesthesia and post-operative pain management. METHODS: We enrolled 80, ASA I-III, male adults scheduled for elective open herniorrhaphy. Patients were randomized to receive either USG II/IHN plus GFN block (Case Group) or USG II/IHN block alone (Control Group). The outcome measures were the assessment of postoperative VAS scores on coughing and the adequacy of anesthesia, measured with intraoperative requirement for extra local anesthetic (LA) infiltration and number of patients needing systemic sedation. RESULTS: The requirement of intraoperative additional doses of LA was significantly lower in the Case Group (median LA volume administered by the surgeon: 13.8±5.6 mL vs. 20.7±9.1 mL, P<0.05). Two patients in the Control Group needed systemic sedation. VAS scores at 15 minutes, 30 minutes, 1 hour, 2 hours, pre-discharge, and 24 hours were significantly lower in the Case Group (P<0.005). Four cases of femoral nerve block were reported, three in the Control Group, one in the Case Group (2.2% vs. 7.7%, P>0.05). CONCLUSIONS: The combination of GFN block and II/IHN block is associated with lower postoperative VAS scores and lower doses of intraoperative additional LA.

An unusual unilateral breast enlargement in a prepubertal girl. - Pavan, Matteo; Faleschini, Elena; Tornese, Gianluca; Zandonà, Lorenzo; Ventura, Alessandro (Arch Dis Child, 2018)

Vaginal microbiota dysmicrobism and role of biofilm-forming bacteria. - Campisciano, Giuseppina; Zanotta, Nunzia; Petix, Vincenzo; Corich, Lucia; De Seta, Francesco; Comar, Manola (Front Biosci (Elite Ed), 2018)
Bacterial vaginosis involves the presence of a polymicrobial biofilm on the vaginal epithelium, guaranteeing immune escape and spread of antibiotic resistance. To spot known biofilm-forming bacteria, we profiled the vaginal microbiome of sixty-four symptomatic women suffering from a different grade of vaginal disorders and sixty asymptomatic healthy women. Specific microbial profiles distinguished symptomatic from asymptomatic women and characterized the grade of dysmicrobism within the symptomatic group. Lactobacillus crispatus and iners predominated on the healthy vaginal mucosa, while Lactobacillus gasseri predominated in the intermediate dysmicrobism. Furthermore, the intermediate grade of dysmicrobism was characterized by other lactic acid-producers species than Lactobacilli, able to rescue the microbial imbalance, and Ureaplasma parvum-serovar 3. The vaginosis group exhibited the overgrowth of Prevotella bivia, which is known to enhance the biofilm formation by Gardnerella vaginalis, and the presence of Streptococcus anginosus, which is emerging as a new cooperating player of the vaginal biofilm. Identifying specific microorganisms promoting or preventing the biofilm formation could increase the accuracy for a better definition of the vaginal dysmicrobism concept and therapeutic intervention.
Keywords: Adult; Biofilms; Female; Humans; Microbiota; Vagina; Vaginosis, Bacterial

ADA2 deficiency (DADA2) as an unrecognised cause of early onset polyarteritis nodosa and stroke: a multicentre national study. - Caorsi, Roberta; Penco, Federica; Grossi, Alice; Insalaco, Antonella; Omenetti, Alessia; Alessio, Maria; Conti, Giovanni; Marchetti, Federico; Picco, Paolo; Tommasini, Alberto; Martino, Silvana; Malattia, Clara; et al. (Ann Rheum Dis, 2017)
OBJECTIVES: To analyse the prevalence of mutations in patients diagnosed with early onset livedo reticularis and/or haemorrhagic/ischaemic strokes in the context of inflammation or polyarteritis nodosa (PAN). Forty-eight patients from 43 families were included in the study. METHODS: Direct sequencing of was performed by Sanger analysis. Adenosine deaminase 2 (ADA2) enzymatic activity was analysed in monocyte isolated from patients and healthy controls incubated with adenosine and with or without an ADA1 inhibitor. RESULTS: Biallelic homozygous or compound heterozygous mutations were detected in 15/48 patients. A heterozygous disease-associated mutation (p.G47V) was observed in two affected brothers. The mean age of onset of the genetically positive patients was 24 months (6 months to 7 years). Ten patients displayed one or more cerebral strokes during their disease course. Low immunoglobulin levels were detected in six patients. Thalidomide and anti-TNF (tumour necrosis factor) blockers were the most effective drugs. Patients without mutations had a later age at disease onset, a lower prevalence of neurological and skin manifestations; one of these patients displayed all the clinical features of adenosine deaminase 2deficiency (DADA2) and a defective enzymatic activity suggesting the presence of a missed mutation or a synthesis defect. CONCLUSIONS: DADA2 accounts for paediatric patients diagnosed with PAN-like disease and strokes and might explain an unrecognised condition in patients followed by adult rheumatologist. Timely diagnosis and treatment with anti-TNF agents are crucial for the prevention of severe complications of the disease. Functional assay to measure ADA2 activity should complement genetic testing in patients with non-confirming genotypes.
Keywords: Adenosine Deaminase; Adolescent; Age of Onset; Case-Control Studies; Child; Child, Preschool; DNA Mutational Analysis; Female; Heterozygote; Homozygote; Humans; Immunoglobulins; Immunosuppressive Agents; Infant; Intercellular Signaling Peptides and Proteins; Italy; Livedo Reticularis; Male; Pedigree; Polyarteritis Nodosa; Stroke; Thalidomide; Tumor Necrosis Factor-alpha; Young Adult

Adolescent Admissions to Emergency Departments for Self-Injurious Thoughts and Behaviors. - Zanus, Caterina; Battistutta, Sara; Aliverti, Renata; Montico, Marcella; Cremaschi, Silvana; Ronfani, Luca; Monasta, Lorenzo; Carrozzi, Marco (PLoS One, 2017)
The objective of the present study was to describe the incidence and the characteristics of Self-Injurious Thoughts and Behaviors (SITBs), among adolescents aged 11-18 admitted, over a two year period, to all the Emergency Departments of a Region of North-eastern Italy through a comprehensive analysis of medical records. A two-step search was performed in the regional ED electronic database. First, we identified the cases that had been clearly diagnosed as SITBs by an Emergency Department physician. Secondly, suspect cases were detected through a keyword search of the database, and the medical records of these cases were hand screened to identify SITBs. The mean annual incidence rate of SITBs was 90 per 100,000 adolescents aged 11-18 years. Events were more frequent in females. Drug poisoning was the most frequently adopted method (54%). In 42% of cases a diagnosis of SITB was not explicitly reported by the physician. In 65% of cases adolescents were discharged within hours of admission. Only 9% of patients started a psychiatric assessment and treatment program during hospital stay. This research confirms the high incidence of SITBs among adolescents and highlights the difficulty in their proper diagnosis and management. Such difficulty is confirmed by the fact that only a few patients, even among those with a clear diagnosis, were sent for psychiatric assessment. Correct identification and management of SITB patients needs to be improved, since SITBs are an important public health problem in adolescence and one of the main risk factors for suicide.
Keywords: Adolescent; Child; Female; Humans; Incidence; Italy; Male; Medical Records; Patient Admission; Retrospective Studies; Self-Injurious Behavior; Sex Factors; Suicidal Ideation; Suicide, Attempted

and Loci Identified through Large-Scale Exome Chip Analysis Regulate Kidney Development and Function. - Li, Man; Li, Yong; Weeks, Olivia; Mijatovic, Vladan; Teumer, Alexander; Huffman, Jennifer E; Tromp, Gerard; Fuchsberger, Christian; Gorski, Mathias; Lyytikäinen, Leo-Pekka; Nutile, Teresa; Sedaghat, Sanaz; et al. (J Am Soc Nephrol, 2017)
Genome-wide association studies have identified >50 common variants associated with kidney function, but these variants do not fully explain the variation in eGFR. We performed a two-stage meta-analysis of associations between genotypes from the Illumina exome array and eGFR on the basis of serum creatinine (eGFRcrea) among participants of European ancestry from the CKDGen Consortium (: 111,666; : 48,343). In single-variant analyses, we identified single nucleotide polymorphisms at seven new loci associated with eGFRcrea (, , and ; <3.7×10), of which most were common and annotated as nonsynonymous variants. Gene-based analysis identified associations of functional rare variants in three genes with eGFRcrea, including a novel association with the SOS Ras/Rho guanine nucleotide exchange factor 2 gene, (=5.4×10 by sequence kernel association test). Experimental follow-up in zebrafish embryos revealed changes in glomerular gene expression and renal tubule morphology in the embryonic kidney of and -knockdowns. These developmental abnormalities associated with altered blood clearance rate and heightened prevalence of edema. This study expands the number of loci associated with kidney function and identifies novel genes with potential roles in kidney formation.
Keywords: Animals; Exome; Genetic Loci; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Protein Tyrosine Phosphatases; Proto-Oncogene Proteins; Son of Sevenless Proteins; Zebrafish

Association between thyroid hormones and TRAIL. - Bernardi, Stella; Bossi, Fleur; Toffoli, Barbara; Giudici, Fabiola; Bramante, Alessandra; Furlanis, Giulia; Stenner, Elisabetta; Secchiero, Paola; Zauli, Giorgio; Carretta, Renzo; Fabris, Bruno (Clin Biochem, 2017)
INTRODUCTION: Recent studies suggest that a circulating protein called TRAIL (TNF-related apoptosis-inducing ligand) might have a role in the regulation of body weight and metabolism. Interestingly, thyroid hormones seem to increase TRAIL tissue expression. This study aimed at evaluating whether overt thyroid disorders affected circulating TRAIL levels. METHODS: TRAIL circulating levels were measured in euthyroid, hyperthyroid, and hypothyroid patients before and after thyroid function normalization. Univariate and multivariate analyses were performed to evaluate the correlation between thyroid hormones and TRAIL. Then, the stimulatory effect of both triiodothyronine (T3) and thyroxine (T4) on TRAIL was evaluated in vitro on peripheral blood mononuclear cells. RESULTS: Circulating levels of TRAIL significantly increased in hyperthyroid and decreased in hypothyroid patients as compared to controls. Once thyroid function was restored, TRAIL levels normalized. There was an independent association between TRAIL and both fT3 and fT4. Consistent with these findings, T3 and T4 stimulated TRAIL release in vitro. CONCLUSION: Here we show that thyroid hormones are associated with TRAIL expression in vivo and stimulate TRAIL expression in vitro. Given the overlap between the metabolic effects of thyroid hormones and TRAIL, this work sheds light on the possibility that TRAIL might be one of the molecules mediating thyroid hormones peripheral effects.
Keywords: Aged; Female; Gene Expression Regulation; Humans; Hyperthyroidism; Hypothyroidism; Leukocytes, Mononuclear; Male; Middle Aged; Thyroxine; TNF-Related Apoptosis-Inducing Ligand; Triiodothyronine

Autoimmune neutropenia of childhood secondary to other autoimmune disorders: Data from the Italian neutropenia registry. - Farruggia, Piero; Puccio, Giuseppe; Fioredda, Francesca; Lanza, Tiziana; Porretti, Laura; Ramenghi, Ugo; Barone, Angelica; Bonanomi, Sonia; Finocchi, Andrea; Ghilardi, Roberta; Ladogana, Saverio; Marra, Nicoletta; et al. (Am J Hematol, 2017)
Keywords: Autoimmune Diseases; Child; Disease Susceptibility; Female; Humans; Immunoglobulins, Intravenous; Immunosuppressive Agents; Infant, Newborn; Infant, Premature; Infant, Premature, Diseases; Italy; Male; Neutropenia; Prevalence; Registries

Child and Adolescent Health From 1990 to 2015: Findings From the Global Burden of Diseases, Injuries, and Risk Factors 2015 Study. - Kassebaum, Nicholas; Kyu, Hmwe Hmwe; Zoeckler, Leo; Olsen, Helen Elizabeth; Thomas, Katie; Pinho, Christine; Bhutta, Zulfiqar A; Dandona, Lalit; Ferrari, Alize; Ghiwot, Tsegaye Tewelde; Hay, Simon I; Kinfu, Yohannes; et al. (JAMA Pediatr, 2017)
Importance: Comprehensive and timely monitoring of disease burden in all age groups, including children and adolescents, is essential for improving population health. Objective: To quantify and describe levels and trends of mortality and nonfatal health outcomes among children and adolescents from 1990 to 2015 to provide a framework for policy discussion. Evidence Review: Cause-specific mortality and nonfatal health outcomes were analyzed for 195 countries and territories by age group, sex, and year from 1990 to 2015 using standardized approaches for data processing and statistical modeling, with subsequent analysis of the findings to describe levels and trends across geography and time among children and adolescents 19 years or younger. A composite indicator of income, education, and fertility was developed (Socio-demographic Index [SDI]) for each geographic unit and year, which evaluates the historical association between SDI and health loss. Findings: Global child and adolescent mortality decreased from 14.18 million (95% uncertainty interval [UI], 14.09 million to 14.28 million) deaths in 1990 to 7.26 million (95% UI, 7.14 million to 7.39 million) deaths in 2015, but progress has been unevenly distributed. Countries with a lower SDI had a larger proportion of mortality burden (75%) in 2015 than was the case in 1990 (61%). Most deaths in 2015 occurred in South Asia and sub-Saharan Africa. Global trends were driven by reductions in mortality owing to infectious, nutritional, and neonatal disorders, which in the aggregate led to a relative increase in the importance of noncommunicable diseases and injuries in explaining global disease burden. The absolute burden of disability in children and adolescents increased 4.3% (95% UI, 3.1%-5.6%) from 1990 to 2015, with much of the increase owing to population growth and improved survival for children and adolescents to older ages. Other than infectious conditions, many top causes of disability are associated with long-term sequelae of conditions present at birth (eg, neonatal disorders, congenital birth defects, and hemoglobinopathies) and complications of a variety of infections and nutritional deficiencies. Anemia, developmental intellectual disability, hearing loss, epilepsy, and vision loss are important contributors to childhood disability that can arise from multiple causes. Maternal and reproductive health remains a key cause of disease burden in adolescent females, especially in lower-SDI countries. In low-SDI countries, mortality is the primary driver of health loss for children and adolescents, whereas disability predominates in higher-SDI locations; the specific pattern of epidemiological transition varies across diseases and injuries. Conclusions and Relevance: Consistent international attention and investment have led to sustained improvements in causes of health loss among children and adolescents in many countries, although progress has been uneven. The persistence of infectious diseases in some countries, coupled with ongoing epidemiologic transition to injuries and noncommunicable diseases, require all countries to carefully evaluate and implement appropriate strategies to maximize the health of their children and adolescents and for the international community to carefully consider which elements of child and adolescent health should be monitored.
Keywords: Adolescent; Adolescent Health; Age Factors; Cause of Death; Child; Child Health; Child Mortality; Disabled Children; Female; Global Burden of Disease; Global Health; Humans; Male; Pregnancy; Pregnancy Complications; Risk Factors; Sex Factors; Wounds and Injuries

Children with cancer: a survey on the experience of Italian primary care pediatricians. - Minute, Marta; Cozzi, Giorgio; Plotti, Chiara; Montanari, Giuseppe; Pecile, Paolo; Zanazzo, Giulio Andrea; Ventura, Alessandro; Barbi, Egidio (Ital J Pediatr, 2017)
BACKGROUND: Cancer is the second cause of death in children and its diagnosis can be difficult, due to the presence of vague and non-specific symptoms. The primary care pediatrician is often involved in the diagnostic process, but no longer in child care once the treatment started. Care models involving both primary care pediatricians and oncologic referral centre highlighted a higher family satisfaction when they worked together. We conducted a survey on primary care pediatricians involved in childhood cancer in order to describe the actual situation. METHODS: We conducted a retrospective survey enrolling primary care pediatricians from a north-eastern area of Italy. They received a questionnaire that consisted in two parts: the first one aimed to assess the physician's seniority and experience and the second one pertained to each case of cancer and explored the relationship between the pediatrician, the family and the referral centre, and pediatricians degree of satisfaction and emotional impact. RESULTS: We obtained data from 79 pediatricians who described 150 cancer cases. In 99 cases the primary care pediatrician had visited the child at the onset of symptoms and had referred him to the hospital. In 89 cases, he understood the severity of the disease. In 53.3% of cases the pediatrician was informed by the referral centre. The relationship between the pediatrician and child's family improved in 38% of cases and this was related with their participation to the multidisciplinary meetings on child health. CONCLUSIONS: Primary pediatricians' sharing in the management of their patients with cancer was not satisfactory. Development of specific protocols targeted to an integrated care is needed to increase primary pediatricians' involvement and families' satisfactions.
Keywords: Child; Child, Preschool; Cross-Sectional Studies; Disease-Free Survival; Female; Humans; Italy; Male; Needs Assessment; Neoplasms; Outcome Assessment (Health Care); Pediatricians; Practice Patterns, Physicians'; Prevalence; Primary Health Care; Retrospective Studies; Risk Assessment; Survival Analysis

Comparison of Efficacy and Safety of Caspofungin Versus Micafungin in Pediatric Allogeneic Stem Cell Transplant Recipients: A Retrospective Analysis. - Maximova, Natalia; Schillani, Giulia; Simeone, Roberto; Maestro, Alessandra; Zanon, Davide (Adv Ther, 2017)
INTRODUCTION: The high morbidity and mortality associated with invasive fungal infections (IFIs) provide the rationale for antifungal prophylaxis in immuno-compromised pediatric patients undergoing hematopoietic stem cell transplantation (HSCT). Caspofungin and micafungin are antifungal agents of interest for prophylaxis of IFIs because of their potency against Candida and minimal toxicity or interactions with other drugs. Few studies have demonstrated the safety and efficacy of such echinocandins as prophylaxis for IFIs in patients undergoing HSCT. METHODS: This retrospective cohort study compared caspofungin and micafungin for prevention of IFIs in 93 pediatric patients undergoing HSCT for oncological or non-oncological disease. The observation began with the first dose of antifungal agent and ended 3 months after transplantation. RESULTS: Patients in the micafungin group had a higher overall treatment success rate of 87.2 versus 84.8% in the caspofungin group, but the difference was not significant. There were no statistically significant differences in the incidence or type of proven/probable IFIs between the 2 groups. The low incidence of death did not differ statistically between the groups. Patients in the caspofungin group presented more frequently with fever, during and after neutropenia. In both groups, we observed an expected worsening of blood chemistry parameters. There were no adverse events definitely attributable to the two antifungal agents. CONCLUSION: These results demonstrate good efficacy and tolerability for caspofungin and micafungin. However, better results with respect to the incidence and resolution of fever in the micafungin group may suggest its use in preference to that of caspofungin.
Keywords: Adolescent; Antifungal Agents; Caspofungin; Child; Child, Preschool; Cohort Studies; Echinocandins; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Infant, Newborn; Lipopeptides; Male; Micafungin; Mycoses; Neutropenia; Retrospective Studies

Complement Protein C1q Binds to Hyaluronic Acid in the Malignant Pleural Mesothelioma Microenvironment and Promotes Tumor Growth. - Agostinis, Chiara; Vidergar, Romana; Belmonte, Beatrice; Mangogna, Alessandro; Amadio, Leonardo; Geri, Pietro; Borelli, Violetta; Zanconati, Fabrizio; Tedesco, Francesco; Confalonieri, Marco; Tripodo, Claudio; Kishore, Uday; et al. (Front Immunol, 2017)
C1q is the first recognition subcomponent of the complement classical pathway, which acts toward the clearance of pathogens and apoptotic cells. C1q is also known to modulate a range of functions of immune and non-immune cells, and has been shown to be involved in placental development and sensorial synaptic pruning. We have recently shown that C1q can promote tumor by encouraging their adhesion, migration, and proliferation in addition to angiogenesis and metastasis. In this study, we have examined the role of human C1q in the microenvironment of malignant pleural mesothelioma (MPM), a rare form of cancer commonly associated with exposure to asbestos. We found that C1q was highly expressed in all MPM histotypes, particularly in epithelioid rather than in sarcomatoid histotype. C1q avidly bound high and low molecular weight hyaluronic acid (HA) its globular domain. C1q bound to HA was able to induce adhesion and proliferation of mesothelioma cells (MES) enhancement of ERK1/2, SAPK/JNK, and p38 phosphorylation; however, it did not activate the complement cascade. Consistent with the modular organization of the globular domain, we demonstrated that C1q may bind to HA through ghA module, whereas it may interact with human MES through the ghC. In conclusion, C1q highly expressed in MPM binds to HA and enhances the tumor growth promoting cell adhesion and proliferation. These data can help develop novel diagnostic markers and molecular targets for MPM.

A congenital purplish tumour. - Matarazzo, L; Delise, A; Zennaro, F; Bussani, R; Demarini, S; Berti, I; Ventura, A (Arch Dis Child Educ Pract Ed, 2017)
Keywords: Congenital Abnormalities; Humans; India; Infant; Infant, Newborn; Knee; Male; Neonatology; Neoplasms; Treatment Outcome

DEFB1 polymorphisms and salivary hBD-1 concentration in Oral Lichen Planus patients and healthy subjects. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Pozzato, Gabriele; Ottaviani, Giulia; Gobbo, Margherita; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2017)
OBJECTIVES: The aetiology of Oral Lichen Planus (OLP), a chronic inflammatory disease of oral mucosa, is not yet well understood. Since innate immunity may be hypothesized as involved in the susceptibility to OLP, we studied human beta defensin 1 (hBD-1) an antimicrobial peptide constitutively expressed in the saliva, looking at functional genetic variants possibly able to diminish hBD-1 production an consequently conferring major susceptibility to OLP. DESIGN: We analysed three DEFB1 polymorphisms at 5' UTR, -52G>A (rs1799946), -44C>G (rs1800972), -20G>A (rs11362) and two DEFB1 polymorphisms at 3'UTR, c*5G>A (rs1047031), c*87A>G (rs1800971), with the aim of correlating these genetic variants and hBD-1 salivary level in a group of OLP patients and in healthy subjects. We also evaluated hBD-1 salivary concentrations, using ELISA, in OLP and healthy controls. RESULTS: We compared hBD-1 concentrations in OLP and healthy subjects: hBD-1 concentration was significantly higher in OLP patients respect to control. When considering the correlation between DEFB1 polymorphisms genotypes and hBD-1 expression levels, significant results were obtained for SNPs -52G>A (p=0.03 both in OLP patients and healthy individuals) and -44C>G (p=0.02 in OLP patients). CONCLUSIONS: hBD-1 production was different between OLP and healthy subjects (not age-matched with OLP). DEFB1 gene polymorphisms, -52G>A and -44C>G, correlated with hBD-1 salivary concentrations.
Keywords: 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; beta-Defensins; Female; Genetic Predisposition to Disease; Genotype; Humans; Lichen Planus, Oral; Male; Middle Aged; Polymorphism, Single Nucleotide; Saliva; Sequence Analysis, DNA

Diagnosis and management of newly diagnosed childhood autoimmune haemolytic anaemia. Recommendations from the Red Cell Study Group of the Paediatric Haemato-Oncology Italian Association. - Ladogana, Saverio; Maruzzi, Matteo; Samperi, Piera; Perrotta, Silverio; Del Vecchio, Giovanni C; Notarangelo, Lucia D; Farruggia, Piero; Verzegnassi, Federico; Masera, Nicoletta; Saracco, Paola; Fasoli, Silvia; Miano, Maurizio; et al. (Blood Transfus, 2017)
Autoimmune haemolytic anaemia is an uncommon disorder to which paediatric haematology centres take a variety of diagnostic and therapeutic approaches. The Red Cell Working Group of the Italian Association of Paediatric Onco-haematology (Associazione Italiana di Ematologia ed Oncologia Pediatrica, AIEOP) developed this document in order to collate expert opinions on the management of newly diagnosed childhood autoimmune haemolytic anaemia.The diagnostic process includes the direct and indirect antiglobulin tests; recommendations are given regarding further diagnostic tests, specifically in the cases that the direct and indirect antiglobulin tests are negative. Clear-cut definitions of clinical response are stated. Specific recommendations for treatment include: dosage of steroid therapy and tapering modality for warm autoimmune haemolytic anaemia; the choice of rituximab as first-line therapy for the rare primary transfusion-dependent cold autoimmune haemolytic anaemia; the indications for supportive therapy; the need for switching to second-line therapy. Each statement is provided with a score expressing the level of appropriateness and the agreement among participants.
Keywords: Anemia, Hemolytic, Autoimmune; Blood Transfusion; Child; Coombs Test; Disease Management; Hematology; Humans; Immunoglobulin M; Italy; Pediatrics; Societies, Medical; Steroids

Enrichment of low-frequency functional variants revealed by whole-genome sequencing of multiple isolated European populations. - Xue, Yali; Mezzavilla, Massimo; Haber, Marc; McCarthy, Shane; Chen, Yuan; Narasimhan, Vagheesh; Gilly, Arthur; Ayub, Qasim; Colonna, Vincenza; Southam, Lorraine; Finan, Christopher; Massaia, Andrea; et al. (Nat Commun, 2017)
The genetic features of isolated populations can boost power in complex-trait association studies, and an in-depth understanding of how their genetic variation has been shaped by their demographic history can help leverage these advantageous characteristics. Here, we perform a comprehensive investigation using 3,059 newly generated low-depth whole-genome sequences from eight European isolates and two matched general populations, together with published data from the 1000 Genomes Project and UK10K. Sequencing data give deeper and richer insights into population demography and genetic characteristics than genotype-chip data, distinguishing related populations more effectively and allowing their functional variants to be studied more fully. We demonstrate relaxation of purifying selection in the isolates, leading to enrichment of rare and low-frequency functional variants, using novel statistics, DVxy and SVxy. We also develop an isolation-index (Isx) that predicts the overall level of such key genetic characteristics and can thus help guide population choice in future complex-trait association studies.
Keywords: European Continental Ancestry Group; Gene Frequency; Genetic Variation; Genetics, Population; Genome, Human; Humans; Polymorphism, Single Nucleotide; Whole Genome Sequencing

Essure Permanent Birth Control, Effectiveness and Safety: An Italian 11-Year Survey. - Franchini, Mario; Zizolfi, Brunella; Coppola, Carmela; Bergamini, Valentino; Bonin, Cecilia; Borsellino, Giovanni; Busato, Enrico; Calabrese, Stefania; Calzolari, Stefano; Fantin, Gian Piero; Giarrè, Giovanna; Litta, Piero; et al. (J Minim Invasive Gynecol, 2017)
STUDY OBJECTIVE: To describe safety, tolerability, and effectiveness results through a minimum 2-year follow-up of patients who underwent permanent sterilization with the Essure insert. DESIGN: A retrospective multicenter study (Canadian Task Force classification II2). SETTING: Seven general hospitals and 4 clinical teaching centers in Italy. PATIENTS: A total of 1968 women, mean age 39.5 years (range, 23-48 years) who underwent office hysteroscopic sterilization using the Essure insert between April 1, 2003, and December 30, 2014. INTERVENTION: The women underwent office hysteroscopic bilateral Essure insert placement, with satisfactory device location and tube occlusion based on hysterosalpingography or hysterosalpingo-contrast sonography (HyCoSy). MEASUREMENTS AND MAIN RESULTS: Placement rate, successful bilateral tubal occlusion, perioperative adverse events, early postoperative (during the first 3 months of follow-up), and late complications were evaluated. Satisfactory insertion was accomplished in 97.2% of women and, in 4, perforation and 1 expulsion were detected during hysterosalpingography. Three unintended pregnancies occurred before the 3-month confirmation test. Two pregnancies were reported among women relying on the Essure inserts. Postprocedure pain was minimal and brief; in 9 women, pelvic pain became intractable, necessitating removal of the devices via laparoscopy. On telephone interviews, overall satisfaction was rated as "very satisfied" by the majority of women (97.6%), and no long-term adverse events were reported. CONCLUSION: The findings from this extended Italian survey further support the effectiveness, tolerability, and satisfaction of Essure hysteroscopic sterilization when motivated women are selected and well informed of the potential risks of the device. Moreover, the results do not demonstrate an increased incidence of complications and pregnancies associated with long-term Essure use. Patients with a known hypersensitivity to nickel may be less suitable candidates for the Essure insert.
Keywords: Adult; Fallopian Tubes; Female; Follow-Up Studies; Humans; Hypersensitivity; Hysterosalpingography; Hysteroscopy; Italy; Laparoscopy; Middle Aged; Nickel; Pain; Pregnancy; Pregnancy, Unplanned; Retrospective Studies; Sterilization, Reproductive; Sterilization, Tubal; Surveys and Questionnaires; Young Adult

First-time success with needle procedures was higher with a warm lidocaine and tetracaine patch than an eutectic mixture of lidocaine and prilocaine cream. - Cozzi, Giorgio; Borrometi, Fabio; Benini, Franca; Neri, Elena; Rusalen, Francesca; Celentano, Loredana; Zanon, Davide; Schreiber, Silvana; Ronfani, Luca; Barbi, Egidio (Acta Paediatr, 2017)
AIM: More than 50% of children report apian during venepuncture or intravenous cannulation and using local anaesthetics before needle procedures can lead to different success rates. This study examined how many needle procedures were successful at the first attempt when children received either a warm lidocaine and tetracaine patch or an eutectic mixture of lidocaine and prilocaine (EMLA) cream. METHODS: We conducted this multicentre randomised controlled trial at three tertiary-level children's hospitals in Italy in 2015. Children aged three to 10 years were enrolled in an emergency department, paediatric day hospital and paediatric ward and randomly allocated to receive a warm lidocaine and tetracaine patch or EMLA cream. The primary outcome was the success rate at the first attempt. RESULTS: The analysis included 172 children who received a warm lidocaine and tetracaine patch and 167 who received an EMLA cream. The needle procedure was successful at the first attempt in 158 children (92.4%) who received the warm patch and in 142 children (85.0%) who received the cream (p = 0.03). The pain scores were similar in both groups. CONCLUSION: This study showed that the first-time needle procedure success was 7.4% higher in children receiving a warm lidocaine and tetracaine patch than EMLA cream.
Keywords: Anesthetics, Local; Catheterization, Peripheral; Child; Child, Preschool; Female; Hot Temperature; Humans; Lidocaine; Lidocaine, Prilocaine Drug Combination; Male; Pain; Phlebotomy; Prilocaine; Tetracaine

Genomic analyses identify hundreds of variants associated with age at menarche and support a role for puberty timing in cancer risk. - Day, Felix R; Thompson, Deborah J; Helgason, Hannes; Chasman, Daniel I; Finucane, Hilary; Sulem, Patrick; Ruth, Katherine S; Whalen, Sean; Sarkar, Abhishek K; Albrecht, Eva; Altmaier, Elisabeth; Amini, Marzyeh; et al. (Nat Genet, 2017)
The timing of puberty is a highly polygenic childhood trait that is epidemiologically associated with various adult diseases. Using 1000 Genomes Project-imputed genotype data in up to ∼370,000 women, we identify 389 independent signals (P < 5 × 10) for age at menarche, a milestone in female pubertal development. In Icelandic data, these signals explain ∼7.4% of the population variance in age at menarche, corresponding to ∼25% of the estimated heritability. We implicate ∼250 genes via coding variation or associated expression, demonstrating significant enrichment in neural tissues. Rare variants near the imprinted genes MKRN3 and DLK1 were identified, exhibiting large effects when paternally inherited. Mendelian randomization analyses suggest causal inverse associations, independent of body mass index (BMI), between puberty timing and risks for breast and endometrial cancers in women and prostate cancer in men. In aggregate, our findings highlight the complexity of the genetic regulation of puberty timing and support causal links with cancer susceptibility.
Keywords: Adolescent; Age Factors; Body Mass Index; Databases, Genetic; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomic Imprinting; Humans; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Neoplasms; Polymorphism, Single Nucleotide; Puberty; Quantitative Trait Loci; Ribonucleoproteins; Risk Factors

Higher growth, fat and fat-free masses correlate with larger cerebellar volumes in preterm infants at term. - Paviotti, Giulia; De Cunto, Angela; Zennaro, Floriana; Boz, Giulia; Travan, Laura; Cont, Gabriele; Bua, Jenny; Demarini, Sergio (Acta Paediatr, 2017)
AIM: Smaller cerebellar volumes in very low-birthweight (VLBW) infants at term have been related to adverse cognitive outcomes, and this study evaluated whether these volumes were associated with a growth in body composition during hospital stays. METHODS: We prospectively recruited 42 VLBW infants from an Italian neonatal unit between January 2013 and August 2015. Cerebellar volumes and body composition were measured by magnetic resonance imaging (MRI) and air-displacement plethysmography, respectively, at 40 weeks of gestational age and anthropometric and nutritional data were collected. We also included 20 term-born controls. RESULTS: The mean gestational age and birthweight of the VLBW infants were 29.4 (±1.9) weeks and 1120 (±290) g. There was a positive correlation between cerebellar volumes and daily weight gain from birth to term (R = 0.26, p = 0.001), weight (R = 0.25, p = 0.001), length (R = 0.16, p = 0.01), fat mass (R = 0.15, p = 0.01) and fat-free mass at term (R = 0.20, p = 0.003). In multiple regression analysis, daily weight gain, mechanical ventilation and postconceptional age at MRI were independently associated with cerebellar volumes. Anthropometric data and cerebellar volumes were similar between VLBW and control infants. CONCLUSION: Higher growth, higher fat mass and fat-free mass were associated with larger cerebellar volumes in VLBW infants at term.
Keywords: Body Composition; Cerebellum; Child Development; Female; Humans; Infant, Newborn; Infant, Premature; Infant, Very Low Birth Weight; Male; Nutritional Status; Organ Size; Prospective Studies; Regression Analysis

HLA-G regulatory polymorphisms are associated with susceptibility to HCV infection. - Catamo, E; Zupin, L; Freato, N; Polesello, V; Celsi, F; Crocè, S L; Masutti, F; Pozzato, G; Segat, L; Crovella, S (HLA, 2017)
BACKGROUND: Hepatitis C virus (HCV) is able to bypass the immune system modulating innate and adaptive immune response and blocking T helper 1 (Th1) cell production. Because the human leukocyte antigen (HLA)-G molecule has immunomodulatory properties inhibiting the function and production of natural killer and cytotoxic lymphocyte T cells, as well as promoting shift from Th1 toward Th2 response, we hypothesized its involvement in susceptibility to HCV infection. MATERIALS AND METHODS: Considering that HLA-G mRNA expression has been reported to be under genetic control, an association study was conducted analyzing 800 base pairs upstream the ATG at the 5'upstream regulator region (URR) and 850 base pairs from ATG to exon 3 and the 3'untranslated region (UTR) of HLA-G gene in Italian HCV-positive patients and uninfected controls. RESULTS: Four 5'URR polymorphisms (-725C>G>T, -509C>G, -400G>A and -398G>A), 7 polymorphisms at coding region (+15G>A, +36G>A, +243G>A, insC506, 531G>C, delA615 and 685G>A), the +644G>T polymorphism, and 1 haplotype (TTGTTCCIGAC) showed different frequency distributions between HCV patients and uninfected controls. CONCLUSION: The results from our study suggest a possible involvement of HLA-G in the risk modulation toward HCV infection.
Keywords: 3' Untranslated Regions; 5' Untranslated Regions; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Exons; Female; Gene Expression; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Haplotypes; Hepacivirus; Hepatitis C; HLA-G Antigens; Humans; Italy; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk; Th1 Cells

Impact of the 13-Valent Pneumococcal Conjugate Vaccine on Clinical and Hypoxemic Childhood Pneumonia over Three Years in Central Malawi: An Observational Study. - McCollum, Eric D; Nambiar, Bejoy; Deula, Rashid; Zadutsa, Beatiwel; Bondo, Austin; King, Carina; Beard, James; Liyaya, Harry; Mankhambo, Limangeni; Lazzerini, Marzia; Makwenda, Charles; Masache, Gibson; et al. (PLoS One, 2017)
BACKGROUND: The pneumococcal conjugate vaccine's (PCV) impact on childhood pneumonia during programmatic conditions in Africa is poorly understood. Following PCV13 introduction in Malawi in November 2011, we evaluated the case burden and rates of childhood pneumonia. METHODS AND FINDINGS: Between January 1, 2012-June 30, 2014 we conducted active pneumonia surveillance in children <5 years at seven hospitals, 18 health centres, and with 38 community health workers in two districts, central Malawi. Eligible children had clinical pneumonia per Malawi guidelines, defined as fast breathing only, chest indrawing +/- fast breathing, or, ≥1 clinical danger sign. Since pulse oximetry was not in the Malawi guidelines, oxygenation <90% defined hypoxemic pneumonia, a distinct category from clinical pneumonia. We quantified the pneumonia case burden and rates in two ways. We compared the period immediately following vaccine introduction (early) to the period with >75% three-dose PCV13 coverage (post). We also used multivariable time-series regression, adjusting for autocorrelation and exploring seasonal variation and alternative model specifications in sensitivity analyses. The early versus post analysis showed an increase in cases and rates of total, fast breathing, and indrawing pneumonia and a decrease in danger sign and hypoxemic pneumonia, and pneumonia mortality. At 76% three-dose PCV13 coverage, versus 0%, the time-series model showed a non-significant increase in total cases (+47%, 95% CI: -13%, +149%, p = 0.154); fast breathing cases increased 135% (+39%, +297%, p = 0.001), however, hypoxemia fell 47% (-5%, -70%, p = 0.031) and hospital deaths decreased 36% (-1%, -58%, p = 0.047) in children <5 years. We observed a shift towards disease without danger signs, as the proportion of cases with danger signs decreased by 65% (-46%, -77%, p<0.0001). These results were generally robust to plausible alternative model specifications. CONCLUSIONS: Thirty months after PCV13 introduction in Malawi, the health system burden and rates of the severest forms of childhood pneumonia, including hypoxemia and death, have markedly decreased.
Keywords: Child; Child Mortality; Cost of Illness; Dose-Response Relationship, Immunologic; Geography; Humans; Hypoxia; Malawi; Pneumococcal Vaccines; Pneumonia, Pneumococcal; Time Factors; Vaccines, Conjugate

Imported arboviral infections in Italy, July 2014-October 2015: a National Reference Laboratory report. - Fortuna, Claudia; Remoli, Maria Elena; Rizzo, Caterina; Benedetti, Eleonora; Fiorentini, Cristiano; Bella, Antonino; Argentini, Claudio; Farchi, Francesca; Castilletti, Concetta; Capobianchi, Maria Rosaria; Zammarchi, Lorenzo; Bartoloni, Alessandro; et al. (BMC Infect Dis, 2017)
BACKGROUND: Imported cases of infections due to Dengue (DENV) and Chikungunya (CHIKV) viruses and, more recently, Zika virus (ZIKV) are commonly reported among travelers returning from endemic regions. In areas where potentially competent vectors are present, the risk of autochthonous transmission of these vector-borne pathogens is relatively high. Laboratory surveillance is crucial to rapidly detect imported cases in order to reduce the risk of transmission. This study describes the laboratory activity performed by the National Reference Laboratory for Arboviruses (NRLA) at the Italian National Institute of Health in the period from July 2014 to October 2015. METHODS: Samples from 180 patients visited/hospitalized with a suspected DENV/CHIKV/ZIKV infection were sent to the NRLA from several Italian Hospitals and from Regional Reference Laboratories for Arboviruses, in agreement with the National Plan on human surveillance of vector-borne diseases. Both serological (ELISA IgM test and Plaque Reduction Neutralization Test-PRNT) and molecular assays (Real Time PCR tests, RT-PCR plus nested PCR and sequencing of positive samples) were performed. RESULTS: DENV infection was the most frequently diagnosed (80 confirmed/probable cases), and all four genotypes were detected. However, an increase in imported CHIKV cases (41 confirmed/probable cases) was observed, along with the detection of the first ZIKV cases (4 confirmed cases), as a consequence of the recent spread of both CHIKV and ZIKV in the Americas. CONCLUSIONS: Main diagnostic issues highlighted in our study are sensitivity limitations of molecular tests, and the importance of PRNT to confirm serological results for differential diagnosis of Arboviruses. The continuous evaluation of diagnostic strategy, and the implementation of laboratories networks involved in surveillance activities is essential to ensure correct diagnosis, and to improve the preparedness for a rapid and proper identification of viral threats.
Keywords: Chikungunya Fever; Chikungunya virus; Dengue; Dengue Virus; Disease Outbreaks; Female; Genotype; Humans; Italy; Male; Molecular Diagnostic Techniques; Population Surveillance; Public Health; Travel; Young Adult; Zika Virus; Zika Virus Infection

Influence of vaginal lactoferrin administration on amniotic fluid cytokines and its role against inflammatory complications of pregnancy. - Maritati, Martina; Comar, Manola; Zanotta, Nunzia; Seraceni, Silva; Trentini, Alessandro; Corazza, Fabrizio; Vesce, Fortunato; Contini, Carlo (J Inflamm (Lond), 2017)
BACKGROUND: An altered amniotic cytokine profile has been reported in inflammatory pregnancy complications with a leading role for IL-6, a marker of the foetal systemic inflammatory response. Up to this date there is no exhaustive information neither on the foetal cytokine balance nor on the best method for its modulation. We aimed to evaluate the influence of vaginal lactoferrin administration on amniotic fluid concentration of 47 cytokines, chemokines and growth factors. METHODS: Sixty women undergoing genetic amniocentesis were enrolled in an open-label clinical trial. 300 mg of vaginal lactoferrin (Florence, Italy) were randomly administered to obtain 3 groups: A, 20 untreated patients; B and C (20 patients in each) respectively treated 4 and 12 h before amniocentesis. Cytokines, chemokines and growth factors concentrations were quantified by a magnetic bead Luminex multiplex immunoassays panel technology. Data analysis was performed with the software Stata (v. 13.1) and GraphPad Prism (v. 5). Group comparisons were performed using Kruskal-Wallis followed by Mann-Whitney U tests, with Bonferroni correction for multiple comparisons. A  < 0.05 was considered significant. RESULTS: Among the 47 tested mediators, 24 (51.06%) were influenced by lactoferrin. 11 (23.4%), showed a highly significant difference (p <0.001); among these IL-9, IL-15, IFN-γ, IP-10, TNF-α, IL-1α and MCP-3 underwent a down-regulation, while IL-17 and FGF-basic, G-CSF, GM-CSF an up-regulation. Difference between group C and both B and A was small for IL-15, IP-10, IL-1α, MCP-3, while it was negligible for IL-9, IFN-γ and TNF-α. IL-17 and the 3 growth factors were strongly enhanced in B and C groups. IL-17, FGF-basic and GM-CSF showed increasing concentrations in both B and C groups, while G-CSF resulted up-regulated only in group C. Significance was intermediate ( < 0.01) for the down regulated IL-2RA, IL-12p40 and IFNα2 (6.38%) while it was small for 10 mediators (21.27%) 7 of which (IL-2, IL-4, eotaxin, PDGF-BB, RANTES, IL-18 and MIF) down-regulated and 3 (MCP-1, IL-3, and SDF-1α) up-regulated. CONCLUSION: Lactoferrin down-regulates 17 pro-inflammatory amniotic mediators while up-regulating 7 anti-inflammatory amniotic mediators, 5 of which definitively belonging to an anti-inflammatory profile. These findings open to clinical investigation on its use against inflammatory complications of pregnancy.

ISL1 is a major susceptibility gene for classic bladder exstrophy and a regulator of urinary tract development. - Zhang, Rong; Knapp, Michael; Suzuki, Kentaro; Kajioka, Daiki; Schmidt, Johanna M; Winkler, Jonas; Yilmaz, Öznur; Pleschka, Michael; Cao, Jia; Kockum, Christina Clementson; Barker, Gillian; Holmdahl, Gundela; et al. (Sci Rep, 2017)
Previously genome-wide association methods in patients with classic bladder exstrophy (CBE) found association with ISL1, a master control gene expressed in pericloacal mesenchyme. This study sought to further explore the genetics in a larger set of patients following-up on the most promising genomic regions previously reported. Genotypes of 12 markers obtained from 268 CBE patients of Australian, British, German Italian, Spanish and Swedish origin and 1,354 ethnically matched controls and from 92 CBE case-parent trios from North America were analysed. Only marker rs6874700 at the ISL1 locus showed association (p = 2.22 × 10). A meta-analysis of rs6874700 of our previous and present study showed a p value of 9.2 × 10. Developmental biology models were used to clarify the location of ISL1 activity in the forming urinary tract. Genetic lineage analysis of Isl1-expressing cells by the lineage tracer mouse model showed Isl1-expressing cells in the urinary tract of mouse embryos at E10.5 and distributed in the bladder at E15.5. Expression of isl1 in zebrafish larvae staged 48 hpf was detected in a small region of the developing pronephros. Our study supports ISL1 as a major susceptibility gene for CBE and as a regulator of urinary tract development.
Keywords: Animals; Bladder Exstrophy; Embryo, Mammalian; Female; Gene Expression Regulation, Developmental; Genetic Predisposition to Disease; Humans; Larva; LIM-Homeodomain Proteins; Mesoderm; Mice; Organogenesis; Polymorphism, Single Nucleotide; Pronephros; Protein Isoforms; Transcription Factors; Urinary Tract; Zebrafish

LTF and DEFB1 polymorphisms are associated with susceptibility toward chronic periodontitis development. - Zupin, L; Robino, A; Navarra, C O; Pirastu, N; Di Lenarda, R; Gasparini, P; Crovella, S; Bevilacqua, L (Oral Dis, 2017)
OBJECTIVES: Chronic periodontitis is a common pathological condition that affects the supporting tissue of the teeth, leading to progressive alveolar bone destruction and teeth loss. The disease is caused by bacteria and derives from an altered host immune and inflammatory response, also involving different factors such as the oral hygiene, smoking, and genetic background. The innate immune response, the first line of host defense, could also play an important role in the susceptibility to chronic periodontitis. In this study, we evaluated the possible association between periodontal disease and seven genetic variations within DEFB1 and LTF genes, encoding for β-defensins 1 and lactoferrin (two members of oral innate immune system), in an Italian isolated population. SUBJECTS AND METHODS: DEFB1 5'UTR g. -52G>A (rs1799946), g. -44C>G (rs1800972), g. -20G>A (rs11362), 3'UTR c*5G>A (rs1047031), c*87A>G (rs1800971), LTF p.Ala29Thr (rs1126477), and p.Lys47Arg (rs1126478) single nucleotide polymorphisms (SNPs) were analyzed in 155 healthy individuals and 439 chronic periodontitis patients from North-East Italy. RESULTS: Significant associations were found between periodontitis and g. -20G>A (rs11362) and g. -44C>G (rs1800972) SNPs in DEFB1 gene as well as p.Ala29Thr (rs1126477) and p.Lys47Arg (rs1126478) SNPs in LTF gene. DISCUSSION: Our results suggest the involvement of DEFB1 and LTF genetic variations in the susceptibility toward development of periodontitis.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; beta-Defensins; Case-Control Studies; Chronic Periodontitis; Female; Genetic Predisposition to Disease; Humans; Lactoferrin; Male; Middle Aged; Polymorphism, Single Nucleotide; Young Adult

Metastatic neuroblastoma in infants: are survival rates excellent only within the stringent framework of clinical trials? - Di Cataldo, A; Agodi, A; Balaguer, J; Garaventa, A; Barchitta, M; Segura, V; Bianchi, M; Castel, V; Castellano, A; Cesaro, S; Couselo, J M; Cruz, O; et al. (Clin Transl Oncol, 2017)
INTRODUCTION: SIOPEN INES protocol yielded excellent 5-year survival rates for MYCN-non-amplified metastatic neuroblastoma. Patients deemed ineligible due to lack or delay of MYCN status or late registration were treated, but not included in the study. Our goal was to analyse survival at 10 years among the whole population. MATERIALS AND METHODS: Italian and Spanish metastatic INES patients' data are reported. SPSS 20.0 was used for statistical analysis. RESULTS: Among 98 infants, 27 had events and 19 died, while 79 were disease free. Five- and 10-year event-free survival (EFS) were 73 and 70 %, and overall survival (OS) was 81 and 74 %, respectively. MYCN status was significant for EFS, but not for OS in multivariate analysis. CONCLUSIONS: The survival rates of patients who complied with all the inclusion criteria for INES trials are higher compared to those that included also not registered patients. Five-year EFS and OS for INES 99.2 were 87.8 and 95.7 %, while our stage 4s population obtained 78 and 87 %. Concerning 99.3, 5-year EFS and OS were 86.7 and 95.6 %, while for stage 4 we registered 61 and 68 %. MYCN amplification had a strong impact on prognosis and therefore we consider it unacceptable that many patients were not studied for MYCN and probably inadequately treated. Ten-year survival rates were shown to decrease: EFS from 73 to 70 % and OS from 81 to 74 %, indicating a risk of late events, particularly in stage 4s. Population-based registries like European ENCCA WP 11-task 11 will possibly clarify these data.
Keywords: Biomarkers, Tumor; Child; Child, Preschool; Clinical Trials as Topic; Combined Modality Therapy; Female; Follow-Up Studies; Gene Amplification; Humans; Infant; Infant, Newborn; Male; N-Myc Proto-Oncogene Protein; Neoplasm Staging; Neuroblastoma; Prognosis; Survival Rate

Neuroimaging Changes in Menkes Disease, Part 1. - Manara, R; D'Agata, L; Rocco, M C; Cusmai, R; Freri, E; Pinelli, L; Darra, F; Procopio, E; Mardari, R; Zanus, C; Di Rosa, G; Soddu, C; et al. (AJNR Am J Neuroradiol, 2017)
Menkes disease is a rare multisystem X-linked disorder of copper metabolism. Despite an early, severe, and progressive neurologic involvement, our knowledge of brain involvement remains unsatisfactory. The first part of this retrospective and review MR imaging study aims to define the frequency rate, timing, imaging features, and evolution of intracranial vascular and white matter changes. According to our analysis, striking but also poorly evolutive vascular abnormalities characterize the very early phases of disease. After the first months, myelination delay becomes evident, often in association with protean focal white matter lesions, some of which reveal an age-specific brain vulnerability. In later phases of the disease, concomitant progressive neurodegeneration might hinder the myelination progression. The currently enriched knowledge of neuroradiologic finding evolution provides valuable clues for early diagnosis, identifies possible MR imaging biomarkers of new treatment efficacy, and improves our comprehension of possible mechanisms of brain injury in Menkes disease.
Keywords: Brain; Disease Progression; Female; Humans; Magnetic Resonance Imaging; Male; Menkes Kinky Hair Syndrome; Neuroimaging; Retrospective Studies; White Matter

Novel Blood Pressure Locus and Gene Discovery Using Genome-Wide Association Study and Expression Data Sets From Blood and the Kidney. - Wain, Louise V; Vaez, Ahmad; Jansen, Rick; Joehanes, Roby; van der Most, Peter J; Erzurumluoglu, A Mesut; O'Reilly, Paul F; Cabrera, Claudia P; Warren, Helen R; Rose, Lynda M; Verwoert, Germaine C; Hottenga, Jouke-Jan; et al. (Hypertension, 2017)
Elevated blood pressure is a major risk factor for cardiovascular disease and has a substantial genetic contribution. Genetic variation influencing blood pressure has the potential to identify new pharmacological targets for the treatment of hypertension. To discover additional novel blood pressure loci, we used 1000 Genomes Project-based imputation in 150 134 European ancestry individuals and sought significant evidence for independent replication in a further 228 245 individuals. We report 6 new signals of association in or near , , , , , and , and provide new replication evidence for a further 2 signals in and Combining large whole-blood gene expression resources totaling 12 607 individuals, we investigated all novel and previously reported signals and identified 48 genes with evidence for involvement in blood pressure regulation that are significant in multiple resources. Three novel kidney-specific signals were also detected. These robustly implicated genes may provide new leads for therapeutic innovation.

Pediatric Ovarian Torsion and its Recurrence: A Multicenter Study. - Bertozzi, Mirko; Esposito, Ciro; Vella, Claudio; Briganti, Vito; Zampieri, Nicola; Codrich, Daniela; Ubertazzi, Michele; Trucchi, Alessandro; Magrini, Elisa; Battaglia, Sonia; Bini, Vittorio; Conighi, Maria Luisa; et al. (J Pediatr Adolesc Gynecol, 2017)
STUDY OBJECTIVE: To report results of a retrospective multicentric Italian survey concerning the management of pediatric ovarian torsion (OT) and its recurrence. DESIGN: Multicenter retrospective cohort study. SETTING: Italian Units of Pediatric Surgery. PARTICIPANTS: Participants were female aged 1-14 years of age with surgically diagnosed OT between 2004 and 2014. INTERVENTIONS: Adnexal detorsion, adnexectomy, mass excision using laparoscopy or laparotomy. Different kinds of oophoropexy (OPY) for OT or recurrence, respectively. MAIN OUTCOME MEASURES: A total of 124 questionnaires were returned and analyzed to understand the current management of pediatric OT and its recurrence. The questionnaires concerned patient age, presence of menarche, OT site, presence and type of mass, performed procedure, OPY technique adopted, intra- and postoperative complications, recurrence and site, procedure performed for recurrence, OPY technique for recurrence, and 1 year follow-up of detorsed ovaries. RESULTS: Mean age at surgery was 9.79 ± 3.54 years. Performed procedures were open adnexectomy (52 of 125; 41.6%), laparoscopic adnexectomy (25 of 125; 20%), open detorsion (10 of 125; 8%), and laparoscopic detorsion (38 of 125; 30.4%). Recurrence occurred in 15 of 125 cases (12%) and resulted as significant (P = .012) if associated with a normal ovary at the first episode of torsion. Recurrence occurred only in 1 of 19 cases after OPY (5.2%). Ultrasonographic results of detorsed ovaries were not significant whether an OPY was performed or not (P = 1.00). CONCLUSION: Unfortunately, oophorectomy and open technique are still widely adopted even if not advised. Recurrence is not rare and the risk is greater in patients without ovarian masses. OPY does not adversely affect ultrasonographic results at 1 year. When possible OPY should be performed at the first episode of OT.
Keywords: Adolescent; Child; Child, Preschool; Cohort Studies; Female; Humans; Infant; Italy; Laparoscopy; Laparotomy; Menarche; Ovarian Diseases; Ovariectomy; Postoperative Complications; Recurrence; Retrospective Studies; Surveys and Questionnaires; Torsion Abnormality

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

SV40 Infection of Mesenchymal Stromal Cells From Wharton's Jelly Drives the Production of Inflammatory and Tumoral Mediators. - Cason, Carolina; Campisciano, Giuseppina; Zanotta, Nunzia; Valencic, Erica; Delbue, Serena; Bella, Ramona; Comar, Manola (J Cell Physiol, 2017)
The Mesenchymal Stromal Cells from umbilical cord Wharton's jelly (WJSCs) are a source of cells with high potentiality for the treatment of human immunological disorders. Footprints of the oncogenic viruses Simian Virus 40 (SV40) and JC Virus (JCPyV) have been recently detected in human WJSCs specimens. The aim of this study is to evaluate if WJSCs can be efficiently infected by these Polyomaviruses and if they can potentially exert tumoral activity. Cell culture experiments indicated that WJSCs could sustain both SV40 and JCPyV infections. A transient and lytic replication was observed for JCPyV, while SV40 persistently infected WJSCs over a long period of time, releasing a viral progeny at low titer without evident cytopathic effect (CPE). Considering the association between SV40 and human tumors and the reported ability of the oncogenic viruses to drive the host innate immune response to cell transformation, the expression profile of a large panel of immune mediators was evaluated in supernatants by the Bioplex platform. RANTES, IL-3, MIG, and IL-12p40, involved in chronic inflammation, cells differentiation, and transformation, were constantly measured at high concentration comparing to control. These findings represent a new aspect of SV40 biological activity in the humans, highlighting its interaction with specific host cellular pathways. In view of these results, it seems to be increasingly urgent to consider Polyomaviruses in the management of WJSCs for their safely use as promising therapeutic source. J. Cell. Physiol. 232: 3060-3066, 2017. © 2016 Wiley Periodicals, Inc.
Keywords: Cell Line, Transformed; Cell Separation; Cell Transformation, Viral; Chemokine CCL5; Chemokine CXCL9; Cytopathogenic Effect, Viral; DNA, Viral; Host-Pathogen Interactions; Humans; Inflammation Mediators; Interleukin-12 Subunit p40; Interleukin-3; JC Virus; Mesenchymal Stem Cells; Real-Time Polymerase Chain Reaction; Simian virus 40; Time Factors; Up-Regulation; Viral Load; Virus Replication; Wharton Jelly

Thrombogenesis in Thrombophilic Pregnancy: Evaluation of Low-Molecular-Weight Heparin Prophylaxis. - Simeone, Roberto; Giacomello, Roberta; Bruno, Germano; Parco, Sergio; Maximova, Natalia; Martinelli, Monica; Zito, Gabriella; Luppi, Stefania; Cervi, Gina; Ricci, Giuseppe (Acta Haematol, 2017)
The aim of this study is to investigate thrombogenesis and the hypercoagulable changes in pregnant women affected by thrombophilia who received low-molecular-weight heparin (LWMH) prophylaxis. We included 21 pregnant women affected by thrombophilia treated with LWMH and 20 nontreated normal pregnant women as the control group. The sample group of thrombophilic pregnant women included different conditions (factor V Leiden mutation, protein C deficiency, protein S deficiency, antiphospholipid antibodies syndrome, and combined defects). Three blood samples were collected during pregnancy (i.e., at 16, 20, and 24 weeks) and tested for activated partial thromboplastin time and prothrombin fragment F1 + 2 (F1 + 2); anti-FXa activity was tested only in treated thrombophilic pregnant women. F1 + 2 levels progressively increased during pregnancy in both study groups. However, the F1 + 2 increase in women exposed to heparin prophylaxis was significantly lower than that in normal pregnant women in all 3 measurements carried out during gestation (p < 0.05); a statistically significant inverse correlation between F1 + 2 levels and anti-Xa activity (R = -0.8575, p < 0.05) was observed in treated women during pregnancy. Our findings suggest that F1 + 2 in addition to anti-Xa measurement could be used to adjust LWMH prophylaxis, at least in high-risk pregnant women.
Keywords: Adult; Anticoagulants; Case-Control Studies; Factor Xa Inhibitors; Female; Heparin, Low-Molecular-Weight; Humans; Nadroparin; Partial Thromboplastin Time; Peptide Fragments; Pilot Projects; Pregnancy; Pregnancy Complications, Hematologic; Prothrombin; Thrombophilia; Thrombosis

An Update on the Pathogenesis and Treatment of Chronic Recurrent Multifocal Osteomyelitis in Children. - Taddio, Andrea; Zennaro, Floriana; Pastore, Serena; Cimaz, Rolando (Paediatr Drugs, 2017)
Chronic recurrent multifocal osteomyelitis (CRMO), also known as chronic non-bacterial osteomyelitis (CNO), is a rare inflammatory disorder that primarily affects children. It is characterized by pain, local bone expansion, and radiological findings suggestive of osteomyelitis, usually at multiple sites. CRMO predominantly affects the metaphyses of long bones, but involvement of the clavicle or mandible are suggestive of the diagnosis. CRMO is a diagnosis of exclusion, and its pathogenesis remains unknown. Differential diagnosis includes infection, malignancies, benign bone tumors, metabolic disorders, and other autoinflammatory disorders. Biopsy of the bone lesion is not often required but could be necessary in unclear cases, especially for differentiation from bone neoplasia. Non-steroidal anti-inflammatory drugs (NSAIDs) are the first-line treatment. Alternative therapies have been used, including corticosteroids, methotrexate, bisphosphonates, and tumor necrosis factor (TNF)-α inhibitors. No guidelines have been established regarding diagnosis and treatment options. This manuscript gives an overview of the most recent findings on the pathogenesis of CRMO and clinical approaches for patients with the condition.
Keywords: Adrenal Cortex Hormones; Anti-Inflammatory Agents, Non-Steroidal; Child; Chronic Disease; Diagnosis, Differential; Humans; Osteomyelitis; Recurrence; Tumor Necrosis Factor-alpha

Whole-body MRI reveals high incidence of osteonecrosis in children treated for Hodgkin lymphoma. - Littooij, Annemieke S; Kwee, Thomas C; Enríquez, Goya; Verbeke, Jonathan I M L; Granata, Claudio; Beishuizen, Auke; de Lange, Charlotte; Zennaro, Floriana; Bruin, Marrie C A; Nievelstein, Rutger A J (Br J Haematol, 2017)
Osteonecrosis is a well-recognized complication in patients treated with corticosteroids. The incidence of osteonecrosis in children treated for Hodgkin lymphoma is unknown because prospective whole-body magnetic resonance imaging (MRI) studies are lacking in this patient population. Paediatric patients with newly diagnosed Hodgkin lymphoma who were treated according to a uniform paediatric Hodgkin protocol were eligible for inclusion in this prospective study. Whole-body MRI was performed in all 24 included patients (mean age 15·1 years, 12 girls) both before treatment and after 2 cycles of chemotherapy, and in 16 patients after completion of chemotherapy. Osteonecrosis was identified in 10 patients (41·7%, 95% confidence interval: 22·0-61·4%), with a total of 56 osteonecrotic sites. Osteonecrosis was detected in 8 patients after 2 cycles of OEPA (vincristine, etoposide, prednisone, doxorubicin), and in 2 additional patients after completion of chemotherapy. Epiphyseal involvement of long bones was seen in 4 of 10 children. None of the patients with osteonecrosis had any signs of bone collapse at the times of scanning. Whole-body MRI demonstrates osteonecrosis to be a common finding occurring during therapy response assessment of paediatric Hodgkin lymphoma. Detection of early epiphyseal osteonecrosis could allow for treatment before bone collapse and joint damage may occur.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Doxorubicin; Epiphyses; Etoposide; Female; Hodgkin Disease; Humans; Incidence; Magnetic Resonance Imaging; Male; Osteonecrosis; Prednisone; Prospective Studies; Vincristine

Whole-Genome Sequencing Coupled to Imputation Discovers Genetic Signals for Anthropometric Traits. - Tachmazidou, Ioanna; Süveges, Dániel; Min, Josine L; Ritchie, Graham R S; Steinberg, Julia; Walter, Klaudia; Iotchkova, Valentina; Schwartzentruber, Jeremy; Huang, Jie; Memari, Yasin; McCarthy, Shane; Crawford, Andrew A; et al. (Am J Hum Genet, 2017)
Deep sequence-based imputation can enhance the discovery power of genome-wide association studies by assessing previously unexplored variation across the common- and low-frequency spectra. We applied a hybrid whole-genome sequencing (WGS) and deep imputation approach to examine the broader allelic architecture of 12 anthropometric traits associated with height, body mass, and fat distribution in up to 267,616 individuals. We report 106 genome-wide significant signals that have not been previously identified, including 9 low-frequency variants pointing to functional candidates. Of the 106 signals, 6 are in genomic regions that have not been implicated with related traits before, 28 are independent signals at previously reported regions, and 72 represent previously reported signals for a different anthropometric trait. 71% of signals reside within genes and fine mapping resolves 23 signals to one or two likely causal variants. We confirm genetic overlap between human monogenic and polygenic anthropometric traits and find signal enrichment in cis expression QTLs in relevant tissues. Our results highlight the potential of WGS strategies to enhance biologically relevant discoveries across the frequency spectrum.
Keywords: Anthropometry; Body Height; Cohort Studies; Databases, Genetic; DNA Methylation; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Lipodystrophy; Male; Meta-Analysis as Topic; Obesity; Physical Chromosome Mapping; Quantitative Trait Loci; Sequence Analysis, DNA; Sex Characteristics; Syndrome; United Kingdom

Withdrawal Assessment Tool-1 Monitoring in PICU: A Multicenter Study on Iatrogenic Withdrawal Syndrome. - Amigoni, Angela; Mondardini, Maria Cristina; Vittadello, Ilaria; Zaglia, Federico; Rossetti, Emanuele; Vitale, Francesca; Ferrario, Stefania; Savron, Fabio; Coffaro, Giancarlo; Brugnaro, Luca; Amato, Roberta; Wolfler, Andrea; et al. (Pediatr Crit Care Med, 2017)
OBJECTIVES: Withdrawal syndrome is an adverse reaction of analgesic and sedative therapy, with a reported occurrence rate between 17% and 57% in critically ill children. Although some factors related to the development of withdrawal syndrome have been identified, there is weak evidence for the effectiveness of preventive and therapeutic strategies. The main aim of this study was to evaluate the frequency of withdrawal syndrome in Italian PICUs, using a validated instrument. We also analyzed differences in patient characteristics, analgesic and sedative treatment, and patients' outcome between patients with and without withdrawal syndrome. DESIGN: Observational multicenter prospective study. SETTING: Eight Italian PICUs belonging to the national PICU network Italian PICU network. PATIENTS: One hundred thirteen patients, less than 18 years old, mechanically ventilated and treated with analgesic and sedative therapy for five or more days. They were admitted in PICU from November 2012 to May 2014. INTERVENTIONS: Symptoms of withdrawal syndrome were monitored with Withdrawal Assessment Tool-1 scale. MEASUREMENTS AND MAIN RESULTS: The occurrence rate of withdrawal syndrome was 64.6%. The following variables were significantly different between the patients who developed withdrawal syndrome and those who did not: type, duration, and cumulative dose of analgesic therapy; duration and cumulative dose of sedative therapy; clinical team judgment about analgesia and sedation's difficulty; and duration of analgesic weaning, mechanical ventilation, and PICU stay. Multivariate logistic regression analysis revealed that patients receiving morphine as their primary analgesic were 83% less likely to develop withdrawal syndrome than those receiving fentanyl or remifentanil. CONCLUSIONS: Withdrawal syndrome was frequent in PICU patients, and patients with withdrawal syndrome had prolonged hospital treatment. We suggest adopting the lowest effective dose of analgesic and sedative drugs and frequent reevaluation of the need for continued use. Further studies are necessary to define common preventive and therapeutic strategies.
Keywords: Adolescent; Analgesics; Child; Child, Preschool; Critical Care; Female; Humans; Hypnotics and Sedatives; Iatrogenic Disease; Infant; Infant, Newborn; Intensive Care Units, Pediatric; Italy; Logistic Models; Male; Prospective Studies; Respiration, Artificial; Substance Withdrawal Syndrome

Acute lobar nephritis in children: Not so easy to recognize and manage. - Bibalo, Cristina; Apicella, Andrea; Guastalla, Veronica; Marzuillo, Pierluigi; Zennaro, Floriana; Tringali, Carmela; Taddio, Andrea; Germani, Claudio; Barbi, Egidio (World J Clin Pediatr, 2016)
Acute lobar nephritis (ALN) is a localized non-liquefactive inflammatory renal bacterial infection, which typically involves one or more lobes. ALN is considered to be a midpoint in the spectrum of upper urinary tract infection, a spectrum ranging from uncomplicated pyelonephritis to intrarenal abscess. This condition may be difficult to recognize due to the lack of specific symptoms and laboratory findings. Therefore the disease is probably underdiagnosed. Computed tomography scanning represents the diagnostic gold standard for ALN, but magnetic resonance imagine could be considered in order to limit irradiation. The diagnosis is relevant since initial intravenous antibiotic therapy and overall length of treatment should not be shorter than 3 wk. We review the literature and analyze the ALN clinical presentation starting from four cases with the aim to give to the clinicians the elements to suspect and recognize the ALN in children.

C1q acts in the tumour microenvironment as a cancer-promoting factor independently of complement activation. - Bulla, Roberta; Tripodo, Claudio; Rami, Damiano; Ling, Guang Sheng; Agostinis, Chiara; Guarnotta, Carla; Zorzet, Sonia; Durigutto, Paolo; Botto, Marina; Tedesco, Francesco (Nat Commun, 2016)
Complement C1q is the activator of the classical pathway. However, it is now recognized that C1q can exert functions unrelated to complement activation. Here we show that C1q, but not C4, is expressed in the stroma and vascular endothelium of several human malignant tumours. Compared with wild-type (WT) or C3- or C5-deficient mice, C1q-deficient (C1qa(-/-)) mice bearing a syngeneic B16 melanoma exhibit a slower tumour growth and prolonged survival. This effect is not attributable to differences in the tumour-infiltrating immune cells. Tumours developing in WT mice display early deposition of C1q, higher vascular density and an increase in the number of lung metastases compared with C1qa(-/-) mice. Bone marrow (BM) chimeras between C1qa(-/-) and WT mice identify non-BM-derived cells as the main local source of C1q that can promote cancer cell adhesion, migration and proliferation. Together these findings support a role for locally synthesized C1q in promoting tumour growth.
Keywords: Animals; Apoptosis; Cell Line, Tumor; Cell Movement; Cell Proliferation; Complement Activation; Complement C1q; Complement C3; Complement C5; Humans; Mice; Mice, Inbred C57BL; Mice, Knockout; Neoplasms

Candidate Soluble Immune Mediators in Young Women with High-Risk Human Papillomavirus Infection: High Expression of Chemokines Promoting Angiogenesis and Cell Proliferation. - Zanotta, Nunzia; Tornesello, Maria Lina; Annunziata, Clorinda; Stellato, Giovanni; Buonaguro, Franco Maria; Comar, Manola (PLoS One, 2016)
BACKGROUND: The causal interpretation of cervical immune response to Human Papillomavirus (HPV) infection is complex and poorly characterized mainly due to the delicate balance that exists between viral infection, increase of inflammatory cytokines and host risk factors. This study aims to explore the significance of cervical immune mediators associated to cell survival, angiogenesis and interaction with immune response, in predicting the risk to develop HPV-related intraepithelial lesions. METHODS: A panel of 48 cytokines and growth factors were explored in a selected cohort of 168 immunocompetent women including 88 diagnosed with low (LSIL) or high (HSIL) squamous intraepithelial lesions of the cervix and 80 with normal cervical cytology (NIL). HPV genotyping was performed by Linear Array HPV test and the soluble concentration of 48 immune molecules was analyzed using the Bio-Plex platform. RESULTS: The prevalence of single HR-HPV infection was 30% in NIL and 100% in LSIL and HSIL women. The expression of 13 cytokines, including interleukins IL-6, IL-3, IL-12p40, IL-12p70, IL-16, IL-18, LIF, of chemokines CCL7 (MCP-3), CXCL9 (MIG), CXCL12 (SDF-1α) and of the tropic factors VEGF, G-CSF, M-CSF were significantly associated with the presence of infection, with levels being higher in women with precancerous lesions compared to NIL HPV negative women. Only the growth factor GM-CSF was positively associated with the cytological abnormalities. CONCLUSIONS: The ability of HR-HPV to escape from innate immune recognition and to orchestrate the production of specific inflammatory and growth factors, involved in early inflammatory response and in the cell-proliferating phase of intraepithelial damage, was documented in women before the development of cervical lesions.
Keywords: Adult; Cell Survival; Cervix Uteri; Chemokines; Cohort Studies; Female; Humans; Neovascularization, Pathologic; Papillomaviridae; Papillomavirus Infections

A Case of Prenatal Neurocytoma Associated With ATR-16 Syndrome. - Quadrifoglio, Mariachiara; Faletra, Flavio; Bussani, Rossana; Pecile, Vanna; Zennaro, Floriana; Grasso, Alessandra; Zandonà, Lorenzo; Alberico, Salvatore; Stampalija, Tamara (J Ultrasound Med, 2016)

CD209 promoter polymorphisms associate with HCV infection and pegylated-interferon plus ribavirin treatment response. - Zupin, Luisa; Polesello, Vania; Alberi, Giulia; Moratelli, Giulia; Crocè, Saveria Lory; Masutti, Flora; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Mol Immunol, 2016)
Hepatitis C is a severe liver disease caused by hepatitis C virus that could persist in the host causing progression towards chronic disease in about 80% of the cases. Pegylated-interferon plus ribavirin was the gold standard therapy, however treatment's response was quite variable among individuals and different host/viral factors may play a role in disease outcome. The cluster of differentiation 209 (CD209 antigen) is a component of the innate immune system able to recognize HCV and consequently activating the immune response. We enrolled 203 Italian HCV infected patients and 220 healthy controls investigating if five promoter polymorphisms within CD209 gene (encoding for CD209 antigen) correlated with HCV infection susceptibility, spontaneous viral clearance and interferon treatment response. CD209 -939G>A and -871A>G polymorphisms associated with HCV infection susceptibility, while, CD209 -871A>G and -336A>G polymorphisms associated with response to treatment. In conclusion, CD209 polymorphisms could play a role in the susceptibility to HCV infection as well as interferon treatment response in our study population from North-East of Italy.

Chemokines involved in the early inflammatory response and in pro-tumoral activity in asbestos-exposed workers from an Italian coastal area with territorial clusters of pleural malignant mesothelioma. - Comar, M; Zanotta, N; Zanconati, F; Cortale, M; Bonotti, A; Cristaudo, A; Bovenzi, M (Lung Cancer, 2016)
OBJECTIVES: Immune mediators are likely to be relevant for the biological response to asbestos exposure. The aim of this study was to investigate the association between immune mediators involved in inflammation, cell survival and angiogenesis, and asbestos-related diseases in workers from a coastal area of North-East Italy with a high incidence of pleural malignant mesothelioma (PMM). MATERIALS AND METHODS: A selected custom set of 12 soluble mediators was evaluated with a Luminex platform in sera, pleural fluid and mesothelioma biopsies from 123 asbestos-exposed workers (38 free from pleural-pulmonary disorders, 46 with non-malignant asbestos diseases, 39 with PMM) and in sera from 33 healthy controls from the same territorial area. RESULTS: Increased immune mediator concentrations were observed in the sera of the asbestos-exposed workers compared to controls for human fibroblast growth factor (FGF-b), vascular endothelial growth factor (VEGF), CCL5 (RANTES), CXCL10 (IP-10), CLEC11A (SCGF-b), CCL27 (CTACK), CCL11 (EOTAXIN), IL-5 and IL-6 (p<0.001). The chemokines IP-10 and RANTES were associated with the severity of asbestos-related diseases. In the workers with PMM, the immune proteins secreted by mesothelioma biopsies showed detectable levels of RANTES, VEGF, and IP-10. In the same workers with PMM, a significant relationship between serum and pleural fluid concentrations was found for RANTES alone. CONCLUSIONS: Occupational exposure to asbestos seems to drive the production of specific growth factors dually involved in the early inflammatory response and in pro-tumoral activity before clinical evidence of related disorders, suggesting that their over-expression may precede the onset of asbestos-related diseases. These findings suggest that some chemokines may have a prognostic role in the progression of asbestos-related diseases and could be used for the health surveillance of either workers with an occupational history of asbestos exposure or patients affected by non-malignant asbestos-related diseases.

Circulating levels of TNF-related apoptosis inducing-ligand are decreased in patients with large adult-type granulosa cell tumors-implications for therapeutic potential. - Färkkilä, Anniina; Zauli, Giorgio; Haltia, Ulla-Maija; Pihlajoki, Marjut; Unkila-Kallio, Leila; Secchiero, Paola; Heikinheimo, Markku (Tumour Biol, 2016)
Targeted treatments are needed for advanced adult-type granulosa cell tumors (AGCTs). We set out to assess tumor tissue and circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a promising anti-cancer cytokine, in patients affected by AGCT. We analyzed tissue expression of TRAIL in 127 AGCTs using immunohistochemistry or RT-PCR. Soluble TRAIL was measured by means of ELISA from 141 AGCT patient serum samples, as well as the conditioned media of 15 AGCT patient-derived primary cell cultures, and the KGN cell line. Tissue and serum TRAIL levels were analyzed in relationship with clinical parameters, and serum estradiol, FSH, and LH levels. We found that AGCT samples expressed TRAIL mRNA and protein at levels comparable to normal granulosa cells. AGCT cells did not release soluble TRAIL. TRAIL protein levels were decreased in tumors over 10 cm in diameter (p = 0.04). Consistently, circulating TRAIL levels correlated negatively to tumor dimension (p = 0.01). Circulating TRAIL levels negatively associated with serum estradiol levels. In multiple regression analysis, tumor size was an independent factor contributing to the decreased levels of soluble TRAIL in AGCT patients. AGCTs associate with significantly decreased tumor tissue and serum TRAIL levels in patients with a large tumor mass. These findings encourage further study of agonistic TRAIL treatments in patients with advanced or recurrent AGCT.

CNV analysis in 169 patients with bladder exstrophy-epispadias complex. - von Lowtzow, Catharina; Hofmann, Andrea; Zhang, Rong; Marsch, Florian; Ebert, Anne-Karoline; Rösch, Wolfgang; Stein, Raimund; Boemers, Thomas M; Hirsch, Karin; Marcelis, Carlo; Feitz, Wouter F J; Brusco, Alfredo; et al. (BMC Med Genet, 2016)
BACKGROUND: The bladder exstrophy-epispadias complex (BEEC) represents the severe end of the congenital uro-rectal malformation spectrum. Initial studies have implicated rare copy number variations (CNVs), including recurrent duplications of chromosomal region 22q11.21, in BEEC etiology. METHODS: To detect further CNVs, array analysis was performed in 169 BEEC patients. Prior to inclusion, 22q11.21 duplications were excluded using multiplex ligation-dependent probe amplification. RESULTS: Following the application of stringent filter criteria, seven rare CNVs were identified: n = 4, not present in 1307 in-house controls; n = 3, frequency of <0.002 in controls. These CNVs ranged from 1 to 6.08 Mb in size. To identify smaller CNVs, relaxed filter criteria used in the detection of previously reported BEEC associated chromosomal regions were applied. This resulted in the identification of six additional rare CNVs: n = 4, not present in 1307 in-house controls; n = 2, frequency <0.0008 in controls. These CNVs ranged from 0.03-0.08 Mb in size. For 10 of these 13 CNVs, confirmation and segregation analyses were performed (5 of maternal origin; 5 of paternal origin). Interestingly, one female with classic bladder extrophy carried a 1.18 Mb duplication of 22q11.1, a chromosomal region that is associated with cat eye syndrome. CONCLUSIONS: A number of rare CNVs were identified in BEEC patients, and these represent candidates for further evaluation. Rare inherited CNVs may constitute modifiers of, or contributors to, multifactorial BEEC phenotypes.

Cross-sectional study of coeliac autoimmunity in a population of Vietnamese children. - Zanella, Sara; De Leo, Luigina; Nguyen-Ngoc-Quynh, Le; Nguyen-Duy, Bo; Not, Tarcisio; Tran-Thi-Chi, Mai; Phung-Duc, Son; Le-Thanh, Hai; Malaventura, Cristina; Vatta, Serena; Ziberna, Fabiana; Mazzocco, Martina; et al. (BMJ Open, 2016)
OBJECTIVE: The prevalence of coeliac disease (CD) in Vietnam is unknown. To fill this void, we assessed the prevalence of serological markers of CD autoimmunity in a population of children in Hanoi. SETTING: The outpatient blood drawing laboratory of the largest paediatric hospital in North Vietnam was used for the study, which was part of an international project of collaboration between Italy and Vietnam. PARTICIPANTS: Children having blood drawn for any reason were included. Exclusion criteria were age younger than 2 years, acquired or congenital immune deficiency and inadequate sample. A total of 1961 children (96%) were enrolled (838 females, 1123 males, median age 5.3 years). OUTCOMES: Primary outcome was the prevalence of positive autoimmunity to both IgA antitransglutaminase antibodies (anti-tTG) assessed with an ELISA test and antiendomysial antibodies (EMA). Secondary outcome was the prevalence of CD predisposing human leucocyte antigens (HLA) (HLA DQ2/8) in the positive children and in a random group of samples negative for IgA anti-tTG. RESULTS: The IgA anti-tTG test was positive in 21/1961 (1%; 95% CI 0.61% to 1.53%); however, EMA antibodies were negative in all. HLA DQ2/8 was present in 7/21 (33%; 95% CI 14.5% to 56.9%) of the anti-tTG-positive children and in 72/275 (26%; 95% CI 21% to 32%) of those who were negative. CONCLUSIONS: Coeliac autoimmunity is rare in Vietnam, although prevalence of HLA DQ2/8 is similar to that of other countries. We hypothesise that the scarce exposure to gluten could be responsible for these findings.

DEFB1 polymorphisms and susceptibility to recurrent tonsillitis in Italian children. - Zupin, Luisa; Polesello, Vania; Grasso, Domenico Leonardo; Crovella, Sergio; Segat, Ludovica (Int J Pediatr Otorhinolaryngol, 2016)
INTRODUCTION: The tonsils are secondary lymphoid organs fundamental for immune system response against pathogens within the oral cavity. Tonsillitis refers to inflammation of the pharyngeal tonsils that may include the adenoids and the lingual tonsils and that can be acute, recurrent, and chronic. Viral or bacterial infections, as well as immunologic factors are the main trigger to tonsillitis and disease's chronicity: the host immune responses, especially the innate one, could play an important role in susceptibility to the disease. OBJECTIVES: The current study aims at investigating the role of functional polymorphisms in the 5'UTR (c.-52G>A, c.-44G>C and c.-20G>A) of DEFB1 gene, encoding for the antimicrobial peptide human beta-defensin 1, in the predisposition to recurrent tonsillitis in children from North Eastern Italy. RESULTS: No significant correlation was found between DEFB1 allele, genotype and haplotype frequencies and recurrent tonsillitis susceptibility with the exception of an increased risk to disease development in patients carrying DEFB1 rare haplotypes. CONCLUSION: Our results may suggest that DEFB1 polymorphisms alone may not influence pathology susceptibility, however they could possibly concur, together with other factors involved in the genetic control of innate immune system, in the predisposition towards recurrent tonsillitis.

Detection of Malawi polyomavirus sequences in secondary lymphoid tissues from Italian healthy children: a transient site of infection. - Papa, N; Zanotta, N; Knowles, A; Orzan, E; Comar, M (Virol J, 2016)
BACKGROUND: The novel Malawi polyomavirus (MWPyV) was initially detected in stool specimens from healthy children and children with gastrointestinal symptoms, mostly diarrhea, indicating that MWPyV might play a role in human gastroenteric diseases. Recently, MWPyV sequences were additionally identified in respiratory secretions from both healthy and acutely ill children suggesting that MWPyV may have a tropism for different human tissues. This study was designed to investigate the possible sites of latency/persistence for MWPyV in a cohort of healthy Italian children. METHODS: Specimens (n° 500) of tonsils, adenoids, blood, urines and feces, from 200 healthy and immunocompetent children (age range: 1-15 years) were tested for the amplification of the MWPyV LT antigen sequence by quantitative real-time PCR. Samples (n° 80) of blood and urines from 40 age-matched children with autoimmune diseases, were screened for comparison. Polyomaviruses JC/BK and Epstein-Barr Virus (EBV) were also tested as markers of infection in all samples using the same molecular technique. RESULTS: In our series of healthy children, MWPyV was detected only in the lymphoid tissues showing a prevalence of 6 % in tonsils and 1 % in adenoids, although with a low viral load. No JCPyV or BKPyV co-infection was found in MWPyV positive samples, while EBV showed a similar percentage of both in tonsils and adenoids (38 and 37 %). Conversely, no MWPyV DNA was detected in stool from babies with gastroenteric syndrome. With regards to autoimmune children, neither MWPyV nor BKPyV were detected in blood, while JCPyV viremia was observed in 15 % (6/40) of children treated with Infliximab. Urinary BKPyV shedding was observed in 12.5 % (5/40) while JCPyV in 100 % of the samples. CONCLUSIONS: The detection of MWPyV sequences in tonsils and adenoids of healthy children suggests that secondary lymphoid tissues can harbour MWPyV probably as transient sites of persistence rather than actual sites of latency.

EPG5-related Vici syndrome: a paradigm of neurodevelopmental disorders with defective autophagy. - Byrne, Susan; Jansen, Lara; U-King-Im, Jean-Marie; Siddiqui, Ata; Lidov, Hart G W; Bodi, Istvan; Smith, Luke; Mein, Rachael; Cullup, Thomas; Dionisi-Vici, Carlo; Al-Gazali, Lihadh; Al-Owain, Mohammed; et al. (Brain, 2016)
Vici syndrome is a progressive neurodevelopmental multisystem disorder due to recessive mutations in the key autophagy gene EPG5. We report genetic, clinical, neuroradiological, and neuropathological features of 50 children from 30 families, as well as the neuronal phenotype of EPG5 knock-down in Drosophila melanogaster. We identified 39 different EPG5 mutations, most of them truncating and predicted to result in reduced EPG5 protein. Most mutations were private, but three recurrent mutations (p.Met2242Cysfs*5, p.Arg417*, and p.Gln336Arg) indicated possible founder effects. Presentation was mainly neonatal, with marked hypotonia and feeding difficulties. In addition to the five principal features (callosal agenesis, cataracts, hypopigmentation, cardiomyopathy, and immune dysfunction), we identified three equally consistent features (profound developmental delay, progressive microcephaly, and failure to thrive). The manifestation of all eight of these features has a specificity of 97%, and a sensitivity of 89% for the presence of an EPG5 mutation and will allow informed decisions about genetic testing. Clinical progression was relentless and many children died in infancy. Survival analysis demonstrated a median survival time of 24 months (95% confidence interval 0-49 months), with only a 10th of patients surviving to 5 years of age. Survival outcomes were significantly better in patients with compound heterozygous mutations (P = 0.046), as well as in patients with the recurrent p.Gln336Arg mutation. Acquired microcephaly and regression of skills in long-term survivors suggests a neurodegenerative component superimposed on the principal neurodevelopmental defect. Two-thirds of patients had a severe seizure disorder, placing EPG5 within the rapidly expanding group of genes associated with early-onset epileptic encephalopathies. Consistent neuroradiological features comprised structural abnormalities, in particular callosal agenesis and pontine hypoplasia, delayed myelination and, less frequently, thalamic signal intensity changes evolving over time. Typical muscle biopsy features included fibre size variability, central/internal nuclei, abnormal glycogen storage, presence of autophagic vacuoles and secondary mitochondrial abnormalities. Nerve biopsy performed in one case revealed subtotal absence of myelinated axons. Post-mortem examinations in three patients confirmed neurodevelopmental and neurodegenerative features and multisystem involvement. Finally, downregulation of epg5 (CG14299) in Drosophila resulted in autophagic abnormalities and progressive neurodegeneration. We conclude that EPG5-related Vici syndrome defines a novel group of neurodevelopmental disorders that should be considered in patients with suggestive features in whom mitochondrial, glycogen, or lysosomal storage disorders have been excluded. Neurological progression over time indicates an intriguing link between neurodevelopment and neurodegeneration, also supported by neurodegenerative features in epg5-deficient Drosophila, and recent implication of other autophagy regulators in late-onset neurodegenerative disease.
Keywords: Agenesis of Corpus Callosum; Animals; Autophagy; Cataract; Child, Preschool; Cross-Sectional Studies; Drosophila melanogaster; Female; Hippocampus; Humans; Male; Mutation; Neurodevelopmental Disorders; Proteins; Retrospective Studies

Evidence for three genetic loci involved in both anorexia nervosa risk and variation of body mass index. - Hinney, A; Kesselmeier, M; Jall, S; Volckmar, A-L; Föcker, M; Antel, J; Heid, I M; Winkler, T W; Grant, S F A; Guo, Y; Bergen, A W; Kaye, W; et al. (Mol Psychiatry, 2016)
The maintenance of normal body weight is disrupted in patients with anorexia nervosa (AN) for prolonged periods of time. Prior to the onset of AN, premorbid body mass index (BMI) spans the entire range from underweight to obese. After recovery, patients have reduced rates of overweight and obesity. As such, loci involved in body weight regulation may also be relevant for AN and vice versa. Our primary analysis comprised a cross-trait analysis of the 1000 single-nucleotide polymorphisms (SNPs) with the lowest P-values in a genome-wide association meta-analysis (GWAMA) of AN (GCAN) for evidence of association in the largest published GWAMA for BMI (GIANT). Subsequently we performed sex-stratified analyses for these 1000 SNPs. Functional ex vivo studies on four genes ensued. Lastly, a look-up of GWAMA-derived BMI-related loci was performed in the AN GWAMA. We detected significant associations (P-values <5 × 10(-5), Bonferroni-corrected P<0.05) for nine SNP alleles at three independent loci. Interestingly, all AN susceptibility alleles were consistently associated with increased BMI. None of the genes (chr. 10: CTBP2, chr. 19: CCNE1, chr. 2: CARF and NBEAL1; the latter is a region with high linkage disequilibrium) nearest to these SNPs has previously been associated with AN or obesity. Sex-stratified analyses revealed that the strongest BMI signal originated predominantly from females (chr. 10 rs1561589; Poverall: 2.47 × 10(-06)/Pfemales: 3.45 × 10(-07)/Pmales: 0.043). Functional ex vivo studies in mice revealed reduced hypothalamic expression of Ctbp2 and Nbeal1 after fasting. Hypothalamic expression of Ctbp2 was increased in diet-induced obese (DIO) mice as compared with age-matched lean controls. We observed no evidence for associations for the look-up of BMI-related loci in the AN GWAMA. A cross-trait analysis of AN and BMI loci revealed variants at three chromosomal loci with potential joint impact. The chromosome 10 locus is particularly promising given that the association with obesity was primarily driven by females. In addition, the detected altered hypothalamic expression patterns of Ctbp2 and Nbeal1 as a result of fasting and DIO implicate these genes in weight regulation.Molecular Psychiatry advance online publication, 17 May 2016; doi:10.1038/mp.2016.71.

Genetic associations at 53 loci highlight cell types and biological pathways relevant for kidney function. - Pattaro, Cristian; Teumer, Alexander; Gorski, Mathias; Chu, Audrey Y; Li, Man; Mijatovic, Vladan; Garnaas, Maija; Tin, Adrienne; Sorice, Rossella; Li, Yong; Taliun, Daniel; Olden, Matthias; et al. (Nat Commun, 2016)
Reduced glomerular filtration rate defines chronic kidney disease and is associated with cardiovascular and all-cause mortality. We conducted a meta-analysis of genome-wide association studies for estimated glomerular filtration rate (eGFR), combining data across 133,413 individuals with replication in up to 42,166 individuals. We identify 24 new and confirm 29 previously identified loci. Of these 53 loci, 19 associate with eGFR among individuals with diabetes. Using bioinformatics, we show that identified genes at eGFR loci are enriched for expression in kidney tissues and in pathways relevant for kidney development and transmembrane transporter activity, kidney structure, and regulation of glucose metabolism. Chromatin state mapping and DNase I hypersensitivity analyses across adult tissues demonstrate preferential mapping of associated variants to regulatory regions in kidney but not extra-renal tissues. These findings suggest that genetic determinants of eGFR are mediated largely through direct effects within the kidney and highlight important cell types and biological pathways.
Keywords: Gene Expression Regulation; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Renal Insufficiency, Chronic

Genome-wide association study identifies 74 loci associated with educational attainment. - Okbay, Aysu; Beauchamp, Jonathan P; Fontana, Mark Alan; Lee, James J; Pers, Tune H; Rietveld, Cornelius A; Turley, Patrick; Chen, Guo-Bo; Emilsson, Valur; Meddens, S Fleur W; Oskarsson, Sven; Pickrell, Joseph K; et al. (Nature, 2016)
Educational attainment is strongly influenced by social and other environmental factors, but genetic factors are estimated to account for at least 20% of the variation across individuals. Here we report the results of a genome-wide association study (GWAS) for educational attainment that extends our earlier discovery sample of 101,069 individuals to 293,723 individuals, and a replication study in an independent sample of 111,349 individuals from the UK Biobank. We identify 74 genome-wide significant loci associated with the number of years of schooling completed. Single-nucleotide polymorphisms associated with educational attainment are disproportionately found in genomic regions regulating gene expression in the fetal brain. Candidate genes are preferentially expressed in neural tissue, especially during the prenatal period, and enriched for biological pathways involved in neural development. Our findings demonstrate that, even for a behavioural phenotype that is mostly environmentally determined, a well-powered GWAS identifies replicable associated genetic variants that suggest biologically relevant pathways. Because educational attainment is measured in large numbers of individuals, it will continue to be useful as a proxy phenotype in efforts to characterize the genetic influences of related phenotypes, including cognition and neuropsychiatric diseases.
Keywords: Alzheimer Disease; Bipolar Disorder; Brain; Cognition; Computational Biology; Educational Status; Fetus; Gene Expression Regulation; Gene-Environment Interaction; Genome-Wide Association Study; Great Britain; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Schizophrenia

Geranylgeraniol and Neurological Impairment: Involvement of Apoptosis and Mitochondrial Morphology. - Marcuzzi, Annalisa; Piscianz, Elisa; Zweyer, Marina; Bortul, Roberta; Loganes, Claudia; Girardelli, Martina; Baj, Gabriele; Monasta, Lorenzo; Celeghini, Claudio (Int J Mol Sci, 2016)
Deregulation of the cholesterol pathway is an anomaly observed in human diseases, many of which have in common neurological involvement and unknown pathogenesis. In this study we have used Mevalonate Kinase Deficiency (MKD) as a disease-model in order to investigate the link between the deregulation of the mevalonate pathway and the consequent neurodegeneration. The blocking of the mevalonate pathway in a neuronal cell line (Daoy), using statins or mevalonate, induced an increase in the expression of the inflammasome gene (NLRP3) and programmed cell death related to mitochondrial dysfunction. The morphology of the mitochondria changed, clearly showing the damage induced by oxidative stress and the decreased membrane potential associated with the alterations of the mitochondrial function. The co-administration of geranylgeraniol (GGOH) reduced the inflammatory marker and the damage of the mitochondria, maintaining its shape and components. Our data allow us to speculate about the mechanism by which isoprenoids are able to rescue the inflammatory marker in neuronal cells, independently from the block of the mevalonate pathway, and about the fact that cell death is mitochondria-related.

Hepatic Gadolinium Deposition and Reversibility after Contrast Agent-enhanced MR Imaging of Pediatric Hematopoietic Stem Cell Transplant Recipients. - Maximova, Natalia; Gregori, Massimo; Zennaro, Floriana; Sonzogni, Aurelio; Simeone, Roberto; Zanon, Davide (Radiology, 2016)
Purpose To determine if hepatic gadolinium deposition occurs in pediatric patients with iron overload but normal renal and hepatic function who undergo gadolinium-based contrast agent (GBCA)-enhanced magnetic resonance (MR) imaging. Materials and Methods Design and execution of this study was approved by the Ethical Committee of Institute for Research in Maternal and Child Health Burlo Garofolo of Trieste (reference no. 1105/2015). Because of the retrospective nature of the study, the requirement to obtain informed consent was waived. Twenty-one recipients of allogeneic hematopoietic stem cell transplants who underwent GBCA-enhanced MR imaging for suspected infection or relapse followed by liver biopsy comprised the study group. The number of GBCA-enhanced MR examinations and cumulative gadolinium dose for each patient was analyzed by comparing liver histologic analysis and iron and gadolinium liver concentration (GLC). Eight patients had siderosis and underwent chelation therapy. The study group was compared with four control patients who were never exposed to GBCA. Statistical analysis was performed with Spearman rank coefficient for correlation. Results All 21 patients had positive correlations between GLC and total GBCA dose (r = 0.4486; P < .05) and between GLC and liver iron concentration (r = 0.56; P < .05). Patients who underwent deferoxamine therapy had a significant reduction of GLC (from 0.64 μg/g ± 0.29 to 0.20 μg/g ± 0.17 [standard deviation]; P < .05). Conclusion In the presence of siderosis, a transmetallation mechanism may be set off between ferric ion and gadoterate meglumine. Deferoxamine appears capable of binding to gadolinium ion. Further studies of the safety of GBCAs in severe siderosis are needed. Chelation should be considered in patients with iron overload and a history of GBCA exposure. (©) RSNA, 2016.

Histopathological data of iron and calcium in the mouse lung after asbestos exposure. - Trevisan, Elisa; Zabucchi, Giuliano; Pascolo, Lorella; Pascotto, Ernesto; Casarsa, Claudia; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; Zweyer, Marina; Borelli, Violetta (Data Brief, 2016)
This data article contains data related to the research article entitled, "Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice" [1]. Asbestos fibers disrupt iron homeostasis in the human and mouse lung, leading to the deposition of iron (Fe) onto longer asbestos fibers which forms asbestos bodies (AB) [2]. Similar to Fe, calcium (Ca) is also deposited in the coats of the AB. This article presents data on iron and calcium in the mouse lung after asbestos exposure detected by histochemical evaluation.

The incidence rate and prevalence of pediatric type 1 diabetes mellitus (age 0-18) in the Italian region Friuli Venezia Giulia: population-based estimates through the analysis of health administrative databases. - Valent, Francesca; Candido, Riccardo; Faleschini, Elena; Tonutti, Laura; Tortul, Carla; Zanatta, Manuela; Zanette, Giorgio; Zanier, Loris (Acta Diabetol, 2016)
AIMS: The main objective of this study was to estimate the incidence rate and prevalence of pediatric type 1 diabetes mellitus (T1DM; population 0-18 years of age) in the northeastern Italian region Friuli Venezia Giulia and to characterize the subjects affected by the disease. METHODS: This was a retrospective population-based study conducted through the individual-level linkage of several health administrative databases of the Friuli Venezia Giulia region. The incidence rate and prevalence were calculated in the population 0-18 years of age. Using the Mid-p exact method, 95 % confidence intervals for rates were calculated. RESULTS: The incidence rate of pediatric T1DM in the years 2010-2013 was 15.8 new cases/100,000 person-years, peaking in the age class 10-14 years. The rate has increased substantially as compared with the previous regional estimate that dated back to 1993. We observed a seasonal pattern both in the date of birth of the incident cases and in the date of onset of the disease. In the region in 2013, there were 294 prevalent cases (15.1/10,000 inhabitants). Most of them had at least one glycated hemoglobin test in the year. More than 15 % had co-existing autoimmune comorbidities. CONCLUSIONS: The incidence rate of pediatric T1DM in Friuli Venezia Giulia has increased in the last years, and the disease is a relevant public health issue in the region.

Iron signature in asbestos-induced malignant pleural mesothelioma: A population-based autopsy study. - Crovella, Sergio; Bianco, Anna Monica; Vuch, Joseph; Zupin, Luisa; Moura, Ronald Rodrigues; Trevisan, Elisa; Schneider, Manuela; Brollo, Alessandro; Nicastro, Enza Maria; Cosenzi, Alessandro; Zabucchi, Giuliano; Borelli, Violetta (J Toxicol Environ Health A, 2016)
Malignant pleural mesothelioma (MPM) is an aggressive cancer with poor prognosis. The development of MPM is frequently linked to inhalation of asbestos fibers. A genetic component of susceptibility to this disease is suggested by the observation that some individuals develop MPM following lower doses of asbestos exposure, whereas others exposed to higher quantities do not seem to be affected. This hypothesis is supported also by frequent reports of MPM familial clustering. Despite the widely recognized role of iron (Fe) in cellular asbestos-induced pulmonary toxicity, the role of the related gene polymorphisms in the etiology of MPM has apparently not been evaluated. Eighty-six single-nucleotide polymorphisms (SNPs) of 10 Fe-metabolism genes were examined by exploiting formalin-fixed paraffin-embedded postmortem samples from 77 patients who died due to MPM (designated AEM) and compared with 48 who were exposed to asbestos but from died in old age of cause other than asbestos (designated AENM). All subjects showed objective signs of asbestos exposure. Three SNPs, localized in the ferritin heavy polypeptide, transferrin, and hephaestin genes, whose frequencies were distributed differently in AEM and AENM populations, were identified. For ferritin and transferrin the C/C and the G/G genotypes, respectively, representing intronic polymorphisms, were significantly associated with protection against MPM and need to be considered as possible genetic markers of protection. Similarly, the C/C hephaestin SNP, a missense variation of this multicopper ferroxidase encoding gene, may be related, also functionally, with protection against MPM. In conclusion, it is proposed that three Fe metabolism-associated genes, significantly associated with protection against development of MPM, may serve as protective markers for this aggressive tumor.
Keywords: Adult; Aged; Asbestos; Autopsy; Case-Control Studies; Female; Ferritins; Gene Frequency; Genetic Markers; Humans; Iron; Lung Neoplasms; Male; Membrane Proteins; Mesothelioma; Middle Aged; Mutation, Missense; Polymorphism, Single Nucleotide; Transferrin; Young Adult

Lack of Evidence of Rotavirus-Dependent Molecular Mimicry as a Trigger of Celiac Disease. - Ziberna, Fabiana; De Lorenzo, Giuditta; Schiavon, Valentina; Arnoldi, Francesca; Quaglia, Sara; De Leo, Luigina; Vatta, Serena; Martelossi, Stefano; Burrone, Oscar R; Ventura, Alessandro; Not, Tarcisio (Clin Exp Immunol, 2016)
New data suggest the involvement of Rotavirus (RV) in triggering autoimmunity in celiac disease (CD) by molecular mimicry between the human-transglutaminase protein and the dodecapeptide (260-271 aa) of the RV protein VP7 (pVP7). To assess the role of RV in the onset of CD, we measured the anti-pVP7 antibodies in the sera of children with CD and of control groups. We analysed serum samples of 118 biopsy proven CD patients and 46 patients with potential-CD; 32 children with other gastrointestinal diseases; 107 no-CD children and 107 blood donors. By ELISA assay, we measured IgA-IgG antibodies against the synthetic peptides pVP7, the human transglutaminase-derived peptide (476-487 aa) which shows an homology with VP7 protein and a control peptide. The triple-layered RV particles (TLPs), containing the VP7 protein, and the double-layered RV-particles (DLPs), lacking the VP7 protein were also used as antigens in ELISA assay. Antibody reactivity to the RV-TLPs was positive in 22/118 (18%) CD patients and in both paediatric (17/107, 16%) and adult (29/107, 27%) control groups, without showing a statistically significant difference among them (p=0.6, p=0.1). Biopsy-proven CD patients as well as the adult control group demonstrated a high positive antibody reactivity against both pVP7 (34/118, 29% CD patients; 66/107, 62% adult controls) and control synthetic peptides (35/118, 30% CD patients; 56/107, 52% adult controls) suggesting a non-specific response against RV pVP7. We show that children with CD do not have higher immune reactivity to RV, thus questioning the molecular mimicry mechanism as a triggering factor of CD. This article is protected by copyright. All rights reserved.

Lactoferrin gene polymorphisms in Italian patients with recurrent tonsillitis. - Zupin, Luisa; Angelelli, Francesco; Grasso, Domenico Leonardo; Crovella, Sergio (Int J Pediatr Otorhinolaryngol, 2016)
INTRODUCTION: Recurrent tonsillitis is an oral pathology characterized by inflammation of tonsils. The disease susceptibility depends upon environmental and host factors, specifically the innate immune response, the first line of host defence could play an important role. Among innate immunity members, lactoferrin, known for its antimicrobial properties, was previously correlated with the risk of oral pathology as periodontitis and dental caries. METHODS: 89 Italian children presenting recurrent tonsillitis and 95 healthy children were genotyped for two LTF non-synonymous polymorphisms, called Thr29Ala and Arg47Lys, in order to investigate their potential role in recurrent tonsillitis susceptibility. RESULTS: no different allele, genotype and haplotype frequency distributions were detected comparing patients and controls. CONCLUSION: data from the current study indicate that LTF polymorphisms might not be involved in recurrent tonsillitis development in our Italian population. However, since the importance of lactoferrin in oral immunity has been previously assessed, further studies should be necessary to unravel the potential role of LTF genetic variants in oral cavity.

MBL2 genetic polymorphisms and HIV-1 mother-to-child transmission in Zambia. - Zupin, Luisa; Polesello, Vania; Segat, Ludovica; Kuhn, Louise; Crovella, Sergio (Immunol Res, 2016)
Since antiretroviral drugs have been introduced to prevent mother-to-child transmission, the risk of HIV-1 infection in infants has decreased considerably worldwide. Nevertheless, many factors are involved in viral transmission and host susceptibility to infection. The immune system and its components, including mannose binding protein C (encoding by MBL2 gene), are already known to play an important role in this scenario. In the present study, 313 children and 98 of their mothers from Zambia were genotyped for the MBL2 promoter HL (rs11003125) and XY (rs7096206) polymorphisms and exon 1 D (rs5030737, at codon 52) B (rs1800450, at codon 54) and C (rs1800451, at codon 57) polymorphisms in order to investigate the potential role of these genetic variants in HIV-1 mother-to-child transmission. No statistical significant association was observed comparing transmitter and non-transmitter mothers and also confronting HIV-positive and HIV-negative children. The findings of the current study obtained on mother and children from Zambia evidence lack of association between MBL2 functional polymorphisms and HIV-1 mother-to-child transmission.

MBL2 Genetic Variants in HCV Infection Susceptibility, Spontaneous Viral Clearance and Pegylated Interferon Plus Ribavirin Treatment Response. - Zupin, L; Polesello, V; Alberi, G; Moratelli, G; Crocè, S L; Masutti, F; Pozzato, G; Crovella, S; Segat, L (Scand J Immunol, 2016)
Hepatitis C is disease that damages the liver, and it is caused by the hepatitis C virus (HCV). The pathology became chronic in about 80% of the cases due to virus persistence in the host organism. The standard of care consists of pegylated interferon plus ribavirin; however, the treatment response is very variable and different host/viral factors may concur in the disease outcome. The mannose-binding protein C (MBL) is a component of the innate immune system, able to recognize HCV and consecutively activating the immune response. MBL is encoded by MBL2 gene, and polymorphisms, two in the promoter region (H/L and X/Y) and three in exon 1 (at codon 52, 54 and 57), have been described as functionally influencing protein expression. In this work, 203 Italian HCV patients and 61 healthy controls were enrolled and genotyped for the five MBL2 polymorphisms mentioned above to investigate their role in HCV infection susceptibility, spontaneous viral clearance and treatment response. MBL2 polymorphisms were not associated with HCV infection susceptibility and with spontaneous viral clearance, while MBL2 O allele, O/O genotype, HYO haplotype and DP combined genotype (all correlated with low or deficient MBL expression) were associated with sustained virological response. Moreover, a meta-analysis to assess the role of MBL2 polymorphisms in HCV infection susceptibility was also performed: YA haplotype could be associated with protection towards HCV infection.

Nationwide study of headache pain in Italy shows that pain assessment is still inadequate in paediatric emergency care. - Benini, Franca; Piga, Simone; Zangardi, Tiziana; Messi, Gianni; Tomasello, Caterina; Pirozzi, Nicola; Cuttini, Marina (Acta Paediatr, 2016)
AIM: Italian national guidelines on pain management were published in 2010, but there is little information on how effective pain management is in paediatric emergency care, with other countries reporting poor levels. Using headache as an indicator, we described pain assessment in Italian emergency departments and identified predictors of algometric scale use. METHODS: All Italian paediatric and maternal and child hospitals participated, plus four general hospitals. Data on all children aged 4-14 years admitted during a one-month period with headache as their chief complaint were abstracted from clinical records. Multivariable analyses identified predictors of algometric assessment, taking into account the cluster study design. RESULTS: We studied 470 admissions. During triage, pain was assessed using a standardised scale (41.5%), informally (15.5%) or was not recorded (42.9%). Only 32.1% of the children received analgesia in the emergency department. The odds ratios for predictors of algometric assessment were non-Italian nationality (3.6), prehospital medication (1.8), admission to a research hospital (7.3) and a more favourable nurses-to-admissions ratio of 10.8 for the highest versus lowest tertile. CONCLUSION: Despite national guidelines, paediatric pain assessment in Italian emergency care was suboptimal. Hospital variables appeared to be stronger predictors of adequate assessment than patient characteristics.

Pitfalls and promises in FTIR spectromicroscopy analyses to monitor iron-mediated DNA damage in sperm. - Pascolo, Lorella; Bedolla, Diana E; Vaccari, Lisa; Venturin, Irene; Cammisuli, Francesca; Gianoncelli, Alessandra; Mitri, Elisa; Giolo, Elena; Luppi, Stefania; Martinelli, Monica; Zweyer, Marina; Ricci, Giuseppe (Reprod Toxicol, 2016)
Many drugs, chemicals, and environmental factors can impair sperm functionality by inducing DNA damage, one of the important causes of reduced fertility potential. The use of vibrational spectromicroscopy represents a promising approach for monitoring DNA integrity in sperm, although some limitations exist, depending from the experimental conditions. Here, we report that when using FTIR spectromicroscopy to reveal oxidative stress mediated by Fenton's reaction on hydrated sperm samples, DNA damage interpretation is partially compromised by unexpected cell surface precipitates. The precipitates give a broad band in the 1150-1000cm(-1) infrared region, which partially covers one of the signatures of DNA (phosphate stretching bands), and are detected as iron and oxygen containing material when using XRF spectroscopy. On the other hand, the analyses further support the potential of FTIR spectromicroscopy to reveal cellular oxidative damage events such as lipid peroxidation, protein misfolding and aggregations, as well as DNA strain breaks.

The prognostic value of biological markers in paediatric Hodgkin lymphoma. - Farruggia, Piero; Puccio, Giuseppe; Sala, Alessandra; Todesco, Alessandra; Buffardi, Salvatore; Garaventa, Alberto; Bottigliero, Gaetano; Bianchi, Maurizio; Zecca, Marco; Locatelli, Franco; Pession, Andrea; Pillon, Marta; et al. (Eur J Cancer, 2016)
BACKGROUND: Many biological and inflammatory markers have been proposed as having a prognostic value at diagnosis of Hodgkin lymphoma (HL), but very few have been validated in paediatric patients. We explored the significance of these markers in a large population of 769 affected children. PATIENTS AND METHODS: By using the database of patients enrolled in A.I.E.O.P. (Associazione Italiana di Emato-Oncologia Pediatrica) trial LH2004 for paediatric HL, we identified 769 consecutive patients treated with curative intent from 1st June 2004 to 1st April 2014 with ABVD (doxorubicin, bleomycin, vinblastine, and dacarbazine), or hybrid COPP/ABV (cyclophosphamide, vincristine, prednisone, procarbazine, doxorubicin, bleomycin and vinblastine) regimens. RESULTS: On multivariate analysis with categorical forms, the 5-year freedom from progression survival was significantly lower in patients with stage IV or elevated value of platelets, eosinophils and ferritin at diagnosis. Furthermore, stage IV and eosinophils seem to maintain their predictive value independently of interim (after IV cycles of chemotherapy) positron emission tomography. CONCLUSION: Using the combination of four simple markers such as stage IV and elevated levels of platelets, ferritin and eosinophils, it is possible to classify the patients into subgroups with very different outcomes.
Keywords: Adolescent; Age Factors; Antineoplastic Combined Chemotherapy Protocols; Biomarkers, Tumor; Blood Platelets; Child; Child, Preschool; Databases, Factual; Disease Progression; Disease-Free Survival; Eosinophils; Female; Ferritins; Hodgkin Disease; Humans; Infant; Infant, Newborn; Italy; Kaplan-Meier Estimate; Leukocyte Count; Male; Multivariate Analysis; Neoplasm Staging; Platelet Count; Predictive Value of Tests; Proportional Hazards Models; Retrospective Studies; Risk Factors; Time Factors; Treatment Outcome

Protective Role of BST2 Polymorphisms in Mother-to-Child Transmission of HIV-1 and Adult AIDS Progression. - Kamada, Anselmo J; Bianco, Anna M; Zupin, Luisa; Girardelli, Martina; Matte, Maria C C; Medeiros, Rúbia Marília de; Almeida, Sabrina Esteves de Matos; Rocha, Marineide M; Segat, Ludovica; Chies, José A B; Kuhn, Louise; Crovella, Sergio (J Acquir Immune Defic Syndr, 2016)
Bone marrow stromal cell antigen-2 (BST-2)/Tetherin is a restriction factor that prevents Human immunodeficiency virus type 1 (HIV-1) release from infected cells and mediates pro-inflammatory cytokine production. This study investigated the risk conferred by single nucleotide polymorphisms (rs919266, rs9192677, and rs9576) at BST-2 coding gene (BST2) in HIV-1 mother-to-child transmission and in disease progression. Initially, 101 HIV-1+ pregnant women and 331 neonates exposed to HIV-1 from Zambia were enrolled. Additional BST2 single nucleotide polymorphism analyses were performed in 2 cohorts with acquired immunodeficiency syndrome (AIDS) progression: an adult Brazilian cohort (37 rapid, 30 chronic and 21 long-term non-progressors) and an Italian pediatric cohort (21 rapid and 67 slow progressors). The rs9576A allele was nominally associated with protection during breastfeeding (P = 0.019) and individuals carrying rs919266 GA showed slower progression to AIDS (P = 0.033). Despite the influence of rs919266 and rs9576 on BST2 expression being still undetermined, a preventive role by BST2 polymorphisms was found during HIV-1 infection.

A reference panel of 64,976 haplotypes for genotype imputation. - McCarthy, Shane; Das, Sayantan; Kretzschmar, Warren; Delaneau, Olivier; Wood, Andrew R; Teumer, Alexander; Kang, Hyun Min; Fuchsberger, Christian; Danecek, Petr; Sharp, Kevin; Luo, Yang; Sidore, Carlo; et al. (Nat Genet, 2016)
We describe a reference panel of 64,976 human haplotypes at 39,235,157 SNPs constructed using whole-genome sequence data from 20 studies of predominantly European ancestry. Using this resource leads to accurate genotype imputation at minor allele frequencies as low as 0.1% and a large increase in the number of SNPs tested in association studies, and it can help to discover and refine causal loci. We describe remote server resources that allow researchers to carry out imputation and phasing consistently and efficiently.

Synchrotron X-ray microscopy reveals early calcium and iron interaction with crocidolite fibers in the lung of exposed mice. - Pascolo, Lorella; Zabucchi, Giuliano; Gianoncelli, Alessandra; Kourousias, George; Trevisan, Elisa; Pascotto, Ernesto; Casarsa, Claudia; Ryan, Chris; Lucattelli, Monica; Lungarella, Giuseppe; Cavarra, Eleonora; Bartalesi, Barbara; et al. (Toxicol Lett, 2016)
Human exposure to asbestos can cause a wide variety of lung diseases that are still a current major health concern, even if asbestos has been banned in many countries. It has been shown in many studies that asbestos fibers, ingested by alveolar macrophages, disrupt lung iron homeostasis by sequestering iron. Calcium can also be deposited on the fibers. The pathways along which iron and above all calcium interact with fibers are still unknown. Our aim was that of investigating if the iron accumulation induced by the inhaled asbestos fibers also involves calcium ions accumulation. Lung sections of asbestos-exposed mice were analyzed using an extremely sensitive procedure available at the synchrotron facilities, that provides morphological and chemical information based on X-ray fluorescence microspectroscopy (μ-XRF). In this study we show that (1) where conventional histochemical procedures revealed only weak deposits of iron and calcium, μ-XRF analysis is able to detect significant deposits of both iron and calcium on the inhaled asbestos fibers; (2) the extent of the deposition of these ions is proportionally directly related and (3) iron and calcium deposition on inhaled asbestos fibers is concomitant with the appearance of inflammatory and hyperplastic reactions.

5-Aminoimidazole-4-carboxamide ribonucleotide-transformylase and inosine-triphosphate-pyrophosphatase genes variants predict remission rate during methotrexate therapy in patients with juvenile idiopathic arthritis. - Pastore, Serena; Stocco, Gabriele; Moressa, Valentina; Zandonà, Luigi; Favretto, Diego; Malusà, Noelia; Decorti, Giuliana; Lepore, Loredana; Ventura, Alessandro (Rheumatol Int, 2015)
For children with juvenile idiopathic arthritis (JIA) who fail to respond to methotrexate, the delay in identifying the optimal treatment at an early stage of disease can lead to long-term joint damage. Recent studies indicate that relevant variants to predict methotrexate response in JIA are those in 5-aminoimidazole-4-carboxamide ribonucleotide-transformylase (ATIC), inosine-triphosphate-pyrophosphatase (ITPA) and solute-liquid-carrier-19A1 genes. The purpose of the study was, therefore, to explore the role of these candidate genetic factors on methotrexate response in an Italian cohort of children with JIA. Clinical response to methotrexate was evaluated as clinical remission stable for a 6-month period, as ACRPed score and as change in Juvenile Arthritis Disease score. The most relevant SNPs for each gene considered were assayed on patients' DNA. ITPA activity was measured in patients' erythrocytes. Sixty-nine patients with JIA were analyzed: 52.2 % responded to therapy (ACRPed70 score), while 37.7 % reached clinical remission stable for 6 months. ATIC rs2372536 GG genotype was associated with improved clinical remission (adjusted p value = 0.0090). For ITPA, rs1127354 A variant was associated with reduced clinical remission: (adjusted p value = 0.028); this association was present even for patients with wild-type ITPA and low ITPA activity. These preliminary results indicate that genotyping of ATIC rs2372536 and ITPA rs1127354 variants or measuring ITPA activity could be useful to predict methotrexate response in children with JIA after validation by further prospective studies on a larger patient cohort.

Acute pseudotumoral hemicerebellitis in a child: a rare and distinct entity? - Alberini, Elena; Vellante, Valerio; Zennaro, Floriana; Calligaris, Lorenzo; Barbi, Egidio; Carrozzi, Marco; Devescovi, Raffaella (J Child Neurol, 2015)
A pseudotumoral presentation of acute hemicerebellitis is rare in pediatric age. The authors report a new single case study of a 7-year-old child with pseudotumoral unilateral cerebellitis mimicking an intracranial tumor, which clinically presented itself with signs of intracranial hypertension and mild contralateral hemiparesis, completely recovered after anti-inflammatory therapy. Brain magnetic resonance imaging (MRI) was essential for the differential diagnosis between inflammatory and neoplastic processes. The literature highlighting specific clues about pseudotumoral hemicerebellitis as a distinct clinical and radiological entity is reviewed.
Keywords: Brain; Cerebellar Diseases; Child; Diagnosis, Differential; Encephalitis; Humans; Magnetic Resonance Imaging; Male

The anti-leukemic activity of sodium dichloroacetate in p53mutated/null cells is mediated by a p53-independent ILF3/p21 pathway. - Agnoletto, Chiara; Brunelli, Laura; Melloni, Elisabetta; Pastorelli, Roberta; Casciano, Fabio; Rimondi, Erika; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2015)
B-chronic lymphocytic leukemia (B-CLL) patients harboring p53 mutations are invariably refractory to therapies based on purine analogues and have limited treatment options and poor survival. Having recently demonstrated that the mitochondria-targeting small molecule sodium dichloroacetate (DCA) exhibits anti-leukemic activity in p53wild-type B-CLL cells, the aim of this study was to evaluate the effect of DCA in p53mutated B-CLL cells and in p53mutated/null leukemic cell lines. DCA exhibited comparable cytotoxicity in p53wild-type and p53mutated B-CLL patient cell cultures, as well as in p53mutated B leukemic cell lines (MAVER, MEC-1, MEC-2). At the molecular level, DCA promoted the transcriptional induction of p21 in all leukemic cell types investigated, including p53null HL-60. By using a proteomic approach, we demonstrated that DCA up-regulated the ILF3 transcription factor, which is a known regulator of p21 expression. The role of the ILF3/p21 axis in mediating the DCA anti-leukemic activity was underscored by knocking-down experiments. Indeed, transfection with ILF3 and p21 siRNAs significantly decreased both the DCA-induced p21 expression and the DCA-mediated cytotoxicity. Taken together, our results emphasize that DCA is a small molecule that merits further evaluation as a therapeutic agent also for p53mutated leukemic cells, by acting through the induction of a p53-independent pathway.

Applications of nanoparticles in cancer medicine and beyond: optical and multimodal in vivo imaging, tissue targeting and drug delivery. - Biffi, Stefania; Voltan, Rebecca; Rampazzo, Enrico; Prodi, Luca; Zauli, Giorgio; Secchiero, Paola (Expert Opin Drug Deliv, 2015)
INTRODUCTION: Nanotechnology has opened up the way to the engineering of new organized materials endowed with improved performances. In the past decade, engineered nanoparticles (NPs) have been progressively implemented by exploiting synthetic strategies that yield complex materials capable of performing functions with applications also in medicine. Indeed, in the field of 'nanomedicine' it has been explored the possibility to design multifunctional nanosystems, characterized by high analytical performances and stability, low toxicity and specificity towards a given cell target. Area covered: In this review article, we summarize the advances in the engineering of NPs for biomedical applications, from optical imaging (OI) to multimodal OI and targeted drug delivery. For this purpose, we will provide some examples of how investigations in nanomedicine can support preclinical and clinical research generating innovative diagnostic and therapeutic strategies in oncology. Expert opinion: The progressive breakthroughs in nanomedicine have supported the development of multifunctional and multimodal NPs. In particular, NPs are significantly impacting the diagnostic and therapeutic strategies since they allow the development of: NP-based OI probes containing more than one modality-specific contrast agent; surface functionalized NPs for specific 'molecular recognition'. Therefore, the design and characterization of innovative NP-based systems/devices have great applicative potential into the medical field.

Are all cases of paediatric essential thrombocythaemia really myeloproliferative neoplasms? Analysis of a large cohort. - Randi, Maria L; Geranio, Giulia; Bertozzi, Irene; Micalizzi, Concetta; Ramenghi, Ugo; Tucci, Fabio; Notarangelo, Lucia D; Ladogana, Saverio; Menna, Giuseppe; Giordano, Paola; Consarino, Caterina; Farruggia, Piero; et al. (Br J Haematol, 2015)
Sporadic essential thrombocythaemia (ET) is rare in paediatrics, and the diagnostic and clinical approach to paediatric cases cannot be simply copied from experience with adults. Here, we assessed 89 children with a clinical diagnosis of ET and found that 23 patients (25·8%) had a clonal disease. The JAK2 V617F mutation was identified in 14 children, 1 child had the MPL W515L mutation, and 6 had CALR mutations. The monoclonal X-chromosome inactivation pattern was seen in six patients (two with JAK2 V617F and two with CALR mutations). The other 66 patients (74·2%) had persistent thrombocytosis with no clonality. There were no clinical or haematological differences between the clonal and non-clonal patients. The relative proportion of ET-specific mutations in the clonal children was much the same as in adults. The higher prevalence of non-clonal cases suggests that some patients may not have myeloproliferative neoplasms, with significant implications for their treatment.
Keywords: Adolescent; Adult; Amino Acid Substitution; Child; Child, Preschool; Cohort Studies; Female; Hematologic Neoplasms; Humans; Infant; Janus Kinase 2; Male; Mutation, Missense; Neoplasm Proteins; Thrombocythemia, Essential

Bedside diagnosis of two major clinical phenotypes of hypertensive disorders of pregnancy. - Ferrazzi, E; Zullino, S; Stampalija, T; Vener, C; Cavoretto, P; Gervasi, M T; Vergani, P; Mecacci, F; Marozio, L; Oggè, G; Algeri, P; Ruffatti, A; et al. (Ultrasound Obstet Gynecol, 2015)
OBJECTIVE: We hypothesized that fetal abdominal circumference (AC) and Uterine Doppler Pulsatility Index (UtA-PI) could select two homogenous subgroups of women affected by hypertensive disorders of pregnancy (HDP), characterized by the coexistence of maternal hypertension with and without IUGR. METHODS: This is a multicentre study that studied cases affected by HDP in whom fetal AC and UtA-PI had been measured at admission to feto Maternal Medicine Units. Maternal characteristics, pregnancy complications and outcome were recorded. These data allowed us to model the characteristics of fetal growth in cases affected by HDP, and to design a composite index for risk factors of maternal metabolic syndrome (rfMMS) and composite index of severity for maternal organ and/or function damage (OFD). RESULTS: Measurements of fetal AC and UtA-PI allowed us to define a group of HDP with AGA fetuses (HDP-AGAf) diagnosed by normal fetal AC and a UtA-PI (#205), and a group of HDP with IUGR fetuses (HDP-IUGR) diagnosed by fetal AC <5(th) centile and UtA-PI >95(th) centile (#124). Curves fitted to birth-weight of the two groups were significantly different, and gestational age at admission for HDP, <34 or ≥34, had no effect on their models. When birth-weight was expressed as standard deviation score (SDS) of local reference charts, the average SDS (±standard error) corresponded to the 6(th) and 48(th) centile respectively. The risk of developing HDP-AGAf was significantly associated with risk factors for maternal metabolic syndrome (OR= 2.79;CI 1.57-4.97), independently of gestational age. The same risk factors yielded a non significant ORs of developing late onset HDP. Women with HDP-IUGR proved to be associated with the worst clinical outcomes. CONCLUSIONS: This study adds genuine new data based on simple prenatal bedside examinations, that might help to differentiate HDP with IUGR, from HDP with AGA fetuses, associated with different fetal growth patterns and different risk factors, not affected by gestational age at onset of the disease.

A brain and heart connection: X-linked periventricular heterotopia. - Naviglio, Samuele; Bruno, Irene; Zanus, Caterina; Faletra, Flavio; Ventura, Alessandro (J Pediatr, 2015)
Keywords: Adolescent; Brain; Diagnosis, Differential; DNA Mutational Analysis; Epilepsy; Female; Filamins; Humans; Magnetic Resonance Imaging; Mutation; Periventricular Nodular Heterotopia

A case of Rubinstein-Taybi syndrome associated with growth hormone deficiency in childhood. - Tornese, Gianluca; Marzuillo, Pierluigi; Pellegrin, Maria Chiara; Germani, Claudio; Faleschini, Elena; Zennaro, Floriana; Grandone, Anna; Miraglia Del Giudice, Emanuele; Perrone, Laura; Ventura, Alessandro (Clin Endocrinol (Oxf), 2015)

Central venous access devices in pediatric malignancies: a position paper of Italian Association of Pediatric Hematology and Oncology. - Crocoli, Alessandro; Tornesello, Assunta; Pittiruti, Mauro; Barone, Angelica; Muggeo, Paola; Inserra, Alessandro; Molinari, Angelo Claudio; Grillenzoni, Valeria; Durante, Viviana; Cicalese, Maria Pia; Zanazzo, Giulio Andrea; Cesaro, Simone (J Vasc Access, 2015)
INTRODUCTION: Treatment of pediatric malignancies is becoming progressively more complex, implying the adoption of multimodal therapies. A reliable, long-lasting venous access represents one of the critical requirements for the success of those treatments. Recent technical innovations-such as minimally invasive procedures for placement, new devices and novel materials-have rapidly spread for clinical use in adult patients, but are still not consistently used in the pediatric population. METHODS: The Supportive Therapy Working Group of Italian Association of Hematology and Oncology (AIEOP) reviewed medical literature focusing on new aspects of central venous access devices (VADs) in pediatric patients affected by oncohematological diseases. RESULTS: Appropriate recommendations for clinical use in these patients have been discussed and formulated. CONCLUSIONS: The importance of the correct choice, management and use of VADs in pediatric oncohematological patients is a necessary prerequisite for an adequate standard of care, also considering the increased chances of cure and the longer life expectancy of those patients with modern therapies.

The combination of N-acetyl cysteine, alpha-lipoic acid, and bromelain shows high anti-inflammatory properties in novel in vivo and in vitro models of endometriosis. - Agostinis, C; Zorzet, S; De Leo, R; Zauli, G; De Seta, F; Bulla, R (Mediators Inflamm, 2015)
To evaluate the efficacy of an association of N-acetyl cystein, alpha-lipoic acid, and bromelain (NAC/LA/Br) in the treatment of endometriosis we set up a new in vivo murine model. We explored the anti-inflammatory and proapoptotic effect of this combination on human endometriotic endothelial cells (EECs) and on endothelial cells isolated from normal uterus (UtMECs). We implanted fragments of human endometriotic cysts intraperitoneally into SCID mice to evaluate the efficacy of NAC/LA/Br treatment. UtMECs and EECs, untreated or treated with NAC/LA/Br, were activated with the proinflammatory stimulus TNF-α and their response in terms of VCAM1 expression was evaluated. The proapoptotic effect of higher doses of NAC/LA/Br on UtMECs and EECs was measured with a fluorogenic substrate for activated caspases 3 and 7. The preincubation of EECs with NAC/LA/Br prior to cell stimulation with TNF-α prevents the upregulation of the expression of the inflammatory "marker" VCAM1. Furthermore NAC/LA/Br were able to induce EEC, but not UtMEC, apoptosis. Finally, the novel mouse model allowed us to demonstrate that mice treated with NAC/LA/Br presented a lower number of cysts, smaller in size, compared to untreated mice. Our findings suggest that these dietary supplements may have potential therapeutic uses in the treatment of chronic inflammatory diseases like endometriosis.

Combined circulating epigenetic markers to improve mesothelin performance in the diagnosis of malignant mesothelioma. - Santarelli, Lory; Staffolani, Sara; Strafella, Elisabetta; Nocchi, Linda; Manzella, Nicola; Grossi, Paola; Bracci, Massimo; Pignotti, Elettra; Alleva, Renata; Borghi, Battista; Pompili, Cecilia; Sabbatini, Armando; et al. (Lung Cancer, 2015)
OBJECTIVES: Malignant mesothelioma (MM) is a highly aggressive tumor with poor prognosis. A major challenge is the development and application of early and highly reliable diagnostic marker(s). Serum biomarkers, such as 'soluble mesothelin-related proteins' (SMRPs), is the most studied and frequently used in MM. However, the low sensitivity of SMRPs for early MM limits its value; therefore, additional biomarkers are required. In this study, two epigenetically regulated markers in MM (microRNA-126, miR-126, and methylated thrombomodulin promoter, Met-TM) were combined with SMRPs and evaluated as a potential strategy to detect MM at an early stage. MATERIALS AND METHODS: A total of 188 subjects, including 45 MM patients, 99 asbestos-exposed subjects, and 44 healthy controls were prospectively enrolled, serum samples collected, and serum levels of SMRPs, miR-126 and Met-TM evaluated. Logistic regression analysis was performed to evaluate the diagnostic value of the three biomarkers. Using this approach, the performance of the '3-biomarker classifier' was tested by calculating the overall probability score of the MM and control samples, respectively, and the ROC curve was generated. RESULTS AND CONCLUSION: The combination of the three biomarkers was the best predictor to differentiate MM patients from asbestos-exposed subjects and healthy controls. The accuracy and cancer specificity was confirmed in a second validation cohort and lung cancer population. We propose that the combination of the two epigenetic biomarkers with SMRPs as a diagnosis for early MM overcomes the limitations of using SMRPs alone.

Design, Synthesis, and Biological Characterization of Novel Mitochondria Targeted Dichloroacetate-Loaded Compounds with Antileukemic Activity. - Trapella, Claudio; Voltan, Rebecca; Melloni, Elisabetta; Tisato, Veronica; Celeghini, Claudio; Bianco, Sara; Fantinati, Anna; Salvadori, Severo; Guerrini, Remo; Secchiero, Paola; Zauli, Giorgio (J Med Chem, 2015)
The mitochondrial kinase inhibitor dichloroacetate (DCA) has recently received attention in oncology due to its ability to target glycolysis. However, DCA molecule exhibits poor bioavailability and cellular uptake with limited ability to reach its target mitochondria. To overcome these biases, we have synthesized novel DCA-loaded compounds. The selection of the most promising therapeutic molecule was evaluated by combining in vitro assays, to test the antitumoral potential on leukemic cells, and a preliminary characterization of the molecule stability in vivo, in mice. Among the newly synthesized compounds, we have selected the multiple DCA-loaded compound 10, characterized by a tertiary amine scaffold, because it exhibited enhanced (>30-fold) in vitro antitumor activity with respect to DCA and increased in vivo stability. On the basis of these results, we believe that compound 10 should be considered for further preclinical evaluations for the treatment of cancers and/or other diseases characterized by altered metabolic origin.

Diagnostic criteria currently proposed for "ictal epileptic headache": Perspectives on strengths, weaknesses and pitfalls. - Parisi, Pasquale; Verrotti, Alberto; Costa, Paola; Striano, Pasquale; Zanus, Caterina; Carrozzi, Marco; Raucci, Umberto; Villa, Maria Pia; Belcastro, Vincenzo (Seizure, 2015)
PURPOSE: When we published the diagnostic criteria for "ictal epileptic headache" in 2012, we deliberately and consciously chose to adopt restrictive criteria that probably underestimate the phenomenon, rather than spread panic among patients and physicians who are reluctant to accept this entity. METHODS: Here we discuss four intriguing clinical cases to highlight why we believe, to this day, that it is necessary to follow these restrictive diagnostic criteria. CONCLUSIONS: EEG is not recommended as a routine examination for children diagnosed with headache, but it is mandatory and must be carried out promptly in cases of prolonged headache that does not respond to antimigraine drugs, if epilepsy is suspected or has been diagnosed previously. This is not a marginal or irrelevant question because possible isolated, non-motor, ictal manifestations should be taken into account before declaring that an epileptic patient is "seizure free" so as to ensure that any decision taken to suspend anticonvulsant therapy is safe.

Differential protein folding and chemical changes in lung tissues exposed to asbestos or particulates. - Pascolo, Lorella; Borelli, Violetta; Canzonieri, Vincenzo; Gianoncelli, Alessandra; Birarda, Giovanni; Bedolla, Diana E; Salomè, Murielle; Vaccari, Lisa; Calligaro, Carla; Cotte, Marine; Hesse, Bernhard; Luisi, Fernando; et al. (Sci Rep, 2015)
Environmental and occupational inhalants may induce a large number of pulmonary diseases, with asbestos exposure being the most risky. The mechanisms are clearly related to chemical composition and physical and surface properties of materials. A combination of X-ray fluorescence (μXRF) and Fourier Transform InfraRed (μFTIR) microscopy was used to chemically characterize and compare asbestos bodies versus environmental particulates (anthracosis) in lung tissues from asbestos exposed and control patients. μXRF analyses revealed heterogeneously aggregated particles in the anthracotic structures, containing mainly Si, K, Al and Fe. Both asbestos and particulates alter lung iron homeostasis, with a more marked effect in asbestos exposure. μFTIR analyses revealed abundant proteins on asbestos bodies but not on anthracotic particles. Most importantly, the analyses demonstrated that the asbestos coating proteins contain high levels of β-sheet structures. The occurrence of conformational changes in the proteic component of the asbestos coating provides new insights into long-term asbestos effects.

Directional dominance on stature and cognition in diverse human populations. - Joshi, Peter K; Esko, Tõnu; Mattsson, Hannele; Eklund, Niina; Gandin, Ilaria; Nutile, Teresa; Jackson, Anne U; Schurmann, Claudia; Smith, Albert V; Zhang, Weihua; Okada, Yukinori; Stančáková, Alena; et al. (Nature, 2015)
Homozygosity has long been associated with rare, often devastating, Mendelian disorders, and Darwin was one of the first to recognize that inbreeding reduces evolutionary fitness. However, the effect of the more distant parental relatedness that is common in modern human populations is less well understood. Genomic data now allow us to investigate the effects of homozygosity on traits of public health importance by observing contiguous homozygous segments (runs of homozygosity), which are inferred to be homozygous along their complete length. Given the low levels of genome-wide homozygosity prevalent in most human populations, information is required on very large numbers of people to provide sufficient power. Here we use runs of homozygosity to study 16 health-related quantitative traits in 354,224 individuals from 102 cohorts, and find statistically significant associations between summed runs of homozygosity and four complex traits: height, forced expiratory lung volume in one second, general cognitive ability and educational attainment (P < 1 × 10(-300), 2.1 × 10(-6), 2.5 × 10(-10) and 1.8 × 10(-10), respectively). In each case, increased homozygosity was associated with decreased trait value, equivalent to the offspring of first cousins being 1.2 cm shorter and having 10 months' less education. Similar effect sizes were found across four continental groups and populations with different degrees of genome-wide homozygosity, providing evidence that homozygosity, rather than confounding, directly contributes to phenotypic variance. Contrary to earlier reports in substantially smaller samples, no evidence was seen of an influence of genome-wide homozygosity on blood pressure and low density lipoprotein cholesterol, or ten other cardio-metabolic traits. Since directional dominance is predicted for traits under directional evolutionary selection, this study provides evidence that increased stature and cognitive function have been positively selected in human evolution, whereas many important risk factors for late-onset complex diseases may not have been.
Keywords: Biological Evolution; Blood Pressure; Body Height; Cholesterol, LDL; Cognition; Cohort Studies; Educational Status; Female; Forced Expiratory Volume; Genome, Human; Homozygote; Humans; Lung Volume Measurements; Male; Phenotype

Effect of seminal leukocytes on in vitro fertilization and intracytoplasmic sperm injection outcomes. - Ricci, Giuseppe; Granzotto, Marilena; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Zito, Gabriella; Borelli, Massimo (Fertil Steril, 2015)
OBJECTIVE: To investigate the influence of seminal leukocytes on conventional IVF and intracytoplasmic sperm injection (ICSI) outcomes, using a flow cytometry method. DESIGN: Prospective study. SETTING: Tertiary infertility center and research institute. PATIENT(S): One hundred sixty-four couples undergoing conventional IVF or ICSI. INTERVENTION(S): Seminal leukocytes were counted by flow cytometry. MAIN OUTCOME MEASURE(S): Correlation between seminal leukocytes concentration and reproductive outcomes in IVF and ICSI cycles. RESULT(S): The median number of oocytes retrieved, the fertilization and cleavage rate, the median number and grade of embryos transferred, the median number of good-quality embryos transferred, and the median percentage of good-quality embryos from total embryos transferred, in leukocytospermic and non-leukocytospermic patients were not statistically different after either IVF or ICSI. Similarly, there were no significant differences between the two groups for implantation rate and clinical pregnancy rate. Multivariate logistic regression analysis showed that the reproductive outcomes were not influenced by adjustment for female age, infertility diagnosis, number of previous attempts, treatment protocol (GnRH agonist or antagonist), assisted reproduction procedure (IVF or ICSI), and leukocytospermia. By profiling the proper Poisson regression models, no leukocytospermia cut-off value was able to identify the subjects at risk for oocyte fertilization or embryo cleavage failure. CONCLUSION(S): Using a flow cytometry method, we demonstrated that leukocytospermia does not significantly influence IVF or ICSI outcomes. The same results were obtained by using lower or higher cut-off values for leukocytospermia (from 0.2 to 2 × 10(6)/mL).
Keywords: Adult; Female; Fertilization in Vitro; Flow Cytometry; Humans; Leukocytes; Male; Pregnancy; Pregnancy Rate; Prospective Studies; Semen; Sperm Injections, Intracytoplasmic

Effect of Thalidomide on Clinical Remission in Children and Adolescents with Ulcerative Colitis Refractory to Other Immunosuppressives: Pilot Randomized Clinical Trial. - Lazzerini, Marzia; Martelossi, Stefano; Magazzù, Giuseppe; Pellegrino, Salvatore; Lucanto, Maria Cristina; Barabino, Arrigo; Calvi, Angela; Arrigo, Serena; Lionetti, Paolo; Lorusso, Monica; Mangiantini, Francesca; Fontana, Massimo; et al. (Inflamm Bowel Dis, 2015)
BACKGROUND: In a randomized controlled trial, thalidomide has shown to be effective in refractory Crohn's disease in children. This pilot study aimed at evaluating thalidomide in refractory pediatric ulcerative colitis (UC). METHODS: Double-blind, placebo-controlled randomized clinical trial on thalidomide 1.5 to 2.5 mg/kg/day in children with active UC despite multiple immunosuppressive treatments. In an open-label extension, nonresponders to placebo received thalidomide for an additional 8 weeks; all responders were followed up for a minimum of 52 weeks. RESULTS: Twenty-six children with refractory UC were randomized to thalidomide or placebo. Clinical remission at week 8 was achieved by significantly more children treated with thalidomide {10/12 (83.3%) versus 2/11 (18.8%); risk ratio, 4.5 (95% confidence interval [CI], 1.2-16.4); P = 0.005; number needed to treat, 1.5}. Of the nonresponders to placebo who were switched to thalidomide, 8 of 11 (72.7%) subsequently reached remission at week 8 (risk ratio, 4.0 [95% CI, 1.1-14.7]; number needed to treat, 2.45; P = 0.01). Clinical remission in the thalidomide group was 135.0 weeks (95% CI, 32-238), compared with 8.0 weeks (95% CI, 2.4-13.6) in the placebo group (P < 0.0001). Cumulative incidence of severe adverse events was 3.1 per 1000 patient-weeks. Peripheral neuropathy and amenorrhea were the most frequent adverse events. CONCLUSIONS: In this pilot randomized controlled trial on cases of UC refractory to immunosuppressive therapy, thalidomide compared with placebo resulted in improved clinical remission at 8 weeks of treatment and in longer term maintenance of remission. These findings require replication in larger clinical studies evaluating both thalidomide efficacy and safety.

Fainting Starting Parenteral Nutrition. - Pederiva, Federica; Barbi, Egidio; Zennaro, Floriana; Neri, Elena (Pediatr Emerg Care, 2015)
Complications such as mechanical accidents, infections, and thrombosis are commonly described in the presence of a central venous catheter. We present a case of a boy who had fainting episodes due to dislocation of a central venous catheter.

Genetic evidence for an origin of the Armenians from Bronze Age mixing of multiple populations. - Haber, Marc; Mezzavilla, Massimo; Xue, Yali; Comas, David; Gasparini, Paolo; Zalloua, Pierre; Tyler-Smith, Chris (Eur J Hum Genet, 2015)
The Armenians are a culturally isolated population who historically inhabited a region in the Near East bounded by the Mediterranean and Black seas and the Caucasus, but remain under-represented in genetic studies and have a complex history including a major geographic displacement during World War I. Here, we analyse genome-wide variation in 173 Armenians and compare them with 78 other worldwide populations. We find that Armenians form a distinctive cluster linking the Near East, Europe, and the Caucasus. We show that Armenian diversity can be explained by several mixtures of Eurasian populations that occurred between ~3000 and ~2000 bce, a period characterized by major population migrations after the domestication of the horse, appearance of chariots, and the rise of advanced civilizations in the Near East. However, genetic signals of population mixture cease after ~1200 bce when Bronze Age civilizations in the Eastern Mediterranean world suddenly and violently collapsed. Armenians have since remained isolated and genetic structure within the population developed ~500 years ago when Armenia was divided between the Ottomans and the Safavid Empire in Iran. Finally, we show that Armenians have higher genetic affinity to Neolithic Europeans than other present-day Near Easterners, and that 29% of Armenian ancestry may originate from an ancestral population that is best represented by Neolithic Europeans.European Journal of Human Genetics advance online publication, 21 October 2015; doi:10.1038/ejhg.2015.206.

Genetic studies of body mass index yield new insights for obesity biology. - Locke, Adam E; Kahali, Bratati; Berndt, Sonja I; Justice, Anne E; Pers, Tune H; Day, Felix R; Powell, Corey; Vedantam, Sailaja; Buchkovich, Martin L; Yang, Jian; Croteau-Chonka, Damien C; Esko, Tõnu; et al. (Nature, 2015)
Obesity is heritable and predisposes to many diseases. To understand the genetic basis of obesity better, here we conduct a genome-wide association study and Metabochip meta-analysis of body mass index (BMI), a measure commonly used to define obesity and assess adiposity, in up to 339,224 individuals. This analysis identifies 97 BMI-associated loci (P < 5 × 10(-8)), 56 of which are novel. Five loci demonstrate clear evidence of several independent association signals, and many loci have significant effects on other metabolic phenotypes. The 97 loci account for ∼2.7% of BMI variation, and genome-wide estimates suggest that common variation accounts for >20% of BMI variation. Pathway analyses provide strong support for a role of the central nervous system in obesity susceptibility and implicate new genes and pathways, including those related to synaptic function, glutamate signalling, insulin secretion/action, energy metabolism, lipid biology and adipogenesis.
Keywords: Adipogenesis; Adiposity; Age Factors; Body Mass Index; Continental Population Groups; Energy Metabolism; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glutamic Acid; Humans; Insulin; Male; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Synapses

Genome sequencing elucidates Sardinian genetic architecture and augments association analyses for lipid and blood inflammatory markers. - Sidore, Carlo; Busonero, Fabio; Maschio, Andrea; Porcu, Eleonora; Naitza, Silvia; Zoledziewska, Magdalena; Mulas, Antonella; Pistis, Giorgio; Steri, Maristella; Danjou, Fabrice; Kwong, Alan; Ortega Del Vecchyo, Vicente Diego; et al. (Nat Genet, 2015)
We report ∼17.6 million genetic variants from whole-genome sequencing of 2,120 Sardinians; 22% are absent from previous sequencing-based compilations and are enriched for predicted functional consequences. Furthermore, ∼76,000 variants common in our sample (frequency >5%) are rare elsewhere (<0.5% in the 1000 Genomes Project). We assessed the impact of these variants on circulating lipid levels and five inflammatory biomarkers. We observe 14 signals, including 2 major new loci, for lipid levels and 19 signals, including 2 new loci, for inflammatory markers. The new associations would have been missed in analyses based on 1000 Genomes Project data, underlining the advantages of large-scale sequencing in this founder population.

Global, regional, and national comparative risk assessment of 79 behavioural, environmental and occupational, and metabolic risks or clusters of risks in 188 countries, 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Forouzanfar, Mohammad H; Alexander, Lily; Anderson, H Ross; Bachman, Victoria F; Biryukov, Stan; Brauer, Michael; Burnett, Richard; Casey, Daniel; Coates, Matthew M; Cohen, Aaron; Delwiche, Kristen; Estep, Kara; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease, Injuries, and Risk Factor study 2013 (GBD 2013) is the first of a series of annual updates of the GBD. Risk factor quantification, particularly of modifiable risk factors, can help to identify emerging threats to population health and opportunities for prevention. The GBD 2013 provides a timely opportunity to update the comparative risk assessment with new data for exposure, relative risks, and evidence on the appropriate counterfactual risk distribution. METHODS: Attributable deaths, years of life lost, years lived with disability, and disability-adjusted life-years (DALYs) have been estimated for 79 risks or clusters of risks using the GBD 2010 methods. Risk-outcome pairs meeting explicit evidence criteria were assessed for 188 countries for the period 1990-2013 by age and sex using three inputs: risk exposure, relative risks, and the theoretical minimum risk exposure level (TMREL). Risks are organised into a hierarchy with blocks of behavioural, environmental and occupational, and metabolic risks at the first level of the hierarchy. The next level in the hierarchy includes nine clusters of related risks and two individual risks, with more detail provided at levels 3 and 4 of the hierarchy. Compared with GBD 2010, six new risk factors have been added: handwashing practices, occupational exposure to trichloroethylene, childhood wasting, childhood stunting, unsafe sex, and low glomerular filtration rate. For most risks, data for exposure were synthesised with a Bayesian meta-regression method, DisMod-MR 2.0, or spatial-temporal Gaussian process regression. Relative risks were based on meta-regressions of published cohort and intervention studies. Attributable burden for clusters of risks and all risks combined took into account evidence on the mediation of some risks such as high body-mass index (BMI) through other risks such as high systolic blood pressure and high cholesterol. FINDINGS: All risks combined account for 57·2% (95% uncertainty interval [UI] 55·8-58·5) of deaths and 41·6% (40·1-43·0) of DALYs. Risks quantified account for 87·9% (86·5-89·3) of cardiovascular disease DALYs, ranging to a low of 0% for neonatal disorders and neglected tropical diseases and malaria. In terms of global DALYs in 2013, six risks or clusters of risks each caused more than 5% of DALYs: dietary risks accounting for 11·3 million deaths and 241·4 million DALYs, high systolic blood pressure for 10·4 million deaths and 208·1 million DALYs, child and maternal malnutrition for 1·7 million deaths and 176·9 million DALYs, tobacco smoke for 6·1 million deaths and 143·5 million DALYs, air pollution for 5·5 million deaths and 141·5 million DALYs, and high BMI for 4·4 million deaths and 134·0 million DALYs. Risk factor patterns vary across regions and countries and with time. In sub-Saharan Africa, the leading risk factors are child and maternal malnutrition, unsafe sex, and unsafe water, sanitation, and handwashing. In women, in nearly all countries in the Americas, north Africa, and the Middle East, and in many other high-income countries, high BMI is the leading risk factor, with high systolic blood pressure as the leading risk in most of Central and Eastern Europe and south and east Asia. For men, high systolic blood pressure or tobacco use are the leading risks in nearly all high-income countries, in north Africa and the Middle East, Europe, and Asia. For men and women, unsafe sex is the leading risk in a corridor from Kenya to South Africa. INTERPRETATION: Behavioural, environmental and occupational, and metabolic risks can explain half of global mortality and more than one-third of global DALYs providing many opportunities for prevention. Of the larger risks, the attributable burden of high BMI has increased in the past 23 years. In view of the prominence of behavioural risk factors, behavioural and social science research on interventions for these risks should be strengthened. Many prevention and primary care policy options are available now to act on key risks. FUNDING: Bill & Melinda Gates Foundation.

Global, regional, and national disability-adjusted life years (DALYs) for 306 diseases and injuries and healthy life expectancy (HALE) for 188 countries, 1990-2013: quantifying the epidemiological transition. - Murray, Christopher J L; Barber, Ryan M; Foreman, Kyle J; Abbasoglu Ozgoren, Ayse; Abd-Allah, Foad; Abera, Semaw F; Aboyans, Victor; Abraham, Jerry P; Abubakar, Ibrahim; Abu-Raddad, Laith J; Abu-Rmeileh, Niveen M; Achoki, Tom; et al. (Lancet, 2015)
BACKGROUND: The Global Burden of Disease Study 2013 (GBD 2013) aims to bring together all available epidemiological data using a coherent measurement framework, standardised estimation methods, and transparent data sources to enable comparisons of health loss over time and across causes, age-sex groups, and countries. The GBD can be used to generate summary measures such as disability-adjusted life-years (DALYs) and healthy life expectancy (HALE) that make possible comparative assessments of broad epidemiological patterns across countries and time. These summary measures can also be used to quantify the component of variation in epidemiology that is related to sociodemographic development. METHODS: We used the published GBD 2013 data for age-specific mortality, years of life lost due to premature mortality (YLLs), and years lived with disability (YLDs) to calculate DALYs and HALE for 1990, 1995, 2000, 2005, 2010, and 2013 for 188 countries. We calculated HALE using the Sullivan method; 95% uncertainty intervals (UIs) represent uncertainty in age-specific death rates and YLDs per person for each country, age, sex, and year. We estimated DALYs for 306 causes for each country as the sum of YLLs and YLDs; 95% UIs represent uncertainty in YLL and YLD rates. We quantified patterns of the epidemiological transition with a composite indicator of sociodemographic status, which we constructed from income per person, average years of schooling after age 15 years, and the total fertility rate and mean age of the population. We applied hierarchical regression to DALY rates by cause across countries to decompose variance related to the sociodemographic status variable, country, and time. FINDINGS: Worldwide, from 1990 to 2013, life expectancy at birth rose by 6·2 years (95% UI 5·6-6·6), from 65·3 years (65·0-65·6) in 1990 to 71·5 years (71·0-71·9) in 2013, HALE at birth rose by 5·4 years (4·9-5·8), from 56·9 years (54·5-59·1) to 62·3 years (59·7-64·8), total DALYs fell by 3·6% (0·3-7·4), and age-standardised DALY rates per 100 000 people fell by 26·7% (24·6-29·1). For communicable, maternal, neonatal, and nutritional disorders, global DALY numbers, crude rates, and age-standardised rates have all declined between 1990 and 2013, whereas for non-communicable diseases, global DALYs have been increasing, DALY rates have remained nearly constant, and age-standardised DALY rates declined during the same period. From 2005 to 2013, the number of DALYs increased for most specific non-communicable diseases, including cardiovascular diseases and neoplasms, in addition to dengue, food-borne trematodes, and leishmaniasis; DALYs decreased for nearly all other causes. By 2013, the five leading causes of DALYs were ischaemic heart disease, lower respiratory infections, cerebrovascular disease, low back and neck pain, and road injuries. Sociodemographic status explained more than 50% of the variance between countries and over time for diarrhoea, lower respiratory infections, and other common infectious diseases; maternal disorders; neonatal disorders; nutritional deficiencies; other communicable, maternal, neonatal, and nutritional diseases; musculoskeletal disorders; and other non-communicable diseases. However, sociodemographic status explained less than 10% of the variance in DALY rates for cardiovascular diseases; chronic respiratory diseases; cirrhosis; diabetes, urogenital, blood, and endocrine diseases; unintentional injuries; and self-harm and interpersonal violence. Predictably, increased sociodemographic status was associated with a shift in burden from YLLs to YLDs, driven by declines in YLLs and increases in YLDs from musculoskeletal disorders, neurological disorders, and mental and substance use disorders. In most country-specific estimates, the increase in life expectancy was greater than that in HALE. Leading causes of DALYs are highly variable across countries. INTERPRETATION: Global health is improving. Population growth and ageing have driven up numbers of DALYs, but crude rates have remained relatively constant, showing that progress in health does not mean fewer demands on health systems. The notion of an epidemiological transition--in which increasing sociodemographic status brings structured change in disease burden--is useful, but there is tremendous variation in burden of disease that is not associated with sociodemographic status. This further underscores the need for country-specific assessments of DALYs and HALE to appropriately inform health policy decisions and attendant actions. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Aged; Chronic Disease; Communicable Diseases; Female; Global Health; Health Transition; Humans; Life Expectancy; Male; Middle Aged; Mortality, Premature; Quality-Adjusted Life Years; Socioeconomic Factors; Wounds and Injuries

HLA-G and susceptibility to develop celiac disease. - Catamo, Eulalia; Zupin, Luisa; Segat, Ludovica; Celsi, Fulvio; Crovella, Sergio (Hum Immunol, 2015)
The Human Leukocyte Antigen-G has immunomodulatory function and its expression has been associated with several diseases. In our study we analyzed HLA-G polymorphisms in order to evaluate their possible association with susceptibility to celiac disease development. A total of 420 celiac patients and 509 controls were genotyped for HLA-G polymorphisms. We sequenced 800bp upstream the ATG codon (5' upstream regulatory region) and the whole 3' untranslated region of the HLA-G gene, whereas the ΔC deletion at exon 3 was detected by RFLP-PCR. Five polymorphisms (namely -477 C>G, -369 C>A, 14bp del/ins, 3187 A>G, 3196 C>G) and one haplotype (TCGGTACGAAITCCCGAG) were significantly more frequent in celiac patients than controls and associated with increased disease susceptibility. The 14bp I/I, 3187 G/G, 3196 G/G genotypes and TCGGTACGAAITCCCGAG haplotype, were still significantly associated with increased disease susceptibility (and in addition also the 3003 C/C genotype) when the analysis was restricted to patients and controls presenting the DQ2.5 or DQ8 HLA-DQ celiac disease risk haplotypes. Our findings indicate an association between HLA-G gene polymorphisms and susceptibility to celiac disease development, suggesting that HLA-G molecule is possibly involved in the pathogenesis of the disease.
Keywords: Adolescent; Adult; Alleles; Case-Control Studies; Celiac Disease; Child; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; HLA-DQ Antigens; HLA-G Antigens; Humans; Male; Middle Aged; Polymorphism, Genetic; Retrospective Studies

Impact of DEFB1 gene regulatory polymorphisms on hBD-1 salivary concentration. - Polesello, Vania; Zupin, Luisa; Di Lenarda, Roberto; Biasotto, Matteo; Ottaviani, Giulia; Gobbo, Margherita; Cecco, Luca; Alberi, Giulia; Pozzato, Gabriele; Crovella, Sergio; Segat, Ludovica (Arch Oral Biol, 2015)
OBJECTIVES: Human β-defensin 1 (hBD-1) is an antimicrobial peptide involved in epithelial defence of various tissues, also present in the saliva. Individual genetic variations within the DEFB1 gene, encoding for hBD-1, could influence gene expression and protein production. DESIGN: Three DEFB1 polymorphisms at 5' untranslated region (UTR), -52G > A (rs1799946), -44C > G (rs1800972) and -20G > A (rs11362), and two polymorphisms at DEFB1 3' UTR, c*5G > A (rs1047031) and c*87A > G (rs1800971), were analysed by direct sequencing and correlated with hDB-1 salivary concentration (tested with enzyme-linked immunosorbent assay (ELISA)) in 40 healthy subjects. RESULTS: Significant associations were found between individuals presenting different DEFB1 polymorphisms at positions -52 and -44 of the gene and hBD-1 salivary concentrations: -52 G/G carriers had higher levels of protein than G/A and A/A; -44C/G subjects showed a higher protein concentration than homozygous wild-type C/C. For the -20G > A, c*5G > A and c*87A > G polymorphisms, no statistically significant differences were found. Combined haplotype analysis confirmed the results obtained considering the single-nucleotide polymorphisms (SNPs) singularly. CONCLUSION: Polymorphisms in the DEFB1 gene influence hBD-1 production and, therefore, could modify the innate immune system responses and, consequently, the oral health.

Improved imputation of low-frequency and rare variants using the UK10K haplotype reference panel. - Huang, Jie; Howie, Bryan; McCarthy, Shane; Memari, Yasin; Walter, Klaudia; Min, Josine L; Danecek, Petr; Malerba, Giovanni; Trabetti, Elisabetta; Zheng, Hou-Feng; Gambaro, Giovanni; Richards, J Brent; et al. (Nat Commun, 2015)
Imputing genotypes from reference panels created by whole-genome sequencing (WGS) provides a cost-effective strategy for augmenting the single-nucleotide polymorphism (SNP) content of genome-wide arrays. The UK10K Cohorts project has generated a data set of 3,781 whole genomes sequenced at low depth (average 7x), aiming to exhaustively characterize genetic variation down to 0.1% minor allele frequency in the British population. Here we demonstrate the value of this resource for improving imputation accuracy at rare and low-frequency variants in both a UK and an Italian population. We show that large increases in imputation accuracy can be achieved by re-phasing WGS reference panels after initial genotype calling. We also present a method for combining WGS panels to improve variant coverage and downstream imputation accuracy, which we illustrate by integrating 7,562 WGS haplotypes from the UK10K project with 2,184 haplotypes from the 1000 Genomes Project. Finally, we introduce a novel approximation that maintains speed without sacrificing imputation accuracy for rare variants.

Interleukin-18 gene promoter polymorphisms and celiac disease in Italian patients. - Zupin, Luisa; Catamo, Eulalia; Polesello, Vania; Crovella, Sergio; Segat, Ludovica (Mol Biol Rep, 2015)
Celiac disease (CD) is the most common food-sensitive enteropathy in genetically susceptible individuals. The major genetic risk factors known are specific human leukocyte antigen (HLA)-DQ haplotypes, but other genetic factors are supposed to be involved. Interleukin-18 (IL-18) is a pro-inflammatory cytokine that has an important role in the immune defense and it has the potential to influence inflammatory disorders. IL-18 is able to promote Th1 cell development and it is expressed in the mucosa of the small intestine in celiac patients. Given the IL-18 biological role, and since a few studies have previously suggested its involvement in CD, in order to investigate the role of IL18 gene in the susceptibility to CD we have performed a case-control study, analyzing two IL18 gene promoter polymorphisms, previously reported to impair the transcriptional activity of the gene, (-137G > C and -607C > A, rs187238 and rs1946518 respectively). A total of 556 CD Italian patients and 582 controls, further stratified for HLA class II (DQ) CD risk haplotypes were enrolled. The -607A > C A allele and A/A genotype, as well as the combination of this allele with the -137G allele in the AG haplotype, were associated with an increased risk towards CD development, in particular in HLA-DQ2.2 patients. Although the association was very moderate, our results indicate the possible involvement of IL18 gene in the susceptibility to CD, and for this reason we do think it should deserve further investigation.

Kinetic Profiles of Inflammatory Mediators in the Conjunctival Sac Fluid of Patients upon Photorefractive Keratectomy. - Tisato, Veronica; Perri, Paolo; Rimondi, Erika; Melloni, Elisabetta; Lamberti, Giuseppe; Milani, Daniela; Secchiero, Paola; Zauli, Giorgio (Mediators Inflamm, 2015)
Photorefractive keratectomy (PRK) represents a therapeutic option to remodel corneal stroma and to compensate refractive errors, which involves inflammatory and/or regenerative processes. In this context, the modulation of cytokines/chemokines in the conjunctival sac fluid and their role in the maintenance of the corneal microenvironment during the healing process upon refractive procedures has not been deeply investigated. In this study, serial samples of conjunctival sac fluid of patients (n = 25) undergoing PRK were harvested before and at different time points after surgery. The levels of 29 cytokines/chemokines/growth factors involved in inflammatory/immune processes were measured with a multiplex array system. The results have firstly highlighted the different pattern of cytokine expression between the microenvironment at the anterior surface of the eye and the systemic circulation. More importantly, the kinetic of modulation of cytokines/chemokines at the conjunctival level following PRK revealed that while the majority of cytokines/chemokines showed a significant decrease, MCP-1 emerged in light of its pronounced and significant increase soon after PRK and during the follow-up. This methodological approach has highlighted the role of MCP-1 in the healing process following PRK and has shown a potential for the identification of expression/modulation of soluble factors for biomarker profiling in ocular surface diseases.

Lactotransferrin gene functional polymorphisms do not influence susceptibility to human immunodeficiency virus-1 mother-to-child transmission in different ethnic groups. - Zupin, Luisa; Polesello, Vania; Coelho, Antônio Victor Campos; Boniotto, Michele; Arraes, Luiz Claudio; Segat, Ludovica; Crovella, Sergio (Mem Inst Oswaldo Cruz, 2015)
Lactotransferrin, also known as lactoferrin, is an iron binding glycoprotein that displays antiviral activity against many different infectious agents, including human immunodeficiency virus (HIV)-1. Lactotransferrin is present in the breast milk and in the female genitourinary mucosa and it has been hypothesised as a possible candidate to prevent mother-to-child HIV-1 transmission. To verify if two functional polymorphisms, Thr29Ala and Arg47Lys, in the lactotransferrin encoding gene (LTF) could affect HIV-1 infection and vertical transmission, a preliminary association study was performed in 238 HIV-1 positive and 99 HIV-1 negative children from Brazil, Italy, Africa and India. No statistically significant association for the Thr29Ala and Arg47Lys LTF polymorphisms and HIV-1 susceptibility in the studied populations was found. Additionally LTF polymorphisms frequencies were compared between the four different ethnic groups.
Keywords: Acquired Immunodeficiency Syndrome; Adolescent; Brazil; Child; Cohort Studies; Ethnic Groups; Female; Gene Frequency; Genetic Predisposition to Disease; Genotyping Techniques; HIV-1; Humans; India; Infant, Newborn; Infectious Disease Transmission, Vertical; Italy; Lactoferrin; Male; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction; Retrospective Studies; Zimbabwe

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.

MBL2 polymorphisms in women with atypical squamous cells of undetermined significance. - Zupin, Luisa; Polesello, Vania; Casalicchio, Giorgia; Freato, Nadia; Maestri, Iva; Comar, Manola; Crovella, Sergio; Segat, Ludovica (J Med Virol, 2015)
Infection with high risk Human papillomavirus (HPV) is the main known cause of cervical cancer. HPV induces different grades of lesions: among them, Atypical squamous cells of undetermined significance are abnormal lesions that could evolve in pre-cancer lesions or spontaneously regress. The mannose binding lectin (MBL) is an innate immunity serum protein also found in cervico-vaginal mucosa, whose expression is known to be affected by polymorphisms in exon 1 and promoter of the MBL2 gene. In the present study the possible association between MBL2 functional polymorphisms and susceptibility to develop atypical squamous cells of undetermined significance was investigated in a group of women from North-East of Italy, stratified for HPV infection status. The MBL2 D and O alleles and the deficient producer combined genotypes, responsible for low MBL production, were more represented among atypical squamous cells of undetermined significance positive women than healthy controls and the results were confirmed when only HPV negative samples were considered. These results suggest a possible involvement of MBL2 functional polymorphisms in atypical squamous cells of undetermined significance susceptibility.
Keywords: Adolescent; Adult; Atypical Squamous Cells of the Cervix; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Italy; Mannose-Binding Lectin; Polymorphism, Single Nucleotide; Young Adult

Metal accumulation in the renal cortex of a pediatric patient with sickle cell disease: a case report and review of the literature. - Maximova, Natalia; Zanon, Davide; Pascolo, Lorella; Zennaro, Floriana; Gregori, Massimo; Grosso, Daniele; Sonzogni, Aurelio (J Pediatr Hematol Oncol, 2015)
BACKGROUND: Sickle cell disease (SCD) is a well-known multisystem illness characterized by vascular injury due to vasoocclusion and hemolysis, as well as infectious complications and iron overload, all of which contribute to high morbidity and mortality rates among children. In these patients, some authors have previously described iron cortical deposition in the kidney. We here report the first case in the literature of a girl affected by SCD showing an anomalous metal and rare element retention in the renal cortex. CASE PRESENTATION: A 10-year-old white girl affected by SCD underwent a routine magnetic resonance imaging investigation that evidenced a reduced signal intensity in the renal cortex, compatible with hemosiderin precipitation. Histologic and elemental analyses of the hepatic and the renal biotic samples, performed with inductively coupled plasma mass spectrometry, revealed that concomitant with the high iron deposition, toxic and potentially carcinogenic elements such as nickel, magnesium, rubidium, and gadolinuim were anomalously retained particularly in the kidney. CONCLUSIONS: The finding of rare and toxic elements in the kidney of SCD patients might be linked to the development of specific neoplastic transformations already described in this patient cohort. To be confirmed, our speculations need to be demonstrated in large sampling of patients.
Keywords: Anemia, Sickle Cell; Child; Female; Humans; Kidney Cortex; Metals; Spectrophotometry, Atomic

Music Training Increases Phonological Awareness and Reading Skills in Developmental Dyslexia: A Randomized Control Trial. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Montico, Marcella; Zoia, Stefania; Schön, Daniele (PLoS One, 2015)
There is some evidence for a role of music training in boosting phonological awareness, word segmentation, working memory, as well as reading abilities in children with typical development. Poor performance in tasks requiring temporal processing, rhythm perception and sensorimotor synchronization seems to be a crucial factor underlying dyslexia in children. Interestingly, children with dyslexia show deficits in temporal processing, both in language and in music. Within this framework, we test the hypothesis that music training, by improving temporal processing and rhythm abilities, improves phonological awareness and reading skills in children with dyslexia. The study is a prospective, multicenter, open randomized controlled trial, consisting of test, rehabilitation and re-test (ID NCT02316873). After rehabilitation, the music group (N = 24) performed better than the control group (N = 22) in tasks assessing rhythmic abilities, phonological awareness and reading skills. This is the first randomized control trial testing the effect of music training in enhancing phonological and reading abilities in children with dyslexia. The findings show that music training can modify reading and phonological abilities even when these skills are severely impaired. Through the enhancement of temporal processing and rhythmic skills, music might become an important tool in both remediation and early intervention programs.Trial Registration: ClinicalTrials.gov NCT02316873

New genetic loci link adipose and insulin biology to body fat distribution. - Shungin, Dmitry; Winkler, Thomas W; Croteau-Chonka, Damien C; Ferreira, Teresa; Locke, Adam E; Mägi, Reedik; Strawbridge, Rona J; Pers, Tune H; Fischer, Krista; Justice, Anne E; Workalemahu, Tsegaselassie; Wu, Joseph M W; et al. (Nature, 2015)
Body fat distribution is a heritable trait and a well-established predictor of adverse metabolic outcomes, independent of overall adiposity. To increase our understanding of the genetic basis of body fat distribution and its molecular links to cardiometabolic traits, here we conduct genome-wide association meta-analyses of traits related to waist and hip circumferences in up to 224,459 individuals. We identify 49 loci (33 new) associated with waist-to-hip ratio adjusted for body mass index (BMI), and an additional 19 loci newly associated with related waist and hip circumference measures (P < 5 × 10(-8)). In total, 20 of the 49 waist-to-hip ratio adjusted for BMI loci show significant sexual dimorphism, 19 of which display a stronger effect in women. The identified loci were enriched for genes expressed in adipose tissue and for putative regulatory elements in adipocytes. Pathway analyses implicated adipogenesis, angiogenesis, transcriptional regulation and insulin resistance as processes affecting fat distribution, providing insight into potential pathophysiological mechanisms.
Keywords: Adipocytes; Adipogenesis; Adipose Tissue; Age Factors; Body Fat Distribution; Body Mass Index; Continental Population Groups; Epigenesis, Genetic; Europe; Female; Genome, Human; Genome-Wide Association Study; Humans; Insulin; Insulin Resistance; Male; Models, Biological; Neovascularization, Physiologic; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Sex Characteristics; Transcription, Genetic; Waist-Hip Ratio

New lenses to look at preeclampsia. - Zullino, Sara; Di Martino, Daniela; Stampalija, Tamara; Ferrazzi, Enrico (Gynecol Endocrinol, 2015)

Normal saline flushes performed once daily maintain peripheral intravenous catheter patency: a randomised controlled trial. - Schreiber, Silvana; Zanchi, Chiara; Ronfani, Luca; Delise, Anna; Corbelli, Alessandra; Bortoluzzi, Rosamaria; Taddio, Andrea; Barbi, Egidio (Arch Dis Child, 2015)
OBJECTIVE: Recent evidence supports the use of normal saline flushes in place of heparin to maintain the patency of peripheral intravenous locks (IVLs); however, there are no data regarding the recommended flush frequency. STUDY DESIGN: This was an open, non-inferiority, randomised controlled trial. Children with IVLs, aged 1-17 years, were randomly assigned to receive saline flushing every 12 h (group A) or every 24 h (group B). The main outcome was the maintenance of catheter patency. RESULTS: Four hundred patients were randomised; 198 subjects were analysed in the 12 h group and 199 in the 24 h group (three patients were lost at follow-up). Occlusion occurred in 15 children (7.6%) in group A versus 9 (4.5%) in group B (p=0.21). The difference in catheter patency was +3.1% in favour of the 24 h group (95% CI -1.6% to 7.7%), showing the non-inferiority of the 24 h procedure (the non-inferiority margin was set at -4%). Catheter-related complications were not different between the two groups (12.1% in group A vs 9.5% in group B; p=0.42). CONCLUSIONS: A flushing procedure with one flush per day allows maintenance of catheter patency without an increase in catheter-related complications. We propose a simplification of the flushing procedure with only one flush per day, thereby reducing costs (materials use and nursing time), labour and unnecessary manipulation of the catheters which can cause distress in younger children and their parents. TRIAL REGISTRATION NUMBER: The study is registered in the international database ClinicalTrial.gov under registration number NCT02221024.
Keywords: Adolescent; Catheterization, Peripheral; Catheters, Indwelling; Child; Child, Preschool; Equipment Failure; Female; Humans; Infant; Male; Outcome Assessment (Health Care); Risk Assessment; Sodium Chloride; Therapeutic Irrigation

The novel dual PI3K/mTOR inhibitor NVP-BGT226 displays cytotoxic activity in both normoxic and hypoxic hepatocarcinoma cells. - Simioni, Carolina; Cani, Alice; Martelli, Alberto M; Zauli, Giorgio; Alameen, Ayman A M; Ultimo, Simona; Tabellini, Giovanna; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
Hepatocellular carcinoma (HCC) is one of the most common lethal human malignancies worldwide and its advanced status is frequently resistant to conventional chemotherapeutic agents and radiation. We evaluated the cytotoxic effect of the orally bioavailable dual PI3K/mTOR inhibitor, NVP-BGT226, on a panel of HCC cell lines, since hyperactivated PI3K/Akt/mTOR signaling pathway could represent a biomolecular target for Small Inhibitor Molecules in this neoplasia. We analyzed the drug activity in both normoxia and hypoxia conditions, the latter playing often a relevant role in the induction of chemoresistance and angiogenesis.In normoxia NVP-BGT226 caused cell cycle arrest in the G0/G1 phase of the cell cycle, induced apoptosis and autophagy at low concentrations. Interestingly the drug inactivated p-Akt and p-S6 at < 10 nM concentration.In hypoxia NVP-BGT226 maintained its cytotoxic efficacy at the same concentration as documented by MTT assays and Western blot analysis. Moreover, the drug showed in hypoxia inhibitory properties against angiogenesis by lowering the expression of the transcription factor HIF-1α and of VEGF.Our results indicate that NVP-BGT226 has a potent cytotoxic effect on HCC cell lines also in hypoxia condition, thus emerging as a potential candidate for cancer treatment in HCC targeted therapy.

Orofacial granulomatosis in children: think about Crohn's disease. - Lazzerini, Marzia; Martelossi, Stefano; Cont, Gabriele; Bersanini, Chiara; Ventura, Giovanna; Fontana, Massimo; Zuin, Giovanna; Ventura, Alessandro; Taddio, Andrea (Dig Liver Dis, 2015)
BACKGROUND: The term orofacial granulomatosis is conventionally used to describe patients with granulomatous lesions affecting the orofacial tissues, in absence of intestinal lesions. Lip swelling and facial swelling are the most common clinical signs. Despite the fact that histologically it is not distinguishable from Crohn's disease, and that both diseases have a chronic/recurrent course, the relationship between orofacial granulomatosis and Crohn's disease is still debated. METHODS: Herein we present five cases of orofacial granulomatosis. RESULTS: All patients presented concomitant Crohn's disease, supporting the hypothesis that orofacial granulomatosis and Crohn's disease may be one single disease. Thalidomide was effective in inducing remission of oral and intestinal symptoms in all five cases and could be considered a valid treatment opportunity for these patients. CONCLUSIONS: Orofacial granulomatosis and Crohn's disease may be part of the same disease; both may respond to thalidomide.
Keywords: Adolescent; Biopsy; Child; Colonoscopy; Crohn Disease; Diagnosis, Differential; Female; Granulomatosis, Orofacial; Humans; Immunosuppressive Agents; Male; Thalidomide

The p.Cys169Tyr variant of connexin 26 is not a polymorphism. - Zonta, Francesco; Girotto, Giorgia; Buratto, Damiano; Crispino, Giulia; Morgan, Anna; Abdulhadi, Khalid; Alkowari, Moza; Badii, Ramin; Gasparini, Paolo; Mammano, Fabio (Hum Mol Genet, 2015)
Mutations in the GJB2 gene, which encodes the gap junction protein connexin 26 (Cx26), are the primary cause of hereditary prelingual hearing impairment. Here, the p.Cys169Tyr missense mutation of Cx26 (Cx26C169Y), previously classified as a polymorphism, has been identified as causative of severe hearing loss in two Qatari families. We have analyzed the effect of this mutation using a combination of confocal immunofluorescence microscopy and molecular dynamics simulations. At the cellular level, our results show that the mutant protein fails to form junctional channels in HeLa transfectants despite being correctly targeted to the plasma membrane. At the molecular level, this effect can be accounted for by disruption of the disulfide bridge that Cys169 forms with Cys64 in the wild-type structure (Cx26WT). The lack of the disulfide bridge in the Cx26C169Y protein causes a spatial rearrangement of two important residues, Asn176 and Thr177. In the Cx26WT protein, these residues play a crucial role in the intra-molecular interactions that permit the formation of an intercellular channel by the head-to-head docking of two opposing hemichannels resident in the plasma membrane of adjacent cells. Our results elucidate the molecular pathogenesis of hereditary hearing loss due to the connexin mutation and facilitate the understanding of its role in both healthy and affected individuals.
Keywords: Alleles; Amino Acid Substitution; Cell Line; Connexins; Female; Gap Junctions; Gene Expression; Genotype; Hearing Loss; Humans; Immunohistochemistry; Male; Models, Molecular; Mutation, Missense; Pedigree; Polymorphism, Genetic; Protein Conformation; Protein Interaction Domains and Motifs; Transfection

Pediatric patients with inflammatory bowel disease exhibit increased serum levels of proinflammatory cytokines and chemokines, but decreased circulating levels of macrophage inhibitory protein-1β, interleukin-2 and interleukin-17. - Kleiner, Giulio; Zanin, Valentina; Monasta, Lorenzo; Crovella, Sergio; Caruso, Lorenzo; Milani, Daniela; Marcuzzi, Annalisa (Exp Ther Med, 2015)
Inflammatory bowel disease (IBD) is a chronic and progressive inflammatory condition of the gastrointestinal tract. Although the causative events that lead to the onset of IBD are yet to be fully elucidated, deregulation of immune and inflammatory mechanisms are hypothesized to significantly contribute to this disorder. Since the onset of IBD is often during infancy, in the present study, the serum values of a large panel of cytokines and chemokines in pediatric patients (<18 years; n=26) were compared with age-matched controls (n=37). While elevations in the serum level of several proinflammatory and immune regulating cytokines were confirmed, such as interleukin (IL)-1β, IL-5, IL-7, interferon (IFN)-γ-inducible protein-10, IL-16, cutaneous T-cell-attracting chemokine, leukemia inhibitory factor, monokine induced by γ-IFN, IFN-α2 and IFN-γ, notably decreased levels of IL-2, IL-17 and macrophage inhibitory protein-1β were also observed. Therefore, while a number of proinflammatory cytokines exhibit increased levels in IBD patients, pediatric IBD patients may also exhibit certain aspects of a reduced immunological response.

Prevalence of celiac disease in patients with severe food allergy. - Pillon, R; Ziberna, F; Badina, L; Ventura, A; Longo, G; Quaglia, S; De Leo, L; Vatta, S; Martelossi, S; Patano, G; Not, T; Berti, I (Allergy, 2015)
The association between food allergy and celiac disease (CD) is still to be clarified. We screened for CD 319 patients with severe food allergy (IgE > 85 kU/l against food proteins and a history of severe allergic reactions) who underwent specific food oral immunotherapy (OIT), together with 128 children with mild allergy who recovered without OIT, and compared the prevalence data with our historical data regarding healthy schoolchildren. Sixteen patients (5%) with severe allergy and one (0.8%) with mild allergy tested positive for both genetic and serological CD markers, while the prevalence among the schoolchildren was 1%. Intestinal biopsies were obtained in 13/16 patients with severe allergy and in the one with mild allergy, confirming the diagnosis of CD. Sufferers from severe food allergy seem to be at a fivefold increased risk of CD. Our findings suggest that routine screening for CD should be recommended in patients with severe food allergy.

Rare coding variants and X-linked loci associated with age at menarche. - Lunetta, Kathryn L; Day, Felix R; Sulem, Patrick; Ruth, Katherine S; Tung, Joyce Y; Hinds, David A; Esko, Tõnu; Elks, Cathy E; Altmaier, Elisabeth; He, Chunyan; Huffman, Jennifer E; Mihailov, Evelin; et al. (Nat Commun, 2015)
More than 100 loci have been identified for age at menarche by genome-wide association studies; however, collectively these explain only ∼3% of the trait variance. Here we test two overlooked sources of variation in 192,974 European ancestry women: low-frequency protein-coding variants and X-chromosome variants. Five missense/nonsense variants (in ALMS1/LAMB2/TNRC6A/TACR3/PRKAG1) are associated with age at menarche (minor allele frequencies 0.08-4.6%; effect sizes 0.08-1.25 years per allele; P<5 × 10(-8)). In addition, we identify common X-chromosome loci at IGSF1 (rs762080, P=9.4 × 10(-13)) and FAAH2 (rs5914101, P=4.9 × 10(-10)). Highlighted genes implicate cellular energy homeostasis, post-transcriptional gene silencing and fatty-acid amide signalling. A frequently reported mutation in TACR3 for idiopathic hypogonatrophic hypogonadism (p.W275X) is associated with 1.25-year-later menarche (P=2.8 × 10(-11)), illustrating the utility of population studies to estimate the penetrance of reportedly pathogenic mutations. Collectively, these novel variants explain ∼0.5% variance, indicating that these overlooked sources of variation do not substantially explain the 'missing heritability' of this complex trait.

Recommendations for the use of long-term central venous catheter (CVC) in children with hemato-oncological disorders: management of CVC-related occlusion and CVC-related thrombosis. On behalf of the coagulation defects working group and the supportive the - Giordano, Paola; Saracco, Paola; Grassi, Massimo; Luciani, Matteo; Banov, Laura; Carraro, Francesca; Crocoli, Alessandro; Cesaro, Simone; Zanazzo, Giulio Andrea; Molinari, Angelo Claudio (Ann Hematol, 2015)
Central venous catheters (CVC), used for the management of children with hemato-oncological disorders, are burdened by a significant incidence of mechanical, infective, or thrombotic complications. These complications favor an increasing risk in prolongation of hospitalization, extra costs of care, and sometimes severe life-threatening events. No guidelines for the management of CVC-related occlusion and CVC-related thrombosis are available for children. To this aim, members of the coagulation defects working group and the supportive therapy working group of the Italian Association of Pediatric Hematology and Oncology (AIEOP) reviewed the pediatric and adult literature to propose the first recommendations for the management of CVC-related occlusion and CVC-related thrombosis in children with hemato-oncological disorders.
Keywords: Adult; Blood Coagulation Disorders; Catheter Obstruction; Catheterization, Central Venous; Central Venous Catheters; Child; Hematologic Neoplasms; Humans; Risk Factors; Thrombosis

Relapse and metastasis of atypical teratoid/rhabdoid tumor in a boy with neurofibromatosis type 1 treated with recombinant human growth hormone. - Tornese, Gianluca; Faleschini, Elena; Matarazzo, Lorenza; Bibalo, Cristina; Zanazzo, Giulio Andrea; Rabusin, Marco; Tonini, Giorgio; Zennaro, Floriana; Ventura, Alessandro (Neuropediatrics, 2015)
Even though no increased recurrence rate seems to be reported in patients with brain tumors receiving recombinant human growth hormone (rhGH) replacement, in some patients multiple risk factors could put at higher risk for recurrence. In such cases, the decision to start rhGH therapy should be very cautious. A boy with neurofibromatosis type 1 developed an atypical teratoid/rhabdoid tumor (AT/RT) of right cerebellum, treated with surgery, radiotherapy, and chemotherapy. After 3 years of remission, he started rhGH for growth hormone deficiency, having a negative magnetic resonance imaging (MRI) scan. Ten weeks after starting therapy, the boy became symptomatic and MRI showed relapse of AT/RT in the right cerebellum and a new lesion in the brainstem. The boy died of progressive disease. In this case, the connection between AT/RT recurrence and the beginning of rhGH therapy, with a negative pretreatment MRI, cannot be excluded. Additional caution should be used for rhGH in patients with multiple risk factors.
Keywords: Brain Stem Neoplasms; Cerebellar Neoplasms; Child; Human Growth Hormone; Humans; Magnetic Resonance Imaging; Male; Neurofibromatosis 1; Recombinant Proteins; Recurrence; Rhabdoid Tumor; Risk Factors; Teratoma

Romiplostim for secondary thrombocytopenia following allogeneic stem cell transplantation in children. - Maximova, Natalia; Zanon, D; Rovere, F; Maestro, A; Schillani, G; Paparazzo, R (Int J Hematol, 2015)
The outcome of romiplostim for secondary failure of platelet recovery (SFPR) was investigated in children who had undergone hematopoietic stem cell transplantation (HSCT). Seven transfusion-dependent pediatric patients (median age 11 years), with platelet counts below 10 × 10(9)/L, received four weekly doses of subcutaneous romiplostim to treat SFPR developed after HSCT. All patients, except one (patient 4), became platelet transfusion-independent in the second week from the beginning of treatment and no patient needed to discontinue drug treatment because of adverse events. Romiplostim could represent a beneficial first-line treatment, but further studies are required.

Sensorineural hearing loss in very low birth weight infants with histological chorioamnionitis. - Vedovato, Stefania; Lo Iacono, Angela; Morando, Carla; Suppiej, Agnese; Orzan, Eva; Trevisanuto, Daniele; Visentin, Silvia; Cavallin, Francesco; Chiarelli, Silvia; Zanardo, Vincenzo (J Matern Fetal Neonatal Med, 2015)
OBJECTIVE: Histological chorioamnionitis (HCAM) has been associated with inflammatory diseases of preterm infants. Recently we have observed that it increased the risk of speech delay and hearing loss. So the aim of this study was to evaluate the relationship between sensorineural hearing loss (SNHL) of VLBW infants and HCAM. METHODS: We performed an observational study on VLBW infants admitted to the NICU of Padua. Each patient with HCAM was matched with one control without HCAM. All infants underwent hearing screening before discharge by means of automated transient-evoked otoacustic emissions and automated auditory brainstem responses, which were repeated at 3 and 6 months of age with tympanometry measurement. Incidence of SNHL at 6 months of age was compared in the 2 groups and risk factors for hearing loss were studied. RESULTS: Two of 77 (2.6%) newborns with HCAM e 6/73 (8.2%) without it presented SNHL at 6 months of corrected age (p = 0.16). Multivariable logistic regression analysis identified surgical ligation of patent ductus arteriosus (PDA) as independent predictors of SNHL (OR: 5.75, 95% CI 1.34-24.84, p = 0.02), whereas the effect of HCAM on SNHL was only near to statistical significance level. CONCLUSIONS: Surgical ligation of PDA is associated with an increased risk of SNHL in VLBW infants, regardless of HCAM.

Serum anti-tissue transglutaminase antibodies detected during febrile illness may not be produced by the intestinal mucosa. - De Leo, Luigina; Quaglia, Sara; Ziberna, Fabiana; Vatta, Serena; Martelossi, Stefano; Maschio, Massimo; Not, Tarcisio (J Pediatr, 2015)
Anti-transglutaminase antibodies are the diagnostic marker of celiac disease, and are considered to be synthesized only by intestinal B-lymphocytes. During an infectious disease, these antibodies are transiently detected in serum. We show that these infection-triggered antibodies may not originate in the intestinal mucosa and are not an indication of celiac disease.
Keywords: Autoantibodies; Celiac Disease; Child, Preschool; Diagnosis, Differential; Enzyme-Linked Immunosorbent Assay; Female; GTP-Binding Proteins; Humans; Intestinal Mucosa; Male; Transglutaminases

Serum TRAIL levels increase shortly after insulin therapy and metabolic stabilization in children with type 1 diabetes mellitus. - Tornese, Gianluca; Tisato, Veronica; Monasta, Lorenzo; Vecchi Brumatti, Liza; Zauli, Giorgio; Secchiero, Paola (Acta Diabetol, 2015)

Sirolimus Therapy in Congenital Hyperinsulinism: A Successful Experience Beyond Infancy. - Minute, Marta; Patti, Giuseppa; Tornese, Gianluca; Faleschini, Elena; Zuiani, Chiara; Ventura, Alessandro (Pediatrics, 2015)
Congenital hyperinsulinism (CHI) due to diffuse involvement of the pancreas is a challenging and severe illness in children. Its treatment is based on chronic therapy with diazoxide and/or octreotide, followed by partial pancreatectomy, which is often not resolutive. Sirolimus, a mammalian target of rapamycin inhibitor, was reported to be effective in treating CHI in infants. We report here the case of an 8-year-old boy affected by a severe form of CHI due to a biallelic heterozygous ABCC8 mutation who responded to sirolimus with a dramatic improvement in his glucose blood level regulation and quality of life, with no serious adverse events after 6 months of follow-up. To the best of our knowledge, this is the first report of a successful intervention in an older child. It provides a promising basis for further studies comparing sirolimus with other treatments, particularly in older children.

Targeted tumor imaging of anti-CD20-polymeric nanoparticles developed for the diagnosis of B-cell malignancies. - Capolla, Sara; Garrovo, Chiara; Zorzet, Sonia; Lorenzon, Andrea; Rampazzo, Enrico; Spretz, Ruben; Pozzato, Gabriele; Núñez, Luis; Tripodo, Claudio; Macor, Paolo; Biffi, Stefania (Int J Nanomedicine, 2015)
The expectations of nanoparticle (NP)-based targeted drug delivery systems in cancer, when compared with convectional therapeutic methods, are greater efficacy and reduced drug side effects due to specific cellular-level interactions. However, there are conflicting literature reports on enhanced tumor accumulation of targeted NPs, which is essential for translating their applications as improved drug-delivery systems and contrast agents in cancer imaging. In this study, we characterized biodegradable NPs conjugated with an anti-CD20 antibody for in vivo imaging and drug delivery onto tumor cells. NPs' binding specificity mediated by anti-CD20 antibody was evaluated on MEC1 cells and chronic lymphocytic leukemia patients' cells. The whole-body distribution of untargeted NPs and anti-CD20 NPs were compared by time-domain optical imaging in a localized human/mouse model of B-cell malignancy. These studies provided evidence that NPs' functionalization by an anti-CD20 antibody improves tumor pharmacokinetic profiles in vivo after systemic administration and increases in vivo imaging of tumor mass compared to non-targeted NPs. Together, drug delivery and imaging probe represents a promising theranostics tool for targeting B-cell malignancies.

TNF-related apoptosis inducing ligand in ocular cancers and ocular diabetic complications. - Perri, Paolo; Zauli, Giorgio; Gonelli, Arianna; Milani, Daniela; Celeghini, Claudio; Lamberti, Giuseppe; Secchiero, Paola (Biomed Res Int, 2015)
TNF-related apoptosis inducing ligand (TRAIL) is an intensively studied cytokine, in particular for its anticancer activity. The discovery that conjunctival sac fluid contains extremely high levels of soluble TRAIL as compared to other body fluids suggested important implications in the context of the immunological surveillance of the eye, in particular of the anterior surface. In this review, we discuss the potential physiopathologic and therapeutic role of the TRAIL/TRAIL receptor system in a variety of ocular cancers. Moreover, since an increasing amount of data has indicated the important biological activities of the TRAIL/TRAIL receptor systems also in a completely different pathologic context such as diabetes mellitus, in the second part of this review we summarize the currently available data on the involvement of TRAIL in the ocular complications of diabetes mellitus as modulator of the inflammatory and angiogenic response in the eye.
Keywords: Apoptosis; Diabetes Complications; Diabetes Mellitus; Eye Neoplasms; Humans; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

TRAIL modulates the immune system and protects against the development of diabetes. - Bossi, Fleur; Bernardi, Stella; Zauli, Giorgio; Secchiero, Paola; Fabris, Bruno (J Immunol Res, 2015)
TRAIL or tumor necrosis factor (TNF) related apoptosis-inducing ligand is a member of the TNF superfamily of proteins, whose best characterized function is the induction of apoptosis in tumor, infected, or transformed cells through activation of specific receptors. In nontransformed cells, however, the actions of TRAIL are less well characterized. Recent studies suggest that TRAIL may be implicated in the development and progression of diabetes. Here we review TRAIL biological actions, its effects on the immune system, and how and to what extent it has been shown to protect against diabetes.
Keywords: Animals; Diabetes Mellitus; Humans; Immune System; Receptors, TNF-Related Apoptosis-Inducing Ligand; Signal Transduction

Triple Akt inhibition as a new therapeutic strategy in T-cell acute lymphoblastic leukemia. - Cani, Alice; Simioni, Carolina; Martelli, Alberto M; Zauli, Giorgio; Tabellini, Giovanna; Ultimo, Simona; McCubrey, James A; Capitani, Silvano; Neri, Luca M (Oncotarget, 2015)
T-cell acute lymphoblastic leukemia (T-ALL) is an aggressive neoplastic disorder in which chemotherapy resistance and refractory relapses occur, with a poorer prognostic outcome.Constitutively active PI3K/Akt/mTOR pathway is a common feature of T-ALL upregulating cell proliferation, survival and drug resistance. This pathway is currently under clinical trials with small molecules inhibitors (SMI).To verify whether a multi-inhibition treatment against Akt protein could enhance the efficacy of individual drug administration and overcome drug resistance as well as to obtain a decrease in single drug concentration, we tested on T-ALL cell lines the effects of combined treatments with three Akt inhibitors with different mode of action, GSK690693, MK-2206 and Perifosine.In cells with hyperactivated Akt, combined administration of the drugs displayed a significant synergistic and cytotoxic effect and affected PI3K/Akt/mTOR pathway at much lower concentration than single drug use. Highest synergistic effect for full inhibition of Akt was also related to the timing of every drug administration. Furthermore the triple treatment had greater efficacy in inducing cell cycle arrest in G0/G1 phase and both apoptosis and autophagy.Targeting Akt as a key protein of PI3K/Akt/mTOR pathway with multiple drugs might represent a new and promising pharmacological strategy for treatment of T-ALL patients.

Two-dimensional gel electrophoresis analysis of the leiomyoma interstitial fluid reveals altered protein expression with a possible involvement in pathogenesis. - Ura, Blendi; Scrimin, Federica; Zanconati, Fabrizio; Arrigoni, Giorgio; Monasta, Lorenzo; Romano, Andrea; Banco, Rubina; Zweyer, Marina; Milani, Daniela; Ricci, Giuseppe (Oncol Rep, 2015)
Uterine leiomyoma is the most common smooth benign neoplasm. In the present study, we analyzed the global interstitial fluid (IF) profile of leiomyoma vs. normal myometrium to identify protein dysregulation involved in leiomyoma pathogenesis. Two-dimensional gel electrophoresis and mass spectrometry were used to generate and compare the global interstitial fluid profiles of the leiomyoma and of the normal tissue. Two proteins were validated by immunohistochemistry. By comparing the interstitial fluid profile of the leiomyoma with that of the normal myometrium, the levels of seven proteins were found to be significantly different: four structural organization proteins (desmin, prelamin-A/C, transgelin and α-actinin-1), an inflammatory response (α1-antitrypsin), a response to oxidative stress (peroxiredoxin-2), and a folding protein (heat shock 70 kDa protein 1A/1B). Desmin, α1-antitrypsin and peroxiredoxin-2 were upregulated in the leiomyoma, whereas heat shock 70 kDa protein 1A/1B, α-actinin-1, prelamin-A/C and transgelin were downregulated. Desmin and α1-antitrypsin were further validated by immunohistochemistry. By identifying proteins with altered expression levels compared to the myometrium from several pathways of the leiomyoma pathogenesis, we found the leiomyoma interstitial fluid to have a characteristic proteomic profile. A better appreciation of the pathophysiology of the disease can be useful in the development of conservative treatments that serve as viable alternatives to hysterectomy.

Two‑gene mutation in a single patient: Biochemical and functional analysis for a correct interpretation of exome results. - Bianco, Anna Monica; Faletra, Flavio; Vozzi, Diego; Girardelli, Martina; Knowles, Alessandra; Tommasini, Alberto; Zauli, Giorgio; Marcuzzi, Annalisa (Mol Med Rep, 2015)
Next-generation sequencing (NGS) has generated a large amount of sequence data with the requirement of frequent critical revisions of reported mutations. This innovative tool has proved to be effective in detecting pathogenic mutations; however, it requires a certain degree of experience to identify incidental findings. In the present study, whole exome sequencing analysis was performed for the molecular diagnosis and correct genotype/phenotype correlation between parents and a patient presenting with an atypical phenotype. In addition, mevalonic acid quantification and frequency analysis of detected variants in public databases and X‑chromosome inactivation (XCI) studies on the patient's mother were performed. V377I as well as the S135L mutations were identified on the mevalonate kinase deficiency gene and the levels of mevalonic acid in the patient were 5,496 µg/ml. A D59G variation, reported in ESP6500 in two healthy individuals, was found on the Martin Probst syndrome gene (RAB40AL). Based on XCI studies on the patient's mother, it is likely that RAB40AL escapes XCI, while still remaining balanced. In conclusion, the results of the present study indicated that the Martin Probst syndrome is an X‑linked condition, which is probably not caused by RAB40AL mutations. Although NGS is a powerful tool to identify pathogenic mutations, the analysis of genetic data requires expert critical revision of all detected variants.

Ultrastructural Morphology of Sperm from Human Globozoospermia. - Ricci, Giuseppe; Andolfi, Laura; Zabucchi, Giuliano; Luppi, Stefania; Boscolo, Rita; Martinelli, Monica; Zweyer, Marina; Trevisan, Elisa (Biomed Res Int, 2015)
Globozoospermia is a rare disorder characterized by the presence of sperm with round head, lacking acrosome. Coiling tail around the nucleus has been reported since early human studies, but no specific significance has conferred it. By contrast, studies on animal models suggest that coiling tail around the nucleus could represent a crucial step of defective spermatogenesis, resulting in round-headed sperm. No observations, so far, support the transfer of this hypothesis to human globozoospermia. The purpose of this work was to compare ultrastructural morphology of human and mouse model globozoospermic sperm. Sperm have been investigated by using scanning and transmission electron microscopy. The images that we obtained show significant similarities to those described in GOPC knockout mice, an animal model of globozoospermia. By using this model as reference, we were able to identify the probable steps of the tail coiling process in human globozoospermia. Although we have no evidence that there is the same pathophysiology in man and knocked-out mouse, the similarities between these ultrastructural observations in human and those in the experimental model are very suggestive. This is the first demonstration of the existence of relevant morphological homologies between the tail coiling in animal model and human globozoospermia.

Association of serum tumor necrosis factor-related apoptosis inducing ligand with body fat distribution as assessed by dual X-rays absorptiometry. - Cervellati, Carlo; Secchiero, Paola; Bonaccorsi, Gloria; Celeghini, Claudio; Zauli, Giorgio (Mediators Inflamm, 2014)
A low chronic inflammation mediated by cytokine release is considered a major pathogenic mechanism accounting for the higher risk of cardiovascular disease in the overweight/obese population. In this context, although the existence of a possible interaction between soluble tumor necrosis factor- (TNF-) related apoptosis inducing ligand (TRAIL) and quantity and localization, of adiposity in the body has been hypothesized, no studies have yet investigated this link by radiologic techniques able to assess directly fat mass (FM) in different body regions. To address this issue, we assessed body fat distribution by dual X-rays absorptiometry (DXA) in a sample of 103 women and investigated the possible association between the derived adiposity measures and serum TRAIL concentration. The level of TRAIL showed a positive and independent correlation with arms FM (P < 0.05), trunk FM (P < 0.001) and trunk FM% (P < 0.05), total FM and total FM% (P < 0.001 for both), and an inverse association with legs FM% (P < 0.05). Only trunk FM retained a significant correlation (P < 0.05) with TRAIL after adjusting for all the other indices of regional adiposity. In conclusion, from our study it emerged a significant and independent association of serum TRAIL levels with overall, and, mainly, central adiposity. Further studies are needed to longitudinally investigate the cause-effect relationship between change in body fat distribution and TRAIL.
Keywords: Absorptiometry, Photon; Adipose Tissue; Adiposity; Adult; Anthropometry; Female; Gene Expression Regulation; Humans; Inflammation; Linear Models; Menopause; Middle Aged; Overweight; TNF-Related Apoptosis-Inducing Ligand

Autoimmune hematological diseases after allogeneic hematopoietic stem cell transplantation in children: an Italian multicenter experience. - Faraci, Maura; Zecca, Marco; Pillon, Marta; Rovelli, Attilio; Menconi, Maria Cristina; Ripaldi, Mimmo; Fagioli, Franca; Rabusin, Marco; Ziino, Ottavio; Lanino, Edoardo; Locatelli, Franco; Daikeler, Thomas; et al. (Biol Blood Marrow Transplant, 2014)
Autoimmune hematological diseases (AHDs) may occur after allogeneic hematopoietic stem cell transplantation (HSCT), but reports on these complications in large cohorts of pediatric patients are lacking. Between 1998 and 2011, 1574 consecutive children underwent allogeneic HSCT in 9 Italian centers. Thirty-three children (2.1%) developed AHDs: 15 autoimmune hemolytic anemia (45%), 10 immune thrombocytopenia (30%), 5 Evans' syndrome (15%), 2 pure red cell aplasia (6%), and 1 immune neutropenia (3%). The 10-year cumulative incidence of AHDs was 2.5% (95% confidence interval, 1.7 to 3.6). In a multivariate analysis, the use of alternative donor and nonmalignant disease was statistically associated with AHDs. Most patients with AHDs (64%) did not respond to steroids. Sustained complete remission was achieved in 87% of cases with the anti-CD20 monoclonal antibody (rituximab). Four patients (9%) (1 autoimmune hemolytic anemia, 1 Evans' syndrome, 2 immune thrombocytopenia) died at a median of 87 days after AHD diagnosis as a direct or indirect consequence of their disorder. Our data suggest that AHDs are a relatively rare complication occurring after HSCT that usually respond to treatment with rituximab.
Keywords: Child; Child, Preschool; Female; Hematologic Diseases; Hematopoietic Stem Cell Transplantation; Humans; Italy; Male; Remission Induction; Risk Factors; Transplantation Conditioning

C1q as a unique player in angiogenesis with therapeutic implication in wound healing. - Bossi, Fleur; Tripodo, Claudio; Rizzi, Lucia; Bulla, Roberta; Agostinis, Chiara; Guarnotta, Carla; Munaut, Carine; Baldassarre, Gustavo; Papa, Giovanni; Zorzet, Sonia; Ghebrehiwet, Berhane; Ling, Guang Sheng; et al. (Proc Natl Acad Sci U S A, 2014)
We have previously shown that C1q is expressed on endothelial cells (ECs) of newly formed decidual tissue. Here we demonstrate that C1q is deposited in wound-healing skin in the absence of C4 and C3 and that C1q mRNA is locally expressed as revealed by real-time PCR and in situ hybridization. C1q was found to induce permeability of the EC monolayer, to stimulate EC proliferation and migration, and to promote tube formation and sprouting of new vessels in a rat aortic ring assay. Using a murine model of wound healing we observed that vessel formation was defective in C1qa(-/-) mice and was restored to normal after local application of C1q. The mean vessel density of wound-healing tissue and the healed wound area were significantly increased in C1q-treated rats. On the basis of these results we suggest that C1q may represent a valuable therapeutic agent that can be used to treat chronic ulcers or other pathological conditions in which angiogenesis is impaired, such as myocardial ischemia.
Keywords: Animals; Cell Proliferation; Complement C1q; DNA Primers; Endothelial Cells; Enzyme-Linked Immunosorbent Assay; Human Umbilical Vein Endothelial Cells; Humans; Immunoblotting; Immunohistochemistry; In Situ Hybridization; Mice; Mice, Inbred C57BL; Mice, Knockout; Neovascularization, Physiologic; Rats; Rats, Wistar; Real-Time Polymerase Chain Reaction; Wound Healing

Childhood high-risk acute lymphoblastic leukemia in first remission: results after chemotherapy or transplant from the AIEOP ALL 2000 study. - Conter, Valentino; Valsecchi, Maria Grazia; Parasole, Rosanna; Putti, Maria Caterina; Locatelli, Franco; Barisone, Elena; Lo Nigro, Luca; Santoro, Nicola; Aricò, Maurizio; Ziino, Ottavio; Pession, Andrea; Testi, Anna Maria; et al. (Blood, 2014)
The outcome of high-risk (HR) acute lymphoblastic leukemia patients enrolled in the AIEOP-BFM ALL 2000 study in Italy is described. HR criteria were minimal residual disease (MRD) levels ≥10(-3) at day 78 (MRD-HR), no complete remission (CR) at day 33, t(4;11) translocation, and prednisone poor response (PPR). Treatment (2 years) included protocol I, 3 polychemotherapy blocks, delayed intensification (protocol IIx2 or IIIx3), cranial radiotherapy, and maintenance. A total of 312 HR patients had a 5-year event-free survival (EFS) of 58.9% (standard error [SE] = 2.8) and an overall survival of 68.9% (SE = 2.6). In hierarchical order, EFS was 45.9% (4.4) in 132 MRD-HR patients, 41.2% (11.9) in 17 patients with no CR at day 33, 36.4% (14.5) in 11 patients with t(4;11), and 74.0% (3.6) in 152 HR patients only for PPR. No statistically significant difference was found for disease-free survival in patients with very HR features [MRD-HR, no CR at day 33, t(4;11) translocation], given hematopoietic stem cell transplantation (HSCT) (n = 66) or chemotherapy only (n = 88), after adjusting for waiting time to HSCT (5.7 months). Patients at HR only for PPR have a favorable outcome. MRD-HR is associated with poor outcome despite intensive treatment and/or HSCT and may qualify for innovative therapies. The study was registered at www.clinicaltrials.gov as #NCT00613457.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Child; Child, Preschool; Combined Modality Therapy; Female; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Neoplasm, Residual; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Radiotherapy; Remission Induction; Treatment Outcome

Class IV laser therapy as treatment for chemotherapy-induced oral mucositis in onco-haematological paediatric patients: a prospective study. - Chermetz, Maddalena; Gobbo, Margherita; Ronfani, Luca; Ottaviani, Giulia; Zanazzo, Giulio A; Verzegnassi, Federico; Treister, Nathaniel S; Di Lenarda, Roberto; Biasotto, Matteo; Zacchigna, Serena (Int J Paediatr Dent, 2014)
BACKGROUND: Oral mucositis is a debilitating side effect of chemotherapy. Laser therapy has recently demonstrated efficacy in the management of oral mucositis (OM). AIM: This prospective study was conducted to evaluate the efficacy of class IV laser therapy in patients affected by OM. DESIGN: Eighteen onco-haematological paediatric patients receiving chemotherapy and/or haematopoietic stem cell transplantation, prior to total body irradiation, affected by OM, were enrolled in this study. Patients were treated with class IV laser therapy for four consecutive days; the assessment of OM was performed through WHO Oral Mucositis Grading Objective Scale, and pain was evaluated through visual analogue scale. Patients completed a validated questionnaire, and photographs of lesions were taken during each session. Patients were re-evaluated 11 days after the first day of laser therapy. RESULTS: All patients demonstrated improvement in pain sensation, and all mucositis was fully resolved at the 11-day follow-up visit, with no apparent side effects. Laser therapy was well tolerated with remarkable reduction in pain associated with oral mucositis after 1-2 days of laser therapy. CONCLUSIONS: Given class IV laser therapy appears to be safe, non-invasive, and potentially effective, prospective, randomized, controlled trials are necessary to further assess efficacy and to determine optimal treatment parameters.

Curcumin and inflammatory bowel disease: potential and limits of innovative treatments. - Vecchi Brumatti, Liza; Marcuzzi, Annalisa; Tricarico, Paola Maura; Zanin, Valentina; Girardelli, Martina; Bianco, Anna Monica (Molecules, 2014)
Curcumin belongs to the family of natural compounds collectively called curcuminoids and it possesses remarkable beneficial anti-oxidant, anti-inflammatory, anti-cancer, and neuroprotective properties. Moreover it is commonly assumed that curcumin has also been suggested as a remedy for digestive diseases such as inflammatory bowel diseases (IBD), a chronic immune disorder affecting the gastrointestinal tract and that can be divided in two major subgroups: Crohn's disease (CD) and Ulcerative Colitis (UC), depending mainly on the intestine tract affected by the inflammatory events. The chronic and intermittent nature of IBD imposes, where applicable, long-term treatments conducted in most of the cases combining different types of drugs. In more severe cases and where there has been no good response to the drugs, a surgery therapy is carried out. Currently, IBD-pharmacological treatments are generally not curative and often present serious side effects; for this reason, being known the relationship between nutrition and IBD, it is worthy of interesting the study and the development of new dietary strategy. The curcumin principal mechanism is the suppression of IBD inflammatory compounds (NF-κB) modulating immune response. This review summarizes literature data of curcumin as anti-inflammatory and anti-oxidant in IBD, trying to understand the different effects in CD e UC.
Keywords: Animals; Anti-Inflammatory Agents, Non-Steroidal; Chemistry, Pharmaceutical; Clinical Trials as Topic; Curcumin; Humans; Inflammatory Bowel Diseases; Molecular Targeted Therapy; Nanotechnology; Treatment Outcome

DEFB1 polymorphisms are involved in susceptibility to human papillomavirus infection in Brazilian gynaecological patients. - Segat, Ludovica; Zupin, Luisa; Moura, Ronald Rodrigues; Coelho, Antônio Victor Campos; Chagas, Bárbara Simas; de Freitas, Antonio Carlos; Crovella, Sergio (Mem Inst Oswaldo Cruz, 2014)
The human beta defensin 1 (hBD-1) antimicrobial peptide is a member of the innate immune system known to act in the first line of defence against microorganisms, including viruses such as human papillomavirus (HPV). In this study, five functional polymorphisms (namely g-52G>A, g-44C>G and g-20G>A in the 5'UTR and c.*5G>A and c.*87A>G in the 3'UTR) in the DEFB1 gene encoding for hBD-1 were analysed to investigate the possible involvement of these genetic variants in susceptibility to HPV infection and in the development of HPV-associated lesions in a population of Brazilian women. The DEFB1 g-52G>A and c.*5G>A single-nucleotide polymorphisms (SNPs) and the GCAAA haplotype showed associations with HPV-negative status; in particular, the c.*5G>A SNP was significantly associated after multiple test corrections. These findings suggest a possible role for the constitutively expressed beta defensin-1 peptide as a natural defence against HPV in the genital tract mucosa.
Keywords: Adolescent; Adult; Aged; beta-Defensins; Brazil; Case-Control Studies; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Middle Aged; Papillomavirus Infections; Polymorphism, Single Nucleotide; Reproductive Tract Infections; Young Adult

Diagnostic accuracy of ultrasonography for hand bony fractures in paediatric patients. - Neri, Elena; Barbi, Egidio; Rabach, Ingrid; Zanchi, Chiara; Norbedo, Stefania; Ronfani, Luca; Guastalla, Veronica; Ventura, Alessandro; Guastalla, Pierpaolo (Arch Dis Child, 2014)
OBJECTIVE: Hand fractures are common in childhood, and radiography is the standard diagnostic procedure. US has been used to evaluate bone injuries, mainly in adults for long-bone trauma; there are only a few studies about hand fractures in children. The purpose of this study was to evaluate and confirm the safety and applicability of the US diagnostic procedure in comparison to X-ray diagnosis. STUDY DESIGN: This cross-sectional study involved a convenience sample of young patients (between 2 and 17 years old) who were taken to the emergency department due to hand trauma. After clinical assessment, patients with a suspected hand fracture first underwent X-ray, and subsequently US examination by two different operators; a radiologist experienced in US and a trained emergency physician in "double-blind" fashion. US and radiographic findings were then compared, and sensitivity as well as specificity was calculated. RESULTS: A total of 204 patients were enrolled in the study. Seventy-nine fractures of phalanges or metacarpals were detected by standard radiography. When US imaging was performed by an expert radiologist, 72 fractures were detected with sensitivity and a specificity of 91.1% and 97.6%, respectively. Sensitivity and specificity were found to be (respectively) 91.5% and 96.8% when US was performed by the ED physicians. CONCLUSIONS: US imaging showed excellent sensitivity and specificity results in the diagnosis of hand fractures in children. The study also showed a great agreement between the results of the US carried out by the senior radiologist and those carried out by the paediatric emergency physician, suggesting that US can be performed by an ED physician, allowing a rapid and accurate evaluation in ED and could become the first diagnostic approach whenever a hand fracture is suspected.
Keywords: Adolescent; Child; Child, Preschool; Cross-Sectional Studies; Double-Blind Method; Emergency Service, Hospital; Female; Fractures, Bone; Hand Bones; Humans; Italy; Male; Sensitivity and Specificity

DNA mismatch repair gene MSH6 implicated in determining age at natural menopause. - Perry, John R B; Hsu, Yi-Hsiang; Chasman, Daniel I; Johnson, Andrew D; Elks, Cathy; Albrecht, Eva; Andrulis, Irene L; Beesley, Jonathan; Berenson, Gerald S; Bergmann, Sven; Bojesen, Stig E; Bolla, Manjeet K; et al. (Hum Mol Genet, 2014)
The length of female reproductive lifespan is associated with multiple adverse outcomes, including breast cancer, cardiovascular disease and infertility. The biological processes that govern the timing of the beginning and end of reproductive life are not well understood. Genetic variants are known to contribute to ∼50% of the variation in both age at menarche and menopause, but to date the known genes explain <15% of the genetic component. We have used genome-wide association in a bivariate meta-analysis of both traits to identify genes involved in determining reproductive lifespan. We observed significant genetic correlation between the two traits using genome-wide complex trait analysis. However, we found no robust statistical evidence for individual variants with an effect on both traits. A novel association with age at menopause was detected for a variant rs1800932 in the mismatch repair gene MSH6 (P = 1.9 × 10(-9)), which was also associated with altered expression levels of MSH6 mRNA in multiple tissues. This study contributes to the growing evidence that DNA repair processes play a key role in ovarian ageing and could be an important therapeutic target for infertility.
Keywords: Age Factors; DNA-Binding Proteins; Female; Genome-Wide Association Study; Humans; Menopause; Polymorphism, Single Nucleotide

The first trimester gravid serum regulates procalcitonin expression in human macrophages skewing their phenotype in vitro. - Rami, Damiano; La Bianca, Martina; Agostinis, Chiara; Zauli, Giorgio; Radillo, Oriano; Bulla, Roberta (Mediators Inflamm, 2014)
Procalcitonin (PCT) is one of the best diagnostic and prognostic markers in clinical practice, widely used to evaluate the evolution of bacterial infections. Although it is mainly produced by thyroid, during sepsis almost all the peripheral tissues are involved in PCT production. Parenchymal cells have been suggested as the main source of PCT expression; however the contribution of macrophages is not clear yet. In response to environmental cues, tissue macrophages acquire distinct functional phenotypes, ranging from proinflammatory (M1) to anti-inflammatory (M2) phenotype. Macrophages at the fetal-maternal interface show immunosuppressive M2-like activities required for the maintenance of immunological homeostasis during pregnancy. This study aims to clarify the ability to synthesise PCT of fully differentiated (M0), polarized (M1/M2) macrophages and those cultured either in the presence of first trimester gravid serum (GS) or pregnancy hormones. We found out that M1 macrophages upregulate PCT expression following LPS stimulation compared to M0 and M2. The GS downregulates PCT expression in macrophages, skewing them towards an M2-like phenotype. This effect seems only partially mediated by the hormonal milieu. Our findings strengthen the key role of macrophages in counteracting inflammatory stimuli during pregnancy, suggesting PCT as a possible new marker of M1-like macrophages.
Keywords: Biomarkers; Calcitonin; Cells, Cultured; Chorionic Gonadotropin; Estradiol; Female; Gene Expression Regulation; Homeostasis; Humans; Inflammation; Macrophages; Monocytes; Phenotype; Pregnancy; Pregnancy Trimester, First; Protein Precursors; Serum; Up-Regulation

A general approach for haplotype phasing across the full spectrum of relatedness. - O'Connell, Jared; Gurdasani, Deepti; Delaneau, Olivier; Pirastu, Nicola; Ulivi, Sheila; Cocca, Massimiliano; Traglia, Michela; Huang, Jie; Huffman, Jennifer E; Rudan, Igor; McQuillan, Ruth; Fraser, Ross M; et al. (PLoS Genet, 2014)
Many existing cohorts contain a range of relatedness between genotyped individuals, either by design or by chance. Haplotype estimation in such cohorts is a central step in many downstream analyses. Using genotypes from six cohorts from isolated populations and two cohorts from non-isolated populations, we have investigated the performance of different phasing methods designed for nominally 'unrelated' individuals. We find that SHAPEIT2 produces much lower switch error rates in all cohorts compared to other methods, including those designed specifically for isolated populations. In particular, when large amounts of IBD sharing is present, SHAPEIT2 infers close to perfect haplotypes. Based on these results we have developed a general strategy for phasing cohorts with any level of implicit or explicit relatedness between individuals. First SHAPEIT2 is run ignoring all explicit family information. We then apply a novel HMM method (duoHMM) to combine the SHAPEIT2 haplotypes with any family information to infer the inheritance pattern of each meiosis at all sites across each chromosome. This allows the correction of switch errors, detection of recombination events and genotyping errors. We show that the method detects numbers of recombination events that align very well with expectations based on genetic maps, and that it infers far fewer spurious recombination events than Merlin. The method can also detect genotyping errors and infer recombination events in otherwise uninformative families, such as trios and duos. The detected recombination events can be used in association scans for recombination phenotypes. The method provides a simple and unified approach to haplotype estimation, that will be of interest to researchers in the fields of human, animal and plant genetics.
Keywords: Chromosome Mapping; Cohort Effect; Family; Genotype; Haplotypes; Humans; Models, Genetic; Pedigree; Phenotype; Recombination, Genetic

Genetic association study of QT interval highlights role for calcium signaling pathways in myocardial repolarization. - Arking, Dan E; Pulit, Sara L; Crotti, Lia; van der Harst, Pim; Munroe, Patricia B; Koopmann, Tamara T; Sotoodehnia, Nona; Rossin, Elizabeth J; Morley, Michael; Wang, Xinchen; Johnson, Andrew D; Lundby, Alicia; et al. (Nat Genet, 2014)
The QT interval, an electrocardiographic measure reflecting myocardial repolarization, is a heritable trait. QT prolongation is a risk factor for ventricular arrhythmias and sudden cardiac death (SCD) and could indicate the presence of the potentially lethal mendelian long-QT syndrome (LQTS). Using a genome-wide association and replication study in up to 100,000 individuals, we identified 35 common variant loci associated with QT interval that collectively explain ∼8-10% of QT-interval variation and highlight the importance of calcium regulation in myocardial repolarization. Rare variant analysis of 6 new QT interval-associated loci in 298 unrelated probands with LQTS identified coding variants not found in controls but of uncertain causality and therefore requiring validation. Several newly identified loci encode proteins that physically interact with other recognized repolarization proteins. Our integration of common variant association, expression and orthogonal protein-protein interaction screens provides new insights into cardiac electrophysiology and identifies new candidate genes for ventricular arrhythmias, LQTS and SCD.
Keywords: Adult; Aged; Arrhythmias, Cardiac; Calcium Signaling; Death, Sudden, Cardiac; Electrocardiography; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Ventricles; Humans; Long QT Syndrome; Male; Middle Aged; Myocardium; Polymorphism, Single Nucleotide

Genome-wide association study of sexual maturation in males and females highlights a role for body mass and menarche loci in male puberty. - Cousminer, Diana L; Stergiakouli, Evangelia; Berry, Diane J; Ang, Wei; Groen-Blokhuis, Maria M; Körner, Antje; Siitonen, Niina; Ntalla, Ioanna; Marinelli, Marcella; Perry, John R B; Kettunen, Johannes; Jansen, Rick; et al. (Hum Mol Genet, 2014)
Little is known about genes regulating male puberty. Further, while many identified pubertal timing variants associate with age at menarche, a late manifestation of puberty, and body mass, little is known about these variants' relationship to pubertal initiation or tempo. To address these questions, we performed genome-wide association meta-analysis in over 11 000 European samples with data on early pubertal traits, male genital and female breast development, measured by the Tanner scale. We report the first genome-wide significant locus for male sexual development upstream of myocardin-like 2 (MKL2) (P = 8.9 × 10(-9)), a menarche locus tagging a developmental pathway linking earlier puberty with reduced pubertal growth (P = 4.6 × 10(-5)) and short adult stature (p = 7.5 × 10(-6)) in both males and females. Furthermore, our results indicate that a proportion of menarche loci are important for pubertal initiation in both sexes. Consistent with epidemiological correlations between increased prepubertal body mass and earlier pubertal timing in girls, body mass index (BMI)-increasing alleles correlated with earlier breast development. In boys, some BMI-increasing alleles associated with earlier, and others with delayed, sexual development; these genetic results mimic the controversy in epidemiological studies, some of which show opposing correlations between prepubertal BMI and male puberty. Our results contribute to our understanding of the pubertal initiation program in both sexes and indicate that although mechanisms regulating pubertal onset in males and females may largely be shared, the relationship between body mass and pubertal timing in boys may be complex and requires further genetic studies.

Global, regional, and national incidence and mortality for HIV, tuberculosis, and malaria during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Murray, Christopher J L; Ortblad, Katrina F; Guinovart, Caterina; Lim, Stephen S; Wolock, Timothy M; Roberts, D Allen; Dansereau, Emily A; Graetz, Nicholas; Barber, Ryan M; Brown, Jonathan C; Wang, Haidong; Duber, Herbert C; et al. (Lancet, 2014)
BACKGROUND: The Millennium Declaration in 2000 brought special global attention to HIV, tuberculosis, and malaria through the formulation of Millennium Development Goal (MDG) 6. The Global Burden of Disease 2013 study provides a consistent and comprehensive approach to disease estimation for between 1990 and 2013, and an opportunity to assess whether accelerated progress has occured since the Millennium Declaration. METHODS: To estimate incidence and mortality for HIV, we used the UNAIDS Spectrum model appropriately modified based on a systematic review of available studies of mortality with and without antiretroviral therapy (ART). For concentrated epidemics, we calibrated Spectrum models to fit vital registration data corrected for misclassification of HIV deaths. In generalised epidemics, we minimised a loss function to select epidemic curves most consistent with prevalence data and demographic data for all-cause mortality. We analysed counterfactual scenarios for HIV to assess years of life saved through prevention of mother-to-child transmission (PMTCT) and ART. For tuberculosis, we analysed vital registration and verbal autopsy data to estimate mortality using cause of death ensemble modelling. We analysed data for corrected case-notifications, expert opinions on the case-detection rate, prevalence surveys, and estimated cause-specific mortality using Bayesian meta-regression to generate consistent trends in all parameters. We analysed malaria mortality and incidence using an updated cause of death database, a systematic analysis of verbal autopsy validation studies for malaria, and recent studies (2010-13) of incidence, drug resistance, and coverage of insecticide-treated bednets. FINDINGS: Globally in 2013, there were 1·8 million new HIV infections (95% uncertainty interval 1·7 million to 2·1 million), 29·2 million prevalent HIV cases (28·1 to 31·7), and 1·3 million HIV deaths (1·3 to 1·5). At the peak of the epidemic in 2005, HIV caused 1·7 million deaths (1·6 million to 1·9 million). Concentrated epidemics in Latin America and eastern Europe are substantially smaller than previously estimated. Through interventions including PMTCT and ART, 19·1 million life-years (16·6 million to 21·5 million) have been saved, 70·3% (65·4 to 76·1) in developing countries. From 2000 to 2011, the ratio of development assistance for health for HIV to years of life saved through intervention was US$4498 in developing countries. Including in HIV-positive individuals, all-form tuberculosis incidence was 7·5 million (7·4 million to 7·7 million), prevalence was 11·9 million (11·6 million to 12·2 million), and number of deaths was 1·4 million (1·3 million to 1·5 million) in 2013. In the same year and in only individuals who were HIV-negative, all-form tuberculosis incidence was 7·1 million (6·9 million to 7·3 million), prevalence was 11·2 million (10·8 million to 11·6 million), and number of deaths was 1·3 million (1·2 million to 1·4 million). Annualised rates of change (ARC) for incidence, prevalence, and death became negative after 2000. Tuberculosis in HIV-negative individuals disproportionately occurs in men and boys (versus women and girls); 64·0% of cases (63·6 to 64·3) and 64·7% of deaths (60·8 to 70·3). Globally, malaria cases and deaths grew rapidly from 1990 reaching a peak of 232 million cases (143 million to 387 million) in 2003 and 1·2 million deaths (1·1 million to 1·4 million) in 2004. Since 2004, child deaths from malaria in sub-Saharan Africa have decreased by 31·5% (15·7 to 44·1). Outside of Africa, malaria mortality has been steadily decreasing since 1990. INTERPRETATION: Our estimates of the number of people living with HIV are 18·7% smaller than UNAIDS's estimates in 2012. The number of people living with malaria is larger than estimated by WHO. The number of people living with HIV, tuberculosis, or malaria have all decreased since 2000. At the global level, upward trends for malaria and HIV deaths have been reversed and declines in tuberculosis deaths have accelerated. 101 countries (74 of which are developing) still have increasing HIV incidence. Substantial progress since the Millennium Declaration is an encouraging sign of the effect of global action. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Epidemics; Female; Global Health; HIV Infections; Humans; Incidence; Malaria; Male; Mortality; Organizational Objectives; Sex Distribution; Tuberculosis

Global, regional, and national levels and causes of maternal mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Kassebaum, Nicholas J; Bertozzi-Villa, Amelia; Coggeshall, Megan S; Shackelford, Katya A; Steiner, Caitlyn; Heuton, Kyle R; Gonzalez-Medina, Diego; Barber, Ryan; Huynh, Chantal; Dicker, Daniel; Templin, Tara; Wolock, Timothy M; et al. (Lancet, 2014)
BACKGROUND: The fifth Millennium Development Goal (MDG 5) established the goal of a 75% reduction in the maternal mortality ratio (MMR; number of maternal deaths per 100,000 livebirths) between 1990 and 2015. We aimed to measure levels and track trends in maternal mortality, the key causes contributing to maternal death, and timing of maternal death with respect to delivery. METHODS: We used robust statistical methods including the Cause of Death Ensemble model (CODEm) to analyse a database of data for 7065 site-years and estimate the number of maternal deaths from all causes in 188 countries between 1990 and 2013. We estimated the number of pregnancy-related deaths caused by HIV on the basis of a systematic review of the relative risk of dying during pregnancy for HIV-positive women compared with HIV-negative women. We also estimated the fraction of these deaths aggravated by pregnancy on the basis of a systematic review. To estimate the numbers of maternal deaths due to nine different causes, we identified 61 sources from a systematic review and 943 site-years of vital registration data. We also did a systematic review of reports about the timing of maternal death, identifying 142 sources to use in our analysis. We developed estimates for each country for 1990-2013 using Bayesian meta-regression. We estimated 95% uncertainty intervals (UIs) for all values. FINDINGS: 292,982 (95% UI 261,017-327,792) maternal deaths occurred in 2013, compared with 376,034 (343,483-407,574) in 1990. The global annual rate of change in the MMR was -0·3% (-1·1 to 0·6) from 1990 to 2003, and -2·7% (-3·9 to -1·5) from 2003 to 2013, with evidence of continued acceleration. MMRs reduced consistently in south, east, and southeast Asia between 1990 and 2013, but maternal deaths increased in much of sub-Saharan Africa during the 1990s. 2070 (1290-2866) maternal deaths were related to HIV in 2013, 0·4% (0·2-0·6) of the global total. MMR was highest in the oldest age groups in both 1990 and 2013. In 2013, most deaths occurred intrapartum or postpartum. Causes varied by region and between 1990 and 2013. We recorded substantial variation in the MMR by country in 2013, from 956·8 (685·1-1262·8) in South Sudan to 2·4 (1·6-3·6) in Iceland. INTERPRETATION: Global rates of change suggest that only 16 countries will achieve the MDG 5 target by 2015. Accelerated reductions since the Millennium Declaration in 2000 coincide with increased development assistance for maternal, newborn, and child health. Setting of targets and associated interventions for after 2015 will need careful consideration of regions that are making slow progress, such as west and central Africa. FUNDING: Bill & Melinda Gates Foundation.
Keywords: Age Distribution; Cause of Death; Female; Global Health; HIV Infections; Humans; Maternal Mortality; Models, Statistical; Organizational Objectives; Pregnancy; Pregnancy Complications, Infectious; Risk Factors; Socioeconomic Factors; Time Factors

Global, regional, and national levels of neonatal, infant, and under-5 mortality during 1990-2013: a systematic analysis for the Global Burden of Disease Study 2013. - Wang, Haidong; Liddell, Chelsea A; Coates, Matthew M; Mooney, Meghan D; Levitz, Carly E; Schumacher, Austin E; Apfel, Henry; Iannarone, Marissa; Phillips, Bryan; Lofgren, Katherine T; Sandar, Logan; Dorrington, Rob E; et al. (Lancet, 2014)
BACKGROUND: Remarkable financial and political efforts have been focused on the reduction of child mortality during the past few decades. Timely measurements of levels and trends in under-5 mortality are important to assess progress towards the Millennium Development Goal 4 (MDG 4) target of reduction of child mortality by two thirds from 1990 to 2015, and to identify models of success. METHODS: We generated updated estimates of child mortality in early neonatal (age 0-6 days), late neonatal (7-28 days), postneonatal (29-364 days), childhood (1-4 years), and under-5 (0-4 years) age groups for 188 countries from 1970 to 2013, with more than 29,000 survey, census, vital registration, and sample registration datapoints. We used Gaussian process regression with adjustments for bias and non-sampling error to synthesise the data for under-5 mortality for each country, and a separate model to estimate mortality for more detailed age groups. We used explanatory mixed effects regression models to assess the association between under-5 mortality and income per person, maternal education, HIV child death rates, secular shifts, and other factors. To quantify the contribution of these different factors and birth numbers to the change in numbers of deaths in under-5 age groups from 1990 to 2013, we used Shapley decomposition. We used estimated rates of change between 2000 and 2013 to construct under-5 mortality rate scenarios out to 2030. FINDINGS: We estimated that 6·3 million (95% UI 6·0-6·6) children under-5 died in 2013, a 64% reduction from 17·6 million (17·1-18·1) in 1970. In 2013, child mortality rates ranged from 152·5 per 1000 livebirths (130·6-177·4) in Guinea-Bissau to 2·3 (1·8-2·9) per 1000 in Singapore. The annualised rates of change from 1990 to 2013 ranged from -6·8% to 0·1%. 99 of 188 countries, including 43 of 48 countries in sub-Saharan Africa, had faster decreases in child mortality during 2000-13 than during 1990-2000. In 2013, neonatal deaths accounted for 41·6% of under-5 deaths compared with 37·4% in 1990. Compared with 1990, in 2013, rising numbers of births, especially in sub-Saharan Africa, led to 1·4 million more child deaths, and rising income per person and maternal education led to 0·9 million and 2·2 million fewer deaths, respectively. Changes in secular trends led to 4·2 million fewer deaths. Unexplained factors accounted for only -1% of the change in child deaths. In 30 developing countries, decreases since 2000 have been faster than predicted attributable to income, education, and secular shift alone. INTERPRETATION: Only 27 developing countries are expected to achieve MDG 4. Decreases since 2000 in under-5 mortality rates are accelerating in many developing countries, especially in sub-Saharan Africa. The Millennium Declaration and increased development assistance for health might have been a factor in faster decreases in some developing countries. Without further accelerated progress, many countries in west and central Africa will still have high levels of under-5 mortality in 2030. FUNDING: Bill & Melinda Gates Foundation, US Agency for International Development.
Keywords: Child Mortality; Child, Preschool; Global Health; Humans; Infant; Infant Mortality; Infant, Newborn; Organizational Objectives; Risk Factors; Socioeconomic Factors

Hematopoietic stem cell transplantation effects on spinal cord compression in Hurler. - Ferrara, Giovanna; Maximova, Natalia; Zennaro, Floriana; Gregori, Massimo; Tamaro, Paolo (Pediatr Transplant, 2014)
Hurler syndrome type 1 (MPS-1) is an autosomal recessive lysosomal disorder due to the deficiency of the enzyme alpha-L-iduronidase which is necessary for the degradation of dermatan and heparan sulfate. It is characterized by deposit of glycosaminoglycans in tissues, progressive multisystem dysfunction, and early death. HSCT for children with MPS-I is effective, resulting in increased life expectancy and improvement of clinical parameters. The spinal MRI performed on a female 10 yr old undergoing HSCT at the age of 18 months and receiving ERT revealed a considerable decrease in soft tissue around the tip of odontoid causing a significant reduction in spinal cord compression. In light of this result, we suppose that combined ERT and HSCT are successful in Hurler I disease.
Keywords: Bone Marrow Transplantation; Child; Enzyme Replacement Therapy; Female; Glycosaminoglycans; Hematopoietic Stem Cell Transplantation; Humans; Iduronidase; Magnetic Resonance Imaging; Mucopolysaccharidosis I; Odontoid Process; Spinal Cord Compression; Treatment Outcome

Heterogeneity of mesenchymal stromal cells in lymphoproliferative disorders. - Campioni, Diana; Voltan, Rebecca; Tisato, Veronica; Zauli, Giorgio (Front Biosci (Landmark Ed), 2014)
Accumulating evidence indicates that bone marrow microenvironment plays an important role in the pathogenesis of some myeloid and lymphoid hematological malignancies (HM). Among different environmental associated parameters, those related to functional, cytogenetic and immunological integrity of mesenchymal stromal cells (MSC) are particularly relevant. Functional alterations and immunophenotypic abnormalities have been described in MSC obtained from HM patients. These data seem to confirm the defective biological pattern of MSC especially in myeloid diseases, while MSC cytogenetic profile in HM is still an open question, because it is not clear whether BM stromal cells are "culprit or bystander" displaying or not an abnormal karyotype. Contradictory findings were reported in different HM but the functional implications of altered MSC karyotype need to be further addressed also in light of a clinical use of MSC. A "pathological" in vivo supportive function of endogenous MSC, which provide important survival and drug resistance signals to leukemic cells especially in lymphoproliferative disorders, is suggested. Thus, the mechanisms underlying these protective versus cytotoxic effects exerted by MSC on leukemic cells need further investigations.
Keywords: Humans; Immunophenotyping; Karyotyping; Lymphoproliferative Disorders; Mesenchymal Stromal Cells

HLA-G 14 bp deletion/insertion polymorphism and mother-to-child transmission of HIV. - Segat, L; Zupin, L; Kim, H-Y; Catamo, E; Thea, D M; Kankasa, C; Aldrovandi, G M; Kuhn, L; Crovella, S (Tissue Antigens, 2014)
The human leukocyte antigen HLA-G, highly expressed at the maternal-fetal interface, has a pivotal role in mediating immune tolerance. In this study we investigated the influence of HLA-G 14 bp insertion polymorphism in human immunodeficiency virus (HIV)-1 mother-to-child HIV-1 transmission. The 14 bp insertion polymorphism was analyzed among 99 HIV-1 positive mothers and 329 infants born to HIV-positive mothers in Zambia, among whom vertical transmission status and timing had been determined. HLA-G 14 bp insertion polymorphism was detected using a custom TaqMan single nucleotide polymorphisms (SNPs) genotyping assay. Logistic regression was conducted to examine the associations between HLA-G alleles and the risk of HIV transmission. The 14 bp insertion allele was more frequent in HIV exposed-uninfected (EU) infants than in infected infants, and was associated with reduced risk of both in utero (IU) and intrapartum (IP) HIV transmission, after adjusting for maternal cluster of differentiation 4 (CD4) cell count and plasma viral load. Maternal HLA-G 14 bp insertion genotype and HLA-G concordance between mother and child were not associated with the risk of perinatal HIV transmission. The presence of the 14 bp insertion associates with protection toward IU and IP HIV infection in children from Zambia, suggesting that HLA-G could be involved in the vertical transmission of HIV.
Keywords: Adult; Alleles; Base Pairing; Child; Genotype; HIV Infections; HLA-G Antigens; Humans; INDEL Mutation; Infant; Infectious Disease Transmission, Vertical; Mothers; Polymorphism, Genetic; Young Adult

In vitro endothelial cell proliferation assay reveals distinct levels of proangiogenic cytokines characterizing sera of healthy subjects and of patients with heart failure. - Voltan, Rebecca; Zauli, Giorgio; Rizzo, Paola; Fucili, Alessandro; Pannella, Micaela; Marci, Roberto; Tisato, Veronica; Ferrari, Roberto; Secchiero, Paola (Mediators Inflamm, 2014)
Although myocardial angiogenesis is thought to play an important role in heart failure (HF), the involvement of circulating proinflammatory and proangiogenic cytokines in the pathogenesis and/or prognosis of HF has not been deeply investigated. By using a highly standardized proliferation assay with human endothelial cells, we first demonstrated that sera from older (mean age 52 ± 7.6 years; n = 46) healthy donors promoted endothelial cell proliferation to a significantly higher extent compared to sera obtained from younger healthy donors (mean age 29 ± 8.6 years; n = 20). The promotion of endothelial cell proliferation was accompanied by high serum levels of several proangiogenic cytokines. When we assessed endothelial cell proliferation in response to HF patients' sera, we observed that a subset of sera (n = 11) promoted cell proliferation to a significantly lesser extent compared to the majority of sera (n = 18). Also, in this case, the difference between the patient groups in the ability to induce endothelial cell proliferation correlated to significant (P < 0.05) differences in serum proangiogenic cytokine levels. Unexpectedly, HF patients associated to the highest endothelial proliferation index showed the worst prognosis as evaluated in terms of subsequent cardiovascular events in the follow-up, suggesting that high levels of circulating proangiogenic cytokines might be related to a worse prognosis.
Keywords: Adult; Cell Proliferation; Cells, Cultured; Chemokines; Cytokines; Heart Failure; Human Umbilical Vein Endothelial Cells; Humans; Middle Aged; Neovascularization, Pathologic; Prognosis

In vivo detection of polyomaviruses JCV and SV40 in mesenchymal stem cells from human umbilical cords. - Comar, Manola; Delbue, Serena; Zanotta, Nunzia; Valencic, Erica; Piscianz, Elisa; Del Savio, Rossella; Tesser, Alessandra; Tommasini, Alberto; Ferrante, Pasquale (Pediatr Blood Cancer, 2014)
BACKGROUND: Multipotent stromal cells are present in the Wharton's jelly matrix (WJSC) of the umbilical cord and can be used as an allogeneic source of cells to treat immunological disorders. Recently it was demonstrated that adult bone marrow (BM)-derived mesenchimal stromal cells (MSC) are susceptible to infection with viruses showing potential oncogenic properties, such as the polyomavirus JC (JCV). The aim of this study was to investigate the presence of human polyomaviruses (JCV, BK Virus-BKV, SV40, and Merkel cell polyomavirus-MCPyV) in WJSC, and explore the risk of infection. PROCEDURE: MSC samples from 35 umbilical cords were investigated by quantitative Real Time PCRs for the presence of DNA sequences of JCV, BKV, SV40, and MCPyV. RESULTS: JCV DNA was detected in 1/35 (2.8%) of MSC samples, while SV40 DNA was found in 3/35 (8.6%) of the examined samples. None of the samples showed sequences of BKV and MCPyV. CONCLUSIONS: The present study demonstrates the in vivo ability of polyomaviruses to infect WJSC. Since the therapeutic approach with the WJSC has high potentiality and a more intensive use can be easily hypothesized, the need to develop consensus guidelines to detect rare viral infections in MSC is pressing.
Keywords: DNA, Viral; Female; Fetal Blood; Humans; JC Virus; Male; Mesenchymal Stromal Cells; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Increased levels of C-C chemokine RANTES in asbestos exposed workers and in malignant mesothelioma patients from an hyperendemic area. - Comar, Manola; Zanotta, Nunzia; Bonotti, Alessandra; Tognon, Mauro; Negro, Corrado; Cristaudo, Alfonso; Bovenzi, Massimo (PLoS One, 2014)
BACKGROUND: Asbestos-induced mesothelial inflammatory processes are thought to be the basic mechanisms underlying Malignant Mesothelioma (MM) development. Detection of MM often occurs at late stage due to the long and unpredictable latent period and the low incidence in asbestos exposed individuals. The aim of this study was to investigate early immunological biomarkers to characterize the prognostic profile of a possible asbestos-induced disease, in subjects from a MM hyperendemic area. METHODS: The Luminex Multiplex Panel Technology was used for the simultaneous measurement of serum levels of a large panel of 47 analytes, including cytokines and growth factors, from workers previously exposed to asbestos (Asb-workers), asbestos-induced MM patients and healthy subjects. In addition, to explore the influence on serum cytokines profile exerted by SV40 infection, a cofactor in MM development, a quantitative real time PCR was performed for sequences detection in the N-terminal and intronic regions of the SV40 Tag gene. Statistical analysis was done by means of the Mann-Whitney test and the Kruskall-Wallis test for variance analysis. RESULTS: A variety of 25 cytokines linked to pulmonary inflammation and tumor development were found significantly associated with Asb-workers and MM patients compared with healthy controls. A specific pattern of cytokines were found highly expressed in Asb-workers: IFN-alpha (p<0.05), EOTAXIN (p<0.01), RANTES (p<0.001), and in MM patients: IL-12(p40), IL-3, IL-1 alpha, MCP-3, beta-NGF, TNF-beta, RANTES (p<0.001). Notably, the chemokine RANTES measured the highest serum level showing an increased gradient of concentration from healthy subjects to Asb-workers and MM patients (p<0.001), independently of SV40 infection. CONCLUSION: This study shows that, in subjects from an hyperendemic area for MM, the C-C chemokine RANTES is associated with the exposure to asbestos fibres. If validated in larger samples, this factor could have the potential to be a critical biomarker for MM prognosis as recently reported for breast tumor.
Keywords: Aged; Aged, 80 and over; Asbestos; Biomarkers, Tumor; Case-Control Studies; Chemokine CCL5; Cytokines; Endemic Diseases; Gene Expression; Gene Expression Profiling; Humans; Lung Neoplasms; Mesothelioma; Middle Aged; Occupational Exposure; Simian virus 40; Viral Proteins

Interleukin-10 gene promoter polymorphisms in celiac patients from north-eastern Italy. - Zupin, Luisa; Polesello, Vania; Catamo, Eulalia; Crovella, Sergio; Segat, Ludovica (Hum Immunol, 2014)
Celiac disease is a complex chronic intestinal disorder driven by an immune response against the gliadin fraction of gluten: many factors are involved in the pathogenesis of the disease, and among these Interleukin-10 could play an important role. In the present study, the -1082A>G, -819T>C and -592A>C IL10 functional polymorphisms were analyzed in 565 celiac patients and 576 healthy controls from north-eastern Italy, stratified for HLA class II celiac disease risk haplotypes. No significant differences were observed for the three IL10 polymorphisms distribution between celiac patients and controls with the exception of a slightly increased risk for the -1082A allele in HLA-DQ8 male individuals. Although our findings suggest that the IL10 genetic variants analyzed do not have a major role in the susceptibility to the development of celiac disease in north-eastern Italian patients, we think that the possible involvement of IL10 gene in CD should deserve further investigation and that large-scale studies are recommended to confirm our findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alleles; Case-Control Studies; Celiac Disease; Child; Child, Preschool; European Continental Ancestry Group; Female; Gene Frequency; HLA-DQ Antigens; Humans; Interleukin-10; Italy; Male; Middle Aged; Models, Genetic; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Risk Factors; Sex Factors

Intestinal-mucosa anti-transglutaminase antibody assays to test for genetic gluten intolerance. - Quaglia, Sara; De Leo, Luigina; Ziberna, Fabiana; Vatta, Serena; Villanacci, Vincenzo; Granzotto, Marilena; Petix, Vincenzo; Martelossi, Stefano; Di Leo, Grazia; Torelli, Lucio; Not, Tarcisio (Cell Mol Immunol, 2014)
Keywords: Celiac Disease; Cell Surface Display Techniques; Child; Diet, Gluten-Free; Disease Progression; Early Diagnosis; Female; Follow-Up Studies; HLA-DQ Antigens; Humans; Immunoassay; Immunoglobulin A; Intestinal Mucosa; Male; Prospective Studies; Transglutaminases

Inverse correlation between circulating levels of TNF-related apoptosis-inducing ligand and 17β-estradiol. - Zauli, Giorgio; Tisato, Veronica; Melloni, Elisabetta; Volpato, Stefano; Cervellati, Carlo; Bonaccorsi, Gloria; Radillo, Oriano; Marci, Roberto; Secchiero, Paola (J Clin Endocrinol Metab, 2014)
CONTEXT: The regulation of the circulating levels of TNF-related apoptosis-inducing ligand (TRAIL), a cytokine of the TNF family, playing a key role in the immune surveillance against cancer, is incompletely understood. OBJECTIVE: The objective of the study was to investigate the potential link between TRAIL and 17β-estradiol. DESIGN, SETTING, AND PARTICIPANTS: Circulating TRAIL levels were measured by an ELISA in plasma samples (n = 246) of healthy, age-matched (range 30-70 y) men and women and in the sera (n = 180) of females belonging to different physiopathological conditions (childhood, pregnancy, under gonadotropin treatment, menopause) characterized by different levels of circulating 17β-estradiol. RESULTS: TRAIL plasma levels in women with aged younger than 50 years were significantly lower compared with age-matched men, whereas in woman 50 years old or older, TRAIL levels were significantly higher compared with the age-matched men and with the younger women. Moreover, an analysis of women with different conditions revealed a significant inverse correlation between the serum levels of TRAIL and 17β-estradiol, with the lowest levels of TRAIL being observed during pregnancy and the highest in childhood and in postmenopausal women. Moreover, gonadotropin treatment in women undergoing assisted reproduction was accompanied by an acute decrease of serum TRAIL levels. Finally, in vitro treatment with 17β-estradiol decreased the TRAIL expression levels in peripheral blood mononuclear cells. CONCLUSIONS: Our data suggest that 17β-estradiol plays a role in regulating TRAIL circulating levels. The demonstration that postmenopausal women exhibit the highest TRAIL levels is of particular interest in light of a previous large study population showing that TRAIL is positively correlated to the overall survival.
Keywords: Adult; Aged; Case-Control Studies; Child; Child, Preschool; Estradiol; Female; Humans; Infant; Male; Middle Aged; Pregnancy; Sex Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

Long-term follow-up in children with benign convulsions associated with gastroenteritis. - Verrotti, Alberto; Moavero, Romina; Vigevano, Federico; Cantonetti, Laura; Guerra, Azzurra; Spezia, Elisabetta; Tricarico, Antonella; Nanni, Giuliana; Agostinelli, Sergio; Chiarelli, Francesco; Parisi, Pasquale; Capovilla, Giuseppe; et al. (Eur J Paediatr Neurol, 2014)
BACKGROUND: The outcome of benign convulsions associated with gastroenteritis (CwG) has generally been reported as being excellent. However, these data need to be confirmed in studies with longer follow-up evaluations. AIM: To assess the long-term neurological outcome of a large sample of children presenting with CwG. METHODS: We reviewed clinical features of 81 subjects presenting with CwG (1994-2010) from three different Italian centers with a follow-up period of at least 3 years. RESULTS: Follow-up period ranged from 39 months to 15 years (mean 9.8 years). Neurological examination and cognitive level at the last evaluation were normal in all the patients. A mild attention deficit was detected in three cases (3.7%). Fourteen children (17.3%) received chronic anti-epileptic therapy. Interictal EEG abnormalities detected at onset in 20 patients (24.7%) reverted to normal. Transient EEG epileptiform abnormalities were detected in other three cases (3.7%), and a transient photosensitivity in one (1.2%). No recurrence of CwG was observed. Three patients (3.7%) presented with a febrile seizure and two (2.5%) with an unprovoked seizure, but none developed epilepsy. CONCLUSIONS: The long-term evaluation of children with CwG confirms the excellent prognosis of this condition, with normal psychomotor development and low risk of relapse and of subsequent epilepsy.
Keywords: Adolescent; Anticonvulsants; Attention Deficit Disorder with Hyperactivity; Child; Child, Preschool; Electroencephalography; Epilepsy; Female; Gastroenteritis; Humans; Longitudinal Studies; Male; Neurologic Examination; Retrospective Studies

Medical treatments for endometriosis-associated pelvic pain. - Zito, Gabriella; Luppi, Stefania; Giolo, Elena; Martinelli, Monica; Venturin, Irene; Di Lorenzo, Giovanni; Ricci, Giuseppe (Biomed Res Int, 2014)
The main sequelae of endometriosis are represented by infertility and chronic pelvic pain. Chronic pelvic pain causes disability and distress with a very high economic impact. In the last decades, an impressive amount of pharmacological agents have been tested for the treatment of endometriosis-associated pelvic pain. However, only a few of these have been introduced into clinical practice. Following the results of the controlled studies available, to date, the first-line treatment for endometriosis associated pain is still represented by oral contraceptives used continuously. Progestins represent an acceptable alternative. In women with rectovaginal lesions or colorectal endometriosis, norethisterone acetate at low dosage should be preferred. GnRH analogues may be used as second-line treatment, but significant side effects should be taken into account. Nonsteroidal anti-inflammatory drugs are widely used, but there is inconclusive evidence for their efficacy in relieving endometriosis-associated pelvic pain. Other agents such as GnRH antagonist, aromatase inhibitors, immunomodulators, selective progesterone receptor modulators, and histone deacetylase inhibitors seem to be very promising, but there is not enough evidence to support their introduction into routine clinical practice. Some other agents, such as peroxisome proliferator activated receptors-γ ligands, antiangiogenic agents, and melatonin have been proven to be efficacious in animal studies, but they have not yet been tested in clinical studies.
Keywords: Endometriosis; Female; Gonadotropin-Releasing Hormone; Histone Deacetylase Inhibitors; Hormone Antagonists; Humans; Pain Management; Pelvic Pain; Progestins

Modulation of circulating cytokine-chemokine profile in patients affected by chronic venous insufficiency undergoing surgical hemodynamic correction. - Tisato, Veronica; Zauli, Giorgio; Gianesini, Sergio; Menegatti, Erica; Brunelli, Laura; Manfredini, Roberto; Zamboni, Paolo; Secchiero, Paola (J Immunol Res, 2014)
The expression of proinflammatory cytokines/chemokines has been reported in in vitro/ex vivo settings of chronic venous insufficiency (CVI), but the identification of circulating mediators that might be associated with altered hemodynamic forces or might represent innovative biomarkers is still missing. In this study, the circulating levels of 31 cytokines/chemokines involved in inflammatory/angiogenic processes were analysed in (i) CVI patients at baseline before surgical hemody namic correction, (ii) healthy subjects, and (iii) CVI patients after surgery. In a subgroup of CVI patients, in whom the baseline levels of cytokines/chemokines were analyzed in paired blood samples obtained from varicose vein and forearm vein, EGF, PDGF, and RANTES were increased at the varicose vein site as compared to the general circulation. Moreover, while at baseline, CVI patients showed increased levels of 14 cytokines/chemokines as compared to healthy subjects, 6 months after surgery, 11 cytokines/chemokines levels were significantly reduced in the treated CVI patients as compared to the CVI patients before surgery. Of note, a patient who exhibited recurrence of the disease 6 months after surgery, showed higher levels of EGF, PDGF, and RANTES compared to nonrecurrent patients, highlighting the potential role of the EGF/PDGF/RANTES triad as sensitive biomarkers in the context of CVI.
Keywords: Adult; Aged; Chemokines; Chronic Disease; Cytokines; Female; Hemodynamics; Humans; Male; Middle Aged; Saphenous Vein; Varicose Veins; Venous Insufficiency

MYH9-related disease: a novel prognostic model to predict the clinical evolution of the disease based on genotype-phenotype correlations. - Pecci, Alessandro; Klersy, Catherine; Gresele, Paolo; Lee, Kieran J D; De Rocco, Daniela; Bozzi, Valeria; Russo, Giovanna; Heller, Paula G; Loffredo, Giuseppe; Ballmaier, Matthias; Fabris, Fabrizio; Beggiato, Eloise; et al. (Hum Mutat, 2014)
MYH9-related disease (MYH9-RD) is a rare autosomal-dominant disorder caused by mutations in the gene for nonmuscle myosin heavy chain IIA (NMMHC-IIA). MYH9-RD is characterized by a considerable variability in clinical evolution: patients present at birth with only thrombocytopenia, but some of them subsequently develop sensorineural deafness, cataract, and/or nephropathy often leading to end-stage renal disease (ESRD). We searched for genotype-phenotype correlations in the largest series of consecutive MYH9-RD patients collected so far (255 cases from 121 families). Association of genotypes with noncongenital features was assessed by a generalized linear regression model. The analysis defined disease evolution associated to seven different MYH9 genotypes that are responsible for 85% of MYH9-RD cases. Mutations hitting residue R702 demonstrated a complete penetrance for early-onset ESRD and deafness. The p.D1424H substitution associated with high risk of developing all the noncongenital manifestations of disease. Mutations hitting a distinct hydrophobic seam in the NMMHC-IIA head domain or substitutions at R1165 associated with high risk of deafness but low risk of nephropathy or cataract. Patients with p.E1841K, p.D1424N, and C-terminal deletions had low risk of noncongenital defects. These findings are essential to patients' clinical management and genetic counseling and are discussed in view of molecular pathogenesis of MYH9-RD.
Keywords: Adult; Age of Onset; Amino Acid Substitution; Cataract; Female; Genetic Association Studies; Genotype; Hearing Loss, Sensorineural; Humans; Italy; Linear Models; Male; Molecular Motor Proteins; Mutation; Myosin Heavy Chains; Phenotype; Risk Factors; Thrombocytopenia

NF-κB pathways in hematological malignancies. - Gasparini, Chiara; Celeghini, Claudio; Monasta, Lorenzo; Zauli, Giorgio (Cell Mol Life Sci, 2014)
The nuclear factor κB or NF-κB transcription factor family plays a key role in several cellular functions, i.e. inflammation, apoptosis, cell survival, proliferation, angiogenesis, and innate and acquired immunity. The constitutive activation of NF-κB is typical of most malignancies and plays a major role in tumorigenesis. In this review, we describe NF-κB and its two pathways: the canonical pathway (RelA/p50) and the non-canonical pathway (RelB/p50 or RelB/p52). We then consider the role of the NF-κB subunits in the development and functional activity of B cells, T cells, macrophages and dendritic cells, which are the targets of hematological malignancies. The relevance of the two pathways is described in normal B and T cells and in hematological malignancies, acute and chronic leukemias (ALL, AML, CLL, CML), B lymphomas (DLBCLs, Hodgkin's lymphoma), T lymphomas (ATLL, ALCL) and multiple myeloma. We describe the interaction of NF-κB with the apoptotic pathways induced by TRAIL and the transcription factor p53. Finally, we discuss therapeutic anti-tumoral approaches as mono-therapies or combination therapies aimed to block NF-κB activity and to induce apoptosis (PARAs and Nutlin-3).
Keywords: Antineoplastic Agents; B-Lymphocytes; Carcinogenesis; Dendritic Cells; Gene Expression Regulation, Neoplastic; Hematologic Neoplasms; Humans; Imidazoles; Macrophages; NF-kappa B; Piperazines; Signal Transduction; T-Lymphocytes; TNF-Related Apoptosis-Inducing Ligand; Transcription Factor RelA; Transcription Factor RelB; Tumor Suppressor Protein p53

No evidence of Polyomavirus and EBV infections in Italian patients with mixed cryoglobulinemia infected chronically with HCV. - Comar, Manola; Zanotta, Nunzia; Del Savio, Rossella; Vascotto, Fulvia; Calabrese, Nadia; Zorat, Francesca; Pozzato, Gabriele (J Med Virol, 2014)
Mixed cryoglobulinemia is a lymphoproliferative disorder associated with hepatitis C virus (HCV). In patients chronically affected by HCV the prevalence of mixed cryoglobulinemia is variable ranging from 0% to 56%. To verify whether polyomaviruses (PyV) play a role in this disorder a total of 222 blood samples from 63 HCV chronic patients, 43 with mixed cryoglobulinemia, 59 chronic lymphocytic leukemia, 50 polytransfused patients, and 50 blood donors were evaluated for Merkel (MCPyV), BKV, JCV, and SV40. EBV was additionally included in the analysis since association with this disorder has been reported. Mixed cryoglobulinemia patients infected chronically with HCV resulted negative for both PyV and EBV. MCPyV was found in 1 subject with Merkel Cell Carcinoma, in 10% of polytransfused and in 10% of blood donors while EBV was detected in 22% of polytransfused, 10% of B-cell lymphatic leukemia patients and 4% of blood donors (P < 0.01). Taken together, the absence of PyV and EBV in HCV-mixed cryoglobulinemia patients seems to exclude a direct involvement of these viruses in the pathogenesis of this disease while the presence of MCPyV in healthy individuals, at the same rate as in polytransfused patients, may reinforce data on a minimal role of this virus in other human pathologies.
Keywords: Adult; Base Sequence; Cryoglobulinemia; DNA, Viral; Epstein-Barr Virus Infections; Female; Hepacivirus; Hepatitis C, Chronic; Herpesvirus 4, Human; Humans; Italy; Leukemia, B-Cell; Male; Middle Aged; Polyomavirus; Polyomavirus Infections; Sequence Analysis, DNA; Vaginal Smears; Young Adult

Non-classical MHC-I human leukocyte antigen (HLA-G) in hepatotropic viral infections and in hepatocellular carcinoma. - Catamo, Eulalia; Zupin, Luisa; Crovella, Sergio; Celsi, Fulvio; Segat, Ludovica (Hum Immunol, 2014)
The human leukocyte antigen (HLA)-G is a "nonclassical" major histocompatibility complex (MHC) class Ib gene, located at chromosome 6, in the 6p21.3 region. The HLA-G presents immunomodulatory functions essential in pregnancy for the tolerance of the semi-allogenic fetus, but an abnormal expression of HLA-G has been observed in numerous pathological conditions, such as tumors, autoimmune diseases and viral infections. In recent years, numerous studies have assessed the clinical relevance of HLA-G expression in different types of cancer: in general, a higher HLA-G expression correlates with a lower survival rate or a shorter disease-free survival. Altered expression of HLA-G has been found in both HCV and HBV infection, and some genetic polymorphisms have been associated with altered susceptibility/disease development for these infections, however, whether the biologic role of HLA-G in HCV and HBV infection is beneficial or hazardous, it is not completely clear. In the context of hepatocellular carcinoma, HLA-G has shown a potential diagnostic role, moreover a prognostic value in HCC patients has been also attributed to HLA-G molecules. We revise here the role of HLA-G in hepatotropic HBV/HCV infections and in hepatocellular carcinoma (HCC).
Keywords: Carcinoma, Hepatocellular; Female; Genetic Predisposition to Disease; Hepatitis B; Hepatitis C; HLA-G Antigens; Humans; Immune Tolerance; Liver Neoplasms; Polymorphism, Genetic; Pregnancy

Osteoprotegerin increases in metabolic syndrome and promotes adipose tissue proinflammatory changes. - Bernardi, Stella; Fabris, Bruno; Thomas, Merlin; Toffoli, Barbara; Tikellis, Christos; Candido, Riccardo; Catena, Cristiana; Mulatero, Paolo; Barbone, Fabio; Radillo, Oriano; Zauli, Giorgio; Secchiero, Paola (Mol Cell Endocrinol, 2014)
BACKGROUND: Inflammation is believed to link obesity to insulin resistance, as in the setting of metabolic syndrome (MetS). Osteoprotegerin (OPG) is a soluble protein that seems to exert proatherogenic and prodiabetogenic effects. This study aims at determining OPG levels in MetS and whether OPG might contribute to MetS development and progression. METHODOLOGY/PRINCIPAL FINDINGS: Circulating OPG was measured in 46 patients with MetS and 63 controls, and was found significantly elevated in those with MetS. In addition, circulating and tissue OPG was significantly increased in high-fat diet (HFD) fed C57BL6 mice, which is one of the animal models for the study of MetS. To evaluate the consequences of OPG elevation, we delivered this protein to C57BL6 mice, finding that it promoted systemic and adipose tissue proinflammatory changes in association with metabolic abnormalities. CONCLUSIONS/SIGNIFICANCE: These data suggest that OPG may trigger adipose tissue proinflammatory changes in MetS/HFD-induced obesity.
Keywords: Adipose Tissue; Adult; Animals; Blood Glucose; Body Mass Index; C-Reactive Protein; Case-Control Studies; Cholesterol, HDL; Cholesterol, LDL; Diet, High-Fat; Female; Humans; Inflammation; Insulin; Insulin Resistance; Male; Metabolic Syndrome X; Mice; Mice, Inbred C57BL; Middle Aged; Obesity; Osteoprotegerin; Triglycerides

The p53 transcriptional pathway is preserved in ATMmutated and NOTCH1mutated chronic lymphocytic leukemias. - Athanasakis, Emmanouil; Melloni, Elisabetta; Rigolin, Gian Matteo; Agnoletto, Chiara; Voltan, Rebecca; Vozzi, Diego; Piscianz, Elisa; Segat, Ludovica; dal Monego, Simeone; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
By using next generation sequencing, we have analyzed 108 B chronic lymphocytic leukemia (B-CLL) patients. Among genes involved in the TP53 pathway, we found frequent mutations in ATM (n=18), TP53 (n=10) and NOTCH1 (n=10) genes, rare mutations of NOTCH2 (n=2) and CDKN1A/p21 (n=1) and no mutations in BAX, MDM2, TNFRSF10A and TNFRSF10B genes. The in vitro treatment of primary B-CLL cells with the activator of p53 Nutlin-3 induced the transcription of p53 target genes, without significant differences between the B-CLL without mutations and those harboring either ATM or NOTCH1mutations. On the other hand, the subgroup of TP53mutated B-CLL exhibited a significantly lower induction of the p53 target genes in response to Nutlin-3 as compared to the other B-CLL samples. However, among the TP53mutated B-CLL, those showing mutations in the high hot spot region of the DNA binding domain [273-280 aa] maintained a significantly higher p53-dependent transcriptional activity as compared to the other TP53mutated B-CLL samples. Since the ability to elicit a p53-dependent transcriptional activity in vitro has a positive prognostic significance, our data suggest that ATMmutated, NOTCH1mutated and surprisingly, also a subset of TP53mutated B-CLL patients might benefit from therapeutic combinations including small molecule activator of the p53 pathway.
Keywords: Aged; Aged, 80 and over; Ataxia Telangiectasia Mutated Proteins; Base Sequence; Female; Genes, p53; Humans; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Models, Molecular; Molecular Sequence Data; Mutation; Receptor, Notch1; Signal Transduction; Tumor Suppressor Protein p53

Parent-of-origin-specific allelic associations among 106 genomic loci for age at menarche. - Perry, John R B; Day, Felix; Elks, Cathy E; Sulem, Patrick; Thompson, Deborah J; Ferreira, Teresa; He, Chunyan; Chasman, Daniel I; Esko, Tõnu; Thorleifsson, Gudmar; Albrecht, Eva; Ang, Wei Q; et al. (Nature, 2014)
Age at menarche is a marker of timing of puberty in females. It varies widely between individuals, is a heritable trait and is associated with risks for obesity, type 2 diabetes, cardiovascular disease, breast cancer and all-cause mortality. Studies of rare human disorders of puberty and animal models point to a complex hypothalamic-pituitary-hormonal regulation, but the mechanisms that determine pubertal timing and underlie its links to disease risk remain unclear. Here, using genome-wide and custom-genotyping arrays in up to 182,416 women of European descent from 57 studies, we found robust evidence (P < 5 × 10(-8)) for 123 signals at 106 genomic loci associated with age at menarche. Many loci were associated with other pubertal traits in both sexes, and there was substantial overlap with genes implicated in body mass index and various diseases, including rare disorders of puberty. Menarche signals were enriched in imprinted regions, with three loci (DLK1-WDR25, MKRN3-MAGEL2 and KCNK9) demonstrating parent-of-origin-specific associations concordant with known parental expression patterns. Pathway analyses implicated nuclear hormone receptors, particularly retinoic acid and γ-aminobutyric acid-B2 receptor signalling, among novel mechanisms that regulate pubertal timing in humans. Our findings suggest a genetic architecture involving at least hundreds of common variants in the coordinated timing of the pubertal transition.
Keywords: Adolescent; Age Factors; Alleles; Body Mass Index; Breast Neoplasms; Cardiovascular Diseases; Child; Diabetes Mellitus, Type 2; Europe; Female; Genetic Loci; Genome-Wide Association Study; Genomic Imprinting; Humans; Hypothalamo-Hypophyseal System; Intercellular Signaling Peptides and Proteins; Male; Membrane Proteins; Menarche; Obesity; Ovary; Parents; Polymorphism, Single Nucleotide; Potassium Channels, Tandem Pore Domain; Proteins; Quantitative Trait Loci; Receptors, GABA-B; Receptors, Retinoic Acid; Ribonucleoproteins

Piccolipiù, a multicenter birth cohort in Italy: protocol of the study. - Farchi, Sara; Forastiere, Francesco; Vecchi Brumatti, Liza; Alviti, Sabrina; Arnofi, Antonio; Bernardini, Tommaso; Bin, Maura; Brescianini, Sonia; Colelli, Valentina; Cotichini, Rodolfo; Culasso, Martina; De Bartolo, Paolo; et al. (BMC Pediatr, 2014)
BACKGROUND: The fetal and infant life are periods of rapid development, characterized by high susceptibility to exposures. Birth cohorts provide unique opportunities to study early-life exposures in association with child development and health, as well as, with longer follow-up, the early life origin of adult diseases. Piccolipiù is an Italian birth cohort recently set up to investigate the effects of environmental exposures, parental conditions and social factors acting during pre-natal and early post-natal life on infant and child health and development. We describe here its main characteristics. METHODS/DESIGN: Piccolipiù is a prospective cohort of expected 3000 newborns, who will be recruiting in six maternity units of five Italian cities (Florence, Rome, Trieste, Turin and Viareggio) since October 2011. Mothers are contacted during pregnancy or at delivery and are offered to participate in the study. Upon acceptance, their newborns are recruited at birth and followed up until at least 18 years of age. At recruitment, the mothers donate a blood sample and complete a baseline questionnaire. Umbilical cord blood, pieces of umbilical cord and heel blood spots are also collected. Postnatal follow-up currently occurs at 6, 12, and 24 months of age using on-line or postal self administered questionnaire; further questionnaires and medical examinations are envisaged. Questionnaires collect information on several factors, including mother's and/or child's environmental exposures, anthropometric measures, reproductive factors, diet, supplements, medical history, cognitive development, mental health and socioeconomic factors. Health promotion materials are also offered to parents. DISCUSSION: Piccolipiù will broaden our understanding of the contribution of early-life factors to infant and child health and development. Several hypotheses on the developmental origins of health can be tested or piloted using the data collected from the Piccolipiù cohort. By pooling these data with those collected by other existing birth cohorts it will be possible to validate previous findings and to study rare exposures and outcomes.
Keywords: Adolescent; Child; Child Development; Child Welfare; Child, Preschool; Cohort Studies; Environmental Exposure; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Socioeconomic Factors

Potential role of circulating microRNAs as early markers of preeclampsia. - Ura, Blendi; Feriotto, Giordana; Monasta, Lorenzo; Bilel, Sabrine; Zweyer, Marina; Celeghini, Claudio (Taiwan J Obstet Gynecol, 2014)
OBJECTIVE: To identify microRNAs (miRNAs) differentially expressed at early stages of gestation (12-14 weeks) in the serum of pregnant women, who later developed severe preeclampsia (sPE) in the third trimester of pregnancy (n = 24) compared to women with normal pregnancy (n = 24). MATERIALS AND METHODS: Sera from 12-14-week-gestation whole blood were subjected to microarray analysis with TaqMan Low Density Array chips (human microRNA panel V3.0), and to quantitative real-time polymerase chain reaction. RESULTS: By using the TaqMan Low Density Array chip technology, 19 mature miRNAs appeared differentially expressed in the group of women who later developed sPE as compared to normal women. The expression of four miRNAs (miR-1233, miR-520, miR-210, miR-144) was validated by quantitative real-time polymerase chain reaction analysis. MiR-1233 was the most overexpressed in the serum of women who later developed sPE. CONCLUSION: Circulating miRNAs deserve further investigation in order to explore their potential role in the pathogenesis of preeclampsia. In particular, miR-1233 might represent a potential marker of early sPE.
Keywords: Adult; Biomarkers; Female; Gestational Age; Humans; MicroRNAs; Oligonucleotide Array Sequence Analysis; Pilot Projects; Pre-Eclampsia; Pregnancy; Retrospective Studies

Radiological contrast media in the breastfeeding woman: a position paper of the Italian Society of Radiology (SIRM), the Italian Society of Paediatrics (SIP), the Italian Society of Neonatology (SIN) and the Task Force on Breastfeeding, Ministry of Health - Cova, Maria Assunta; Stacul, Fulvio; Quaranta, Roberto; Guastalla, Pierpaolo; Salvatori, Guglielmo; Banderali, Giuseppe; Fonda, Claudio; David, Vincenzo; Gregori, Massimo; Zuppa, Antonio Alberto; Davanzo, Riccardo (Eur Radiol, 2014)
OBJECTIVES: Breastfeeding is a well-recognised investment in the health of the mother-infant dyad. Nevertheless, many professionals still advise breastfeeding mothers to temporarily discontinue breastfeeding after contrast media imaging. Therefore, we performed this review to provide health professionals with basic knowledge and skills for appropriate use of contrast media. METHODS: A joint working group of the Italian Society of Radiology (SIRM), Italian Society of Paediatrics (SIP), Italian Society of Neonatology (SIN) and Task Force on Breastfeeding, Ministry of Health, Italy prepared a review of the relevant medical literature on the safety profile of contrast media for the nursing infant/child. RESULTS: Breastfeeding is safe for the nursing infant of any post-conceptional age after administration of the majority of radiological contrast media to the mother; only gadolinium-based agents considered at high risk of nephrogenic systemic fibrosis (gadopentetate dimeglumine, gadodiamide, gadoversetamide) should be avoided in the breastfeeding woman as a precaution; there is no need to temporarily discontinue breastfeeding or to express and discard breast milk following the administration of contrast media assessed as compatible with breastfeeding. CONCLUSIONS: Breastfeeding women should receive unambiguous professional advice and clear encouragement to continue breastfeeding after imaging with the compatible contrast media. KEY POINTS: • Breastfeeding is a well-known investment in the health of the mother-infant dyad. • Breastfeeding is safe after administration of contrast media to the mother. • There is no need to temporarily discontinue breastfeeding following administration of contrast media.
Keywords: Adult; Breast Feeding; Contrast Media; Female; Humans; Infant; Italy; Neonatology; Practice Guidelines as Topic; Radiology; Societies, Medical

Recommendations for self-monitoring in pediatric diabetes: a consensus statement by the ISPED. - Scaramuzza, Andrea; Cherubini, Valentino; Tumini, Stefano; Bonfanti, Riccardo; Buono, Pietro; Cardella, Francesca; d'Annunzio, Giuseppe; Frongia, Anna Paola; Lombardo, Fortunato; Monciotti, Anna Carla Maria; Rabbone, Ivana; Schiaffini, Riccardo; et al. (Acta Diabetol, 2014)
A panel of experts of the Italian Society of Pediatric Endocrinology and Diabetology comprehensively discussed and approved the Italian recommendations regarding self-monitoring of blood glucose, continuous glucose monitoring and other measures of glycemic control in children and adolescents with type 1 diabetes. After an extensive review of the literature, we took these issues into account: self-monitoring blood glucose, continuous glucose monitoring, glycemic variability, glycosuria, ketonuria, ketonemia, glycated hemoglobin, fructosamine and glycated albumin, logbook, data downloading, lancing devices, carbohydrate counting, and glycemic measurements at school. We concluded that clinical guidelines on self-management should be developed in every country with faithful adaptation to local languages and taking into account specific contexts and local peculiarities, without any substantial modifications to the international recommendations. We believe that the National Health Service should provide all necessary resources to ensure self-monitoring of blood glucose and possibly continuous glucose monitoring of all children and adolescents with type 1 diabetes, according to the standards of care provided by these recommendations and internationally.

Rhythm perception and production predict reading abilities in developmental dyslexia. - Flaugnacco, Elena; Lopez, Luisa; Terribili, Chiara; Zoia, Stefania; Buda, Sonia; Tilli, Sara; Monasta, Lorenzo; Montico, Marcella; Sila, Alessandra; Ronfani, Luca; Schön, Daniele (Front Hum Neurosci, 2014)
Rhythm organizes events in time and plays a major role in music, but also in the phonology and prosody of a language. Interestingly, children with developmental dyslexia-a learning disability that affects reading acquisition despite normal intelligence and adequate education-have a poor rhythmic perception. It has been suggested that an accurate perception of rhythmical/metrical structure, that requires accurate perception of rise time, may be critical for phonological development and subsequent literacy. This hypothesis is mostly based on results showing a high degree of correlation between phonological awareness and metrical skills, using a very specific metrical task. We present new findings from the analysis of a sample of 48 children with a diagnosis of dyslexia, without comorbidities. These children were assessed with neuropsychological tests, as well as specifically-devised psychoacoustic and musical tasks mostly testing temporal abilities. Associations were tested by multivariate analyses including data mining strategies, correlations and most importantly logistic regressions to understand to what extent the different auditory and musical skills can be a robust predictor of reading and phonological skills. Results show a strong link between several temporal skills and phonological and reading abilities. These findings are discussed in the framework of the neuroscience literature comparing music and language processing, with a particular interest in the links between rhythm processing in music and language.

Single-day trimethoprim/sulfamethoxazole prophylaxis for Pneumocystis pneumonia in children with cancer. - Caselli, Désirée; Petris, Maria Grazia; Rondelli, Roberto; Carraro, Francesca; Colombini, Antonella; Muggeo, Paola; Ziino, Ottavio; Melchionda, Fraia; Russo, Giovanna; Pierani, Paolo; Soncini, Elena; DeSantis, Raffaella; et al. (J Pediatr, 2014)
OBJECTIVE: To determine whether a simplified, 1-day/week regimen of trimethoprim/sulfamethoxazole is sufficient to prevent Pneumocystis (jirovecii [carinii]) pneumonia (PCP). Current recommended regimens for prophylaxis against PCP range from daily administration to 3 consecutive days per week dosing. STUDY DESIGN: A prospective survey of the regimens adopted for the PCP prophylaxis in all patients treated for childhood cancer at pediatric hematology-oncology centers of the Associazione Italiana Ematologia Oncologia Pediatrica. RESULTS: The 20 centers participating in the study reported a total of 2466 patients, including 1093 with solid tumor and 1373 with leukemia/lymphoma (or primary immunodeficiency; n = 2). Of these patients, 1371 (55.6%) received the 3-day/week prophylaxis regimen, 406 (16.5%) received the 2-day/week regimen, and 689 (27.9%), including 439 with leukemia/lymphoma, received the 1-day/week regimen. Overall, only 2 cases of PCP (0.08%) were reported, both in the 2-day/week group. By intention to treat, the cumulative incidence of PCP at 3 years was 0.09% overall (95% CI, 0.00-0.40%) and 0.51% for the 2-day/week group (95% CI, 0.10%-2.00%). Remarkably, both patients who failed had withdrawn from prophylaxis. CONCLUSION: A single-day course of prophylaxis with trimethoprim/sulfamethoxazole may be sufficient to prevent PCP in children with cancer undergoing intensive chemotherapy regimens. This simplified strategy might have implications for the emerging need for PCP prophylaxis in other patients subjected to the increased use of biological and nonbiological agents that induce higher levels of immune suppression, such as those with rheumatic diseases.
Keywords: Anti-Infective Agents; Child; Dose-Response Relationship, Drug; Drug Administration Schedule; Follow-Up Studies; Hematologic Neoplasms; Humans; Incidence; Italy; Pneumocystis carinii; Pneumonia, Pneumocystis; Prospective Studies; Treatment Outcome; Trimethoprim, Sulfamethoxazole Drug Combination

Sodium dichloroacetate exhibits anti-leukemic activity in B-chronic lymphocytic leukemia (B-CLL) and synergizes with the p53 activator Nutlin-3. - Agnoletto, Chiara; Melloni, Elisabetta; Casciano, Fabio; Rigolin, Gian Matteo; Rimondi, Erika; Celeghini, Claudio; Brunelli, Laura; Cuneo, Antonio; Secchiero, Paola; Zauli, Giorgio (Oncotarget, 2014)
The anti-leukemic activity of the mitochondria-targeting small molecule sodium dichloroacetate (DCA), used alone and in association with the small molecule inhibitor of the p53/MDM2 interaction Nutlin-3, was analyzed in primary B-chronic lymphocytic leukemia (B-CLL) samples (n=22), normal peripheral blood cells (n=10) and in p53wild-type EHEB, JVM-2, JVM-3 B lymphoblastoid cell lines. DCA exhibited a dose-dependent anti-leukemic activity in both primary B-CLL and B leukemic cell lines with a functional p53 status and showed a synergistic cytotoxic activity when used in combination with Nutlin-3. At the molecular level, DCA positively regulated p53 activity, as documented by post-transcriptional modifications of p53 protein and synergized with Nutlin-3 in increasing the expression of the p53-target genes MDM2, PUMA, TIGAR and in particular p21. The potential role of p21 in mediating the DCA+Nutlin-3 anti-leukemic activity was underscored in knocking-down experiments. Indeed, transfection of leukemic cells with p21 siRNAs significantly decreased the DCA+Nutlin-3-induced cytotoxicity. Taken together, our data emphasize that DCA is a molecule that merits to be further evaluated as a chemotherapeutic agent for B-CLL, likely in combination with other therapeutic compounds.
Keywords: Aged; Aged, 80 and over; Dichloroacetic Acid; Drug Synergism; Female; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Middle Aged; Piperazines; Tumor Suppressor Protein p53

Soluble TRAIL is present at high concentrations in seminal plasma and promotes spermatozoa survival. - Zauli, Giorgio; Celeghini, Claudio; Monasta, Lorenzo; Martinelli, Monica; Luppi, Stefania; Gonelli, Arianna; Grill, Vittorio; Ricci, Giuseppe; Secchiero, Paola (Reproduction, 2014)
The expression of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL(TNFSF10)) and of its receptors (TRAILR1, TRAILR2, TRAILR3, and TRAILR4) have been documented in testis, but the presence of soluble TRAIL in seminal fluid, as well as the potential physiopathological role of the TRAIL/TRAILR system in spermatozoa, has not been previously investigated. Male donors (n=123) among couples presenting for infertility evaluation were consecutively enrolled in this study. The presence of soluble TRAIL was analyzed in seminal samples by ELISA, while the surface expression of TRAIL receptors was investigated by flow cytometry. High levels of soluble TRAIL were detected in seminal plasma (median, 11 621 pg/ml and mean±s.d., 13 371±8367 pg/ml) and flow cytometric analysis revealed a variable expression of TRAIL receptors in the sperm cellular fraction among different subjects. In addition, the effect of physiologically relevant concentrations of recombinant TRAIL was investigated on survival and motility of spermatozoa. Of interest, the in vitro exposure of capacitated spermatozoa to recombinant TRAIL (10 ng/ml) significantly preserved their overall survival. Therefore, the present study demonstrates for the first time the presence of elevated levels of the anti-inflammatory cytokine TRAIL in seminal fluids. Moreover, the demonstration that recombinant TRAIL promotes spermatozoa survival after capacitation suggests potential therapeutic implications.
Keywords: Adult; Apoptosis; Enzyme-Linked Immunosorbent Assay; Flow Cytometry; Humans; Infertility, Male; Male; Receptors, TNF-Related Apoptosis-Inducing Ligand; Semen; Sperm Capacitation; Sperm Motility; Spermatozoa; TNF-Related Apoptosis-Inducing Ligand

Spectrum of the mutations in Bernard-Soulier syndrome. - Savoia, Anna; Kunishima, Shinji; De Rocco, Daniela; Zieger, Barbara; Rand, Margaret L; Pujol-Moix, Núria; Caliskan, Umran; Tokgoz, Huseyin; Pecci, Alessandro; Noris, Patrizia; Srivastava, Alok; Ward, Christopher; et al. (Hum Mutat, 2014)
Bernard-Soulier syndrome (BSS) is a rare autosomal recessive bleeding disorder characterized by defects of the GPIb-IX-V complex, a platelet receptor for von Willebrand factor (VWF). Most of the mutations identified in the genes encoding for the GP1BA (GPIbα), GP1BB (GPIbβ), and GP9 (GPIX) subunits prevent expression of the complex at the platelet membrane or more rarely its interaction with VWF. As a consequence, platelets are unable to adhere to the vascular subendothelium and agglutinate in response to ristocetin. In order to collect information on BSS patients, we established an International Consortium for the study of BSS, allowing us to enrol and genotype 132 families (56 previously unreported). With 79 additional families for which molecular data were gleaned from the literature, the 211 families characterized so far have mutations in the GP1BA (28%), GP1BB (28%), or GP9 (44%) genes. There is a wide spectrum of mutations with 112 different variants, including 22 novel alterations. Consistent with the rarity of the disease, 85% of the probands carry homozygous mutations with evidence of founder effects in some geographical areas. This overview provides the first global picture of the molecular basis of BSS and will lead to improve patient diagnosis and management.
Keywords: Alleles; Bernard-Soulier Syndrome; Databases, Nucleic Acid; Founder Effect; Genetic Variation; Humans; Mutation; Platelet Glycoprotein GPIb-IX Complex; Polymorphism, Single Nucleotide; von Willebrand Diseases; Web Browser

Teleradiology for remote consultation using iPad improves the use of health system human resources for paediatric fractures: prospective controlled study in a tertiary care hospital in Italy. - Zennaro, Floriana; Grosso, Daniele; Fascetta, Riccardo; Marini, Marta; Odoni, Luca; Di Carlo, Valentina; Dibello, Daniela; Vittoria, Francesca; Lazzerini, Marzia (BMC Health Serv Res, 2014)
BACKGROUND: The growing cost of health care and lack of specialised staff have set e-Health high on the European political agenda. In a prospective study we evaluated the effect of providing images for remote consultation through an iPad on the number of in-hospital orthopaedic consultations for children with bone fractures. METHODS: Children from 0 to 18 years diagnosed with a bone fracture by the radiologist during the hours when an orthopaedic service is provided only on-call were eligible for enrollment. Cases were enrolled prospectively during September and October 2013. A standard approach (verbal information only, no X-Ray provided remotely) was compared to an experimental approach (standard approach plus the provision of X-ray for remote consultation through an iPad). The primary outcome was the number of orthopaedic in-hospital consultations that occurred. Other outcomes included: immediate activation of other services; time needed for decision-making; technical difficulties; quality of images and diagnostic confidence (on a likert scale of 1 to 10). RESULTS: Forty-two children were enrolled in the study. Number of in-hospital consultancies dropped from 32/42 (76.1%) when no X-ray was provided to 16/42 (38%) when the X-rays was provided (p < 0.001). With remote X-ray consultation in 14/42 (33.3%) cases services such as surgery and plaster room could be immediately activated, compared to no service activated without teleradiology (p < 0.001). Average time for decision making was 23.4 ± 21.8 minutes with remote X-ray consultation, compared to 56.2 ± 16.1 when the X-ray was not provided (p < 0.001). The comparison between images on the iPad and on the standard system for X- Ray visualisation resulted in a non statistically significant difference in the quality of images (average score 9.89 ± 0.37 vs 9.91 ± 0.30; p = 0.79), and in non statistically significant difference in diagnostic confidence (average score 9.91 ± 0.32 vs 9.92 ± 0.31; p = 0.88). CONCLUSIONS: Remote X-ray consultation through Aycan OsiriX PRO and iPad should be considered as a means for reducing the need of in-hospital orthopaedic consultation during on-call times, and potentially decrease the cost of care for the health system. In the future, alternative systems less expensive than Aycan OsiriX PRO should be further developed and tested.
Keywords: Adolescent; Child; Child, Preschool; Computers, Handheld; Decision Making; Fractures, Bone; Humans; Infant; Infant, Newborn; Italy; Prospective Studies; Remote Consultation; Teleradiology; Time Factors

Trans-ethnic meta-analysis of white blood cell phenotypes. - Keller, Margaux F; Reiner, Alexander P; Okada, Yukinori; van Rooij, Frank J A; Johnson, Andrew D; Chen, Ming-Huei; Smith, Albert V; Morris, Andrew P; Tanaka, Toshiko; Ferrucci, Luigi; Zonderman, Alan B; Lettre, Guillaume; et al. (Hum Mol Genet, 2014)
White blood cell (WBC) count is a common clinical measure used as a predictor of certain aspects of human health, including immunity and infection status. WBC count is also a complex trait that varies among individuals and ancestry groups. Differences in linkage disequilibrium structure and heterogeneity in allelic effects are expected to play a role in the associations observed between populations. Prior genome-wide association study (GWAS) meta-analyses have identified genomic loci associated with WBC and its subtypes, but much of the heritability of these phenotypes remains unexplained. Using GWAS summary statistics for over 50 000 individuals from three diverse populations (Japanese, African-American and European ancestry), a Bayesian model methodology was employed to account for heterogeneity between ancestry groups. This approach was used to perform a trans-ethnic meta-analysis of total WBC, neutrophil and monocyte counts. Ten previously known associations were replicated and six new loci were identified, including several regions harboring genes related to inflammation and immune cell function. Ninety-five percent credible interval regions were calculated to narrow the association signals and fine-map the putatively causal variants within loci. Finally, a conditional analysis was performed on the most significant SNPs identified by the trans-ethnic meta-analysis (MA), and nine secondary signals within loci previously associated with WBC or its subtypes were identified. This work illustrates the potential of trans-ethnic analysis and ascribes a critical role to multi-ethnic cohorts and consortia in exploring complex phenotypes with respect to variants that lie outside the European-biased GWAS pool.
Keywords: African Americans; Asian Continental Ancestry Group; Bayes Theorem; European Continental Ancestry Group; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Leukocyte Count; Leukocytes; Linkage Disequilibrium; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait Loci

An unusual long-term complication of transobturator polypropylene mesh. - Sartore, Andrea; Zennaro, Floriana; Banco, Rubina (Arch Gynecol Obstet, 2014)
Serious complications associated with surgical mesh for transvaginal repair of POP, as infections, vaginal mesh exposure, painful mesh shrinkage and dyspareunia, are not rare. A 48-year-old woman underwent the Perigee procedure because of a stage 3 anterior wall prolapse. Eleven months after surgery, the patient became suddenly unable to walk because of a strong pain to the left thigh root after running. The MRI revealed an external obturator left muscle hyperintensity consistent with muscular oedema; the patient was treated with oral corticosteroids with a complete resolution of the pain. We could hypothesize that the posterior arm of the mesh caused a laceration of the muscles of the obturator space with consequent oedema and pain. The use of the meshes in prolapse surgery can cause unexpected long-term complications.
Keywords: Cystocele; Dyspareunia; Female; Glucocorticoids; Humans; Middle Aged; Pelvic Organ Prolapse; Polypropylenes; Postoperative Complications; Prednisone; Surgical Mesh; Treatment Outcome; Vagina

Family history in early-onset inflammatory bowel disease. - Bianco, Anna Monica; Zanin, Valentina; Monasta, Lorenzo; Martelossi, Stefano; Marcuzzi, Annalisa; Crovella, Sergio (J Gastroenterol, 2013)
Keywords: Colitis, Ulcerative; Crohn Disease; Female; Humans; Male

Genome-wide association analyses identify 18 new loci associated with serum urate concentrations. - Köttgen, Anna; Albrecht, Eva; Teumer, Alexander; Vitart, Veronique; Krumsiek, Jan; Hundertmark, Claudia; Pistis, Giorgio; Ruggiero, Daniela; O'Seaghdha, Conall M; Haller, Toomas; Yang, Qiong; Tanaka, Toshiko; et al. (Nat Genet, 2013)
Elevated serum urate concentrations can cause gout, a prevalent and painful inflammatory arthritis. By combining data from >140,000 individuals of European ancestry within the Global Urate Genetics Consortium (GUGC), we identified and replicated 28 genome-wide significant loci in association with serum urate concentrations (18 new regions in or near TRIM46, INHBB, SFMBT1, TMEM171, VEGFA, BAZ1B, PRKAG2, STC1, HNF4G, A1CF, ATXN2, UBE2Q2, IGF1R, NFAT5, MAF, HLF, ACVR1B-ACVRL1 and B3GNT4). Associations for many of the loci were of similar magnitude in individuals of non-European ancestry. We further characterized these loci for associations with gout, transcript expression and the fractional excretion of urate. Network analyses implicate the inhibins-activins signaling pathways and glucose metabolism in systemic urate control. New candidate genes for serum urate concentration highlight the importance of metabolic control of urate production and excretion, which may have implications for the treatment and prevention of gout.
Keywords: Analysis of Variance; European Continental Ancestry Group; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Glucose; Gout; Humans; Inhibins; Polymorphism, Single Nucleotide; Signal Transduction; Uric Acid

Human colostrum and breast milk contain high levels of TNF-related apoptosis-inducing ligand (TRAIL). - Davanzo, Riccardo; Zauli, Giorgio; Monasta, Lorenzo; Vecchi Brumatti, Liza; Abate, Maria Valentina; Ventura, Giovanna; Rimondi, Erika; Secchiero, Paola; Demarini, Sergio (J Hum Lact, 2013)
BACKGROUND: TNF-related apoptosis inducing ligand (TRAIL) is a pleiotropic cytokine, which plays a key role in the immune system as well as in controlling the balance of apoptosis and proliferation in various organs and tissues. OBJECTIVE: To investigate the presence and levels of soluble TRAIL in human colostrum and milk. METHODS: The levels of soluble human TRAIL were measured in human colostrum (day 2 after delivery) and breast milk (day 5 after delivery). The presence of TRAIL was also measured in infant formula. RESULTS: Levels of soluble TRAIL in the colostrum and mature human milk were, respectively, at least 400 and 100 fold higher than those detected in human serum. No TRAIL was detected in formula. CONCLUSION: Human soluble TRAIL is present at extremely high levels in human colostrum and human milk and might have a significant role in mediating the anti-cancer activity of human milk.
Keywords: Adult; Apgar Score; Colostrum; Female; Gestational Age; Humans; Infant Formula; Infant, Newborn; Milk, Human; TNF-Related Apoptosis-Inducing Ligand

MYH9-related disease: five novel mutations expanding the spectrum of causative mutations and confirming genotype/phenotype correlations. - De Rocco, Daniela; Zieger, Barbara; Platokouki, Helen; Heller, Paula G; Pastore, Annalisa; Bottega, Roberta; Noris, Patrizia; Barozzi, Serena; Glembotsky, Ana C; Pergantou, Helen; Balduini, Carlo L; Savoia, Anna; et al. (Eur J Med Genet, 2013)
MYH9-related disease (MYH9-RD) is a rare autosomal dominant syndromic disorder caused by mutations in MYH9, the gene encoding for the heavy chain of non-muscle myosin IIA (myosin-9). MYH9-RD is characterized by congenital macrothrombocytopenia and typical inclusion bodies in neutrophils associated with a variable risk of developing sensorineural deafness, presenile cataract, and/or progressive nephropathy. The spectrum of mutations responsible for MYH9-RD is limited. We report five families, each with a novel MYH9 mutation. Two mutations, p.Val34Gly and p.Arg702Ser, affect the motor domain of myosin-9, whereas the other three, p.Met847_Glu853dup, p.Lys1048_Glu1054del, and p.Asp1447Tyr, hit the coiled-coil tail domain of the protein. The motor domain mutations were associated with more severe clinical phenotypes than those in the tail domain.
Keywords: Adolescent; Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; Child; Child, Preschool; Exons; Female; Genes, Dominant; Genetic Association Studies; Humans; Male; Middle Aged; Models, Molecular; Molecular Motor Proteins; Molecular Sequence Data; Mutation; Myosin Heavy Chains; Pedigree; Protein Conformation; Sequence Alignment; Syndrome; Thrombocytopenia; Young Adult

The non-genotoxic activator of the p53 pathway Nutlin-3 shifts the balance between E2F7 and E2F1 transcription factors in leukemic cells. - di Iasio, Maria Grazia; Zauli, Giorgio (Invest New Drugs, 2013)
The effect of Nutlin-3, a small molecule inhibitor of the MDM2/p53 interaction, was investigated on the steady-state mRNA levels of the transcription factors E2F1 and E2F7 in a cohort of primary B-chronic lymphocytic leukemia (B-CLL) patient samples (n = 15) and normal peripheral blood mononuclear cells (PBMC). A 24-h treatment with Nutlin-3 significantly down-regulated E2F1 and promoted the concomitant up-regulation of E2F7 in both leukemic and normal cells. Our data suggest that the ability of Nutlin-3 to up-regulate E2F7 likely represents an important molecular determinant in the anti-proliferative activity of Nutlin-3.
Keywords: Case-Control Studies; Cells, Cultured; E2F1 Transcription Factor; E2F7 Transcription Factor; Gene Expression Regulation, Leukemic; Humans; Imidazoles; In Situ Hybridization, Fluorescence; Leukemia, Lymphocytic, Chronic, B-Cell; Leukocytes, Mononuclear; Piperazines; Real-Time Polymerase Chain Reaction; Reverse Transcriptase Polymerase Chain Reaction; RNA, Messenger; Tumor Suppressor Protein p53

Patients affected by metabolic syndrome show decreased levels of circulating platelet derived growth factor (PDGF)-BB. - Tisato, Veronica; Toffoli, Barbara; Monasta, Lorenzo; Bernardi, Stella; Candido, Riccardo; Zauli, Giorgio; Secchiero, Paola (Clin Nutr, 2013)
BACKGROUND & AIMS: The development and/or progression of metabolic syndrome (MetS) in overweight and obese individuals have been associated to low-grade inflammation, but few studies have simultaneously analyzed the circulating levels of several cytokines. METHODS: In this pilot study, a group of 27 cytokines and growth factors was analyzed in the serum of obese patients (n=40) diagnosed for MetS in comparison with sex- and age-matched control subjects without MetS (n=53) by using a multiplex immunoassay. Release of cytokines was measured in culture supernatants of human primary endothelial cells, THP-1 macrophagic cells and HuH-7 hepatoma cells upon exposure to a high fat mixture. RESULTS: While the majority of cytokines did not show significant differences between the investigated groups, the circulating levels of CXCL10/IP-10 and IL-6 were higher in the MetS group versus overweight control group. In contrast, PDGF-BB serum levels were significantly decreased in MetS patients. The in vitro addition of a high fat mixture increased the release of IL-6 and/or CXCL10/IP-10 in the culture supernatant of human primary endothelial cells and THP-1 macrophagic cells, while the same mixture significantly decreased the release of PDGF-BB by human THP-1 macrophagic and HuH-7 hepatoma cells. CONCLUSIONS: The current demonstration that MetS is associated with decrease of the pro-fibrotic PDGF cytokine is a completely novel finding, which adds complexity to the interplay between inflammation and fibrosis in patients affected by MetS.
Keywords: Adolescent; Adult; Aged; Case-Control Studies; Cell Line, Tumor; Chemokine CXCL10; Endothelial Cells; Female; Humans; Interleukin-6; Linear Models; Male; Metabolic Syndrome X; Middle Aged; Obesity; Pilot Projects; Proto-Oncogene Proteins c-sis; RNA, Messenger; Young Adult

Presence of CTAK/CCL27, MCP-3/CCL7 and LIF in human colostrum and breast milk. - Radillo, Oriano; Norcio, Alessia; Addobbati, Riccardo; Zauli, Giorgio (Cytokine, 2013)
Human colostrum and breast milk are known to contain high levels of cytokines and chemokines, which are thought to contribute to the development of the newborn. The aim of this study was to investigate the difference in the presence and levels of 21 soluble cytokines and chemokines in paired samples of human colostrum (day 2 after delivery) and breast milk (day 4-5 after delivery) by using the multiplex technology. Of the 21 cytokine investigated in 10 pairs of samples, only β-NGF was absent in both colostrum and milk, while INF-α2, SCF and TNF-β were present in colostrum but not in human milk. As a general rule, colostrum contained higher concentrations of cytokines and chemokines with respect to breast milk. The majority of cytokines, detected in colostrum alone or in colostrum and human milk (IL-1α, IL-2Rα, IL-3, IL-16, IL-18, GRO-α, HGF, IFN-α2, M-CSF, MIF, MIG, TNF-β, SDF-1α, TRAIL) have been described in previous studies, while for the first time we describe the presence of additional cytokines either in colostrum alone (SCF) or in both colostrum and breast milk (CTAK/CCL27, MCP-3/CCL7, LIF). Our data confirm and expand previous studies showing that some cytokines/chemokines, which might contribute to the development of the gastro-intestinal and nervous systems, are overexpressed in human colostrum and breast milk, and might contribute to the development of these systems.
Keywords: Adult; Chemokine CCL27; Chemokine CCL7; Chemokines; Colostrum; Cytokines; Female; Humans; Infant, Newborn; Leukemia Inhibitory Factor; Milk, Human

Safety and efficacy of infliximab and adalimumab for refractory uveitis in juvenile idiopathic arthritis: 1-year followup data from the Italian Registry. - Zannin, Maria E; Birolo, Carolina; Gerloni, Valeria M; Miserocchi, Elisabetta; Pontikaki, Irene; Paroli, Maria P; Bracaglia, Claudia; Shardlow, Alison; Parentin, Fulvio; Cimaz, Rolando; Simonini, Gabriele; Falcini, Fernanda; et al. (J Rheumatol, 2013)
OBJECTIVE: To evaluate safety and efficacy of adalimumab (ADA) and infliximab (IFX) for the treatment of juvenile idiopathic arthritis-related anterior uveitis (JIA-AU). METHODS: Starting January 2007, patients with JIA-AU treated with IFX and ADA were managed by a standard protocol and data were entered into the National Italian Registry (NIR). At baseline, all patients were refractory to standard immunosuppressive treatment and/or were corticosteroid-dependent. Data recorded every 3 months included uveitis course, number/type of ocular complications, drug-related adverse events (AE), treatment change or withdrawal, and laboratory measures. Data of patients treated for at least 1 year were retrieved from the NIR and analyzed using descriptive statistics. Treatment efficacy was based on change in uveitis course and in number of ocular complications. RESULTS: Up to December 2009, data for 108 patients with JIA-AU treated with anti-tumor necrosis factor-α agents were recorded in the NIR and data from 91, with at least 12 months' followup, were included in the study. Forty-eight patients were treated with IFX, 43 with ADA. Forty-seven patients (55.3%) achieved remission of AU, 28 (32.9%) had recurrent AU, and 10 (11.8%) maintained a chronic course. A higher remission rate was observed with ADA (67.4% vs 42.8% with IFX; p = 0.025). Ocular complications decreased from 0.47 to 0.32 per subject. Five patients experienced resolution of structural complications. No patient reported serious AE; 8 (8.8%) experienced 11 minor AE (9 with IFX, 2 with ADA). CONCLUSION: IFX and ADA appear to be effective and safe for treatment of refractory JIA-related uveitis, with a better performance of ADA in the medium-term period.
Keywords: Adolescent; Antibodies, Monoclonal; Antibodies, Monoclonal, Humanized; Antirheumatic Agents; Arthritis, Juvenile; Child; Child, Preschool; Female; Follow-Up Studies; Humans; Infant; Italy; Male; Registries; Treatment Outcome; Tumor Necrosis Factor-alpha; Uveitis

Is treatment with hydroxychloroquine effective in surfactant protein C deficiency? - Rabach, Ingrid; Poli, Furio; Zennaro, Floriana; Germani, Claudio; Ventura, Alessandro; Barbi, Egidio (Arch Bronconeumol, 2013)
We present the case of two twin brothers with surfactant protein C deficiency who were treated with hydroxychloroquine for three years, with apparent success. The exact physiopathology of this disease is not known and there is no specific treatment for it. There is merely news from a few previous descriptions in the literature about the use of hydroxychloroquine for surfactant protein C deficiency with satisfactory results. Two years after the treatment was withdrawn, the twins were evaluated once again: they presented no new infections, growth and general state were normal and chest CT showed a notable additional reduction in the interstitial pneumopathy. These data seem to cast some doubt on the efficacy of hydroxychloroquine, and they suggest that the clinical improvement was simply the natural evolution of the disease.
Keywords: Disease Progression; Diseases in Twins; Dyspnea; Failure to Thrive; Humans; Hydroxychloroquine; Infant, Newborn; Male; Pulmonary Alveolar Proteinosis; Pulmonary Surfactant-Associated Protein C; Respiratory Insufficiency; Tomography, X-Ray Computed; Twins, Monozygotic

Activation of the p53 pathway induces α-smooth muscle actin expression in both myeloid leukemic cells and normal macrophages. - Secchiero, Paola; Rimondi, Erika; di Iasio, Maria Grazia; Voltan, Rebecca; Gonelli, Arianna; Zauli, Giorgio (J Cell Physiol, 2012)
A range of cell types of mesenchymal origin express α-smooth muscle actin (α-SMA), a protein that plays a key role in controlling cell motility and differentiation along the fibrocyte and myofibroblast lineages. Although α-SMA is often expressed in stromal cells associated to a variety of cancers including hematological malignancies, up to now the role of anti-cancer drugs on α-SMA has not been deeply investigated. In this study, we demonstrated that Nutlin-3, the small molecule inhibitor of the MDM2/p53 interactions, significantly up-regulated the mRNA and protein levels of α-SMA in normal macrophages as well as in p53(wild-type) but not in p53(mutated/null) myeloid leukemic cells. The p53-dependence of α-SMA up-regulation induced by Nutlin-3 was demonstrated in experiments performed with siRNA for p53. Of note, Nutlin-3 mediated up-regulation of α-SMA in OCI leukemic cells was accompanied by cell adhesion to plastic substrate and by reduced cell migratory response in transwell assays. Notably, the role of α-SMA induction in the modulation of myeloid cell migration was clearly documented in α-SMA gene knockdown experiments. In addition, Nutlin-3 significantly up-regulated α-SMA expression in primary endothelial cells, but not in fibroblasts and mesenchymal stem cells (MSC). Conversely, transforming growth factor-β1 up-regulated α-SMA in fibroblasts and MSC, but not in macrophages and endothelial cells. Taken together, these data indicate that Nutlin-3 is a potent inducer of α-SMA in both normal and leukemic myeloid cells as well as in endothelial cells.
Keywords: Actins; Cell Movement; Cells, Cultured; Endothelial Cells; Fibroblasts; Humans; Imidazoles; Leukemia, Myeloid; Macrophages; Mesenchymal Stromal Cells; Piperazines; Proto-Oncogene Proteins c-mdm2; RNA, Small Interfering; Signal Transduction; Transforming Growth Factor beta1; Tumor Suppressor Protein p53

Allogeneic hematopoietic stem cell transplantation for Philadelphia-positive acute lymphoblastic leukemia in children and adolescents: a retrospective multicenter study of the Italian Association of Pediatric Hematology and Oncology (AIEOP). - Fagioli, Franca; Zecca, Marco; Rognoni, Carla; Lanino, Edoardo; Balduzzi, Adriana; Berger, Massimo; Messina, Chiara; Favre, Claudio; Rabusin, Marco; Lo Nigro, Luca; Masetti, Riccardo; Prete, Arcangelo; et al. (Biol Blood Marrow Transplant, 2012)
Philadelphia-positive acute lymphoblastic leukemia (Ph+ ALL) still represents a major challenge. We report the experience of the Italian Association of Pediatric Hematology and Oncology (AIEOP) with allogeneic hematopoietic stem cell transplantation (HSCT) in children with Ph+ ALL from 1990 to 2008. Sixty-nine patients received HSCT from either a related (37, 54%) or an unrelated (32, 46%) donor. Twenty-five patients (36%) underwent transplantation before 2000 and 44 (64%) after 2000. Twenty-three patients (33%) received Imatinib mesylate treatment before HSCT and seven (10%) after HSCT. After a median follow-up of 56 months, the overall survival (OS) probability was 51% (95% confidence interval [CI], 38-63), the leukemia-free survival (LFS) was 47% (95% CI, 34-59), transplantation-related mortality (TRM) was 17% (95% CI, 10-30), and relapse incidence (RI) was 36% (95% CI, 26-50). Transplantation in first complete remission, female gender, and lower WBC count at diagnosis were associated with a better LFS in both univariate and multivariate analyses. Patients with p210 transcript had a trend for a worse prognosis compared with those who had the p190 transcript. Our series confirms the role of HSCT in the eradication of Ph+ ALL. Early HSCT is recommended once morphologic remission is obtained.
Keywords: Adolescent; Antineoplastic Combined Chemotherapy Protocols; Benzamides; Child; Child, Preschool; Disease-Free Survival; Drug Administration Schedule; Female; Fusion Proteins, bcr-abl; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Humans; Infant; Italy; Male; Philadelphia Chromosome; Piperazines; Precursor Cell Lymphoblastic Leukemia-Lymphoma; Pyrimidines; Remission Induction; Retrospective Studies; Secondary Prevention; Transplantation, Homologous; Young Adult

Asbestos and SV40 in malignant pleural mesothelioma from a hyperendemic area of north-eastern Italy. - Comar, Manola; Zanotta, Nunzia; Pesel, Giuliano; Visconti, Patrizia; Maestri, Iva; Rinaldi, Rosa; Crovella, Sergio; Cortale, Maurizio; De Zotti, Renata; Bovenzi, Massimo (Tumori, 2012)
AIMS AND BACKGROUND: Malignant mesothelioma is a fatal cancer of increasing incidence in north-eastern Italy. Together with asbestos, the polyomavirus SV40 was hypothesized to contribute to the onset of malignant mesothelioma. To investigate the putative role of SV40 in the individual susceptibility to asbestos-induced malignant mesothelioma, we conducted a molecular epidemiological study on a series of malignant mesothelioma patients from an area in north-eastern Italy hyperendemic for malignant pleural mesothelioma. METHODS AND STUDY DESIGN: We collected 63 mesothelioma samples from incidence cases of patients diagnosed with malignant pleural mesothelioma in the period 2009-2010. DNA was extracted from patients' tissue biopsies using the BioRobot EZ1 Qiagen workstation. SV40 sequence detection and quantification was performed by specific real time PCR. The 74.6% of the 63 enrolled patients had a history of asbestos exposure. The epithelioid histotype was more prevalent in males (64.0%) and the mixed in females (61.5%) who showed significantly higher cancer co-morbidity (46.1% vs 12%, P = 0.005). SV40 was detected in 22% of MM tumors, with a low viral load. In SV40-positive patients, a threefold increased risk of asbestos exposure was observed, more evident in females (OR 4.32) than in males (OR 1.20). CONCLUSIONS: Our findings indicate that a high prevalence of SV40 was present in malignant mesothelioma incident cases from an area hyperendemic for malignant mesothelioma in north-eastern Italy. Although asbestos is considered the main risk factor in malignant mesothelioma onset, a role for SV40 could be hypothesized.
Keywords: Adult; Aged; Asbestos; Carcinogens; Disease Susceptibility; DNA, Viral; Endemic Diseases; Female; Humans; Italy; Male; Mesothelioma; Middle Aged; Pleural Neoplasms; Polyomavirus Infections; Real-Time Polymerase Chain Reaction; Risk Factors; Simian virus 40; Tumor Virus Infections; Viral Load

Association between the JC polyomavirus infection and male infertility. - Comar, Manola; Zanotta, Nunzia; Croci, Eleonora; Murru, Immacolata; Marci, Roberto; Pancaldi, Cecilia; Dolcet, Ornella; Luppi, Stefania; Martinelli, Monica; Giolo, Elena; Ricci, Giuseppe; Tognon, Mauro (PLoS One, 2012)
In recent years the incidence of male infertility has increased. Many risk factors have been taken into consideration, including viral infections. Investigations into viral agents and male infertility have mainly been focused on human papillomaviruses, while no reports have been published on polyomaviruses and male infertility. The aim of this study was to verify whether JC virus and BK virus are associated with male infertility. Matched semen and urine samples from 106 infertile males and 100 fertile males, as controls, were analyzed. Specific PCR analyses were carried out to detect and quantify large T (Tag) coding sequences of JCV and BKV. DNA sequencing, carried out in Tag JCV-positive samples, was addressed to viral protein 1 (VP1) coding sequences. The prevalence of JCV Tag sequences in semen and urine samples from infertile males was 34% (72/212), whereas the BKV prevalence was 0.94% (2/212). Specifically, JCV Tag sequences were detected in 24.5% (26/106) of semen and 43.4% (46/106) of urine samples from infertile men. In semen and urine samples from controls the prevalence was 11% and 28%, respectively. A statistically significant difference (p<0.05) in JCV prevalence was disclosed in semen and urine samples of cases vs. controls. A higher JC viral DNA load was detected in samples from infertile males than in controls. In samples from infertile males the JC virus type 2 strain, subtype 2b, was more prevalent than ubiquitous type 1. JCV type 2 strain infection has been found to be associated with male infertility. These data suggest that the JC virus should be taken into consideration as an infectious agent which is responsible for male infertility.
Keywords: Adult; Amino Acid Sequence; Amino Acid Substitution; Base Sequence; BK Virus; Capsid Proteins; DNA, Viral; Humans; Infertility, Male; JC Virus; Male; Molecular Sequence Data; Polyomavirus Infections; Semen; Sequence Analysis, DNA; Tumor Virus Infections

A child with severe pneumomediastinum and ABCA3 gene mutation: a puzzling connection. - Copertino, Marco; Barbi, Egidio; Poli, Furio; Zennaro, Floriana; Ferrari, Maurizio; Carrera, Paola; Ventura, Alessandro (Arch Bronconeumol, 2012)
Keywords: Anemia; ATP-Binding Cassette Transporters; Child, Preschool; Dyspnea; Genetic Predisposition to Disease; Heterozygote; Humans; Intensive Care; Leukocytosis; Male; Mediastinal Emphysema; Mutation, Missense; Point Mutation; Pulmonary Emphysema; Respiratory Tract Infections; Subcutaneous Emphysema; Tomography, X-Ray Computed

Clarification of the pleiotropic effects of statins on mevalonate pathway and the feedback regulation of isoprenoids requires more comprehensive investigation. - Bianco, Anna Monica; Zanin, Valentina; Marcuzzi, Annalisa; Crovella, Sergio (Cell Biochem Funct, 2012)
Keywords: Carcinoma, Hepatocellular; Enzyme Inhibitors; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Liver Neoplasms; Simvastatin; Terpenes

Coeliac disease diagnosis: ESPGHAN 1990 criteria or need for a change? Results of a questionnaire. - Ribes-Koninckx, C; Mearin, M L; Korponay-Szabó, I R; Shamir, R; Husby, S; Ventura, A; Branski, D; Catassi, C; Koletzko, S; Mäki, M; Troncone, R; Zimmer, K P (J Pediatr Gastroenterol Nutr, 2012)
BACKGROUND AND OBJECTIVES: A revision of criteria for diagnosing coeliac disease (CD) is being conducted by The European Society for Pediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN). In parallel, we have performed a survey aimed to evaluate present practices for CD among paediatric gastroenterologists and to learn their views on the need for modification of present criteria for CD diagnosis. PATIENTS AND METHODS: Questionnaires were distributed to experienced paediatric gastroenterologists (ESPGHAN members) via the Internet. RESULTS: Overall, 95 valid questionnaires were available for analysis, pertaining to 28 different countries, with the majority of responders treating patients with CD for >15 years. Only about 12% of the responders comply with present criteria, noncompliance being related mainly to the challenge policy. Approximately 90% request a revision and modification of the present criteria. Forty-four percent want to omit the small bowel biopsy in symptomatic children with positive anti-tissue transglutaminase immunoglobulin (Ig) A or endomysial IgA antibodies, especially if they are DQ2/DQ8 positive. For silent cases detected by screening with convincingly positive anti-tissue transglutaminase IgA or EMA IgA, about 30% consider that no small bowel biopsy should be required in selected cases. Adding human leukocyte antigen typing in the diagnostic workup was asked for by 42% of the responders. As for gluten challenge, a new policy is advocated restricting its obligation to cases whenever the diagnosis is doubtful or unclear. CONCLUSIONS: Based on these opinions, revision of the ESPGHAN criteria for diagnosing CD is urgently needed.
Keywords: Adolescent; Adult; Biopsy; Celiac Disease; Child; Child, Preschool; Glutens; Guideline Adherence; Guidelines as Topic; Health Care Surveys; Humans; Immunoglobulin A; Intestine, Small; Physician's Practice Patterns; Questionnaires; Societies, Medical; Transglutaminases; Young Adult

Comments to the editor concerning the paper entitled "Preclinical renal cancer chemopreventive efficacy of geraniol by modulation of multiple molecular pathways" Shiekh Tanveer Ahmad et al. - Vuch, Josef; Marcuzzi, Annalisa; Zanin, Valentina; Crovella, Sergio (Toxicology, 2012)
Keywords: Animals; Antineoplastic Agents; Kidney Neoplasms; Male; Signal Transduction; Terpenes

A common genetic background could explain early-onset Crohn's disease. - Bianco, Anna Monica; Zanin, Valentina; Girardelli, Martina; Magnolato, Andrea; Martelossi, Stefano; Martellossi, Stefano; Tommasini, Alberto; Marcuzzi, Annalisa; Crovella, Sergio (Med Hypotheses, 2012)
Crohn's disease (CD) is a multifactorial disease, in which environmental, microbial and genetic factors play important roles. CD is characterized by a chronic granulomatous inflammation by necrotic scarring with aspects of full-thickness wall. In spite of affecting mainly young adults, sometimes, CD can be present in the first year of life (early onset Crohn disease, EOCD) showing an unpredictable course and being often more severe than at older ages. In this paper we propose the hypothesis that EOCD patients should be analyzed using a Mendelian approach with family studies aimed to identify new loci directly involved in the early onset Crohn's disease. So we will leave the classic association study approach used until now for the identification of genes responsible for susceptibility to CD and propose linkage family analysis as alternative and powerful tool for the identification of new genetic variants associated with familiar cases of EOCD.
Keywords: Crohn Disease; Genetic Linkage; Genetic Predisposition to Disease; Humans; Models, Biological

Congenital hemangiopericytoma. - Travan, Laura; Demarini, Sergio; Del Frate, Giovanni; Zacchi, Alberto (J Pediatr, 2012)
Keywords: Biopsy, Needle; Female; Gestational Age; Hemangiopericytoma; Humans; Immunohistochemistry; Infant, Newborn; Magnetic Resonance Imaging; Pregnancy; Prognosis; Risk Assessment; Soft Tissue Neoplasms; Treatment Outcome; Ultrasonography, Prenatal

DEFB1 gene 5' untranslated region (UTR) polymorphisms in inflammatory bowel diseases. - Zanin, Valentina; Segat, Ludovica; Bianco, Anna Monica; Padovan, Lara; Tavares, Nathalia de Alencar Cunha; Crovella, Sergio (Clinics (Sao Paulo), 2012)
Keywords: 5' Untranslated Regions; Adult; Antimicrobial Cationic Peptides; beta-Defensins; Case-Control Studies; Colitis, Ulcerative; Crohn Disease; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Inflammatory Bowel Diseases; Male; Polymorphism, Genetic; Polymorphism, Single Nucleotide

Editorial: innovative therapeutic approaches for the treatment of pediatric autoimmune and inflammatory diseases. - Zauli, Giorgio (Curr Pharm Des, 2012)
Keywords: Anti-Inflammatory Agents; Autoimmune Diseases; Child; Drug Design; Humans; Inflammation

The effect of clodronate on a mevalonate kinase deficiency cellular model. - Zanin, Valentina; Marcuzzi, Annalisa; Piscianz, Elisa; Vuch, Josef; Bianco, Anna Monica; Monasta, Lorenzo; Decorti, Giuliana; Crovella, Sergio (Inflamm Res, 2012)
BACKGROUND: A potential anti-inflammatory effect of clodronate--an aminobisphosphonate--was described to antagonize the pro-inflammatory effects of the block in the mevalonate pathway, the main feature of a rare auto-inflammatory disease called mevalonate kinase deficiency (MKD). OBJECTIVE: In this study we evaluated the potential anti-inflammatory effect of clodronate in MKD--a still orphan drug pediatric disease. METHODS: We studied some biological parameters, nitric oxide production using Griess reagents and programmed cell death by flow cytometry, as common inflammatory parameters in MKD, in the presence of different doses of clodronate (1, 10 and 100 μM). RESULTS: In our cellular model and in monocytes from patients with MKD, clodronate induced an increase in programed cell death and nitric oxide production in comparison with non-treated cells. CONCLUSION: Our findings suggest that clodronate does not have an anti-inflammatory effect as previously reported but that it increases the epiphenomena of this pediatric disease.
Keywords: Adolescent; Adult; Alendronate; Animals; Anti-Inflammatory Agents; Apoptosis; Cell Line; Cells, Cultured; Child; Clodronic Acid; Female; Humans; Inflammation; Lipopolysaccharides; Male; Mevalonate Kinase Deficiency; Mice; Models, Biological; Monocytes; Nitric Oxide; Young Adult

Endothelial cells obtained from patients affected by chronic venous disease exhibit a pro-inflammatory phenotype. - Tisato, Veronica; Zauli, Giorgio; Voltan, Rebecca; Gianesini, Sergio; di Iasio, Maria Grazia; Volpi, Ilaria; Fiorentini, Guido; Zamboni, Paolo; Secchiero, Paola (PLoS One, 2012)
BACKGROUND: The inflammatory properties of vein endothelium in relation to chronic venous disease (CVD) have been poorly investigated. Therefore, new insights on the characteristics of large vein endothelium would increase our knowledge of large vessel physiopathology. METHODOLOGY/PRINCIPAL FINDINGS: Surgical specimens of veins were obtained from the tertiary venous network (R3) and/or saphenous vein (SF) of patients affected by CVD and from control individuals. Highly purified venous endothelial cell (VEC) cultures obtained from CVD patients were characterized for morphological, phenotypic and functional properties compared to control VEC. An increase of CD31/PECAM-1, CD146 and ICAM-1 surface levels was documented at flow cytometry in pathological VEC with respect to normal controls. Of note, the strongest expression of these pro-inflammatory markers was observed in VEC obtained from patients with more advanced disease. Similarly, spontaneous cell proliferation and resistance to starvation was higher in pathological than in normal VEC, while the migratory response of VEC showed an opposite trend, being significantly lower in VEC obtained from pathological specimens. In addition, in keeping with a higher baseline transcriptional activity of NF-kB, the release of the pro-inflammatory cytokines osteoprotegerin (OPG) and vascular endothelial growth factor (VEGF) was higher in pathological VEC cultures with respect to control VEC. Interestingly, there was a systemic correlation to these in vitro data, as demonstrated by higher serum OPG and VEGF levels in CVD patients with respect to normal healthy controls. CONCLUSION/SIGNIFICANCE: Taken together, these data indicate that large vein endothelial cells obtained from CVD patients exhibit a pro-inflammatory phenotype, which might significantly contribute to systemic inflammation in CVD patients.
Keywords: Adult; Antigens, CD146; Antigens, CD31; Body Mass Index; Cell Culture Techniques; Endothelial Cells; Female; Flow Cytometry; Humans; Inflammation; Intercellular Adhesion Molecule-1; Kinetics; Male; Microscopy, Electron, Scanning; Middle Aged; Phenotype; Saphenous Vein; Vascular Diseases

The energy balance positively regulates the levels of circulating TNF-related apoptosis inducing ligand in humans. - Biolo, Gianni; Secchiero, Paola; De Giorgi, Sara; Tisato, Veronica; Zauli, Giorgio (Clin Nutr, 2012)
BACKGROUND & AIMS: Although decreased levels of circulating TRAIL have been associated to cardiovascular risk and overall mortality, the mechanisms controlling TRAIL levels in physiopathological conditions are currently unknown. The aim of the present study was to investigate whether changes in the energy intake and insulin sensitivity may influence circulating TRAIL, and to analyze potential relationships between circulating TRAIL and changes in fat mass in healthy subjects receiving hypocaloric or hypercaloric diets. METHODS: Three distinct groups of participants were studied, at the end of a 14-day (n = 9), 35-day (n = 30) or 60-day (n = 16) period of experimental bed rest to induce insulin resistance and during controlled ambulation, after receiving eucaloric, hypocaloric or hypercaloric diets. RESULTS: After bed rest conditions, energy restriction significantly decreased circulating TRAIL, while overfeeding significantly increased TRAIL levels with respect to eucaloric control subjects. Moreover, a positive correlation was found between levels of circulating TRAIL and energy intake as well as between circulating TRAIL and energy balance, as determined by changes in fat mass in these subjects. CONCLUSIONS: Circulating levels of TRAIL exhibit a clear-cut positive correlation with the energy intake and balance in healthy subjects during experimental physical inactivity.
Keywords: Adult; Apoptosis; Bed Rest; Cross-Over Studies; Diet; Energy Intake; Energy Metabolism; Female; Humans; Insulin Resistance; Male; Motor Activity; Risk Factors; TNF-Related Apoptosis-Inducing Ligand; Young Adult

European Society for Pediatric Gastroenterology, Hepatology, and Nutrition guidelines for the diagnosis of coeliac disease. - Husby, S; Koletzko, S; Korponay-Szabó, I R; Mearin, M L; Phillips, A; Shamir, R; Troncone, R; Giersiepen, K; Branski, D; Catassi, C; Lelgeman, M; Mäki, M; et al. (J Pediatr Gastroenterol Nutr, 2012)
OBJECTIVE: Diagnostic criteria for coeliac disease (CD) from the European Society for Paediatric Gastroenterology, Hepatology, and Nutrition (ESPGHAN) were published in 1990. Since then, the autoantigen in CD, tissue transglutaminase, has been identified; the perception of CD has changed from that of a rather uncommon enteropathy to a common multiorgan disease strongly dependent on the haplotypes human leukocyte antigen (HLA)-DQ2 and HLA-DQ8; and CD-specific antibody tests have improved. METHODS: A panel of 17 experts defined CD and developed new diagnostic criteria based on the Delphi process. Two groups of patients were defined with different diagnostic approaches to diagnose CD: children with symptoms suggestive of CD (group 1) and asymptomatic children at increased risk for CD (group 2). The 2004 National Institutes of Health/Agency for Healthcare Research and Quality report and a systematic literature search on antibody tests for CD in paediatric patients covering the years 2004 to 2009 was the basis for the evidence-based recommendations on CD-specific antibody testing. RESULTS: In group 1, the diagnosis of CD is based on symptoms, positive serology, and histology that is consistent with CD. If immunoglobulin A anti-tissue transglutaminase type 2 antibody titers are high (>10 times the upper limit of normal), then the option is to diagnose CD without duodenal biopsies by applying a strict protocol with further laboratory tests. In group 2, the diagnosis of CD is based on positive serology and histology. HLA-DQ2 and HLA-DQ8 testing is valuable because CD is unlikely if both haplotypes are negative. CONCLUSIONS: The aim of the new guidelines was to achieve a high diagnostic accuracy and to reduce the burden for patients and their families. The performance of these guidelines in clinical practice should be evaluated prospectively.
Keywords: Adolescent; Celiac Disease; Child; Duodenum; HLA-DQ Antigens; Humans; Immunoglobulin A; Transglutaminases

Evidence of inbreeding depression on human height. - McQuillan, Ruth; Eklund, Niina; Pirastu, Nicola; Kuningas, Maris; McEvoy, Brian P; Esko, Tõnu; Corre, Tanguy; Davies, Gail; Kaakinen, Marika; Lyytikäinen, Leo-Pekka; Kristiansson, Kati; Havulinna, Aki S; et al. (PLoS Genet, 2012)
Stature is a classical and highly heritable complex trait, with 80%-90% of variation explained by genetic factors. In recent years, genome-wide association studies (GWAS) have successfully identified many common additive variants influencing human height; however, little attention has been given to the potential role of recessive genetic effects. Here, we investigated genome-wide recessive effects by an analysis of inbreeding depression on adult height in over 35,000 people from 21 different population samples. We found a highly significant inverse association between height and genome-wide homozygosity, equivalent to a height reduction of up to 3 cm in the offspring of first cousins compared with the offspring of unrelated individuals, an effect which remained after controlling for the effects of socio-economic status, an important confounder (χ(2) = 83.89, df = 1; p = 5.2 × 10(-20)). There was, however, a high degree of heterogeneity among populations: whereas the direction of the effect was consistent across most population samples, the effect size differed significantly among populations. It is likely that this reflects true biological heterogeneity: whether or not an effect can be observed will depend on both the variance in homozygosity in the population and the chance inheritance of individual recessive genotypes. These results predict that multiple, rare, recessive variants influence human height. Although this exploratory work focuses on height alone, the methodology developed is generally applicable to heritable quantitative traits (QT), paving the way for an investigation into inbreeding effects, and therefore genetic architecture, on a range of QT of biomedical importance.
Keywords: Adult; Aged; Body Height; Consanguinity; Databases, Genetic; Family; Female; Genes, Recessive; Genetic Heterogeneity; Genome-Wide Association Study; Homozygote; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

Extra-large letter spacing improves reading in dyslexia. - Zorzi, Marco; Barbiero, Chiara; Facoetti, Andrea; Lonciari, Isabella; Carrozzi, Marco; Montico, Marcella; Bravar, Laura; George, Florence; Pech-Georgel, Catherine; Ziegler, Johannes C (Proc Natl Acad Sci U S A, 2012)
Although the causes of dyslexia are still debated, all researchers agree that the main challenge is to find ways that allow a child with dyslexia to read more words in less time, because reading more is undisputedly the most efficient intervention for dyslexia. Sophisticated training programs exist, but they typically target the component skills of reading, such as phonological awareness. After the component skills have improved, the main challenge remains (that is, reading deficits must be treated by reading more--a vicious circle for a dyslexic child). Here, we show that a simple manipulation of letter spacing substantially improved text reading performance on the fly (without any training) in a large, unselected sample of Italian and French dyslexic children. Extra-large letter spacing helps reading, because dyslexics are abnormally affected by crowding, a perceptual phenomenon with detrimental effects on letter recognition that is modulated by the spacing between letters. Extra-large letter spacing may help to break the vicious circle by rendering the reading material more easily accessible.
Keywords: Attention; Awareness; Child; Dyslexia; Form Perception; France; Humans; Italy; Language; Pattern Recognition, Visual; Phonetics; Reading; Vision, Ocular; Visual Fields

Genome-wide association and functional follow-up reveals new loci for kidney function. - Pattaro, Cristian; Köttgen, Anna; Teumer, Alexander; Garnaas, Maija; Böger, Carsten A; Fuchsberger, Christian; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (PLoS Genet, 2012)
Chronic kidney disease (CKD) is an important public health problem with a genetic component. We performed genome-wide association studies in up to 130,600 European ancestry participants overall, and stratified for key CKD risk factors. We uncovered 6 new loci in association with estimated glomerular filtration rate (eGFR), the primary clinical measure of CKD, in or near MPPED2, DDX1, SLC47A1, CDK12, CASP9, and INO80. Morpholino knockdown of mpped2 and casp9 in zebrafish embryos revealed podocyte and tubular abnormalities with altered dextran clearance, suggesting a role for these genes in renal function. By providing new insights into genes that regulate renal function, these results could further our understanding of the pathogenesis of CKD.
Keywords: African Americans; Aged; Animals; Caspase 9; Cyclin-Dependent Kinases; DEAD-box RNA Helicases; DNA Helicases; European Continental Ancestry Group; Female; Follow-Up Studies; Gene Knockdown Techniques; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Kidney Failure, Chronic; Male; Middle Aged; Phosphoric Diester Hydrolases; Zebrafish

Hydrogen sulfide down-regulates the expression and release of osteoprotegerin (OPG) by vascular endothelial cells. - Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Celeghini, Claudio; Secchiero, Paola; Zauli, Giorgio (Invest New Drugs, 2012)
Keywords: Cell Death; Cytostatic Agents; Down-Regulation; Human Umbilical Vein Endothelial Cells; Humans; Hydrogen Sulfide; Osteoprotegerin; Tumor Necrosis Factor-alpha

In vivo anti-lymphoma activity of an agonistic human recombinant anti-TRAIL-R2 minibody. - Zauli, Giorgio; Corallini, Federica; Zorzet, Sonia; Grill, Vittorio; Marzari, Roberto; Secchiero, Paola (Invest New Drugs, 2012)
A new single-chain fragment variable (scFv) to TRAIL-R2 receptor produced as minibody (MB2.23) was characterized for anti-lymphoma activity in vivo. For this purpose, a disseminated lymphoma model was generated by intraperitoneal inoculation of BJAB cells in severe combined immunodeficiency mice. Two weekly injections with MB2.23 (10 mg/kg) were able to significantly increase the median survival time of lymphoma-bearing animals with respect to the vehicle-treated control mice, providing a rationale for further investigating the use of MB2.23 in anticancer therapy.
Keywords: Animals; Humans; Immunotherapy; Injections, Intraperitoneal; Lymphoma, B-Cell; Mice; Mice, SCID; Receptors, TNF-Related Apoptosis-Inducing Ligand; Single-Chain Antibodies; Time Factors; Xenograft Model Antitumor Assays

Integration of genome-wide association studies with biological knowledge identifies six novel genes related to kidney function. - Chasman, Daniel I; Fuchsberger, Christian; Pattaro, Cristian; Teumer, Alexander; Böger, Carsten A; Endlich, Karlhans; Olden, Matthias; Chen, Ming-Huei; Tin, Adrienne; Taliun, Daniel; Li, Man; Gao, Xiaoyi; et al. (Hum Mol Genet, 2012)
In conducting genome-wide association studies (GWAS), analytical approaches leveraging biological information may further understanding of the pathophysiology of clinical traits. To discover novel associations with estimated glomerular filtration rate (eGFR), a measure of kidney function, we developed a strategy for integrating prior biological knowledge into the existing GWAS data for eGFR from the CKDGen Consortium. Our strategy focuses on single nucleotide polymorphism (SNPs) in genes that are connected by functional evidence, determined by literature mining and gene ontology (GO) hierarchies, to genes near previously validated eGFR associations. It then requires association thresholds consistent with multiple testing, and finally evaluates novel candidates by independent replication. Among the samples of European ancestry, we identified a genome-wide significant SNP in FBXL20 (P = 5.6 × 10(-9)) in meta-analysis of all available data, and additional SNPs at the INHBC, LRP2, PLEKHA1, SLC3A2 and SLC7A6 genes meeting multiple-testing corrected significance for replication and overall P-values of 4.5 × 10(-4)-2.2 × 10(-7). Neither the novel PLEKHA1 nor FBXL20 associations, both further supported by association with eGFR among African Americans and with transcript abundance, would have been implicated by eGFR candidate gene approaches. LRP2, encoding the megalin receptor, was identified through connection with the previously known eGFR gene DAB2 and extends understanding of the megalin system in kidney function. These findings highlight integration of existing genome-wide association data with independent biological knowledge to uncover novel candidate eGFR associations, including candidates lacking known connections to kidney-specific pathways. The strategy may also be applicable to other clinical phenotypes, although more testing will be needed to assess its potential for discovery in general.
Keywords: Amino Acid Transport Systems, Basic; Antigens, CD98 Heavy Chain; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Inhibin-beta Subunits; Intracellular Signaling Peptides and Proteins; Low Density Lipoprotein Receptor-Related Protein-2; Membrane Proteins; Polymorphism, Single Nucleotide

Involuntary movements after correction of vitamin B12 deficiency: a video-case report. - Zanus, Caterina; Alberini, Elena; Costa, Paola; Colonna, Franco; Zennaro, Floriana; Carrozzi, Marco (Epileptic Disord, 2012)
Involuntary movements can appear before and after initiation of vitamin B12 treatment. The pathogenesis of involuntary movements in vitamin B12 deficiency and their relationship with cobalamin injection remain unclear due to a lack of video-EEG documentation making the electroclinical correlation difficult to ascertain. Here, we report video-EEG and neuroimaging findings of an 11-month-old girl with vitamin B12 deficiency, who acutely developed involuntary movements a few days after initiation of vitamin B12 treatment with normal vitamin plasmatic levels. Abnormal movements were a combination of tremor and myoclonus involving the face, mouth, and left arm, which disappeared after discontinuation of therapy. [Published with video sequences].
Keywords: Atrophy; Brain; Dyskinesias; Electroencephalography; Female; Humans; Infant; Magnetic Resonance Imaging; Myelin Sheath; Myoclonus; Tremor; Video Recording; Vitamin B 12; Vitamin B 12 Deficiency; Vitamins

JCV+ Patients with Inflammatory bowel disease show elevated plasma levels of MIG and SCF. - Comar, Manola; Secchiero, Paola; De Lorenzo, Elisa; Martelossi, Stefano; Tommasini, Alberto; Zauli, Giorgio (Inflamm Bowel Dis, 2012)
Keywords: Adolescent; Adult; Chemokine CXCL9; Child; DNA, Viral; Female; Humans; Inflammatory Bowel Diseases; JC Virus; Leukoencephalopathy, Progressive Multifocal; Male; Stem Cell Factor; Young Adult

Letter: inflammatory bowel disease, complementary and alternative medicine, and genetics. - Bianco, A M; Vuch, J; Girardelli, M; Zanin, V; Marcuzzi, A; Crovella, S (Aliment Pharmacol Ther, 2012)
Keywords: Complementary Therapies; Female; Humans; Inflammatory Bowel Diseases; Male; Medication Adherence

Lovastatin-induced apoptosis is modulated by geranylgeraniol in a neuroblastoma cell line. - Marcuzzi, Annalisa; Zanin, Valentina; Piscianz, Elisa; Tricarico, Paola Maura; Vuch, Josef; Girardelli, Martina; Monasta, Lorenzo; Bianco, Anna Monica; Crovella, Sergio (Int J Dev Neurosci, 2012)
Mevalonic aciduria (MA), the most severe form of mevalonate kinase deficiency (MKD), is still an orphan drug disease and the pathogenetic mechanisms underlying neuronal dysfunction is still poorly understood. In our study we have investigated the apoptotic mechanism mediated by the exposure of the cultured neuroblastoma cell line, SH-SY5Y, to lovastatin in absence or in presence of the isoprenoid, geranylgeraniol, with the aim of unraveling the pathogenesis of MA. Lovastatin, blocks the mevalonate pathway inhibiting the 3-hydroxy-3-methylglutaryl-CoA reductase (HMG-CR), an enzyme of the mevalonate pathway upstream the mevalonate kinase enzyme, reproducing biochemical features similar to those found in MKD. We demonstrate that apoptosis in neuronal lovastatin treated-cells is induced by the mitochondrial pathway, with caspase-9 as the initiator and caspase-3 as the effector caspase. The presence of geranylgeraniol modulates both the caspase-9 and caspase-3 activity in a dose-dependent way, confirming that this isoprenoid enters the mevalonate pathway, is metabolized and finally is able to by-pass the statin biochemical block reconstituting the mevalonate pathway. According to our findings, it should not be the time course adopted that modulates the apoptotic response but rather the isoprenoid itself. Being aware that our results have been obtained using a biochemical model of MKD, and not cells from patients with the disease, we believe our findings increase the knowledge of MA pathogenesis, and may possibly contribute to the development of novel therapeutic strategies.
Keywords: Analysis of Variance; Apoptosis; Caspases; Cell Line, Tumor; Diterpenes; Dose-Response Relationship, Drug; Drug Interactions; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Lovastatin; Neuroblastoma; Time Factors

MCL1 down-regulation plays a critical role in mediating the higher anti-leukaemic activity of the multi-kinase inhibitor Sorafenib with respect to Dasatinib. - Secchiero, Paola; Melloni, Elisabetta; Voltan, Rebecca; Norcio, Alessia; Celeghini, Claudio; Zauli, Giorgio (Br J Haematol, 2012)
Keywords: Antineoplastic Agents; Benzenesulfonates; Cell Line, Tumor; Down-Regulation; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Protein Kinase Inhibitors; Proto-Oncogene Proteins c-bcl-2; Pyridines; Pyrimidines; Thiazoles

The MDM2 inhibitor Nutlin-3 modulates dendritic cell-induced T cell proliferation. - Gasparini, Chiara; Tommasini, Alberto; Zauli, Giorgio (Hum Immunol, 2012)
Nutlin-3, a small molecule inhibitor of the MDM2/p53 interaction, has been recently taken into consideration as a promising therapeutic tool for tumor treatment based on its ability to stabilize and activate the p53 transcription factor pathway. Since Nutlin-3 displays non cell-autonomous tumor-suppressor activities, we wanted to investigate its effect on dendritic cell functions, given the central role of these cells in the modulation of the immune response. We found that Nutlin-3 alone slightly affected the levels of major histocompatibility complex and costimulatory molecules and significantly promoted the ability of dendritic cells to stimulate T cells in the mixed lymphocyte reaction. Taken together, our findings suggest that the ability of Nutlin-3 to modulate dendritic cell functions and therefore lymphocyte proliferation might represent an additional important mechanism by which Nutlin-3 exerts its non cell-autonomous tumor-suppression function.
Keywords: Dendritic Cells; Humans; Imidazoles; Immunologic Factors; Immunophenotyping; Lymphocyte Activation; Piperazines; Proto-Oncogene Proteins c-mdm2; T-Lymphocytes

Merkel-cell polyomavirus (MCPyV) is rarely associated to B-chronic lymphocytic leukemia (1 out of 50) samples and occurs late in the natural history of the disease. - Comar, Manola; Cuneo, Antonio; Maestri, Iva; Melloni, Elisabetta; Pozzato, Gabriele; Soffritti, Olga; Secchiero, Paola; Zauli, Giorgio (J Clin Virol, 2012)
BACKGROUND: Previous studies have reported conflicting results on the frequency and potential pathogenetic role of Merkel-cell polyomavirus (MCPyV) in B-chronic lymphocytic leukemia (B-CLL). OBJECTIVES: To evaluate the association of MCPyV to B-CLL and to investigate the occurrence of MCPyV infection in relationship to the natural history of B-CLL. STUDY DESIGN: Samples of primary B-CLL peripheral blood mononuclear cells were obtained from two distinct University Hospitals of Italy from January 2010. For one B-CLL patient, it was possible to retrospectively examine the blood sample at diagnosis of B-CLL (March 2004) and several pathological tissues of cutaneous tumors occurring during the course of the disease. RESULTS: Only one out of 50 B-CLL blood samples examined was positive for MCPyV DNA. Retrospective analysis revealed that MCPyV DNA was absent in peripheral blood sample at diagnosis, becoming present only in advanced disease stages also in tonsil tissue as well as in a biopsy of differentiated squamous cell carcinoma. CONCLUSIONS: The association with MCPyV seems to represent a rare and late event during the natural history of B-CLL.
Keywords: Aged; Aged, 80 and over; Blood; Female; Humans; Italy; Leukemia, Lymphocytic, Chronic, B-Cell; Male; Merkel cell polyomavirus; Middle Aged; Palatine Tonsil; Polyomavirus Infections; Prevalence; Skin; Tumor Virus Infections

Mesenchymal stem cells display hepato-protective activity in lymphoma bearing xenografts. - Secchiero, Paola; Corallini, Federica; Zavan, Barbara; Tripodo, Claudio; Vindigni, Vincenzo; Zauli, Giorgio (Invest New Drugs, 2012)
A disseminated model of non-Hodgkin's lymphoma with prevalent liver metastasis was generated by intraperitoneal (i.p.) injection of EBV(+) B lymphoblastoid SKW6.4 in nude-SCID mice. The survival of SKW6.4 xenografts (median survival = 27 days) was significantly improved when hyaluronan scaffolds embedded with mesenchimal stem cells (MSC) were implanted in the abdominal area 4 days after SKW6.4 injection (median survival = 39.5 days). Mice implanted with MSC showed a significant improvement of hepatic functionality in lymphoma xenografts, as demonstrated by measurement of serum ALT/AST levels. Co-culture of MSC with lymphoma cells enhanced the release of hepatocyte growth factor (HGF) by MSC. These data suggest that hyaluronan-embedded MSC exert anti-lymphoma activity by ameliorating hepatic functionality.
Keywords: Alanine Transaminase; Animals; Aspartate Aminotransferases; Biological Markers; Cell Communication; Cell Line, Tumor; Cell Survival; Coculture Techniques; Hepatocyte Growth Factor; Humans; Hyaluronic Acid; Liver; Liver Neoplasms; Lymphoma, Non-Hodgkin; Mesenchymal Stem Cell Transplantation; Mesenchymal Stromal Cells; Mice; Mice, Nude; Mice, SCID; Time Factors; Tissue Scaffolds; Xenograft Model Antitumor Assays

Meta-analyses identify 13 loci associated with age at menopause and highlight DNA repair and immune pathways. - Stolk, Lisette; Perry, John R B; Chasman, Daniel I; He, Chunyan; Mangino, Massimo; Sulem, Patrick; Barbalic, Maja; Broer, Linda; Byrne, Enda M; Ernst, Florian; Esko, Tõnu; Franceschini, Nora; et al. (Nat Genet, 2012)
To newly identify loci for age at natural menopause, we carried out a meta-analysis of 22 genome-wide association studies (GWAS) in 38,968 women of European descent, with replication in up to 14,435 women. In addition to four known loci, we identified 13 loci newly associated with age at natural menopause (at P < 5 × 10(-8)). Candidate genes located at these newly associated loci include genes implicated in DNA repair (EXO1, HELQ, UIMC1, FAM175A, FANCI, TLK1, POLG and PRIM1) and immune function (IL11, NLRP11 and PRRC2A (also known as BAT2)). Gene-set enrichment pathway analyses using the full GWAS data set identified exoDNase, NF-κB signaling and mitochondrial dysfunction as biological processes related to timing of menopause.
Keywords: Age Factors; DNA Helicases; DNA Primase; DNA Repair; DNA Repair Enzymes; DNA-Directed DNA Polymerase; European Continental Ancestry Group; Exodeoxyribonucleases; Female; Genetic Loci; Genome-Wide Association Study; Humans; Immunity; Menopause; Polymorphism, Single Nucleotide; Proteins

Meta-analysis identifies multiple loci associated with kidney function-related traits in east Asian populations. - Okada, Yukinori; Sim, Xueling; Go, Min Jin; Wu, Jer-Yuarn; Gu, Dongfeng; Takeuchi, Fumihiko; Takahashi, Atsushi; Maeda, Shiro; Tsunoda, Tatsuhiko; Chen, Peng; Lim, Su-Chi; Wong, Tien-Yin; et al. (Nat Genet, 2012)
Chronic kidney disease (CKD), impairment of kidney function, is a serious public health problem, and the assessment of genetic factors influencing kidney function has substantial clinical relevance. Here, we report a meta-analysis of genome-wide association studies for kidney function-related traits, including 71,149 east Asian individuals from 18 studies in 11 population-, hospital- or family-based cohorts, conducted as part of the Asian Genetic Epidemiology Network (AGEN). Our meta-analysis identified 17 loci newly associated with kidney function-related traits, including the concentrations of blood urea nitrogen, uric acid and serum creatinine and estimated glomerular filtration rate based on serum creatinine levels (eGFRcrea) (P < 5.0 × 10(-8)). We further examined these loci with in silico replication in individuals of European ancestry from the KidneyGen, CKDGen and GUGC consortia, including a combined total of ∼110,347 individuals. We identify pleiotropic associations among these loci with kidney function-related traits and risk of CKD. These findings provide new insights into the genetics of kidney function.
Keywords: Asian Continental Ancestry Group; Blood Urea Nitrogen; Cohort Studies; Creatinine; Genetic Predisposition to Disease; Genome-Wide Association Study; Glomerular Filtration Rate; Humans; Kidney; Polymorphism, Single Nucleotide; Renal Insufficiency, Chronic; Uric Acid

Molecular analysis of HEXA gene in Argentinean patients affected with Tay-Sachs disease: possible common origin of the prevalent c.459+5A>G mutation. - Zampieri, Stefania; Montalvo, Annalisa; Blanco, Mariana; Zanin, Irene; Amartino, Hernan; Vlahovicek, Kristian; Szlago, Marina; Schenone, Andrea; Pittis, Gabriela; Bembi, Bruno; Dardis, Andrea (Gene, 2012)
Tay-Sachs disease (TSD) is a recessively inherited disorder caused by the deficient activity of hexosaminidase A due to mutations in the HEXA gene. Up to date there is no information regarding the molecular genetics of TSD in Argentinean patients. In the present study we have studied 17 Argentinean families affected by TSD, including 20 patients with the acute infantile form and 3 with the sub-acute form. Overall, we identified 14 different mutations accounting for 100% of the studied alleles. Eight mutations were novel: 5 were single base changes leading to drastic residue changes or truncated proteins, 2 were small deletions and one was an intronic mutation that may cause a splicing defect. Although the spectrum of mutations was highly heterogeneous, a high frequency of the c.459+5G>A mutation, previously described in different populations was found among the studied cohort. Haplotype analysis suggested that in these families the c.459+5G>A mutation might have arisen by a single mutational event.
Keywords: Child; Cohort Studies; Female; Hexosaminidase A; Humans; Infant; Male; Mutation; Tay-Sachs Disease

Molecular diagnosis of Usher syndrome: application of two different next generation sequencing-based procedures. - Licastro, Danilo; Mutarelli, Margherita; Peluso, Ivana; Neveling, Kornelia; Wieskamp, Nienke; Rispoli, Rossella; Vozzi, Diego; Athanasakis, Emmanouil; D'Eustacchio, Angela; Pizzo, Mariateresa; D'Amico, Francesca; Ziviello, Carmela; et al. (PLoS One, 2012)
Usher syndrome (USH) is a clinically and genetically heterogeneous disorder characterized by visual and hearing impairments. Clinically, it is subdivided into three subclasses with nine genes identified so far. In the present study, we investigated whether the currently available Next Generation Sequencing (NGS) technologies are already suitable for molecular diagnostics of USH. We analyzed a total of 12 patients, most of which were negative for previously described mutations in known USH genes upon primer extension-based microarray genotyping. We enriched the NGS template either by whole exome capture or by Long-PCR of the known USH genes. The main NGS sequencing platforms were used: SOLiD for whole exome sequencing, Illumina (Genome Analyzer II) and Roche 454 (GS FLX) for the Long-PCR sequencing. Long-PCR targeting was more efficient with up to 94% of USH gene regions displaying an overall coverage higher than 25×, whereas whole exome sequencing yielded a similar coverage for only 50% of those regions. Overall this integrated analysis led to the identification of 11 novel sequence variations in USH genes (2 homozygous and 9 heterozygous) out of 18 detected. However, at least two cases were not genetically solved. Our result highlights the current limitations in the diagnostic use of NGS for USH patients. The limit for whole exome sequencing is linked to the need of a strong coverage and to the correct interpretation of sequence variations with a non obvious, pathogenic role, whereas the targeted approach suffers from the high genetic heterogeneity of USH that may be also caused by the presence of additional causative genes yet to be identified.
Keywords: Child, Preschool; Exome; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Molecular Diagnostic Techniques; Pilot Projects; Sequence Analysis, DNA; Usher Syndromes

MYH9-related disorders: report on a patient of Greek origin presenting with macroscopic hematuria and presenile cataract, caused by an R1165C mutation. - Economou, Marina; Batzios, Spyros P; Pecci, Alessandro; Printza, Nikoletta; Savoia, Anna; Barozzi, Serena; Theodoridou, Stamatia; Teli, Aikaterini; Psillas, Georgios; Zafeiriou, Dimitrios I (J Pediatr Hematol Oncol, 2012)
Myosin heavy chain-9 (MYH9)-related disorders represent a heterogenous group of hereditary diseases caused by mutations in the gene encoding the heavy chain of nonmuscle myosin IIA. May-Hegglin anomaly and Fechtner, Sebastian, and Epstein syndromes are the four phenotypes of the disease, characterized by congenital macrothrombocytopenia and distinguished by different combinations of clinical signs that may include glomerulonephritis, sensorineural hearing loss, and presenile cataract. The spectrum of mutations responsible for the disease is wide and the existence of genotype-phenotype correlation remains a critical issue. We report the first case of an MYH9-RD in a patient of Greek origin presenting with macroscopic hematuria and presenile cataract caused by a p.R1165C mutation. The same mutation was present in the patient's father, who exhibited no extrahematological features of the disease. The p.R1165C mutation is one of the MYH9 alterations whose prognostic significance is still poorly defined. Thus, the patients described add to the limited existing data on the MYH9 mutations and their resultant phenotypes.
Keywords: Adolescent; Cataract; Diagnosis, Differential; DNA Mutational Analysis; Greece; Hematuria; Humans; Male; Molecular Motor Proteins; Myosin Heavy Chains; Point Mutation

The negative prognostic value of TRAIL overexpression in oral squamous cell carcinomas does not preclude the potential therapeutic use of recombinant TRAIL. - Carinci, Francesco; Monasta, Lorenzo; Rubini, Corrado; Stramazzotti, Daniela; Palmieri, Annalisa; Melloni, Elisabetta; Knowles, Alex; Ronfani, Luca; Zauli, Giorgio; Secchiero, Paola (Invest New Drugs, 2012)
Keywords: Adult; Aged; Aged, 80 and over; Antineoplastic Agents; Apoptosis; Carcinoma, Squamous Cell; Female; Flow Cytometry; HL-60 Cells; Humans; Immunohistochemistry; Male; Middle Aged; Mouth Neoplasms; Predictive Value of Tests; Prognosis; Proportional Hazards Models; Recombinant Proteins; Risk Assessment; Risk Factors; Survival Analysis; TNF-Related Apoptosis-Inducing Ligand; Tumor Markers, Biological; Up-Regulation; Young Adult

Peroxidase-like activity of ferruginous bodies isolated by exploiting their magnetic property. - Borelli, Violetta; Trevisan, Elisa; Vita, Francesca; Bottin, Cristina; Melato, Mauro; Rizzardi, Clara; Zabucchi, Giuliano (J Toxicol Environ Health A, 2012)
Ferruginous bodies (FB) are polymorphic structures whose formation is macrophage dependent, and are composed of a core, which may consist of an asbestos fiber coated with proteins, among which ferritin is the main component. Within ferritin, the ferric and ferrous ions are coordinated as ferrihydrite, which is the main iron (Fe) storage compound. However, when ferritin accumulates in some tissues following Fe overload it also contains magnetite along with ferrihydrite, which endows it with magnetic properties. Recently studies showed that magnetite exerts peroxidase-like activity, and since ferruginous bodies display magnetic properties, it was postulated that these particular structures may also contain magnetite within the ferritin coating, and thus may also exert peroxidase-like activity. Histochemical analysis for peroxidase of isolated FB smears demonstrated positive staining. Samples isolated from 4 different autopsy lung fragments were also able to oxidize 3,3',5,5'-tetramethyl-benzidine to a blue colored compound that absorbs at 655 nm. This activity was (1) azide and heat insensitive with optimal pH from 5 to 6, and (2) highly variable, changing more than 25-fold from one sample to another. These findings, together with evidence that the peroxidase-like activity of ferruginous bodies has a hydrogen peroxide and substrate requirement different from that of human myeloperoxidase, can exclude that this enzyme gives a significant contribution to the formation of FB. Standard Fe-rich asbestos fibers also express a peroxidase-like activity, but this appears negligible compared to that of ferruginous bodies. Strong acidification of standard Fe-containing asbestos fibers or magnetically isolated ferruginous bodies liberates a high amount of peroxidase-like activity, which is probably accounted for by the release of Fe ions. Further, FB also damage mesothelial cells in vitro. Data suggest that FB exert peroxidase-like activity and cytotoxic activity against mesothelial cells, and hence may be an important factor in pathogenesis of asbestos-related diseases.
Keywords: Air Pollutants, Occupational; Asbestos; Asbestosis; Benzidines; Catalysis; Cell Line; Chromogenic Compounds; Cytotoxins; Ferric Compounds; Ferritins; Ferrosoferric Oxide; Humans; Hydrogen-Ion Concentration; Lung; Magnetic Phenomena; Mesothelioma; Mineral Fibers; Oxidation-Reduction; Peroxidases; Respiratory Mucosa

Polymorphisms in DC-SIGN and L-SIGN genes are associated with HIV-1 vertical transmission in a Northeastern Brazilian population. - da Silva, Ronaldo Celerino; Segat, Ludovica; Zanin, Valentina; Arraes, Luiz Claudio; Crovella, Sergio (Hum Immunol, 2012)
DC-SIGN and L-SIGN are receptors expressed on specialized macrophages in decidua, (Hofbauer and placental capillary endothelial cells), known to interact with several pathogens, including HIV-1. To disclose the possible involvement of these molecules in the susceptibility to HIV vertical transmission, we analyzed DC-SIGN and L-SIGN gene single nucleotide polymorphisms (SNPs) in 192 HIV-1 positive children and 58 HIV-1 negative children all born to HIV-1 positive mothers, as well as 96 healthy uninfected children not exposed to HIV-1, all from Northeast Brazil. The frequency of three SNPs in the DC-SIGN promoter (-139G>A, -201G>T and -336A>G) were significantly different when comparing HIV positive children with HIV-1 exposed uninfected children, indicating an association with susceptibility to HIV-1 vertical transmission. This genetic association suggests that DC-SIGN molecule may play a role in susceptibility to HIV-1 infection through vertical transmission.
Keywords: Alleles; Brazil; Cell Adhesion Molecules; Child; Child, Preschool; Exons; Female; Gene Frequency; Genotype; HIV Infections; HIV-1; Humans; Infectious Disease Transmission, Vertical; Lectins, C-Type; Male; Polymorphism, Single Nucleotide; Promoter Regions, Genetic; Receptors, Cell Surface; Tandem Repeat Sequences

Potential role of TRAIL in the management of autoimmune diabetes mellitus. - Bernardi, Stella; Norcio, Alessia; Toffoli, Barbara; Zauli, Giorgio; Secchiero, Paola (Curr Pharm Des, 2012)
Type 1 diabetes mellitus (T1DM) is an autoimmune disease, due to the immune-mediated destruction of pancreatic β-cells, whose incidence has been steadily increasing during the last decades. Insulin replacement therapy can treat T1DM, which, however, is still associated with substantial morbidity and mortality. For this reason, great effort is being put into developing strategies that could eventually prevent and/or cure this disease. These strategies are mainly focused on blocking the immune system from attacking β-cells together with functional islet restoration either by regeneration or transplantation. Recent experimental evidences suggest that TNFrelated apoptosis-inducing ligand (TRAIL), which is an immune system modulator protein, could represent an interesting candidate for the cure for T1DM and/or its complications. Here we review the evidences on the potential role of TRAIL in the management of T1DM.
Keywords: Animals; Autoimmunity; Diabetes Mellitus, Type 1; Humans; Hypoglycemic Agents; Insulin; Insulin-Secreting Cells; Islets of Langerhans; TNF-Related Apoptosis-Inducing Ligand

Recurrent fever and fitful abdominal pain in a child. - Zanchi, Chiara; Paloni, Giulia; Marchetti, Federico (Gastroenterology, 2012)
Keywords: Abdominal Pain; Child; Female; Fever; Giant Lymph Node Hyperplasia; Humans; Recurrence

RICH (rapidly involuting congenital hemangioma): not only a definition of wealth. - Abate, Maria Valentina; Davanzo, Riccardo; Bibalo, Chiara; Zennaro, Floriana; Berti, Irene (J Pediatr, 2012)
Keywords: Female; Hemangioma; Humans; Infant, Newborn; Skin Neoplasms

Sedation with intranasal midazolam of Angolan children undergoing invasive procedures. - Kawanda, Lumana; Capobianco, Ivan; Starc, Meta; Felipe, Daniel; Zanon, Davide; Barbi, Egidio; Munkela, Nadine; Rodrigues, Verónica; Malundo, Lúis; Not, Tarcisio (Acta Paediatr, 2012)
AIM: Ambulatory surgery is a daily requirement in poor countries, and limited means and insufficient trained staff lead to the lack of attention to the patient's pain. Midazolam is a rapid-onset, short-acting benzodiazepine which is used safely to reduce pain in children. We evaluated the practicability of intranasal midazolam sedation in a suburban hospital in Luanda (Angola), during the surgical procedures. METHODS: Intranasal midazolam solution was administered at a dose of 0.5 mg/kg. Using the Ramsay's reactivity score, we gave a score to four different types of children's behaviour: moaning, shouting, crying and struggling, and the surgeon evaluated the ease of completing the surgical procedure using scores from 0 (very easy) to 3 (managing with difficulty). RESULTS: Eighty children (median age, 3 years) were recruited, and 140 surgical procedures were performed. Fifty-two children were treated with midazolam during 85 procedures, and 28 children were not treated during 55 procedures. We found a significant difference between the two groups on the shouting, crying and struggling parameters (p < 0.001). The mean score of the ease of completing the procedures was significantly different among the two groups (p < 0.0001). CONCLUSION: These results provide a model of procedural sedation in ambulatory surgical procedures in poor countries, thus abolishing pain and making the surgeon's job easier.
Keywords: Administration, Intranasal; Adolescent; Ambulatory Surgical Procedures; Angola; Child; Child Behavior; Child, Preschool; Conscious Sedation; Crying; Female; Humans; Hypnotics and Sedatives; Infant; Male; Midazolam; Prospective Studies

Serum amyloid A and cholesterol: a pivotal role on inflammation. - Tricarico, Paola Maura; Marcuzzi, Annalisa; Zanin, Valentina; Kleiner, Giulio; Bianco, Anna Monica; Crovella, Sergio (Amyloid, 2012)
Keywords: Animals; Humans; Serum Amyloid A Protein

Sexually transmitted infections and diseases: old and new challenges - part I - Introduction. - Guaschino, S; Zuccati, G (G Ital Dermatol Venereol, 2012)
Keywords: Humans; Sexually Transmitted Diseases

Simultaneous determination of multiple cytokines reveals a pro-inflammatory and pro-angiogenic signature after major cardiothoracic surgery: potential role of C-reactive protein. - Tisato, Veronica; Monasta, Lorenzo; Biolo, Gianni; Donatelli, Francesco; Secchiero, Paola; Zauli, Giorgio (Cytokine, 2012)
Keywords: C-Reactive Protein; Coronary Artery Bypass; Cytokines; Humans; Inflammation; Macrophages; Neovascularization, Physiologic; Risk Factors

SOCS1 is significantly up-regulated in Nutlin-3-treated p53wild-type B chronic lymphocytic leukemia (B-CLL) samples and shows an inverse correlation with miR-155. - di Iasio, Maria Grazia; Norcio, Alessia; Melloni, Elisabetta; Zauli, Giorgio (Invest New Drugs, 2012)
The basal SOCS1 mRNA levels were significantly lower in p53(mutated) BJAB and MAVER leukemic cell lines with respect to p53(wild-type) SKW6.4 and JVM-2 leukemic cell lines, p53(wild-type) primary B chronic lymphocytic leukemia (B-CLL) cells and primary normal peripheral blood mononuclear cells (PBMC). Moreover, the MDM2 small molecule inhibitor Nutlin-3 significantly increased the levels of SOCS1 mRNA in both primary p53(wild-type) B-CLL cells as well as in p53(wild-type) B leukemic cell lines, but not in p53(mutated) B leukemic cell lines nor in primary PBMC. Of note, a significant inverse correlation was observed between SOCS1 mRNA and miR-155 levels in Nutlin-3-treated primary B-CLL cells and PBMC, suggesting that the miRNA-155/SOCS1 axis represents a potentially important therapeutic target of Nutlin-3 in B-CLL.
Keywords: Cell Line, Tumor; Cells, Cultured; Down-Regulation; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Leukocytes, Mononuclear; MicroRNAs; Piperazines; Suppressor of Cytokine Signaling Proteins; Tumor Suppressor Protein p53; Up-Regulation

Soluble TRAIL is elevated in recurrent miscarriage and inhibits the in vitro adhesion and migration of HTR8 trophoblastic cells. - Agostinis, Chiara; Bulla, Roberta; Tisato, Veronica; De Seta, Francesco; Alberico, Salvatore; Secchiero, Paola; Zauli, Giorgio (Hum Reprod, 2012)
STUDY QUESTION: What is the potential physiopathological role of tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) in recurrent miscarriage (RM), characterized by at least three consecutive pregnancy losses. SUMMARY ANSWER: The levels of serum TRAIL immediately after miscarriage in RM patients are significantly elevated with respect to that in first-trimester normal pregnant women, and recombinant TRAIL inhibits the adhesion and migration of HTR8 trophoblastic cells in vitro. WHAT IS KNOWN ALREADY: Both TRAIL and its trans-membrane receptors (TRAIL-R1, TRAIL-R2, TRAIL-R3 and TRAIL-R4) have been documented in the placenta, but their physiopathological role is incompletely understood. STUDY DESIGN, SIZE, DURATION: The study populations consisted of RM patients (n = 80) and first-trimester normal pregnant women (n = 80). Blood samples were obtained within 24 h after abortion (RM) or at gestational 12-week (normal pregnant women). As additional controls, third-trimester normal pregnant women (n = 28) were examined before (within 72 h) and after (within 24 h) partum. PARTICIPANTS/MATERIALS, SETTING, METHODS: The concentrations of TRAIL were analysed in serum samples by ELISA. In parallel, the effect of soluble recombinant TRAIL (0.1-1000 ng/ml) was analysed on the survival of primary extravillus trophoblasts (EVTs) and on the survival, proliferation, adhesion and migration of trophoblastic HTR8 cells. MAIN RESULTS AND THE ROLE OF CHANCE: The circulating levels of TRAIL in RM women (median: 52.5 pg/ml; mean and SD: 55.5 ± 24.4 pg/ml) were significantly higher with respect to first-trimester normal pregnant women (median: 44.9 pg/ml; mean and SD: 47 ± 15.1 pg/ml) and third-trimester normal pregnant women, as assessed before (median: 45.1 pg/ml; mean and SD: 46 ± 12.4 pg/ml) and after partum (median: 35.4 pg/ml; mean and SD: 38 + 17.5 pg/ml). Both primary EVT and HTR8 cells expressed detectable levels of TRAIL death receptors, but exposure to soluble recombinant TRAIL did not induce cell death of trophoblastic cells. On the other hand, TRAIL dose-dependently inhibited the adhesion of HTR8 cells to decidual endothelial cells (DEC) as well as the migration of HTR8 in transwell assays using either fibronectin or DEC. LIMITATIONS, REASONS FOR CAUTION: Although this study suggests that TRAIL might have a pathogenic role in RM by inhibiting both the adhesion and migration capabilities of first trimester trophoblastic cells, there is a possibility that the elevated serum levels of TRAIL in RM are not cause but rather the result of RM. WIDER IMPLICATIONS OF THE FINDINGS: Our current findings together with data of other authors suggest that circulating TRAIL should be further analysed as a potential important biomarker in different physiopathological settings. STUDY FUNDING/COMPETING INTEREST(S): This study was funded by FIRB projects (RBAP11Z4Z9_002 to Giorgio Zauli and RBAP10447J_002 to Paola Secchiero). The authors have no competing interests to declare.
Keywords: Abortion, Habitual; Apoptosis; Cell Adhesion; Cell Line; Cell Movement; Cells, Cultured; Enzyme-Linked Immunosorbent Assay; Female; Humans; Pregnancy; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand; Trophoblasts

The sorafenib plus nutlin-3 combination promotes synergistic cytotoxicity in acute myeloid leukemic cells irrespectively of FLT3 and p53 status. - Zauli, Giorgio; Celeghini, Claudio; Melloni, Elisabetta; Voltan, Rebecca; Ongari, Manuele; Tiribelli, Mario; di Iasio, Maria Grazia; Lanza, Francesco; Secchiero, Paola (Haematologica, 2012)
BACKGROUND: Both the multi-kinase inhibitor sorafenib and the small molecule inhibitor of the MDM2/p53 interaction, nutlin-3, used alone, have shown promising anti-leukemic activity in acute myeloid leukemia cells. Thus, in this study we investigated the effect of the combination of sorafenib plus nutlin-3 in acute myeloid leukemia. DESIGN AND METHODS: Primary acute myeloid leukemia blasts (n=13) and FLT3(wild-type)/p53(wild-type) (OCI-AML3), FLT3(mutated)/p53(wild-type) (MOLM), FLT3(mutated)/p53(mutated) (MV4-11), FLT3(wild-type)/p53(deleted) (HL60) or FLT3(wild-type)/p53(mutated) (NB4) acute myeloid cell lines were exposed to sorafenib, used alone or in association with nutlin-3 at a 1:1 ratio, in a range of clinically achievable concentrations (1-10 μM). Induction of apoptosis and autophagy was evaluated by transmission electron microscopy and by specific flow cytometry analyses. The levels of Mcl-1, p53 and Bak proteins were analyzed by western blotting. Knock-down of Bax and Bak gene expression was performed in transfection experiments with specific short interfering RNA. RESULTS: The sorafenib+nutlin-3 drug combination exhibits synergistic cytotoxicity in primary acute myeloid leukemia blasts and in acute myeloid leukemia cell lines with maximal cytotoxicity in FLT3(mutated) MV4-11 and MOLM, followed by the FLT3(wild-type) OCI-AML3, HL60 and NB4 cell lines. The cytotoxic activity of sorafenib+nutlin-3 was characterized by an increase of both apoptosis and autophagy. Moreover, Bax and Bak showed prominent roles in mediating the decrease of cell viability in response to the drug combination in p53(wild-type) OCI-AML3 and p53(deleted) HL-60 cells, respectively, as demonstrated in transfection experiments performed with specific short interfering RNA. CONCLUSIONS: Our data demonstrate that acute myeloid leukemia cells show a variable but overall good susceptibility to the innovative therapeutic combination of sorafenib+nutlin-3, which differentially involves the pro-apoptotic Bcl-2 family members Bax and Bak in p53(wild-type) and p53(deleted) cells.
Keywords: Antineoplastic Agents; Drug Synergism; Female; fms-Like Tyrosine Kinase 3; HL-60 Cells; Humans; Imidazoles; Leukemia, Myeloid, Acute; Male; Niacinamide; Phenylurea Compounds; Piperazines; Tumor Suppressor Protein p53

Specific protein profile in cerebrospinal fluid from HIV-1-positive cART-treated patients affected by neurological disorders. - Zanin, Valentina; Delbue, Serena; Marcuzzi, Annalisa; Tavazzi, Eleonora; Del Savio, Rossella; Crovella, Sergio; Marchioni, Enrico; Ferrante, Pasquale; Comar, Manola (J Neurovirol, 2012)
Cytokines/chemokines are involved in the immune response of infections, including HIV-1. We defined the profile of 48 cytokines/chemokines in cerebrospinal fluid from 18 cART patients with chronic HIV-1 infection by Luminex technology. Nine patients were affected with leukoencephalopathies: five with John Cunningham virus (JCV) + progressive multifocal leukoencephalopathy (PML) and four with JCV-not determined leukoencephalopathy (NDLE). In addition, nine HIV-1-positive patients with no neurological signs (NND) and five HIV-1-negative patients affected with acute disseminated encephalomyelitis (ADEM) were enrolled. Ten cytokines (IL-15, IL-3, IL-16, IL-18, CTACK, GRO1, SCF, MCP-1, MIF, SDF) were highly expressed in HIV-1-positive patients while IL-1Ra and IL-17 were present at a lower level. In addition, the levels of IL-17, IL-9, FGF-basic, MIP-1β, and MCP-1 were significantly higher (p < 0.05) in patients with neurological diseases (PML, NDLE, ADEM) with respect to NND. Focusing the attention to the cytokine profile in JCV + PML patients with respect to JCV-NDLE patients, only TNF-β was significantly downregulated (p < 0.05) in JCV + PML patients. This pilot study emphasized the role of immunoregulation in HIV-1-related neurological disorders during cART treatment.
Keywords: Adult; Aged; Anti-HIV Agents; Cytokines; Encephalomyelitis, Acute Disseminated; Female; HIV Infections; HIV-1; Humans; Leukoencephalopathy, Progressive Multifocal; Male; Middle Aged; Pilot Projects

State of art and recent developments of anti-cancer strategies based on TRAIL. - Bernardi, Stella; Secchiero, Paola; Zauli, Giorgio (Recent Pat Anticancer Drug Discov, 2012)
Multicellular organisms require apoptosis whereby the human body eliminates unnecessary and/or damaged cells. Apoptosis, or programmed cell death, can indeed be considered as a constitutive anti-cancer mechanism that seems to be defective in more than 50% of cancers. Molecular insights on the biology of the apoptotic process have led to the development of new anti-cancer strategies aiming at recovering and stimulating this process. Preclinical and clinical studies of our and other groups have demonstrated that targeting the extrinsic apoptotic pathway by various death receptors agonists is a safe and effective anti-cancer strategy, which thus may become a new cornerstone of cancer therapy. Here, we review the most recent acquisitions and patents on TRAIL or TRAIL mimetics, as well as the combination therapies that could be used with them.
Keywords: Animals; Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Apoptosis; Clinical Trials as Topic; Humans; Mice; Neoplasms; Receptors, Death Domain; TNF-Related Apoptosis-Inducing Ligand

State of the art of the therapeutic perspective of sorafenib against hematological malignancies. - Zauli, G; Voltan, R; Tisato, V; Secchiero, P (Curr Med Chem, 2012)
The bi-aryl urea multi-kinase inhibitor Sorafenib (BAY 43-9006, Nexavar) was initially approved for the treatment of unresectable hepatocellular carcinoma and advanced renal cell carcinoma. Eleven years after its first description in PubMed, the therapeutic potential of Sorafenib has been evaluated in an increasing number of studies, mainly focused on solid tumors. More recently, the potential usefullness of Sorafenib has started to emerge also against hematological malignancies. At the molecular level, besides the RAF kinase pathway, which represents the first therapeutic target of Sorafenib, additional kinases, in particular the vascular endothelial growth factor receptor, have been identified as important targets of Sorafenib. A great interest for the potential use of Sorafenib against acute myeloid leukemia (AML) arose when it was demonstrated that a specific mutation of a kinase gene, called FMS-like tyrosin-kinase-3- internal tandem duplication (FLT-3-ITD) and occurring in more than 30% of AML, represents a molecular target of Sorafenib. However, recent phase I and II clinical studies showed that, in spite of its ability to suppress the activity of this mutated kinase, resistence to Sorafenib rapidly occurs in AML, suggesting that Sorafenib will be more effective in combined therapy than used as single drug. Another critical molecular target of Sorafenib is the anti-apoptotic protein Mcl-1. The ability of Sorafenib to rapidly shut-off Mcl-1 in virtually all the hematological malignancies investigated, including the B-chronic lymphocytic leukemia, represents a key element for its antileukemic activity as well as for therapeutic combinations based on Sorafenib. In this respect, it is of particular interest that many chemotherapeutic drugs or innovative anti-neoplastic compounds, such as recombinant TRAIL or inibitors of MDM2 protein, are either unable to down-regulate Mcl-1 or in some instances promote a paradoxical induction of Mcl-1. In this review, the growing evidences for the role of Mcl-1 in mediating the anti-leukemic activity of Sorafenib will be discussed in relationship with promising therapeutic perspectives.
Keywords: Apoptosis; Clinical Trials as Topic; fms-Like Tyrosine Kinase 3; Hematologic Neoplasms; Humans; Leukemia, Myeloid, Acute; Myeloid Cell Leukemia Sequence 1 Protein; Niacinamide; Phenylurea Compounds; Proto-Oncogene Proteins c-bcl-2; Proto-Oncogene Proteins c-mdm2; Receptors, Vascular Endothelial Growth Factor; TNF-Related Apoptosis-Inducing Ligand

Stem cells in severe infantile spinal muscular atrophy (SMA1). - Carrozzi, Marco; Amaddeo, Alessandro; Biondi, Andrea; Zanus, Caterina; Monti, Fabrizio; Alessandro, Ventura (Neuromuscul Disord, 2012)
Keywords: Humans; Spinal Muscular Atrophies of Childhood; Stem Cell Transplantation; Stem Cells; Treatment Outcome

TNF-related apoptosis-inducing ligand significantly attenuates metabolic abnormalities in high-fat-fed mice reducing adiposity and systemic inflammation. - Bernardi, Stella; Zauli, Giorgio; Tikellis, Christos; Candido, Riccardo; Fabris, Bruno; Secchiero, Paola; Cooper, Mark E; Thomas, Merlin C (Clin Sci (Lond), 2012)
TRAIL [TNF (tumour necrosis factor)-related apoptosis-inducing ligand] has recently been shown to ameliorate the natural history of DM (diabetes mellitus). It has not been determined yet whether systemic TRAIL delivery would prevent the metabolic abnormalities due to an HFD [HF (high-fat) diet]. For this purpose, 27 male C57bl6 mice aged 8 weeks were randomly fed on a standard diet, HFD or HFD+TRAIL for 12 weeks. TRAIL was delivered weekly by intraperitoneal injection. Body composition was evaluated; indirect calorimetry studies, GTT (glucose tolerance test) and ITT (insulin tolerance test) were performed. Pro-inflammatory cytokines, together with adipose tissue gene expression and apoptosis, were measured. TRAIL treatment reduced significantly the increased adiposity associated with an HFD. Moreover, it reduced significantly hyperglycaemia and hyperinsulinaemia during a GTT and it improved significantly the peripheral response to insulin. TRAIL reversed the changes in substrate utilization induced by the HFD and ameliorated skeletal muscle non-esterified fatty acids oxidation rate. This was associated with a significant reduction of pro-inflammatory cytokines together with a modulation of adipose tissue gene expression and apoptosis. These findings shed light on the possible anti-adipogenic and anti-inflammatory effects of TRAIL and open new therapeutic possibilities against obesity, systemic inflammation and T2DM (Type 2 DM).
Keywords: Adiposity; Animals; Apoptosis; Calorimetry; Cytokines; Dietary Fats; Energy Intake; Glucose Tolerance Test; Hyperglycemia; Hyperinsulinism; Inflammation; Inflammation Mediators; Male; Mice; Mice, Inbred C57BL; Oxidation-Reduction; Palmitic Acid; Real-Time Polymerase Chain Reaction; TNF-Related Apoptosis-Inducing Ligand

TRAIL, a new weapon against neointimal hyperplasia. - Secchiero, Paola; Zauli, Giorgio (Cardiology, 2012)
Keywords: Coronary Restenosis; Drug-Eluting Stents; Female; Humans; Male; Neointima; TNF-Related Apoptosis-Inducing Ligand

TRAIL administration down-modulated the acute systemic inflammatory response induced in a mouse model by muramyldipeptide or lipopolysaccharide. - Marcuzzi, Annalisa; Secchiero, Paola; Crovella, Sergio; Zauli, Giorgio (Cytokine, 2012)
The potent inducer of apoptosis TRAIL/Apo2 ligand is now under considerations in clinical trials for the treatment of different types of cancer. Since the natural history of cancer is often characterized by microbial infections, we have investigated the effect of recombinant human TRAIL in a mouse model of systemic acute inflammation of microbial origin represented by BALB/c mice treated with either bacterial muramyldipeptide (MDP) or lipopolysaccharide (LPS). When administered intraperitoneally (i.p.), these inflammatory bacterial compounds triggered a severe systemic inflammatory response within 2h, represented by body temperature elevation, increase of circulating serum amyloid-A (SAA) and of the number of leukocytes in the peritoneal cavity. Moreover, both MDP and LPS induced a significant elevation of the circulating levels of several inflammatory cytokines and chemokines. Noteworthy, pre-treatment with recombinant human TRAIL 48 and 72 h before administration of either MDP or LPS, significantly counteracted all acute inflammatory responses, including the elevation of key pro-inflammatory cytokines/chemokines such as IL-1α, IL-6, G-CSF, MCP-1. These data demonstrate for the first time that TRAIL has a potent anti-inflammatory activity, which might be beneficial for the anti-tumoral activity of TRAIL.
Keywords: Acetylmuramyl-Alanyl-Isoglutamine; Acute Disease; Animals; Chemokine CCL2; Cytokines; Disease Models, Animal; Down-Regulation; Granulocyte Colony-Stimulating Factor; Humans; Immunoassay; Inflammation; Inflammation Mediators; Interleukin-1alpha; Interleukin-6; Lipopolysaccharides; Male; Mice; Mice, Inbred BALB C; Recombinant Proteins; Serum Amyloid A Protein; TNF-Related Apoptosis-Inducing Ligand

TRAIL as biomarker and potential therapeutic tool for cardiovascular diseases. - Bernardi, Stella; Milani, Daniela; Fabris, Bruno; Secchiero, Paola; Zauli, Giorgio (Curr Drug Targets, 2012)
This review focuses on TNF-related apoptosis-inducing ligand (TRAIL), also called Apo2 ligand, a protein belonging to the TNF superfamily. TRAIL can be found either in its transmembrane or circulating form, and its mostly studied peripheral effect is the induction of cellular apoptosis. Here, we discuss the evidences supporting the use of TRAIL as biomarker of cardiovascular diseases as well as the evidences showing the potential beneficial therapeutic effects of TRAIL on cardiovascular diseases and diabetes.
Keywords: Biological Markers; Cardiovascular Diseases; Humans; Prognosis; TNF-Related Apoptosis-Inducing Ligand

TRAIL shows potential cardioprotective activity. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Zacchigna, Serena; Fabris, Bruno; Secchiero, Paola (Invest New Drugs, 2012)
Recent clinical trials carried out in patients with advanced cancer have shown that recombinant TRAIL administration is usually safe and well tolerated when used either alone or in association with chemotherapeutic drugs. Notably, anticancer chemotherapy can be associated to cardiomiopathy. We have here demonstrated that TRAIL (administrated as either recombinant soluble TRAIL or as AAV-TRAIL expression viral vector) reduced the development of cardiomyopathy in the ApoE(-/-) diabetic mouse model. These data suggest, for the first time, that therapeutically administration of TRAIL might have a cardioprotective effect.
Keywords: Animals; Apolipoproteins E; Apoptosis; Cardiotonic Agents; Diabetes Mellitus, Experimental; Diabetes Mellitus, Type 1; Diabetic Cardiomyopathies; Fibrosis; Male; Mice; Mice, Knockout; Recombinant Proteins; TNF-Related Apoptosis-Inducing Ligand

Association of tumor necrosis factor-related apoptosis-inducing ligand with total and cardiovascular mortality in older adults. - Volpato, Stefano; Ferrucci, Luigi; Secchiero, Paola; Corallini, Federica; Zuliani, Giovanni; Fellin, Renato; Guralnik, Jack M; Bandinelli, Stefania; Zauli, Giorgio (Atherosclerosis, 2011)
OBJECTIVE: Tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) exhibits biological activity on vascular cells in vitro. Rapid variation of circulating TRAIL levels occurs during acute coronary ischemia, suggesting that biological pathways involving TRAIL may be activated during ischemic heart disease. However, whether differential levels of soluble TRAIL in normal individuals are associated with adverse health outcomes has not been investigated. We tested the hypothesis that TRAIL levels predict mortality in a population based sample of community dwelling men and women. METHODS: Plasma TRAIL level was measured by ELISA at baseline in 1282 adults (mean age 68 years) enrolled in the InCHIANTI study. Vital status was ascertained over the six-year follow-up. RESULTS: In multivariable Cox regression analysis adjusted for potential confounders including prevalent cardiovascular diseases (CVD), ankle-brachial index, electrocardiogram abnormalities, and inflammatory markers, baseline TRAIL levels were inversely related to all-cause mortality (p=0.008). In stratified analyses, the prognostic effect of TRAIL level was strong and highly significant in participants with prevalent CVD (N=321), (lowest versus highest quartile: HR 3.1; 95% CI 1.5-6.5) while it was negligible in those free of CVD (p value for the interaction term between CVD status and TRAIL levels=0.038). Similar findings were obtained when CVD mortality was considered as the outcome of interest. CONCLUSIONS: In older patients with CVD, low levels of TRAIL were associated with increased risk of death over a period of 6 years. Lower concentration of circulating TRAIL may be related to the clinical evolution of older adults with CVD.
Keywords: Adult; Aged; Ankle Brachial Index; Cardiovascular Diseases; Female; Follow-Up Studies; Humans; Italy; Male; Middle Aged; TNF-Related Apoptosis-Inducing Ligand

Circulating TRAIL shows a significant post-partum decline associated to stressful conditions. - Zauli, Giorgio; Monasta, Lorenzo; Rimondi, Erika; Vecchi Brumatti, Liza; Radillo, Oriano; Ronfani, Luca; Montico, Marcella; D'Ottavio, Giuseppina; Alberico, Salvatore; Secchiero, Paola (PLoS One, 2011)
BACKGROUND: Since circulating levels of TNF-related apoptosis inducing ligand (TRAIL) may be important in the physiopathology of pregnancy, we tested the hypothesis that TRAIL levels change at delivery in response to stressful conditions. METHODS/PRINCIPAL FINDINGS: We conducted a longitudinal study in a cohort of 73 women examined at week 12, week 16, delivery and in the corresponding cord blood (CB). Serum TRAIL was assessed in relationship with maternal characteristics and to biochemical parameters. TRAIL did not vary between 12 (67.6±27.6 pg/ml, means±SD) and 16 (64.0±16.2 pg/ml) weeks' gestation, while displaying a significant decline after partum (49.3±26.4 pg/ml). Using a cut-off decline >20 pg/ml between week 12 and delivery, the subset of women with the higher decline of circulating TRAIL (41.7%) showed the following characteristics: i) nullipara, ii) higher age, iii) operational vaginal delivery or urgent CS, iv) did not receive analgesia during labor, v) induced labor. CB TRAIL was significantly higher (131.6±52 pg/ml) with respect to the corresponding maternal TRAIL, and the variables significantly associated with the first quartile of CB TRAIL (<90 pg/ml) were higher pre-pregnancy BMI, induction of labor and fetal distress. With respect to the biochemical parameters, maternal TRAIL at delivery showed an inverse correlation with C-reactive protein (CRP), total cortisol, glycemia and insulin at bivariate analysis, but only with CRP at multivariate analysis. CONCLUSIONS: Stressful partum conditions and elevated CRP levels are associated with a decrease of circulating TRAIL.
Keywords: Adult; Biological Markers; C-Reactive Protein; Female; Fetal Blood; Fetal Distress; Humans; Labor, Obstetric; Logistic Models; Multivariate Analysis; Postpartum Period; Pregnancy; Pregnancy Outcome; Statistics, Nonparametric; Stress, Physiological; TNF-Related Apoptosis-Inducing Ligand

Comments on ''Geranylgeraniol--a new potential therapeutic approach to bisphosphonate associated osteonecrosis of the jaw" by Ziebart T et al. (2011). - Marcuzzi, Annalisa; Zanin, Valentina; Crovella, Sergio; Pontillo, Alessandra (Oral Oncol, 2011)
Keywords: Bone Density Conservation Agents; Diphosphonates; Diterpenes; Humans; Jaw Diseases; Osteonecrosis

Compliance with the gluten-free diet: the role of locus of control in celiac disease. - Bellini, Anna; Zanchi, Chiara; Martelossi, Stefano; Di Leo, Grazia; Not, Tarcisio; Ventura, Alessandro (J Pediatr, 2011)
OBJECTIVES: To verify whether subjects with celiac disease (CD) have a different locus of control (LoC) compared with healthy subjects, and to evaluate the relationship between LoC and compliance with a prescribed gluten-free diet (GFD) and quality of life (QoL). STUDY DESIGN: We studied 156 subjects on a GFD (mean age, 10 years) and 353 healthy controls (mean age, 12 years). All subjects completed tests on the Nowicki-Strickland Locus of Control Scale; the subjects with CD also completed a questionnaire to measure compliance with dietary treatment and the disease's impact on QoL. RESULTS: There was no difference in LoC values between patients with CD and controls. Subjects with CD with good dietary compliance had a more internal LoC compared with those who were not compliant (P = .01). Patients who reported a satisfactory QoL had a more internal LoC compared with those who reported negative affects on QoL due to CD (P = .01). CONCLUSIONS: Our study confirms the usefulness of the LoC concept for identifying those patients who might be at risk for dietary transgression. Given the enhanced, psychological, and social well being that can result from adherence to a GFD, educational and psychological support can help internalize the LoC in those patients at risk for dietary transgression.
Keywords: Adolescent; Age Factors; Case-Control Studies; Celiac Disease; Child; Diet, Gluten-Free; Female; Humans; Internal-External Control; Italy; Male; Patient Compliance; Quality of Life

Consensus on diagnosis and empiric antibiotic therapy of febrile neutropenia. - Giurici, Nagua; Zanazzo, Giulio A (Pediatr Rep, 2011)
Controversial issues on the management of empiric therapy and diagnosis of febrile neutropenia (FN) were faced by a Consensus Group of the Italian Association of Pediatric Hematology-Oncology (AIEOP). In this paper we report the suggestions of the consensus process regarding the role of aminoglycosides, glycopeptides and oral antibiotics in empiric therapy of FN, the rules for changing or discontinuing the therapy as well as the timing of the blood cultures.

Cryptic genetic gluten intolerance revealed by intestinal antitransglutaminase antibodies and response to gluten-free diet. - Not, Tarcisio; Ziberna, Fabiana; Vatta, Serena; Quaglia, Sara; Martelossi, Stefano; Villanacci, Vincenzo; Marzari, Roberto; Florian, Fiorella; Vecchiet, Monica; Sulic, Ana-Marija; Ferrara, Fortunato; Bradbury, Andrew; et al. (Gut, 2011)
BACKGROUND AND OBJECTIVE: Antitransglutaminase (anti-TG2) antibodies are synthesised in the intestine and their presence seems predictive of future coeliac disease (CD). This study investigates whether mucosal antibodies represent an early stage of gluten intolerance even in the absence of intestinal damage and serum anti-TG2 antibodies. METHODS: This study investigated 22 relatives of patients with CD genetically predisposed to gluten intolerance but negative for both serum anti-TG2 antibodies and intestinal abnormalities. Fifteen subjects were symptomatic and seven were asymptomatic. The presence of immunoglobulin A anti-TG2 antibodies in the intestine was studied by creating phage-antibody libraries against TG-2. The presence of intestinal anti-TG2 antibodies was compared with the serum concentration of the intestinal fatty acid-binding protein (I-FABP), a marker for early intestinal mucosal damage. The effects of a 12-month gluten-free diet on anti-TG2 antibody production and the subjects' clinical condition was monitored. Twelve subjects entered the study as controls. RESULTS: The intestinal mucosa appeared normal in 18/22; 4 had a slight increase in intraepithelial lymphocytes. Mucosal anti-TG2 antibodies were isolated in 15/22 subjects (68%); in particular symptomatic subjects were positive in 13/15 cases and asymptomatic subjects in 2/7 cases (p=0.01). No mucosal antibodies were selected from the controls' biopsies. There was significant correlation between the presence of intestinal anti-TG2 antibodies and positive concentrations of I-FABP (p=0.0008). After a gluten-free diet, 19/22 subjects underwent a second intestinal biopsy, which showed that anti-TG2 antibodies had disappeared in 12/15 (p=0.002), while I-FABP decreased significantly (p<0.0001). The diet resolved both extraintestinal and intestinal symptoms. CONCLUSIONS: A new form of genetic-dependent gluten intolerance has been described in which none of the usual diagnostic markers is present. Symptoms and intestinal anti-TG2 antibodies respond to a gluten free-diet. The detection of intestinal anti-TG2 antibodies by the phage-antibody libraries has an important diagnostic and therapeutic impact for the subjects with gluten-dependent intestinal or extraintestinal symptoms. Clinical trial number NCT00677495.
Keywords: Adolescent; Adult; Antibodies, Anti-Idiotypic; Asymptomatic Diseases; Celiac Disease; Child; Child, Preschool; Diet, Gluten-Free; Fatty Acid-Binding Proteins; Female; Genetic Predisposition to Disease; GTP-Binding Proteins; Health Status; Humans; Intestinal Mucosa; Male; Middle Aged; Peptide Library; Transglutaminases; Young Adult

Dasatinib plus Nutlin-3 shows synergistic antileukemic activity in both p53 wild-type and p53 mutated B chronic lymphocytic leukemias by inhibiting the Akt pathway. - Zauli, Giorgio; Voltan, Rebecca; Bosco, Raffaella; Melloni, Elisabetta; Marmiroli, Sandra; Rigolin, Gian Matteo; Cuneo, Antonio; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To analyze the effect of the combination of Dasatinib, a multikinase inhibitor, plus Nutlin-3, a nongenotoxic activator of the p53 pathway, in primary B chronic lymphocytic leukemia (B-CLL) patient samples and B leukemic cell line models. EXPERIMENTAL DESIGN: The induction of cytotoxicity was evaluated in both primary B-CLL cell samples (n = 20) and in p53(wild-type) (EHEB, JVM-2) and p53(deleted/mutated) (MEC-2, BJAB) B leukemic cell lines. The role of Akt in modulating leukemic cell survival/apoptosis in response to Dasatinib or Dasatinib + Nutlin-3 was documented by functional experiments carried out using specific pharmacological inhibitors and by overexpression of membrane-targeted constitutively active form of Akt. RESULTS: The combination of Dasatinib + Nutlin-3 exhibited a synergistic cytotoxicity in the majority (19 out of 20) of B-CLL samples, including patients carrying 17p- (n = 4), and in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. At the molecular level, Dasatinib significantly counteracted the Nutlin-3-mediated induction of the p53 transcriptional targets MDM2 and p21 observed in p53(wild-type) leukemic cells. Conversely, Nutlin-3 did not interfere with the ability of Dasatinib to decrease the phosphorylation levels of ERK1/2, p38/MAPK, and Akt in both p53(wild-type) and p53(deleted/mutated) B leukemic cell lines. A critical role of Akt downregulation in mediating the antileukemic activity of Dasatinib and Dasatinib + Nutlin-3 was demonstrated in experiments carried out by specifically modulating the Akt pathway. CONCLUSIONS: These findings suggest that Dasatinib + Nutlin-3 might represent an innovative therapeutic combination for both p53(wild-type) and p53(deleted/mutated) B-CLL.
Keywords: Antineoplastic Agents; Apoptosis; Cell Line, Tumor; Cell Survival; Down-Regulation; Drug Synergism; Humans; Imidazoles; Leukemia, Lymphocytic, Chronic, B-Cell; Mutation; Piperazines; Protein Kinase Inhibitors; Protein Kinases; Proto-Oncogene Proteins c-akt; Pyrimidines; Thiazoles; Transcription, Genetic; Tumor Suppressor Protein p53

Decreased levels of soluble TNF-related apoptosis-inducing ligand (TRAIL) in the conjunctival sac fluid of patients with diabetes affected by proliferative retinopathy. - Secchiero, P; Perri, P; Melloni, E; Martini, A; Lamberti, G; Sebastiani, A; Zauli, G (Diabet Med, 2011)
Keywords: Apoptosis Regulatory Proteins; Body Fluids; Conjunctiva; Diabetic Retinopathy; Female; Humans; Male; Middle Aged; Receptors, TNF-Related Apoptosis-Inducing Ligand; TNF-Related Apoptosis-Inducing Ligand

Fine tuning of protein kinase C (PKC) isoforms in cancer: shortening the distance from the laboratory to the bedside. - Bosco, R; Melloni, E; Celeghini, C; Rimondi, E; Vaccarezza, M; Zauli, G (Mini Rev Med Chem, 2011)
The serine/threonine protein kinase C (PKC) family was first identified as intracellular receptor(s) for the tumor promoting agents phorbol esters. Thirty years after the discovery of PKC, the role of specific PKC isoforms has been described in relationship with an altered pattern of expression in different types of cancer and a good number of small molecule inhibitors (inhibitory peptides, antisense oligonucleotides or natural compounds) targeting PKC are now available. Despite all these achievements and a huge amount of basic research studies on the biochemical regulation of PKC, there has been a delay in clinical trials with drugs targeting PKC function. This delay is easily explained taking into account the extreme biological complexity of the PKC family of isoforms and the incomplete understanding of the specific role of each PKC isozyme in different types of cancers. Some of the difficulties in developing pharmacological compounds selectively tuning the different PKCs have started to be overcome. In this review, the growing evidences of the role of the PKC isoforms α, βII, δ, ε, ζ and ι is in promoting or counteracting tumor progression will be discussed in relationship with promising therapeutic perspectives.
Keywords: Antineoplastic Agents; Biological Products; Enzyme Inhibitors; Humans; Isoenzymes; Neoplasms; Oligonucleotides, Antisense; Peptides; Protein Kinase C

Foreign children with cancer in Italy. - Rondelli, Roberto; Dini, Giorgio; De Rosa, Marisa; Quarello, Paola; Bisogno, Gianni; Aricò, Maurizio; Vasconcelos, Carivaldo; Tamaro, Paolo; Casazza, Gabriella; Zecca, Marco; De Laurentis, Clementina; Porta, Fulvio; et al. (Ital J Pediatr, 2011)
BACKGROUND: There has been a noticeable annual increase in the number of children coming to Italy for medical treatment, just like it has happened in the rest of the European Union. In Italy, the assistance to children suffering from cancer is assured by the current network of 54 centres members of the Italian Association of Paediatric Haematology and Oncology (AIEOP), which has kept records of all demographic and clinical data in the database of Mod.1.01 Registry since 1989. METHODS: We used the information stored in the already mentioned database to assess the impact of immigration of foreign children with cancer on centres' activity, with the scope of drawing a map of the assistance to these cases. RESULTS: Out of 14,738 cases recorded by all centres in the period from 1999 to 2008, 92.2% were born and resident in Italy, 4.1% (608) were born abroad and living abroad and 3.7% (538) were born abroad and living in Italy. Foreign children cases have increased over the years from 2.5% in 1999 to. 8.1% in 2008.Most immigrant children came from Europe (65.7%), whereas patients who came from America, Asia and Oceania amounted to 13.2%, 10.1%, 0.2%, respectively. The immigrant survival rate was lower compared to that of children who were born in Italy. This is especially true for acute lymphoblastic leukaemia patients entered an AIEOP protocol, who showed a 10-years survival rate of 71.0% vs. 80.7% (p < 0.001) for immigrants and patients born in Italy, respectively. CONCLUSIONS: Children and adolescents are an increasingly important part of the immigration phenomenon, which occurs in many parts of the world. In Italy the vast majority of children affected by malignancies are treated in AIEOP centres. Since immigrant children are predominantly treated in northern Italy, these centres have developed a special expertise in treating immigrant patients, which is certainly very useful for the entire AIEOP network.
Keywords: Adolescent; Africa; Asia; Child; Child, Preschool; Databases, Factual; Emigrants and Immigrants; Ethnic Groups; Europe, Eastern; European Union; Female; Humans; Incidence; Infant; Infant, Newborn; Italy; Male; Neoplasms; North America; Oceania; Prevalence; Retrospective Studies; South America; Survival Rate

Genome-wide association study identifies six new loci influencing pulse pressure and mean arterial pressure. - Wain, Louise V; Verwoert, Germaine C; O'Reilly, Paul F; Shi, Gang; Johnson, Toby; Johnson, Andrew D; Bochud, Murielle; Rice, Kenneth M; Henneman, Peter; Smith, Albert V; Ehret, Georg B; Amin, Najaf; et al. (Nat Genet, 2011)
Numerous genetic loci have been associated with systolic blood pressure (SBP) and diastolic blood pressure (DBP) in Europeans. We now report genome-wide association studies of pulse pressure (PP) and mean arterial pressure (MAP). In discovery (N = 74,064) and follow-up studies (N = 48,607), we identified at genome-wide significance (P = 2.7 × 10(-8) to P = 2.3 × 10(-13)) four new PP loci (at 4q12 near CHIC2, 7q22.3 near PIK3CG, 8q24.12 in NOV and 11q24.3 near ADAMTS8), two new MAP loci (3p21.31 in MAP4 and 10q25.3 near ADRB1) and one locus associated with both of these traits (2q24.3 near FIGN) that has also recently been associated with SBP in east Asians. For three of the new PP loci, the estimated effect for SBP was opposite of that for DBP, in contrast to the majority of common SBP- and DBP-associated variants, which show concordant effects on both traits. These findings suggest new genetic pathways underlying blood pressure variation, some of which may differentially influence SBP and DBP.
Keywords: Arteries; Blood Pressure; Case-Control Studies; Follow-Up Studies; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Linkage Disequilibrium; Polymorphism, Single Nucleotide

Glutamine-enriched nutrition does not reduce mucosal morbidity or complications after stem-cell transplantation for childhood malignancies: a prospective randomized study. - Uderzo, Cornelio; Rebora, Paola; Marrocco, Emanuela; Varotto, Stefania; Cichello, Francesca; Bonetti, Maurizio; Maximova, Natalia; Zanon, Davide; Fagioli, Franca; Nesi, Francesca; Masetti, Riccardo; Masetti, Roberto; et al. (Transplantation, 2011)
BACKGROUND: Intravenous glutamine-enriched solution seems to be effective in posttransplant period in decreasing the severity and duration of mucositis. The aim of this randomized study was to determine the benefit of glutamine supplementation both on mucosal morbidity and in posttransplant associated complications. METHODS: Children undergoing allogeneic hematopoietic stem-cell transplantation (HSCT) for malignant hematological diseases were randomly assigned to standard total parenteral nutrition (S-TPN) or glutamine-enriched (GE)-TPN solution consisting of 0.4 g/kg/day of l-alanine-glutamine dipeptide. This treatment started on the day of HSCT and ended when the patients could orally cover more than 50% of their daily energy requirements. The severity and the rate of post-HSCT mucositis were based on World Health Organization criteria. All the analyses were conducted on intention-to-treat principle. RESULTS: One hundred twenty consecutive patients (83 men; median age, 8.1 years) were enrolled. The mean duration of treatment was 23.5 and 23 days in the two treatment arms. The mean calorie intake was 1538 kcal/d in the S-TPN group and 1512 kcal/d in GE-TPN group. All patients were well nourished before and after HSCT. Mucositis occurred in 91.4% and 91.7% of patients in S-TPN and GE-TPN arm, respectively (P=0.98). Odds ratio adjusted by type of HSCT was 0.98 (95% confidence interval, 0.26-2.63). Type and duration of analgesic treatment, clinical outcome (engraftment, graft versus host disease, early morbidity, and mortality, relapse rate up to 180 days post-HSCT) were not significantly different in the two treatment arms. CONCLUSION: GE-TPN solution does not affect mucositis and outcome in well-nourished HSCT allogeneic patients.
Keywords: Adolescent; Analgesia; Child; Child, Preschool; Double-Blind Method; Female; Glutamine; Hematopoietic Stem Cell Transplantation; Humans; Infant; Male; Mucositis; Mucous Membrane; Neoplasms; Odds Ratio; Parenteral Nutrition; Prospective Studies; Recurrence; Stem Cells; Treatment Outcome

Hearing function and thresholds: a genome-wide association study in European isolated populations identifies new loci and pathways. - Girotto, Giorgia; Pirastu, Nicola; Sorice, Rossella; Biino, Ginevra; Campbell, Harry; d'Adamo, Adamo P; Hastie, Nicholas D; Nutile, Teresa; Polasek, Ozren; Portas, Laura; Rudan, Igor; Ulivi, Sheila; et al. (J Med Genet, 2011)
BACKGROUND: Hearing is a complex trait, but until now only a few genes are known to contribute to variability of this process. In order to discover genes and pathways that underlie auditory function, a genome-wide association study was carried out within the International Consortium G-EAR. METHODS: Meta-analysis of genome-wide association study's data from six isolated populations of European ancestry for an overall number of 3417 individuals. RESULTS: Eight suggestive significant loci (p<10(-7)) were detected with a series of genes expressed within the inner ear such as: DCLK1, PTPRD, GRM8, CMIP. Additional biological candidates marked by a single nucleotide polymorphism (SNP) with a suggestive association (p<10(-6)) were identified, as well as loci encompassing 'gene desert regions'-genes of unknown function or genes whose function has not be linked to hearing so far. Some of these new loci map to already known hereditary hearing loss loci whose genes still need to be identified. Data have also been used to construct a highly significant 'in silico' pathway for hearing function characterised by a network of 49 genes, 34 of which are certainly expressed in the ear. CONCLUSION: These results provide new insights into the molecular basis of hearing function and may suggest new targets for hearing impairment treatment and prevention.
Keywords: Adaptor Proteins, Signal Transducing; Animals; Auditory Threshold; Carrier Proteins; Databases, Genetic; Europe; European Continental Ancestry Group; Female; Founder Effect; Genetic Linkage; Genome-Wide Association Study; Hearing; Hearing Loss; Humans; Intracellular Signaling Peptides and Proteins; Male; Mice; Phenotype; Polymorphism, Single Nucleotide; Protein-Serine-Threonine Kinases; Receptor-Like Protein Tyrosine Phosphatases, Class 2; Receptors, Metabotropic Glutamate

High prevalence of BK polyomavirus sequences in human papillomavirus-16-positive precancerous cervical lesions. - Comar, Manola; Bonifacio, Daniela; Zanconati, Fabrizio; Di Napoli, Michela; Isidoro, Erica; Martini, Fernanda; Torelli, Lucio; Tognon, Mauro (J Med Virol, 2011)
High- and low-grade cervical lesions were analyzed for the presence of polyomavirus (PYV) and human papillomavirus (HPV) sequences. In precancerous cervical lesions, the overall prevalence of PYV sequences was 44% (41/93). Specifically, among the PYV-positive samples, 83% (34/41) tested positive for BK polyomavirus (BKV) sequences, whereas 17% (7/41) were positive for JC-virus. None of the samples were positive for simian virus 40. The presence of BKV DNA in high-grade squamous intraepithelial lesions was confirmed by in situ PCR. BKV sequences were detected more frequently in high-grade squamous intraepithelial lesions, together with the genotype HPV-16. The association of BKV with precancerous cervical lesions suggests that this polyomavirus participates with HPV-16 in the cell transformation process. Alternatively, BKV might multiply better in HPV-16-positive cells from precancerous cervical lesions than in HPV-16-negative cells.
Keywords: Adult; BK Virus; Cervical Intraepithelial Neoplasia; Cervix Uteri; DNA, Viral; Female; Human papillomavirus 16; Human papillomavirus 18; Human papillomavirus 31; Humans; JC Virus; Middle Aged; Oncogene Proteins, Viral; Papillomavirus Infections; Precancerous Conditions; Simian virus 40; Uterine Cervical Diseases

Letter to the editor: acute effects of intravenous administration of pamidronate in patients with osteoporosis. - Marcuzzi, Annalisa; Zanin, Valentina; Vuch, Josef; Pontillo, Alessandra; Crovella, Sergio (J Korean Med Sci, 2011)
Keywords: Anti-Inflammatory Agents; Cytokines; Diphosphonates; Humans; Injections, Intravenous; Osteoporosis

Long-term clinical profile of children with the low-penetrance R92Q mutation of the TNFRSF1A gene. - Pelagatti, M A; Meini, A; Caorsi, R; Cattalini, M; Federici, S; Zulian, F; Calcagno, G; Tommasini, A; Bossi, G; Sormani, M P; Caroli, F; Plebani, A; et al. (Arthritis Rheum, 2011)
OBJECTIVE: To analyze the long-term impact of the R92Q mutation of TNFRSF1A in children with periodic fever, in comparison with children with tumor necrosis factor receptor-associated periodic syndrome (TRAPS) with TNFRSF1A structural mutations and children with periodic fever of unknown origin fulfilling the criteria for periodic fever, aphthosis, pharyngitis, and adenitis syndrome (PFAPA). METHODS: The extracellular region of TNFRSF1A was analyzed in 720 consecutive children with periodic fever, using denaturing high-performance liquid chromatography and DNA sequencing. Followup data on 11 pediatric patients with TNFRSF1A structural mutations (cysteine or T50M), 23 pediatric patients with an R92Q substitution, and 64 pediatric patients with PFAPA were collected during routine clinic visits. The 50-item Child Health Questionnaire was used to assess health-related quality of life (HRQOL). RESULTS: The frequency of typical TRAPS-related clinical manifestations was significantly lower and the impact of the disease on HRQOL was significantly reduced in patients with the R92Q mutation compared with TRAPS patients carrying structural mutations of TNFRSF1A. Followup data on 11 TRAPS patients with TNFRSF1A structural mutations (mean followup 7.9 years), 16 patients with theR92Q substitution (mean followup 7.3 years), and 64 patients with PFAPA (mean followup 5.2 years) were available. Patients with R92Q mutations and patients with PFAPA displayed a higher rate of self-resolution or amelioration of the fever episodes than did TRAPS patients with structural mutations. CONCLUSION: Although some cases may progress to a more chronic disease course, the majority of children with an R92Q mutation of the TNFRSFA1 gene show a milder disease course than that in children with TNFRSFA1 structural mutations and have a high rate of spontaneous resolution and amelioration of the recurrent fever episodes.
Keywords: Adolescent; Antirheumatic Agents; Biological Therapy; Child; Child, Preschool; Familial Mediterranean Fever; Female; Fever; Follow-Up Studies; Genotype; Health Surveys; Humans; Infant; Interleukin 1 Receptor Antagonist Protein; Longitudinal Studies; Lymphadenitis; Male; Mutation; Pharyngitis; Quality of Life; Receptors, Tumor Necrosis Factor; Receptors, Tumor Necrosis Factor, Type I; Recurrence; Retrospective Studies; Steroids; Syndrome

Management of the adnexal mass. - Ricci, Giuseppe; Zito, Gabriella; Fischer-Tamaro, Leo (Obstet Gynecol, 2011)
Keywords: Female; Humans; Ovarian Neoplasms

Marriage and parenthood among childhood cancer survivors: a report from the Italian AIEOP Off-Therapy Registry. - Pivetta, Emanuele; Maule, Milena M; Pisani, Paola; Zugna, Daniela; Haupt, Riccardo; Jankovic, Momcilo; Aricò, Maurizio; Casale, Fiorina; Clerico, Anna; Cordero di Montezemolo, Luca; Kiren, Valentina; Locatelli, Franco; et al. (Haematologica, 2011)
BACKGROUND: The aim of this study was to describe the patterns of marriage and parenthood in a cohort of childhood cancer survivors included in the Off-Therapy Registry maintained by the Italian Association of Pediatric Hematology and Oncology. DESIGN AND METHODS: We analyzed a cohort of 6,044 patients diagnosed with cancer between 1960 and 1998, while aged 0 to 14 years and who were 18 years old or older by December 2003. They were followed up through the regional vital statistics registers until death or the end of follow up (October 30, 2006), whichever occurred first, and their marital status and date of birth of their children were recorded. The cumulative probabilities of being married and having a first child were computed by gender and compared by tumor type within the cohort. Marriage and fertility rates (the latter defined as the number of live births per woman-year) were compared with those of the Italian population of the same age, gender, area of residence and calendar period by means of the observed to expected (O/E) ratios. RESULTS: During the follow-up period, 4,633 (77%) subjects had not married. The marriage O/E ratios were 0.56 (95% CI: 0.51-0.61) and 0.70 (95% CI: 0.65-0.76) among men and women, respectively. Overall, 263 men had 367 liveborn children, and 473 women had 697 liveborn children. The female fertility O/E ratio was 0.57 (95% CI: 0.53-0.62) overall, and 1.08 (95% CI: 0.99-1.17) when analyses were restricted to married/cohabiting women CONCLUSIONS: Childhood cancer survivors are less likely to marry and to have children than the general population, confirming the life-long impact of their previous disease on their social behavior and choices. The inclusion of counseling in the strategies of management and long-term surveillance of childhood cancer patients could be beneficial to survivors as they approach adulthood.
Keywords: Adult; Child; Child, Preschool; Cohort Studies; Female; Follow-Up Studies; Hematologic Neoplasms; Humans; Infant; Infant, Newborn; Italy; Male; Marriage; Middle Aged; Parents; Registries; Survivors

miR-34a induces the downregulation of both E2F1 and B-Myb oncogenes in leukemic cells. - Zauli, Giorgio; Voltan, Rebecca; di Iasio, Maria Grazia; Bosco, Raffaella; Melloni, Elisabetta; Sana, Maria Elena; Secchiero, Paola (Clin Cancer Res, 2011)
PURPOSE: To elucidate new molecular mechanisms able to downregulate the mRNA levels of key oncogenes, such as B-Myb and E2F1, in a therapeutic perspective. EXPERIMENTAL DESIGN: B-Myb and E2F1 mRNA levels were evaluated in primary B chronic lymphocytic leukemia (B-CLL, n = 10) and acute myeloid leukemia (AML, n = 5) patient cells, in a variety of p53(wild-type) and p53(mutated/deleted) leukemic cell lines, as well as in primary endothelial cells and fibroblasts. Knockdown experiments with siRNA for p53 and E2F1 and overexpression experiments with miR34a were conducted to elucidate the role of these pathways in promoting B-Myb downregulation. RESULTS: In vitro exposure to Nutlin-3, a nongenotoxic activator of p53, variably downregulated the expression of B-Myb in primary leukemic cells and in p53(wild-type) myeloid (OCI, MOLM) and lymphoblastoid (SKW6.4, EHEB) but not in p53(mutated) (NB4, BJAB, MAVER) or p53(deleted) (HL-60) leukemic cell lines. The transcriptional repression of B-Myb was also observed in primary normal endothelial cells and fibroblasts. B-Myb downregulation played a critical role in the cell-cycle block in G(1) phase induced by Nutlin-3, as shown by transfection experiments with specific siRNA. Moreover, we have provided experimental evidence suggesting that miR-34a is a central mediator in the repression of B-Myb both directly and through E2F1. CONCLUSIONS: Owing to the role of B-Myb and E2F1 transcription factors in controlling cell-cycle progression of leukemic cells, the downregulation of these oncogenes by miR-34a suggests the usefulness of therapeutic approaches aimed to modulate the levels of miR-34a.
Keywords: Base Sequence; Cell Cycle Proteins; Cell Line, Tumor; Cells, Cultured; Down-Regulation; E2F1 Transcription Factor; Gene Expression Regulation, Leukemic; HCT116 Cells; HL-60 Cells; Humans; Imidazoles; Leukemia; MicroRNAs; Models, Biological; Oncogenes; Piperazines; Sequence Homology, Nucleic Acid; Trans-Activators; Transfection

Molecular targets for selective killing of TRAIL-resistant leukemic cells. - Zauli, Giorgio; Bosco, Raffaella; Secchiero, Paola (Expert Opin Ther Targets, 2011)
INTRODUCTION: TNF-related apoptosis-inducing ligand (TRAIL) is a member of the TNF family of cytokines, and shows promising therapeutic activity against solid tumors and lymphomas, in a variety of Phase I and II clinical trials. In contrast, primary leukemias have shown poor susceptibility to TRAIL-mediated cytotoxicity, suggesting the need for sensitizing TRAIL-resistant leukemic cells, by combining soluble recombinant TRAIL either with chemotherapeutic drugs, or with targeted small molecules. AREAS COVERED: This review discusses potential therapeutic applications of combinations able to restore the sensitivity of leukemic cells to either recombinant TRAIL or anti-TRAIL-receptor agonistic antibodies for the treatment of hematological malignancies. EXPERT OPINION: Up-to-date knowledge of the most innovative anti-leukemic therapies including functional screening of specific-sensitizers, enhancing TRAIL-mediated cytotoxicity. Strategies aimed to enhance TRAIL-mediated apoptosis, include the combination of novel sensitizers, functionally identified from libraries of pharmaceutically active, synthetic or naturally derived compounds. Other approaches aim to employ the administration of stem cells engineered to express TRAIL, in the leukemic stem cell niche, and promise to be a successful treatment with reduced specific toxicity.
Keywords: Humans; Leukemia; TNF-Related Apoptosis-Inducing Ligand

Multiple loci are associated with white blood cell phenotypes. - Nalls, Michael A; Couper, David J; Tanaka, Toshiko; van Rooij, Frank J A; Chen, Ming-Huei; Smith, Albert V; Toniolo, Daniela; Zakai, Neil A; Yang, Qiong; Greinacher, Andreas; Wood, Andrew R; Garcia, Melissa; et al. (PLoS Genet, 2011)
White blood cell (WBC) count is a common clinical measure from complete blood count assays, and it varies widely among healthy individuals. Total WBC count and its constituent subtypes have been shown to be moderately heritable, with the heritability estimates varying across cell types. We studied 19,509 subjects from seven cohorts in a discovery analysis, and 11,823 subjects from ten cohorts for replication analyses, to determine genetic factors influencing variability within the normal hematological range for total WBC count and five WBC subtype measures. Cohort specific data was supplied by the CHARGE, HeamGen, and INGI consortia, as well as independent collaborative studies. We identified and replicated ten associations with total WBC count and five WBC subtypes at seven different genomic loci (total WBC count-6p21 in the HLA region, 17q21 near ORMDL3, and CSF3; neutrophil count-17q21; basophil count- 3p21 near RPN1 and C3orf27; lymphocyte count-6p21, 19p13 at EPS15L1; monocyte count-2q31 at ITGA4, 3q21, 8q24 an intergenic region, 9q31 near EDG2), including three previously reported associations and seven novel associations. To investigate functional relationships among variants contributing to variability in the six WBC traits, we utilized gene expression- and pathways-based analyses. We implemented gene-clustering algorithms to evaluate functional connectivity among implicated loci and showed functional relationships across cell types. Gene expression data from whole blood was utilized to show that significant biological consequences can be extracted from our genome-wide analyses, with effect estimates for significant loci from the meta-analyses being highly corellated with the proximal gene expression. In addition, collaborative efforts between the groups contributing to this study and related studies conducted by the COGENT and RIKEN groups allowed for the examination of effect homogeneity for genome-wide significant associations across populations of diverse ancestral backgrounds.
Keywords: Genetic Loci; Genome-Wide Association Study; Humans; Leukocyte Count; Leukocytes; Molecular Epidemiology; Multigene Family; Phenotype; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Mutations in ANKRD26 are responsible for a frequent form of inherited thrombocytopenia: analysis of 78 patients from 21 families. - Noris, Patrizia; Perrotta, Silverio; Seri, Marco; Pecci, Alessandro; Gnan, Chiara; Loffredo, Giuseppe; Pujol-Moix, Núria; Zecca, Marco; Scognamiglio, Francesca; De Rocco, Daniela; Punzo, Francesca; Melazzini, Federica; et al. (Blood, 2011)
Until recently, thrombocytopenia 2 (THC2) was considered an exceedingly rare form of autosomal dominant thrombocytopenia and only 2 families were known. However, we recently identified mutations in the 5'-untranslated region of the ANKRD26 gene in 9 THC2 families. Here we report on 12 additional pedigrees with ANKRD26 mutations, 6 of which are new. Because THC2 affected 21 of the 210 families in our database, it has to be considered one of the less rare forms of inherited thrombocytopenia. Analysis of all 21 families with ANKRD26 mutations identified to date revealed that thrombocytopenia and bleeding tendency were usually mild. Nearly all patients had no platelet macrocytosis, and this characteristic distinguishes THC2 from most other forms of inherited thrombocytopenia. In the majority of cases, platelets were deficient in glycoprotein Ia and α-granules, whereas in vitro platelet aggregation was normal. Bone marrow examination and serum thrombopoietin levels suggested that thrombocytopenia was derived from dysmegakaryopoiesis. Unexplained high values of hemoglobin and leukocytes were observed in a few cases. An unexpected finding that warrants further investigation was a high incidence of acute leukemia. Given the scarcity of distinctive characteristics, the ANKRD26-related thrombocytopenia has to be taken into consideration in the differential diagnosis of isolated thrombocytopenias.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Ankyrin Repeat; Child; Cohort Studies; Family; Female; Gene Frequency; Humans; Inheritance Patterns; Male; Middle Aged; Mutation; Pedigree; Thrombocytopenia; Transcription Factors; Young Adult

Mutations in TTC19 cause mitochondrial complex III deficiency and neurological impairment in humans and flies. - Ghezzi, Daniele; Arzuffi, Paola; Zordan, Mauro; Da Re, Caterina; Lamperti, Costanza; Benna, Clara; d'Adamo, Pio; Diodato, Daria; Costa, Rodolfo; Mariotti, Caterina; Uziel, Graziella; Smiderle, Cristina; et al. (Nat Genet, 2011)
Although mutations in CYTB (cytochrome b) or BCS1L have been reported in isolated defects of mitochondrial respiratory chain complex III (cIII), most cIII-defective individuals remain genetically undefined. We identified a homozygous nonsense mutation in the gene encoding tetratricopeptide 19 (TTC19) in individuals from two families affected by progressive encephalopathy associated with profound cIII deficiency and accumulation of cIII-specific assembly intermediates. We later found a second homozygous nonsense mutation in a fourth affected individual. We demonstrated that TTC19 is embedded in the inner mitochondrial membrane as part of two high-molecular-weight complexes, one of which coincides with cIII. We then showed a physical interaction between TTC19 and cIII by coimmunoprecipitation. We also investigated a Drosophila melanogaster knockout model for TTC19 that showed low fertility, adult-onset locomotor impairment and bang sensitivity, associated with cIII deficiency. TTC19 is a putative cIII assembly factor whose disruption is associated with severe neurological abnormalities in humans and flies.
Keywords: Adult; Animals; Brain; Codon, Nonsense; Drosophila melanogaster; Electron Transport Complex III; Female; Gene Knockdown Techniques; Humans; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Nervous System Diseases

Neonatal necrotizing tracheobronchitis. - Bua, Jenny; Trappan, Antonella; Demarini, Sergio; Grasso, Domenico; Schleef, Jurgen; Zennaro, Floriana (J Pediatr, 2011)
Keywords: Bronchitis; Bronchoscopy; High-Frequency Ventilation; Humans; Infant, Newborn; Male; Necrosis; Respiratory Insufficiency; Respiratory Mucosa; Tracheitis

Neuromotor deficits in developmental coordination disorder: evidence from a reach-to-grasp task. - Biancotto, Marina; Skabar, Aldo; Bulgheroni, Maria; Carrozzi, Marco; Zoia, Stefania (Res Dev Disabil, 2011)
Developmental coordination disorder (DCD) has been classified as a specific learning disability, nonetheless the underlying cognitive mechanisms are still a matter of discussion. After a summary of the main hypotheses on the principal neuromotor causes of DCD, this study applies a causal model framework to describe the possible coexistence of more than one deficit in this disorder. For this purpose, kinematic analysis was applied to an ecological task, the reach-to-grasp action, introducing the manipulation of three variables: vision, distance and object size. After a thorough neurological and neuropsychological evaluation, 9 children with DCD (7-9 years old) were selected and compared to 27 age-matched control children. The results suggest that children with DCD have a normal neurological characterization of the reaching and grasping movements, in terms of proximal to distal action, but their grasping aperture (MGA) was always wider with respect to controls, particularly when vision was not allowed. In addition, the performance of children with DCD was always slower, more dependent on vision and more variable than that of controls. The MGA of children with DCD could be explained by a deficit in the internal construction of movement for a forward model, while slowness could be related to a control problem in the neuronal firing of the muscles. The idea of a possible coexistence of these two deficits is discussed in accordance to a causal model framework and also addressed considering recent neurophysiologic evidences.
Keywords: Analysis of Variance; Biomechanical Phenomena; Child; Female; Humans; Male; Motor Skills Disorders; Psychometrics; Psychomotor Performance; Reaction Time; Space Perception

Osteoprotegerin induces morphological and functional alterations in mouse pancreatic islets. - Toffoli, Barbara; Bernardi, Stella; Candido, Riccardo; Sabato, Nicoletta; Carretta, Renzo; Corallini, Federica; Secchiero, Paola; Zauli, Giorgio; Fabris, Bruno (Mol Cell Endocrinol, 2011)
Although serum osteoprotegerin (OPG) is significantly increased in diabetic subjects, its potential role in beta cell dysfunction has not been investigated. This study aimed to assess the effect of full-length OPG administered in vivo in mice on pancreatic islet structure and function and its interaction with the renin-angiotensin system (RAS). OPG-treated mice showed increased islet monocyte/macrophage infiltration, fibrosis and apoptosis with reduction of islet function. The remodeling of islet architecture was associated with increased pancreatic expression of components of the RAS, growth factor genes (transforming growth factor β and connective tissue growth factor) and inflammatory molecules (monocyte chemotactic protein-1 and vascular adhesion molecule type 1). Prevention of these changes with improvement of insulin secretion was observed in ramipril treated animals. Our data suggest that OPG might play an important role in promoting beta cell dysfunction and that the upregulation of the local RAS represents one possible mechanism responsible for the OPG-induced beta cell dysfunction.
Keywords: Animals; Apoptosis; Blood Glucose; Blood Pressure; Body Weight; Cell Lineage; Cell Movement; Chemokine CCL2; Connective Tissue Growth Factor; Fibrosis; Gene Expression Regulation; Humans; Insulin; Islets of Langerhans; Macrophages; Mice; Monocytes; Organ Size; Osteoprotegerin; Peptidyl-Dipeptidase A; Receptor, Angiotensin, Type 1; Systole; Transforming Growth Factor beta; Vascular Cell Adhesion Molecule-1

Osteoprotegerin promotes vascular fibrosis via a TGF-β1 autocrine loop. - Toffoli, Barbara; Pickering, Raelene J; Tsorotes, Despina; Wang, Bo; Bernardi, Stella; Kantharidis, Phillip; Fabris, Bruno; Zauli, Giorgio; Secchiero, Paola; Thomas, Merlin C (Atherosclerosis, 2011)
BACKGROUND: This study was designed to evaluate the potential role of osteoprotegerin (OPG) in arterial fibrosis. METHODS: Aortic samples were analyzed after in vivo treatment of ApoE(-/-) mice with recombinant human OPG. Mouse vascular smooth muscle cells (VSMC) were exposed in vitro to recombinant OPG and analyzed for markers of inflammation and fibrosis, such as fibronectin, collagen I, III, IV and transforming growth factor-β1 (TGF-β1). Conversely, the potential modulation of endogenous OPG expression and release by VSMC was analyzed in response to different pro-atherosclerotic cytokines, TGF-β1, platelet derived growth factor (PDGF) and angiogensin II (Ang II). RESULTS: In vivo treatment with human OPG induced signs of fibrosis and up-regulated the arterial expression of TGF-β1. Consistently, in vitro treatment of VSMC with human OPG induced the expression of fibronectin, collagen type I, III, IV, metalloprotein-2 (MMP-2) and MMP-9, as well as of TGF-β1. On the other hand, exposure to recombinant TGF-β1 promoted the expression/release of endogenous OPG and mediated the increase of OPG release induced by PDGF and Ang II in VSMC. CONCLUSIONS: Taken together, these data support a pathogenic role for OPG in the development and progression of atherosclerotic lesions and suggest the existence of a vicious circle between TGF-β1 and OPG.
Keywords: Animals; Apolipoproteins E; Cell Proliferation; Collagen; Fibronectins; Fibrosis; Gene Expression Regulation; Humans; Mice; Mice, Inbred C57BL; Mice, Transgenic; Muscle, Smooth, Vascular; Myocytes, Smooth Muscle; Osteoprotegerin; Platelet-Derived Growth Factor; Transforming Growth Factor beta1

A Phase II study on the safety and efficacy of a single dose of pegfilgrastim for mobilization and transplantation of autologous hematopoietic stem cells in pediatric oncohematology patients. - Cesaro, Simone; Zanazzo, Andrea Giulio; Frenos, Stefano; Luksch, Roberto; Pegoraro, Anna; Tridello, Gloria; Dallorso, Sandro (Transfusion, 2011)
BACKGROUND: Limited data are available on the use of pegfilgrastim in pediatric patients as a mobilizing agent in association with chemotherapy. STUDY DESIGN AND METHODS: This was a prospective, multicenter, Phase II study to evaluate the safety and efficacy of a single dose of 100 µg/kg pegfilgrastim in mobilizing peripheral blood stem cells (PBSCs) in pediatric patients. The primary endpoint of the study was the percentage of good mobilizers with pegfilgrastim (blood peak of CD34+ cells ≥ 20 × 10(6) /L). The results were compared with a historical control group. RESULTS: Thirty of 36 recruited patients were classified as good mobilizers (83%). The median value of circulating CD34+ at leukapheresis was 143 × 10(6) /L (range, 20 × 10(6) -1988 × 10(6) /L). No significant adverse effects were associated with the use of pegfilgrastim and no patient was withdrawn from using the drug. A blood peak of 20 × 10(6) /L or more CD34+ was observed in 33 of 36 control patients (92%) and the median CD34+ count at leukapheresis was 158 × 10(6) /kg (range, 28 × 10(6) -4529 × 10(6) /kg; p = 0.7). No significant differences were found between the two groups in terms of toxicity or other variables of mobilization. As at October 2008, 23 patients of the pegfilgrastim group and 32 patients of the filgrastim group underwent autologous transplant. No significant differences were found in terms of early toxicity, myeloid recovery, and Day 100 survival. CONCLUSION: A single dose of 100 µg/kg pegfilgrastim was safe and effective for PBSC collection in pediatric patients. We suggest that these results support the use of pegfilgrastim for pediatric patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Female; Granulocyte Colony-Stimulating Factor; Hematopoietic Stem Cell Mobilization; Humans; Infant; Male; Neoplasms; Peripheral Blood Stem Cell Transplantation; Prospective Studies; Recombinant Proteins; Transplantation, Autologous

A polymorphism in the 5' UTR of the DEFB1 gene is associated with the lung phenotype in F508del homozygous Italian cystic fibrosis patients. - Crovella, Sergio; Segat, Ludovica; Amato, Annalisa; Athanasakis, Emmanouil; Bezzerri, Valentino; Braggion, Cesare; Casciaro, Rosaria; Castaldo, Giuseppe; Colombo, Carla; Covone, Angela Elvira; De Rose, Virginia; Gagliardini, Rolando; et al. (Clin Chem Lab Med, 2011)
BACKGROUND: The identification of cystic fibrosis (CF) patients who are at greater risk of lung damage could be clinically valuable. Thus, we attempted to replicate previous findings and verify the possible association between three single nucleotide polymorphisms (SNPs c.-52G>A, c.-44C>G and c.-20G>A) in the 5' untranslated region (5' UTR) of the β defensin 1 (DEFB1) gene and the CF pulmonary phenotype. METHODS: Genomic DNA from 92 Italian CF patients enrolled in different regional CF centres was extracted from peripheral blood and genotyped for DEFB1 SNPs using TaqMan(®) allele specific probes. In order to avoid genetic confounding causes that can account for CF phenotype variability, all patients were homozygous for the F508del CFTR mutation, and were then classified on the basis of clinical and functional data as mild lung phenotype (Mp, n=50) or severe lung phenotype patients (Sp, n=42). RESULTS: For the c.-20G>A SNP, the frequency of the A allele, as well as the AA genotype, were significantly more frequent in Mp than in Sp patients, and thus this was associated with a protective effect against severe pulmonary disease (OR=0.48 and 0.28, respectively). The effect of the c.-20G>A A allele is consistent with a recessive model, and the protective effect against Sp is exerted only when it is present in homozygosis. For the other two SNPs, no differences were observed as allelic and genotypic frequency in the two subgroups of CF patients. CONCLUSIONS: Our results, although necessary to be confirmed in larger and multiethnic populations, reinforce DEFB1 as a candidate modifier gene of the CF pulmonary phenotype.
Keywords: 5' Untranslated Regions; Adult; beta-Defensins; Cystic Fibrosis; Cystic Fibrosis Transmembrane Conductance Regulator; Female; Genotype; Homozygote; Humans; Italy; Male; Mutation; Phenotype; Polymorphism, Genetic; Young Adult

Recent advances in the therapeutic perspectives of Nutlin-3. - Secchiero, Paola; Bosco, Raffaella; Celeghini, Claudio; Zauli, Giorgio (Curr Pharm Des, 2011)
Nutlin-3 is a small molecule inhibitor of the MDM2/p53 interaction, which leads to the non-genotoxic p53 stabilization, activation of cell cycle arrest and apoptosis pathways. A series of recent studies have strengthened the concept that selective, non-genotoxic p53 activation by Nutlin-3 might represent an alternative to the current cytotoxic chemotherapy, in particular for pediatric tumors and for hematological malignancies, which retain a high percentage of p53(wild-type) status at diagnosis. Like most other drugs employed in cancer therapy, it will be unlikely that Nutlin-3 will be used as a monotherapy. In this respect, Nutlin-3 shows a synergistic cytotoxic effect when used in combination with innovative drugs, such as TRAIL or bortozemib. Although Nutlin-3 is currently in phase I clinical trial for the treatment of retinoblastoma, its effects on normal tissues and cell types remain largely to be determined and will require further investigation in the future years.
Keywords: Antineoplastic Agents; Antineoplastic Combined Chemotherapy Protocols; Drug Synergism; Genes, p53; Humans; Imidazoles; Neoplasms; Piperazines; Proto-Oncogene Proteins c-mdm2; Tumor Suppressor Protein p53

Secondary lymphoid tissue as an important site for WU polyomavirus infection in immunocompetent children. - Comar, Manola; Zanotta, Nunzia; Rossi, Tatiana; Pelos, Giorgio; D'Agaro, Pierlanfranco (J Med Virol, 2011)
The polyomaviruses KI and WU (KIPyV and WUPyV) have been identified in respiratory specimens from children with acute respiratory infections, which suggests the respiratory tract as a possible site of infection. However, the persistence of infection in the lymphoid system is unknown. Fresh samples (n = 211) of tonsils, adenoids, and peripheral blood mononuclear cells (PBMCs) from 83 immunocompetent children (mean age 4.8 years) were tested for amplification of the KIPyV VP1 and WUPyV VP2 genes. The known BK and JC polyomaviruses and the lymphotropic human herpesvirus (HHV)-6 were also investigated by quantitative real-time PCR and direct sequencing. In addition, 98 nasopharyngeal swabs collected from children (mean age 6.2 years) affected by seasonal influenza-like illness were tested. Of the lymphoid tissues, 34.9% were positive for WUPyV, 4.8% for BK virus, and 33.8% for HHV-6. KIPyV and JC virus were not detected in these specimens. None of the polyomaviruses were detected in PBMCs. Among the nasopharyngeal samples, the prevalence of WUPyV was 27.5%, although 70% of the positive samples were co-infected with at least one of the following respiratory viruses: influenza virus, adenovirus, and respiratory syncytial virus. Phylogenetic analysis revealed high sequence homology (99%) between lymphoid- and nasopharynx-derived WUPyV strains. These results suggest that the tonsils and adenoids of immunocompetent children are a reservoir for WUPyV infection; probably due to the respiratory route of transmission. In addition, the prevalence of WUPyV was high among the children, and the virus was identified more frequently in older children than during the first years of life.
Keywords: Adenoids; Child; Child, Preschool; DNA, Viral; Female; Humans; Infant; Leukocytes, Mononuclear; Male; Nasopharynx; Palatine Tonsil; Phylogeny; Polymerase Chain Reaction; Polyomavirus; Polyomavirus Infections; Prevalence; Sequence Analysis, DNA; Sequence Homology

Splicing mutations in glycogen-storage disease type II: evaluation of the full spectrum of mutations and their relation to patients' phenotypes. - Zampieri, Stefania; Buratti, Emanuele; Dominissini, Silvia; Montalvo, Anna Lisa; Pittis, Maria Gabriela; Bembi, Bruno; Dardis, Andrea (Eur J Hum Genet, 2011)
Glycogen-storage disease type II is an autosomal recessive-inherited disorder due to the deficiency of acid α-glucosidase. A large number of mutations in the acid α-glucosidase gene have been described to date. Among them, ~15% are variations that may affect mRNA splicing process. In this study, we have for the first time comprehensively reviewed the available information on splicing mutations of the acid α-glucosidase gene and we have evaluated their possible impact on the splicing process using different in silico approaches. Out of the 39 different GAA-sequence variations described, an in silico analysis using seven different programs showed that 97% of them are predicted to have an impact on the splicing process. Moreover, this analysis showed a quite good correlation between the impact of the mutation on the splicing process and the clinical phenotype. In addition, we have performed the functional characterization of three novel sequence variants found in Italian patients and still uncharacterized. Using a minigene system, we have confirmed their pathogenic nature. In conclusion, this study has shown that in silico analysis represents a useful tool to select mutations that affect the splicing process of the acid α-glucosidase gene and provides an updated picture of all this kind of mutations reported till now.
Keywords: alpha-Glucosidases; Cell Line; Computational Biology; DNA Mutational Analysis; Exons; Glycogen Storage Disease Type II; Humans; Introns; Mutagenesis, Site-Directed; Mutation; Phenotype; RNA Splicing

Successful treatment of acne with isotretinoin in chronic granulomatous disease. - Barbi, Egidio; Berti, Irene; Minute, Marta; Zennaro, Floriana (Eur J Dermatol, 2011)
Keywords: Acne Vulgaris; Adult; Anti-Infective Agents; Comorbidity; Dermatologic Agents; Granulomatous Disease, Chronic; Humans; Isotretinoin; Male; Trimethoprim-Sulfamethoxazole Combination

Trail down-regulates the release of osteoprotegerin (OPG) by primary stromal cells. - Corallini, Federica; Celeghini, Claudio; Rimondi, Erika; di Iasio, Maria Grazia; Gonelli, Arianna; Secchiero, Paola; Zauli, Giorgio (J Cell Physiol, 2011)
The soluble member of the TNF-R superfamily osteoprotegerin (OPG) is abundantly released under basal conditions by both mesenchymal stem cells (MSC) and fibroblasts and by endothelial cells upon stimulation with inflammatory cytokines. Since MSC, fibroblasts and endothelial cells represent key elements of the normal and tumor microenvironment and express detectable levels of surface TRAIL receptors, we investigated the effect of TRAIL on OPG release. Unexpectedly, recombinant TRAIL decreased the spontaneous OPG release in all cell types examined. Moreover, TRAIL decreased OPG release also in stromal cells co-cultured with lymphoma cells and counteracted the OPG induction by TN-alpha in HUVEC and MSC. Such down-regulation was not due to a masking effect in the ELISA quantification of the OPG released in the culture supernatants due to binding of OPG to its ligands (TRAIL and RANKL), as demonstrated by competition experiments with recombinant TRAIL and by the lack of RANKL release/induction. In addition, OPG down-regulation was not due to induction of cytotoxic effects by TRAIL, since the degree of apoptosis in response to TRAIL was negligible in all primary cell types. With regards to the possible molecular mechanism accounting for the down-regulation of OPG release by TRAIL, we found that treatment of MSC with TRAIL significantly decreased the phosphorylation levels of p38/MAPK. There is a suggestion that this pathway is involved in the stabilization of OPG mRNA. In this respect, the ability of TRAIL to decrease the release of OPG, in the absence of cell cytotoxicity, was mimicked by the p38/MAPK inhibitor SB203580.
Keywords: Bone Marrow Cells; Cell Death; Cells, Cultured; Coculture Techniques; Down-Regulation; Endothelial Cells; Enzyme Activation; Enzyme-Linked Immunosorbent Assay; Fibroblasts; Humans; MAP Kinase Signaling System; Mesenchymal Stromal Cells; Osteoprotegerin; p38 Mitogen-Activated Protein Kinases; Protein Binding; Recombinant Proteins; Stromal Cells; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor-alpha

TRAIL promotes a pro-survival signal in erythropoietin-deprived human erythroblasts through the activation of an NF-kB/IkBalpha pathway. - Sancilio, S; Di Giacomo, V; Quaglietta, A M; Iacone, A; Angelucci, D; Tatasciore, U; Rana, R A; Cataldi, A; Zauli, G; Di Pietro, R (J Biol Regul Homeost Agents, 2011)
The biological activity of TNF-related apoptosis inducing ligand (TRAIL) was analyzed in primary human erythroblasts derived from mononuclear cells of blood donors, kept in culture in the presence of 20 percent foetal calf serum, growth factors (EPO, SCF, IL-3) and glucocorticoids (10-6 M dexamethasone, 10-6 M oestradiol) or under growth factor and serum starvation. In the presence of growth factors and serum, primary erythroblasts showed a differential expression of TRAIL-Receptors (Rs) at various degrees of maturation and responded to TRAIL treatment with a mild cytotoxicity. On the other hand, in the absence of serum and growth factors, TRAIL treatment unexpectedly up-regulated TRAIL-R4 decoy receptor and promoted erythroblast survival. The concomitant activation of NF-kB/IkB survival pathway was detected with Western blotting and immunofluorescence procedures and confirmed by experiments performed with SN50, a pharmacological inhibitor of the NF-kB/IkB pathway. Our study indicates that TRAIL has a twofold activity on erythroid lineages: it induces a mild erythroid cell cytotoxicity in the presence of serum and growth factors, while it promotes erythroid cell survival through the activation of the NF-kB/IkB pathway under starvation conditions.
Keywords: Cell Survival; Erythroblasts; Erythropoietin; Gene Expression Regulation; Humans; I-kappa B Kinase; Jurkat Cells; NF-kappa B; Peptides; TNF-Related Apoptosis-Inducing Ligand; Tumor Necrosis Factor Decoy Receptors

Beta defensin-1 gene (DEFB1) polymorphisms are not associated with atopic dermatitis in children and adolescents from northeast Brazil (Recife, Pernambuco). - Segat, Ludovica; Guimarães, Rafael L; Brandão, Lucas A C; Rocha, Cintia R C; Zanin, Valentina; Trevisiol, Chiara; de Lima Filho, José Luiz; Crovella, Sergio (Int J Dermatol, 2010)
BACKGROUND: Atopic dermatitis (AD) is a common inflammatory skin disease resulting from the interplay between environmental, immunological and genetic factors. In our study, we investigated the role of three single nucleotide polymorphisms (SNPs) at 5'-UTR of DEFB1 gene, encoding for the human beta defensin-1, on the susceptibility to develop AD in a group of Brazilian children and adolescents. METHODS: Three SNPs, -20 G/A (rs11362), -44 C/G (rs1800972), and -52 G/A (rs1799946) at 5'-UTR of DEFB1 gene were genotyped in two groups of children and adolescents, one affected by AD (96 subjects), the other healthy (191 individuals), from northeast Brazil. RESULTS: -44 C/G frequencies were comparable between the two groups. The -20 GG genotype was more frequent in AD subjects than in healthy controls; the -52 GG, conversely, was more frequent in healthy controls than in AD. However, both these differences did not reach statistical significance. Also, association between SNPs and AD severity has been shown. The analysis of DEFB1 haplotypes did not highlight any association of the three SNPs with AD development or disease severity. CONCLUSIONS: Our results seem to exclude a role for the -44 C/G DEFB1 SNPs on the pathogenesis and severity of AD, while for the -20 C/G and -52 G/A, even if not statistically significant, we evidenced a slight trend for susceptibility (-20 GG) and protection (-52 GG) for the development of AD. However, as controversial findings have been reported in the literature, the role of DEFB1 in the development of AD and in the severity of the phenotype deserves further investigation.
Keywords: Adolescent; beta-Defensins; Brazil; Child; Child, Preschool; Dermatitis, Atopic; Female; Gene Frequency; Genetic Predisposition to Disease; Haplotypes; Humans; Infant; Male; Polymorphism, Single Nucleotide; Risk Factors

A child with pain after mild trauma. - Londero, Margherita; Pastore, Serena; Zanazzo, Giulio A; Bruno, Irene; Ventura, Alessandro (J Pediatr, 2010)
Keywords: Antigens, CD; Antigens, CD31; Antigens, CD34; Antigens, Differentiation, Myelomonocytic; Biopsy; Child; Factor VIII; Fingers; Hand Injuries; Hemangioendothelioma; Humans; Immunohistochemistry; Injury Severity Score; Male; Osteolysis; Pain; Pain Measurement; S100 Proteins; Vascular Neoplasms

Circulating levels of frizzled-related protein (FRZB) are increased in patients with early rheumatoid arthritis and decrease in response to disease-modifying antirheumatic drugs. - Corallini, Federica; Secchiero, Paola; Castellino, Gabriella; Montecucco, Maurizio; Trotta, Francesco; Zauli, Giorgio (Ann Rheum Dis, 2010)
Keywords: Antirheumatic Agents; Arthritis, Rheumatoid; Biological Markers; Glycoproteins; Humans

Design and development of a computer program for the evaluation of the healthcare executive - biomed 2010. - Zotti, Daniel; Bava, Michele; Delendi, Mauro (Biomed Sci Instrum, 2010)
According to the Italian law which regulates executive healthcare contracts, the professional evaluation is mandatory. The goal of the periodic evaluation is to enhance and motivate the professional involved. In addition this process should 1. increase the sense of duty towards the patients, 2. become aware of ones own professional growth and aspirations and 3. enhance the awareness of the healthcare executive regarding the companys strategies. To satisfy these requirements a data sheet has been modeled for every evaluated subject, divided in two sections. In the first part, the chief executive officer (CEO) scores: 1. behavioral characteristics, 2. multidisciplinary collaboration and involvement, 3. organizational skills, 4. professional quality and training, 5. relationships with the citizens. The scores for these fields are decided by the CEO. In the second part the CEO evaluates: 1. quantitative job dimension, 2.technology innovation, 3. scientific and educational activities. The value scores of these fields are decided by the CEO together with the professional under evaluation. A previously established correction coefficient can be used for all the scores. This evaluation system model has been constructed according to the enhancement quality approaches (Deming cycle) and a web-based software has been developed on a Linux platform using LAMP technology and php programming techniques. The program replicates all the evaluation process creating different profiles of authentications and authorizations which can then give to the evaluator the possibility to make lists of the professionals to evaluate, to upload documents regarding their activities and goals, to receive individual documents in automatically generated folders, to change the correction coefficients, to obtain year by year the individual scores. The advantages of using this web-based software include easy data consultation and update, the implementation of IT security issues, the easy portability and scalability of the system itself in different contexts even beyond healthcare.

Detection of SV40 in colon cancer: a molecular case-control study from northeast Italy. - Campello, Cesare; Comar, Manola; Zanotta, Nunzia; Minicozzi, Anna; Rodella, Luca; Poli, Albino (J Med Virol, 2010)
To explore the involvement of the simian polyomavirus SV40 in human colon cancer, a molecular case-control study was undertaken in patients and in their relatives living in an area where the spread of SV40 has already been documented. From 2006 to 2008, 94 colon cancer patients (age: 37-90 years) and 91 subjects (age: 32-70 years) relatives of each index case were enrolled. A blood sample and a specimen of cancer tissue or biopsy were collected, from each patient or control, respectively. Samples were analyzed twice for Polyomavirus (i.e., SV40, JCV, and BKV) by PCR and by quantitative real-time PCR (RT-qPCR) with reproducible results. No BKV/JCV was detected either in normal or pathological tissues. SV40 was not present in control subjects, either normal tissue or in biopsies from adenomas or polyps. All blood samples were negative. Conversely, six adenocarcinoma specimens were positive for SV40 sequences (overall prevalence 6.4%, P = 0.03 in comparison with controls). Nevertheless, the SV40-associated colon cancer risk proved statistically not significant (OR = 3.91; P = 0.115) when adjusted for age. Quantitation of SV40 DNA performed by RT-qPCR showed a low viral load ranging from 6.2 x 10(1) to 9 x 10(3) copies per reaction. This molecular case-control survey showed, for the first time in fresh samples and by RT-qPCR, that SV40 can be detected in colon cancer tissue. However, the finding was not statistically significant when compared with a well-structured community control group. Thus, the role of SV40 and other polyomavirus in colon cancer genesis deserves further investigation.
Keywords: Adenocarcinoma; Adult; Aged; Aged, 80 and over; BK Virus; Case-Control Studies; Colonic Neoplasms; DNA, Viral; Female; Humans; Italy; JC Virus; Male; Middle Aged; Polymerase Chain Reaction; Polyomavirus Infections; Simian virus 40; Tumor Virus Infections

Epidemiological and molecular assessment of a rubella outbreak in North-Eastern Italy. - D'Agaro, Pierlanfranco; Dal Molin, Gianna; Zamparo, Emanuela; Rossi, Tatiana; Micuzzo, Michele; Busetti, Marina; Santon, Daniela; Campello, Cesare (J Med Virol, 2010)
From January to June 2008, a rubella outbreak involving 111 laboratory confirmed cases occurred in the Friuli Venezia Giulia (FVG) region of North-Eastern Italy. The outbreak occurred initially in two residential homes for young adults disabled mentally and physically. Subsequently, the epidemic spread to the general population. Young adult cohorts were mostly affected and the mean age of the patients was 26.8 years; the majority of cases were male (73.8%), with a mean age of 26.6 years in males and 27.4 in females. Three pregnant women had a primary infection and two had their pregnancies terminated. Genotyping of 16 isolates showed the circulation of RUBV 2B, a genotype originating from Asia and South Africa and now present in Europe. In addition, molecular analysis revealed a well defined space-temporal spread of two viruses showing distinct sequences. A seroepidemiological survey carried out in a city within the same geographical area showed that the proportion of women of childbearing age still susceptible to rubella virus was 5.5%, fairly close to the figure (<5%) expected by 2010.
Keywords: Adolescent; Adult; Antibodies, Viral; Disease Outbreaks; Epidemics; Female; Genotype; Humans; Immunoglobulin G; Italy; Male; Pregnancy; Pregnancy Complications, Infectious; Rubella; Rubella virus; Young Adult

EULAR/PRINTO/PRES criteria for Henoch-Schönlein purpura, childhood polyarteritis nodosa, childhood Wegener granulomatosis and childhood Takayasu arteritis: Ankara 2008. Part I: Overall methodology and clinical characterisation. - Ruperto, Nicolino; Ozen, Seza; Pistorio, Angela; Dolezalova, Pavla; Brogan, Paul; Cabral, David A; Cuttica, Ruben; Khubchandani, Raju; Lovell, Daniel J; O'Neil, Kathleen M; Quartier, Pierre; Ravelli, Angelo; et al. (Ann Rheum Dis, 2010)
OBJECTIVES: To report methodology and overall clinical, laboratory and radiographic characteristics for Henoch-Schönlein purpura (HSP), childhood polyarteritis nodosa (c-PAN), c-Wegener granulomatosis (c-WG) and c-Takayasu arteritis (c-TA) classification criteria. METHODS: The preliminary Vienna 2005 consensus conference, which proposed preliminary criteria for paediatric vasculitides, was followed by a EULAR/PRINTO/PRES - supported validation project divided into three main steps. Step 1: retrospective/prospective web-data collection for HSP, c-PAN, c-WG and c-TA, with age at diagnosis <or=18 years. Step 2: blinded classification by consensus panel of a subgroup of 280 cases (128 difficult cases, 152 randomly selected) enabling expert diagnostic verification. Step 3: Ankara 2008 Consensus Conference and statistical evaluation (sensitivity, specificity, area under the curve, kappa-agreement) using as 'gold standard' the final consensus classification or original treating physician diagnosis. RESULTS: A total of 1183/1398 (85%) samples collected were available for analysis: 827 HSP, 150 c-PAN, 60 c-WG, 87 c-TA and 59 c-other. Prevalence, signs/symptoms, laboratory, biopsy and imaging reports were consistent with the clinical picture of the four c-vasculitides. A representative subgroup of 280 patients was blinded to the treating physician diagnosis and classified by a consensus panel, with a kappa-agreement of 0.96 for HSP (95% CI 0.84 to 1), 0.88 for c-WG (95% CI 0.76 to 0.99), 0.84 for c-TA (95% CI 0.73 to 0.96) and 0.73 for c-PAN (95% CI 0.62 to 0.84), with an overall kappa of 0.79 (95% CI 0.73 to 0.84). CONCLUSION: EULAR/PRINTO/PRES propose validated classification criteria for HSP, c-PAN, c-WG and c-TA, with substantial/almost perfect agreement with the final consensus classification or original treating physician diagnosis.
Keywords: Adolescent; Biopsy; Child; Delphi Technique; Granulomatosis with Polyangiitis; Humans; International Cooperation; Internet; Polyarteritis Nodosa; Purpura, Schoenlein-Henoch; Reproducibility of Results; Takayasu Arteritis

Five new OTOF gene mutations and auditory neuropathy. - Zadro, Cristina; Ciorba, Andrea; Fabris, Annalisa; Morgutti, Marcello; Trevisi, Patrizia; Gasparini, Paolo; Martini, Alessandro (Int J Pediatr Otorhinolaryngol, 2010)
OBJECTIVE: Purpose of this paper is to analyse OTOF gene in a series of subjects affected by auditory neuropathy. METHODS: Four children showing mild to profound prelingual deafness, confirmed by the absence of a clear and detectable responses at auditory brainstem responses (ABR), associated with the presence of bilateral OAE, were enrolled in the study. RESULTS AND CONCLUSIONS: Genetic analysis identified five new mutations (a nonsense, a small and a large deletion and two splicing site mutations), and one missense mutation (F1795C) previously described. These results further confirm the role of OTOF gene in auditory neuropathy. In the absence of a context of neurological syndrome, the combination of absent ABR and positive OAE responses should lead to an auditory neuropathy diagnosis and to a mutational screening in OTOF.
Keywords: Auditory Diseases, Central; Deafness; Evoked Potentials, Auditory, Brain Stem; Female; Humans; Male; Membrane Proteins; Mutation; Otoacoustic Emissions, Spontaneous; Polymerase Chain Reaction

Follow-up and quality of life of patients with cryopyrin-associated periodic syndromes treated with Anakinra. - Lepore, Loredana; Paloni, Giulia; Caorsi, Roberta; Alessio, Maria; Rigante, Donato; Ruperto, Nicola; Cattalini, Marco; Tommasini, Alberto; Zulian, Francesco; Ventura, Alessando; Martini, Alberto; Gattorno, Marco (J Pediatr, 2010)
OBJECTIVE: To evaluate the quality of life and long-term follow-up of patients enrolled in the Italian registry of cryopyrin-associated periodic syndromes (CAPS). STUDY DESIGN: Since 2004, 20 patients with CAPS were enrolled in a common registry from different Italian Centers of Pediatric Rheumatology; 14 patients were treated with Anakinra in an open fashion. Both treated and untreated patients were routinely followed according to standard of care. The Child Health Questionnaire (CHQ-PF 50) was used to assess the health-related quality of life. RESULTS: The mean duration of follow-up was 37.5 months. In all treated patients, a complete and persistent control of the inflammatory manifestations was observed with no further progression of the disease. At enrollment in the registry, patients showed a poorer health-related quality of life than healthy children in both physical and the psychosocial summary scores. Treatment was associated with a dramatic and sustained amelioration of a variety of measures of poor quality of life, particularly in those concerning the global health perception, bodily pain-discomfort, and other physical domains. CONCLUSIONS: Long-term IL-1 blockade produces a significant and persistent improvement in the clinical manifestations associated with the disease and on the overall quality of life.
Keywords: Adolescent; Adult; Case-Control Studies; Child; Child, Preschool; Cryopyrin-Associated Periodic Syndromes; Female; Follow-Up Studies; Humans; Inflammation; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Male; Phenotype; Quality of Health Care; Quality of Life; Questionnaires; Syndrome; Treatment Outcome

Incidence of bacteremias and invasive mycoses in children with acute non-lymphoblastic leukemia: results from a multi-center Italian study. - Castagnola, Elio; Rossi, Mario R; Cesaro, Simone; Livadiotti, Susanna; Giacchino, Mareva; Zanazzo, Giulio; Fioredda, Francesca; Beretta, Chiara; Ciocchello, Francesca; Carli, Modesto; Putti, Maria Caterina; Pansini, Valeria; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: Data on the epidemiology of bacteremias and invasive fungal diseases (IFD) in children with acute myeloid leukemia (AML) are scarce. DESIGN AND METHODS: In a multi-center, retrospective study, we analyzed proportion, rate per 1,000 person-days at risk, and cumulative risk of bacteremias and IFD in children with AML. RESULTS: Between January 1998 and December 2005, 240 children were treated for AML at 8 Italian Centers, for a total of 521 treatment courses and 63,232 person-days at risk. Bacteremia was observed in 32% of treatment courses and IFD was seen in 10% (P < 0.0001), with rates of 2.62 and 0.84, respectively (P < 0.001). There was a significantly higher frequency of IFD during relapse treatment: proportion 15% versus 9% (P = 0.05), rate 2.10 versus 0.64 (P = 0.008) and cumulative risk 32% versus 12% (P = 0.007), while there were no differences in the proportion, rate and cumulative risk of bacteremia during front-line or relapse treatment. The epidemiology of bacteremias and IFD was different during front-line therapy for M3 as compared to other types of AML, but the differences were not statistically significant. CONCLUSIONS: Severe infectious complications are frequent during the treatment of pediatric AML, especially during relapse treatment, and bacteremias are more frequent than IFD.
Keywords: Antineoplastic Combined Chemotherapy Protocols; Bacteremia; Child; Female; Follow-Up Studies; Humans; Incidence; Italy; Leukemia, Myeloid, Acute; Male; Mycoses; Neoplasm Recurrence, Local; Retrospective Studies

JCV/BKV and SV40 viral load in lymphoid tissues of young immunocompetent children from an area of north-east Italy. - Comar, Manola; Zanotta, Nunzia; Bovenzi, Massimo; Campello, Cesare (J Med Virol, 2010)
Polyomavirus infection occurring during childhood is followed by a lifelong latency in immunocompetent subjects. The major site of polyomavirus persistence are the uroepithelial cells which leads to oral transmission. It has recently been hypothesized that tonsils could be a possible reservoir. The role of tonsil, adenoid, and peripheral blood mononuclear cells (PBMCs) as possible sites of JCV, BKV, and SV40 latency in young healthy children was assessed. Two hundred fifteen fresh specimens, including 57 tonsil, 80 adenoid, and 78 PBMC samples from 80 immunocompetent children (mean age 4.8 years) were analyzed to determine the viral load by quantitative real-time PCR. The human herpes virus 6 (HHV-6) was tested as a lymphotropic reference virus. Polyomavirus was detected in 5/80 (6.2%) children while HHV-6 infection affected 27/80 children (33.7%) (P < 0.001). SV40 was detected in one adenoid sample, while footprints of BKV were found in one adenoid and three tonsil samples. JCV was never found in all samples. Polyomavirus sequences were not detected in the 78 blood samples. One adenoid and two tonsils from three children (1.4%) were positive for both polyomavirus and HHV-6. Infections were characterized by low replication rates ranging typically from 1 x 10e(2)/5.5 x 10e(4) to 6.8 x 10e(3)/8.5 x 10e(4) viral copies/number of cells. In conclusion, tonsils and adenoids of children could effectively harbor BKV and SV40, although only very few cells proved to be infected. Nevertheless, the low prevalence of polyomavirus, in comparison with the lymphotropic HHV-6, suggests that these tissues are unlikely to be the preferred site of polyomavirus latency, at least in younger children.
Keywords: Adenoids; BK Virus; Carrier State; Child; Child, Preschool; Female; Herpesvirus 6, Human; Humans; Immunocompetence; Italy; JC Virus; Male; Neutrophils; Palatine Tonsil; Polyomavirus Infections; Simian virus 40; Viral Load; Virus Latency

Modeling the effect of 3 missense AGXT mutations on dimerization of the AGT enzyme in primary hyperoxaluria type 1. - Robbiano, Angela; Frecer, Vladimir; Miertus, Jan; Zadro, Cristina; Ulivi, Sheila; Bevilacqua, Elena; Mandrile, Giorgia; De Marchi, Mario; Miertus, Stanislav; Amoroso, Antonio (J Nephrol, 2010)
INTRODUCTION: Mutations of the AGXT gene encoding the alanine:glyoxylate aminotransferase liver enzyme (AGT) cause primary hyperoxaluria type 1 (PH1). Here we report a molecular modeling study of selected missense AGXT mutations: the common Gly170Arg and the recently described Gly47Arg and Ser81Leu variants, predicted to be pathogenic using standard criteria. METHODS: Taking advantage of the refined 3D structure of AGT, we computed the dimerization energy of the wild-type and mutated proteins. RESULTS: Molecular modeling predicted that Gly47Arg affects dimerization with a similar effect to that shown previously for Gly170Arg through classical biochemical approaches. In contrast, no effect on dimerization was predicted for Ser81Leu. Therefore, this probably demonstrates pathogenic properties via a different mechanism, similar to that described for the adjacent Gly82Glu mutation that affects pyridoxine binding. CONCLUSION: This study shows that the molecular modeling approach can contribute to evaluating the pathogenicity of some missense variants that affect dimerization. However, in silico studies--aimed to assess the relationship between structural change and biological effects--require the integrated use of more than 1 tool.
Keywords: Amino Acid Sequence; Female; Humans; Male; Models, Molecular; Molecular Sequence Data; Mutation, Missense; Protein Multimerization; Transaminases

Morbidity of pandemic H1N1 influenza in children with cancer. - Caselli, Désirée; Carraro, Francesca; Castagnola, Elio; Ziino, Ottavio; Frenos, Stefano; Milano, Giuseppe Maria; Livadiotti, Susanna; Cesaro, Simone; Marra, Nicoletta; Zanazzo, Giulio; Meazza, Cristina; Cellini, Monica; et al. (Pediatr Blood Cancer, 2010)
BACKGROUND: To define the mortality and the current impact of the H1N1 pandemic in pediatric hematology-oncology centers, we performed a specific survey. PROCEDURE: Pharyngeal swabs from patients with fevers of unknown origin, flu-like symptoms or bronchopneumonia were screened for H1N1 using PCR. RESULTS: Sixty-two patients with documented H1N1 infection were reported: 16 had recently stopped therapy, 2 were at the diagnosis stage, and 44 were receiving therapy. The clinical course was severe (requiring ICU admission) in only 1 patient, moderate (requiring hospital admission) in 38, and mild in the remaining 23 (37%), treated as outpatients. While none of the patients died of H1N1-related complications, two patients died of progressive cancer; in all of the remaining cases, symptoms resolved within 11 days. The clinical course was complicated by respiratory distress or bronchopneumonia in 10 cases. Oseltamivir was given to 82% of patients. Chemotherapy was temporarily withdrawn in 54% of cases for a median time of 21 days (range, 4-43 days). CONCLUSION: H1N1 infection in children with cancer was not reported as the cause of death in any case but resulted in reduced intensity of anti-cancer therapy.
Keywords: Adolescent; Antineoplastic Agents; Cause of Death; Child; Child, Preschool; Data Collection; Disease Outbreaks; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Leukemia; Lymphoma, Non-Hodgkin; Morbidity; Neoplasms; Treatment Outcome; Young Adult

Multidrug resistant Pseudomonas aeruginosa infection in children undergoing chemotherapy and hematopoietic stem cell transplantation. - Caselli, Désirée; Cesaro, Simone; Ziino, Ottavio; Zanazzo, Giulio; Manicone, Rosaria; Livadiotti, Susanna; Cellini, Monica; Frenos, Stefano; Milano, Giuseppe M; Cappelli, Barbara; Licciardello, Maria; Beretta, Chiara; et al. (Haematologica, 2010)
Pseudomonas aeruginosa is one leading gram-negative organism associated with nosocomial infections. Bacteremia is life-threatening in the immunocompromised host. Increasing frequency of multi-drug-resistant (MDRPA) strains is concerning. We started a retrospective survey in the pediatric hematology oncology Italian network. Between 2000 and 2008, 127 patients with Pseudomonas aeruginosa bacteremia were reported from 12 centers; 31.4% of isolates were MDRPA. Death within 30 days of a positive blood culture occurred in 19.6% (25/127) of total patients; in patients with MDRPA infection it occurred in 35.8% (14/39). In the multivariate analysis, only MDRPA had significant association with infection-related death. This is the largest series of Pseudomonas aeruginosa bacteremia cases from pediatric hematology oncology centers. Monitoring local bacterial isolates epidemiology is mandatory and will allow empiric antibiotic therapy to be tailored to reduce fatalities.
Keywords: Adolescent; Antineoplastic Agents; Bacteremia; Child; Child, Preschool; Drug Resistance, Multiple; Female; Hematopoietic Stem Cell Transplantation; Humans; Immunocompromised Host; Infant; Infant, Newborn; Italy; Male; Pseudomonas aeruginosa; Pseudomonas Infections; Retrospective Studies; Young Adult

Severe X-linked mitochondrial encephalomyopathy associated with a mutation in apoptosis-inducing factor. - Ghezzi, Daniele; Sevrioukova, Irina; Invernizzi, Federica; Lamperti, Costanza; Mora, Marina; d'Adamo, Pio; Novara, Francesca; Zuffardi, Orsetta; Uziel, Graziella; Zeviani, Massimo (Am J Hum Genet, 2010)
We investigated two male infant patients who were given a diagnosis of progressive mitochondrial encephalomyopathy on the basis of clinical, biochemical, and morphological features. These patients were born from monozygotic twin sisters and unrelated fathers, suggesting an X-linked trait. Fibroblasts from both showed reduction of respiratory chain (RC) cIII and cIV, but not of cI activities. We found a disease-segregating mutation in the X-linked AIFM1 gene, encoding the Apoptosis-Inducing Factor (AIF) mitochondrion-associated 1 precursor that deletes arginine 201 (R201 del). Under normal conditions, mature AIF is a FAD-dependent NADH oxidase of unknown function and is targeted to the mitochondrial intermembrane space (this form is called AIF(mit)). Upon apoptogenic stimuli, a soluble form (AIF(sol)) is released by proteolytic cleavage and migrates to the nucleus, where it induces "parthanatos," i.e., caspase-independent fragmentation of chromosomal DNA. In vitro, the AIF(R201 del) mutation decreases stability of both AIF(mit) and AIF(sol) and increases the AIF(sol) DNA binding affinity, a prerequisite for nuclear apoptosis. In AIF(R201 del) fibroblasts, staurosporine-induced parthanatos was markedly increased, whereas re-expression of AIF(wt) induced recovery of RC activities. Numerous TUNEL-positive, caspase 3-negative nuclei were visualized in patient #1's muscle, again indicating markedly increased parthanatos in the AIF(R201 del) critical tissues. We conclude that AIF(R201 del) is an unstable mutant variant associated with increased parthanatos-linked cell death. Our data suggest a role for AIF in RC integrity and mtDNA maintenance, at least in some tissues. Interestingly, riboflavin supplementation was associated with prolonged improvement of patient #1's neurological conditions, as well as correction of RC defects in mutant fibroblasts, suggesting that stabilization of the FAD binding in AIF(mit) is beneficial.
Keywords: Apoptosis; Apoptosis Inducing Factor; Caspase 3; Computer Simulation; Dietary Supplements; DNA Primers; DNA, Mitochondrial; Electron Transport; Female; Fibroblasts; Flavin-Adenine Dinucleotide; Genes, X-Linked; Humans; In Situ Nick-End Labeling; Infant, Newborn; Magnetic Resonance Imaging; Male; Mitochondrial Encephalomyopathies; Muscle, Skeletal; Mutation; Nervous System Diseases; Pedigree; Poly(ADP-ribose) Polymerases; Protein Conformation; Riboflavin; Staurosporine; Twins, Monozygotic

Splenomegaly as presentation of a wandering spleen. - Maschio, Massimo; Cozzi, Giorgio; Sanabor, Daniela; Zennaro, Floriana; Gloria, Pelizzo; Barbi, Egidio (J Pediatr, 2010)
Keywords: Child; Female; Humans; Splenomegaly; Wandering Spleen

Thirty new loci for age at menarche identified by a meta-analysis of genome-wide association studies. - Elks, Cathy E; Perry, John R B; Sulem, Patrick; Chasman, Daniel I; Franceschini, Nora; He, Chunyan; Lunetta, Kathryn L; Visser, Jenny A; Byrne, Enda M; Cousminer, Diana L; Gudbjartsson, Daniel F; Esko, Tõnu; et al. (Nat Genet, 2010)
To identify loci for age at menarche, we performed a meta-analysis of 32 genome-wide association studies in 87,802 women of European descent, with replication in up to 14,731 women. In addition to the known loci at LIN28B (P = 5.4 × 10⁻⁶⁰) and 9q31.2 (P = 2.2 × 10⁻³³), we identified 30 new menarche loci (all P < 5 × 10⁻⁸) and found suggestive evidence for a further 10 loci (P < 1.9 × 10⁻⁶). The new loci included four previously associated with body mass index (in or near FTO, SEC16B, TRA2B and TMEM18), three in or near other genes implicated in energy homeostasis (BSX, CRTC1 and MCHR2) and three in or near genes implicated in hormonal regulation (INHBA, PCSK2 and RXRG). Ingenuity and gene-set enrichment pathway analyses identified coenzyme A and fatty acid biosynthesis as biological processes related to menarche timing.
Keywords: Adolescent; Aging; Body Height; Body Size; Child; DNA Copy Number Variations; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Inheritance Patterns; Menarche; Obesity; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Reproducibility of Results; Time Factors

Transmission of hemagglutinin D222G mutant strain of pandemic (H1N1) 2009 virus. - Puzelli, Simona; Facchini, Marzia; Spagnolo, Domenico; De Marco, Maria A; Calzoletti, Laura; Zanetti, Alessandro; Fumagalli, Roberto; Tanzi, Maria L; Cassone, Antonio; Rezza, Giovanni; Donatelli, Isabella (Emerg Infect Dis, 2010)
A pandemic (H1N1) 2009 virus strain carrying the D222G mutation was identified in a severely ill man and was transmitted to a household contact. Only mild illness developed in the contact, despite his obesity and diabetes. The isolated virus reacted fully with an antiserum against the pandemic vaccine strain.
Keywords: Adult; Amino Acid Substitution; Disease Outbreaks; Hemagglutinin Glycoproteins, Influenza Virus; Humans; Influenza A Virus, H1N1 Subtype; Influenza, Human; Male; Middle Aged; Mutation, Missense; Phylogeny; Retrospective Studies; RNA, Viral; Sequence Analysis, RNA; Severity of Illness Index

Treatment with recombinant tumor necrosis factor-related apoptosis-inducing ligand alleviates the severity of streptozotocin-induced diabetes. - Zauli, Giorgio; Toffoli, Barbara; di Iasio, Maria Grazia; Celeghini, Claudio; Fabris, Bruno; Secchiero, Paola (Diabetes, 2010)
OBJECTIVE: To evaluate the potential therapeutic effect of recombinant human tumor necrosis factor (TNF)-related apoptosis-inducing ligand (TRAIL) treatment in a model of type 1 diabetes. RESEARCH DESIGN AND METHODS: Recombinant TRAIL was added in vitro to primary human and mouse peripheral blood mononuclear cells (PBMCs) and isolated human islets to evaluate the expression of the immunoregulatory gene SOCS1. Diabetes was induced by five consecutive daily injections of low-concentration (50 mg/kg) streptozotocin (STZ) in C57 black mice (n = 24). A group of these mice (n = 12) was co-injected with recombinant TRAIL (20 microg/day) for 5 days, and the diabetic status (glycemia and body weight) was followed over time. After 6 weeks, circulating levels of insulin, TNF-alpha, and osteoprotegerin (OPG) were measured, and animals were killed to perform the histological analysis of the pancreas. RESULTS: The in vitro exposure of both PBMCs and human islets to recombinant TRAIL significantly upregulated the expression of SOCS1. With respect to STZ-treated animals, mice co-injected with STZ+TRAIL were characterized by 1) lower levels of hyperglycemia, 2) higher levels of body weight and insulinemia, 3) a partial preservation of pancreatic islets with normal morphology, and 4) a lower expression of both systemic (TNF-alpha and OPG) and pancreatic (vascular cell adhesion molecule [VCAM]-1) inflammatory markers. CONCLUSIONS: Overall, these data demonstrate that the administration of recombinant TRAIL ameliorates the severity of STZ-induced type 1 diabetes, and this effect was accompanied by the upregulation of SOCS1 expression.
Keywords: Animals; Cells, Cultured; Diabetes Mellitus, Experimental; Gene Expression; Humans; Islets of Langerhans; Leukocytes, Mononuclear; Mice; Recombinant Proteins; Suppressor of Cytokine Signaling Proteins; TNF-Related Apoptosis-Inducing Ligand

Two cases of Noonan syndrome with severe respiratory and gastroenteral involvement and the SOS1 mutation F623I. - Fabretto, Antonella; Kutsche, Kerstin; Harmsen, May-Britt; Demarini, Sergio; Gasparini, Paolo; Fertz, Maria Cristina; Zenker, Martin (Eur J Med Genet, 2010)
Noonan syndrome (NS) is an autosomal dominant, inherited disorder characterized by facial dysmorphism, congenital heart defects, and reduced postnatal growth. Dysregulated RAS-MAPK signalling is the common molecular basis for NS, a genetically heterogeneous disease. Germline mutations in genes encoding small GTPases of the RAS family (KRAS and NRAS), modulators of RAS function (PTPN11, SOS1 and SHOC2) or downstream signal transducers (RAF1) are causative for NS. SOS1 is the second major gene for NS after PTPN11. Compared to patients with mutations in other genes, SOS1 mutation-positive individuals in general tend to have a more favorable outcome, with less short stature and cognitive impairment. We describe two unrelated patients with NS carrying the same heterozygous SOS1 missense mutation (c.1867T > A/p.F623I). The phenotype of both patients is remarkable as they show uncommon clinical features such as pulmonary lymphangiectasis, congenital pleural effusions, severe feeding problems, and laryngomalacia. These findings may be related to the specific mutation present in our two patients, or be part of the SOS1 phenotype. Detailed clinical assessment of large cohorts of patients with NS and SOS1 mutation is required to clarify this initial observation.
Keywords: Child, Preschool; Genes, ras; Germ-Line Mutation; Heterozygote; Humans; Infant; Infant, Newborn; Male; Mutation, Missense; Noonan Syndrome; Phenotype; SOS1 Protein

A web-based system for total parenteral nutrition prescription in a pediatric hospital - biomed 2010. - Bava, Michele; Bradashia, Fulvio; Rovere, Francesca; Maestro, Alessandra; Vecchi Brumatti, Liz; Accardo, Agostino; Paparazzo, Rossella; Zanon, Davide (Biomed Sci Instrum, 2010)
otal Parenteral Nutrition (TPN) is defined as feeding a patient by infusing nutrients intravenously, bypassing the usual process of eating and digestion. There are two kinds of TPN: short-term TPN may be used when a patient's digestive system is temporarily nonfunctional because of an interruption in its continuity; long-term TPN is used to treat patients with an impairment or a lack in nutrient absorption. TPN has extended the life of children born with nonexistent or severely deformed digestive organs and is a vital support for these patients. In Burlos Pediatric Department, pediatricians fill in a pharmacy request form in which nutritional needs are included for each patient. Subsequently, clinical pharmacists evaluate the patients individual data and decide which TPN formula to prepare. To enhance the TPN prescription process, an intranet web-based system has been developed to replicate the original paper-based forms. The software, developed in PHP and based on open source tools and services, has been constructed according to pharmacists requirements. These professionals, together with the Hospital Information System technicians, thanks to the availability of affordable instruments, perceive the advantages that such a system would have in improving clinical practice and quality of care. The system was devised with the goal to avoid common reading errors, to improve the correct text comprehension, to ensure prescription preparation, administration and tracking. According to a process of total quality control, the system reduces clinical risks regarding issues such as the correct and rapid availability of medical prescriptions and the incorrect identification of the patients. In comparison with paper-based TPN prescriptions, electronic-based forms have reduced the incidence of errors, the possible lack of patient data and reading misunderstandings. Regarding future improvements, IT technicians are defining the procedures to implement digital signature and medical aspects of the electronic TPN medical prescriptions.

Wired to be social: the ontogeny of human interaction. - Castiello, Umberto; Becchio, Cristina; Zoia, Stefania; Nelini, Cristian; Sartori, Luisa; Blason, Laura; D'Ottavio, Giuseppina; Bulgheroni, Maria; Gallese, Vittorio (PLoS One, 2010)
BACKGROUND: Newborns come into the world wired to socially interact. Is a propensity to socially oriented action already present before birth? Twin pregnancies provide a unique opportunity to investigate the social pre-wiring hypothesis. Although various types of inter-twins contact have been demonstrated starting from the 11(th) week of gestation, no study has so far investigated the critical question whether intra-pair contact is the result of motor planning rather then the accidental outcome of spatial proximity. METHODOLOGY/PRINCIPAL FINDINGS: Kinematic profiles of movements in five pairs of twin foetuses were studied by using four-dimensional ultrasonography during two separate recording sessions carried out at the 14(th) and 18(th) week of gestation. We demonstrate that by the 14th week of gestation twin foetuses do not only display movements directed towards the uterine wall and self-directed movements, but also movements specifically aimed at the co-twin, the proportion of which increases between the 14(th) and 18(th) gestational week. Kinematic analysis revealed that movement duration was longer and deceleration time was prolonged for other-directed movements compared to movements directed towards the uterine wall. Similar kinematic profiles were observed for movements directed towards the co-twin and self-directed movements aimed at the eye-region, i.e. the most delicate region of the body. CONCLUSIONS/SIGNIFICANCE: We conclude that performance of movements towards the co-twin is not accidental: already starting from the 14th week of gestation twin foetuses execute movements specifically aimed at the co-twin.
Keywords: Female; Fetus; Humans; Pregnancy; Social Behavior; Ultrasonography, Prenatal